The impact of climate change on education: An evidence synthesis focused on classroom experience in hot climates - Haßler, Björn; Eso, Olamide; Villavicencio, Xuzel; Jengo, Eunice; McBurnie, Chris (Open Development & Education, 2024)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 11403758 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1139 ZenodoArchiveConcept: 11403757
Keywords: Coming soon; Internal; _publish; _r:AddedByMyEducationEvidence

A comparison between grey-box models and neural networks for indoor air temperature prediction in buildings - Vivian, J.; Prataviera, E.; Gastaldello, N.; Zarrella, A. (Journal of Building Engineering, 2024)
Model Predictive Control has gained much attention due to its potential to improve building operations by reducing costs, integrating renewable energy sources, and increasing thermal comfort. This paper aims to compare the accuracy of grey-box models based on resistance–capacitance (RC) networks and Long-Short-Term Memory (LSTM) neural networks in the prediction of the buildings’ thermal response, which is a key feature for the successful implementation of predictive controllers. Indoor air temperature prediction tests have been performed on simulated and measured data from buildings with different thermal insulation and thermal mass during both heating and cooling seasons. Results show that neural networks have, on average, a better prediction performance than grey-box models. Both modelling approaches are affected by the building characteristics and by the season considered. The grey-box models require less training data, although the latter seems to play a role only in the worse-performing tests. When user setpoint changes in the testing phase, the LSTM neural network shows a significant drop in the root mean square error. In conclusion, although LSTM outperforms grey-box models on average, the reduced training data and higher reliability under normal operating conditions, as well as their linearity, make RC models a strong alternative for predictive controllers.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.jobe.2024.108583 5072953:7SFU48A9 5072953:GYNWF4CU openalex: W4391070705
Keywords: Building simulation; Grey-box models; Long Short-Term Memory Neural Networks; Model Predictive Control; _important; _z:class:countries; _z:class:themes; _z:no_pdf; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; oa:topic:T11529 Refrigeration Systems and Technologies; openalex:n:1; openalex:yes; selected_for:Predictive models for classroom conditions 2024

DeepVision based detection for energy-efficiency and indoor air quality enhancement in highly polluted spaces - Wei, Shuangyu; Tien, Paige; Zhang, Wuxia; Wei, Zhichen; Wang, Zu; Calautit, John Kaiser (Journal of Building Engineering, 2024)
Cooking can generate substantial heat from cooking equipment, potentially resulting in reduced thermal comfort levels if this excess heat is not adequately dissipated. Additionally, it can significantly affect indoor air quality (IAQ), not only in kitchen spaces but also in adjacent areas lacking sufficient ventilation. To ensure a healthy and comfortable indoor environment while avoiding unnecessary energy use, this research proposes an approach for detecting equipment usage. Utilizing deep learning and computer vision techniques (referred to as DeepVision), this method aids the operation of demand-driven ventilation systems in highly polluted spaces. A Faster RCNN model was employed and trained to detect kitchen equipment usage in real-time. The ventilation rate for the kitchen space was adjusted based on this real-time detection. Experimental tests were carried out in a case study kitchen and results showed that the detection model achieved an overall F1 score of 0.9142. Overall, the model achieved good performance in real-time detection, accurately identifying appliances in use, such as stoves, ovens, and toasters. Field experimental results showed the advantages of combining mechanical ventilation methods, such as extractor fans and cooker hoods, to mitigate IAQ issues while also achieving energy savings. Moreover, the energy simulations demonstrate its potential to reduce energy consumption by dynamically adjusting ventilation rates in response to real-time equipment usage. When the fan speed was varied according to the real-time detection method, the PM2.5 concentration in the cooking period was 16.5 % lower, with only a 3.7 % rise in fan power and a 0.8 % rise in daily heating demand, compared to using a constant fan speed.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.jobe.2024.108530 5072953:ZQ5TL6YS openalex: W4390858395
Keywords: _important; _z:class:countries; _z:class:themes; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10990 Airborne Transmission of Respiratory Viruses; oa:topic:T12120 Low-Cost Air Quality Monitoring Systems; openalex:n:1; openalex:yes; selected_for:Predictive models for classroom conditions 2024

DeepVision based detection for energy-efficiency and indoor air quality enhancement in highly polluted spaces - Wei, Shuangyu; Tien, Paige; Zhang, Wuxia; Wei, Zhichen; Wang, Zu; Calautit, John Kaiser (Journal of Building Engineering, 2024)
Cooking can generate substantial heat from cooking equipment, potentially resulting in reduced thermal comfort levels if this excess heat is not adequately dissipated. Additionally, it can significantly affect indoor air quality (IAQ), not only in kitchen spaces but also in adjacent areas lacking sufficient ventilation. To ensure a healthy and comfortable indoor environment while avoiding unnecessary energy use, this research proposes an approach for detecting equipment usage. Utilizing deep learning and computer vision techniques (referred to as DeepVision), this method aids the operation of demand-driven ventilation systems in highly polluted spaces. A Faster RCNN model was employed and trained to detect kitchen equipment usage in real-time. The ventilation rate for the kitchen space was adjusted based on this real-time detection. Experimental tests were carried out in a case study kitchen and results showed that the detection model achieved an overall F1 score of 0.9142. Overall, the model achieved good performance in real-time detection, accurately identifying appliances in use, such as stoves, ovens, and toasters. Field experimental results showed the advantages of combining mechanical ventilation methods, such as extractor fans and cooker hoods, to mitigate IAQ issues while also achieving energy savings. Moreover, the energy simulations demonstrate its potential to reduce energy consumption by dynamically adjusting ventilation rates in response to real-time equipment usage. When the fan speed was varied according to the real-time detection method, the PM2.5 concentration in the cooking period was 16.5 % lower, with only a 3.7 % rise in fan power and a 0.8 % rise in daily heating demand, compared to using a constant fan speed.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.jobe.2024.108530 5072953:ZQ5TL6YS openalex: W4390858395
Keywords: _important; _z:class:countries; _z:class:themes; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10990 Airborne Transmission of Respiratory Viruses; oa:topic:T12120 Low-Cost Air Quality Monitoring Systems; openalex:n:1; openalex:yes; selected_for:Predictive models for classroom conditions 2024

Impacts of Extreme Weather Events on Education Outcomes: A Review of Evidence - Venegas Marin, Sergio; Schwarz, Lara; Sabarwal, Shwetlena (The World Bank Research Observer, 2024)
Extreme weather events are increasingly disrupting schooling. Yet, these are underrepresented in the climate change literature. Of 15 review articles on the economic impacts of climate change published since 2010, only three mention the impacts of climate change on education. We review available literature on the effects of weather extremes on education. We outline key pathways through which these events impact education outcomes, as well as the magnitude of those impacts. Evidence implies a significant and adverse relationship between heat and learning. Studies suggest surpassing a high temperature threshold makes learning difficult and results in learning losses. Across studies, each additional day subject to extreme heat reduces learning. Tropical cyclones, floods, and wildfires precipitate school closures, which halt learning. Evidence suggests that one day of school closures leads to one day of learning lost. Weather extremes also negatively impact education outcomes through health, nutrition, poverty, and fragility, among other distal pathways. We discuss the implications of this evidence for policy, including the need to adapt education systems to climate change. Mitigation and adaptation are both urgently needed as extreme weather events become more frequent and severe in the context of climate change.
KerkoCite.ItemAlsoKnownAs: 10.1093/wbro/lkae001 2129771:F96JM88U
Keywords: evidence_review; interesting

Project updates for Climate, Environment and Education Adaptation Research (CLEEAR) Tanzania Steering Committee - Villavicencio, Xuzel; Haßler, Björn; Jengo, Eunice (2024)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10944958 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1130 ZenodoArchiveConcept: 10944957
Keywords: _publish; _r:AddedByMyEducationEvidence

Digital Earth Partnership: Climate, Environment & Education in Tanzania – Gaps & Policy implications - Anderson, Edward (2024)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10912243 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1127 ZenodoArchiveConcept: 10912242
Keywords: Coming soon; _r:AddedByMyEducationEvidence

What impact do climate conditions in classrooms have on teachers? - Koomar, Saalim (2024)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10912313 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1129 ZenodoArchiveConcept: 10912312
Keywords: _publish; _r:AddedByMyEducationEvidence

Identifying and prioritizing strategies to strengthen climate resilience of education systems - Ryan, Benjamin; Garner, Shelby; Flynnn, Rachael (2024)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10912284 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1128 ZenodoArchiveConcept: 10912283
Keywords: Coming soon; _r:AddedByMyEducationEvidence

Assessing the growing threat of heat stress in the North Africa and Arabian Peninsula region connected to climate change - Hamed, Mohammed Magdy; Al-Hasani, Alaa A. Jasim; Nashwan, Mohamed Salem; Sa'adi, Zulfaqar; Shahid, Shamsuddin (Journal of Cleaner Production, 2024)
Climate change exacerbates extreme heat events in the North Africa and Arabian Peninsula (NAAP) region, posing a significant threat to human health and well-being. This study proposes a novel approach for reliable mapping of population exposure in NAAP to different UTCI levels under future climate change scenarios by improved prediction of UTCI using machine learning (ML) methods. Daily mean UTCI was calculated using hourly ERA-HEAT data from 1979 to 2022. Sobol's global sensitivity analysis was used to identify the most influential meteorological variables affecting UTCI. Three ML models were trained to predict monthly UTCI based on these variables. The best-performing model was used to generate historical and future projections of UTCI for four CMIP6 climate models under Paris Agreement goal scenarios. Finally, the projected change in population exposure to mean UTCI was assessed by comparing historical and future projections. The results showed a significant influence of air temperature, wind speed, surface pressure, solar radiation, and humidity on UTCI in NAAP. Estimation of UTCI using these variables showed a higher performance of random forest (RF) (Kling-Gupta Efficiency = 0.84) compared to other models. The projection of UTCI from CMIP6 climatic model simulations using the RF model revealed a decrease in UTCI for the 1.5 °C temperature rise scenario by 0.25–0.75 °C, while an increase by 0.25–0.75 °C for the 2.0 °C temperature rise scenario in most of NAAP. The study revealed that even a modest increase of 0.5 °C in global warming could lead to a 20-day increase in the number of days with moderate thermal stress in Egypt and Sudan and a significant increase in the number of days with strong thermal stress in the Arabian Peninsula. The population exposure to heat stress would increase significantly even under the most ambitious Paris Agreement goals. These findings highlight the urgent need for adaptation and mitigation strategies to protect public health and well-being in the NAAP region from escalating risks.
Keywords: Machine learning; Paris agreement goals; Population exposure; Thermal extremes; UTCI

The Impact of Climate Change on Education - Venegas Marin, Sergio; Schwarz, Lara; Sabarwal, Shwetlena (2024)
KerkoCite.ItemAlsoKnownAs: 2129771:2S3PRB7I
Keywords: evidence_review

Impact of Climate Change and Environmental Risks on Learning Outcomes - Haßler, Björn; Eso, Olamide; Villavicencio Peralta, Xuzel Ana; Waziri, Nafisa (Commonwealth Secretariat, 2024)
An output of the Open Development & Education (https://opendeved.net/), developed for 22CCEM.
ZenodoArchiveID: 10719044 ZenodoArchiveConcept: 10719043 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1079 2129771:R8TU4GMW 4874017:QWQBCKPL
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon; evidence_review

South Sudan announces schools closure as heatwave deepens (Sudan Tribune, 2024)
March 16, 2024 (JUBA) – South Sudan on Saturday announced an indefinite closure of all schools due to heatwaves characterized by very high temperatures in recent days. The Health minister, Yolanda Awel Deng said the heatwave could last for two weeks, with temperatures ranging between 41 degrees and 45 degrees Celsius. “The government has decided to take the following measures, one, close down all schools with effect from March 18, two, during the closure of the schools, parents are advised to stop their children from playing outdoors for prolonged periods and they should also monitor children, especially the young ones, for signs of heat exhaustion and heatstroke,” Awel told reporters in the capital, Juba. Heatwaves, the minister said, can acutely impact large populations for short periods, often trigger public health emergencies, and result in excess mortality and cascading socioeconomic impacts like loss of work capacity and labor productivity and can also cause loss of health service delivery capacity. Awel said the disease surveillance department at the national Health ministry has put a system in place meant to detect and respond to cases, adding there are already cases of death related to excessive heat being reported in South Sudan. The Undersecretary in the Ministry of Environment, Joseph Africano Bartel said climate change is becoming a global phenomenon in which South Sudan will experience a lot of temperature fluctuations. Africano advised the public to take precaution against rising heatwaves in the country. He urged developed countries to cut emissions, saying South Sudan will soon experience climate change impact, including heavy rains, floods and droughts. A circular from the Environment and Forestry ministry warns of likely illness and deaths among adult and children should they be exposed to the high heatwaves. According to the World Meteorological Organization (WMO), a heatwave can be defined as a period where local excess heat accumulates over a sequence of unusually hot days and nights. As such, heatwaves amplify many risks, such as health-related or economic risks, including increased human mortality, drought and water quality, wildlife and smoke, power shortages and agricultural losses.
KerkoCite.ItemAlsoKnownAs: 2129771:XG4BC8Z7 2129771:XG4BC8Z7 2129771:XG4BC8Z7 2129771:XG4BC8Z7 2129771:XG4BC8Z7 2129771:XG4BC8Z7 2129771:XG4BC8Z7 5072953:VHMEVJNH
Keywords: _z:class:countries; evidence_review

South Sudan closes schools due to extreme heatwave (Monitor, 2024)
"During the closure of the schools, parents are advised to stop their children from playing outdoors for prolonged periods and they should also monitor children, especially the young ones, for...
Keywords: _z:class:countries; evidence_review_2

South Sudan closes schools due to extreme heatwave (Monitor, 2024)
"During the closure of the schools, parents are advised to stop their children from playing outdoors for prolonged periods and they should also monitor children, especially the young ones, for...
Keywords: _z:class:countries

South Sudan shutters all schools as it prepares for an extreme heat wave (Washington Post, 2024)
South Sudan’s government is closing down all schools starting Monday as the country prepares for a wave of extreme heat expected to last two weeks
Keywords: _z:class:countries; evidence_review_2

South Sudan shutters all schools as it prepares for an extreme heat wave - Machol, Deng (AP News, 2024)
South Sudan’s government is closing down all schools starting Monday as the country prepares for a wave of extreme heat expected to last two weeks.
KerkoCite.ItemAlsoKnownAs: 2129771:F98WG4DI 2129771:F98WG4DI 2129771:F98WG4DI 2129771:F98WG4DI 2129771:F98WG4DI 2129771:F98WG4DI 2129771:F98WG4DI 5072953:MVVSI96A
Keywords: _z:class:countries; evidence_review

UPDATE: The government of the republic of South Sudan has ordered the closure of all schools starting from Monday, 18th, March 2024 due to the high temperatures. According to the country's health ministry, there are reported cases of death resulting from high heat #NTVNews https://t.co/8s6Vr71yK1 - NTV UGANDA [@ntvuganda] (Twitter, 2024)
KerkoCite.ItemAlsoKnownAs: 2129771:SJQKPD99 2129771:SJQKPD99 2129771:SJQKPD99 2129771:SJQKPD99 2129771:SJQKPD99 2129771:SJQKPD99 2129771:SJQKPD99 5072953:449RER6Y
Keywords: _z:class:countries; evidence_review

Inclusive Climate Action: A Scoping Review on the Representation and Inclusion of People with Intellectual Disability in Climate Change Research - Watfern, Chloe; Carnemolla, Phillippa (Research Square (Research Square), 2024)
Abstract Climate change disproportionally affects people with intellectual disability. Despite this, people with intellectual disability are rarely included in conversations about just environmental futures. Using PRISMA-P guidelines, this scoping review maps the academic literature surrounding intellectual disability and climate change. We identified three key themes in the thirteen articles included in our review. First, people with intellectual disability experience heightened risks and barriers during and after natural disasters. Second, they are largely absent from government disaster planning and response. Third, inclusive education initiatives are in their infancy. Overall, people with intellectual disability are not involved as leaders or collaborators in research or practice related to climate change. The literature focuses almost exclusively on natural disasters as opposed to the broader context of the climate crisis. We take a critical lens, reframing the role of people with intellectual disability in climate change discourses: from helpless victims to potential caretakers and advocates for a safer climate.
openalex: W4392699796
Keywords: _z:class:countries; openalex:import; openalex:yes

A systematic review of ambient heat and sleep in a warming climate - Chevance, Guillaume; Minor, Kelton; Vielma, Constanza; Campi, Emmanuel; O’Callaghan-Gordo, Cristina; Basagaña, Xavier; Ballester, Joan; Bernard, Paquito (Sleep Medicine Reviews, 2024)
Climate change is elevating nighttime and daytime temperatures worldwide, affecting a broad continuum of behavioral and health outcomes. Disturbed sleep is a plausible pathway linking rising ambient temperatures with several observed adverse human responses shown to increase during hot weather. This systematic review aims to provide a comprehensive overview of the literature investigating the relationship between ambient temperature and valid sleep outcomes measured in real-world settings, globally. We show that higher outdoor or indoor temperatures are generally associated with degraded sleep quality and quantity worldwide. The negative effect of heat persists across sleep measures, and is stronger during the hottest months and days, in vulnerable populations, and the warmest regions. Although we identify opportunities to strengthen the state of the science, limited evidence of fast sleep adaptation to heat suggests rising temperatures induced by climate change and urbanization pose a planetary threat to human sleep, and therefore health, performance, and wellbeing.
openalex: W4392505490
Keywords: _z:class:countries; evidence_review; openalex:citedBy; openalex:import; selected_for:effects of climate ch...on learning...LMICs 2024; tagged

‘We don’t need air con’: how Burkina Faso builds schools that stay cool in 40C heat (The Guardian, 2024)
Architects use local materials and merge traditional techniques with modern technology to make schools and orphanages cool, welcoming places
KerkoCite.ItemAlsoKnownAs: 2129771:BA957YF9 2129771:BA957YF9 2129771:BA957YF9 2129771:BA957YF9 5072953:3PWYGTL3 5072953:EIAHFERP
Keywords: Africa; Architecture; Burkina Faso; Environment; _z:class:countries; evidence_review_2

Improving the forecast of fine dust emission and transmission from cattle barns: a comprehensive data package and analysis - Mostafa, Ehab; Paßmann, Jessica; Abdellatif, Hassan R. S.; Buescher, Wolfgang (Environmental Sciences Europe, 2024)
Abstract The livestock sector emits harmful gases and bioaerosols, impacting animals, plants, and human health. Ventilation systems in livestock buildings disperse polluted air, affecting nearby air quality depending on the wind patterns and atmospheric stability. Understanding pollutant emission and transmission is crucial for environmental mitigation. This study focuses on fine dust dispersion from dairy cattle buildings. Chemical and microscopic analyses were conducted to identify the cattle barn dust sources. Particle mass emissions were quantified by measuring particle mass concentrations and air volume flow using the tracer gas decay method. Seasonal and daily effects on dust emissions were studied. Remarkably, particle emissions remained below prescribed values in Germany. Additionally, particle transmission, including resuspension and adsorption parameters, was investigated using a developed wind tunnel. Resuspension measurements revealed minimal resuspended particle mass due to low ground wind speeds. Notably, wheat, as a model plant, exhibited high adsorption rates, which increased with particle size. Overall, the findings for resuspension and adsorption parameters provide an initial database for understanding fine dust transmission from cattle barns.
Keywords: _z:class:countries

Long-Term Characterization of Indoor Air Quality at a Research Area Building: Comparing Reference Instruments and Low-Cost Sensors - Calvello, Mariarosaria; Agresti, Francesca; Esposito, Francesco; Pavese, Giulia (Indoor Air, 2024)
Indoor particle number size distribution (0.3-10 μm), equivalent black carbon (eBC), and Ångström absorption exponent (AAE) data were collected in real conditions, over a ten-month period at a research area building, in a semirural site, to characterize indoor aerosol loading. Additionally, during the campaign, emissions from four indoor sources commonly used at the site (incense, traditional cigarettes, electronic cigarettes, and heat-not-burn products) were studied during short-term experiments with the support of ultrafine particle (UFP) monitoring. Two particle low-cost sensors (PM LCS), Sensirion SPS30 (0.3-10 μm), were evaluated in the long-term campaign and during fast emission processes, to assess their accuracy and reliability. Penetration and infiltration of both fine and coarse particles from outdoor traffic, domestic heating, and dust resuspension were inferred as the main sources of indoor aerosols on a long-term basis. Moreover, long-range transported dust aerosols were found to influence indoor coarse number concentration. Among the source events, heat-not-burn (HNB) product resulted in the lowest effect on indoor air quality, whereas the highest AAE values from incense and traditional cigarettes suggest the brown carbon (BrC) production. The highest emission of UFP was caused by electronic cigarettes (e-cig), which spanned particles from the ultrafine to the coarse fractions. This was likely due to the release of metal and silicate from the coil. Analysis of number size distributions of the four experiments revealed the emission of fine particles (0.3-1 μm) and super micron particles. SPS30s performance was satisfactory in terms of accuracy, precision, and durability, indicating that these devices are suitable for monitoring indoor air quality. Additionally, the two PM LCS were able to detect all simulated fast emission sources.
KerkoCite.ItemAlsoKnownAs: 5072953:5LC9WZ9A 5072953:M745DDSL
Keywords: _important; _z:class:countries

Applications of artificial intelligence for energy efficiency throughout the building lifecycle: An overview - Yussuf, Raheemat O.; Asfour, Omar S. (Energy and Buildings, 2024)
The use of Artificial Intelligence (AI) technologies in buildings can assist in reducing energy consumption through enhanced control, automation, and reliability. This review aims to explore the use of AI to enhance energy efficiency throughout various stages of the building lifecycle, including building design, construction, operation and control, maintenance, and retrofit. The review encompasses multiple studies in the field published between 2018 and 2023. These studies were identified through keyword searches that best represent the topic, using various research databases. In addition to summarizing the technologies and approaches related to AI and energy efficiency, this review discusses future opportunities for the application of AI in energy efficiency within these lifecycle stages. The review highlights that AI-based solutions are currently employed in building design generation and optimization, decision-making, predictive and adaptive control, fault detection and diagnosis, as well as energy benchmarking. These applications effectively facilitate energy efficiency in buildings to meet today's energy needs. However, further research is needed to explore the use of AI in the construction phase to support the development of energy-efficient construction techniques and systems, in addition to scheduling and predictive decision-making.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2024.113903 5072953:DJZPDDXN openalex: W4390748878
Keywords: Artificial Intelligence; Building Lifecycle; Buildings; Energy Efficiency; _z:class:countries; _z:class:themes; _z:no_pdf; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11006 Building Information Modeling in Construction Industry; oa:topic:T12120 Low-Cost Air Quality Monitoring Systems; openalex:n:1; openalex:yes

Improved grey principal component analysis neural network based adaptive thermal comfort model: Application in the enclosed cabin with microclimatic conditions - Chen, Siyu; Xue, Hongjun; Zhang, Xiaoyan; Dang, Sina; Qu, Jue (Energy and Buildings, 2024)
Predicting the thermal comfort of operators in enclosed cabins under extreme operational conditions is crucial for the enhanced and optimal design of cabin air circulation systems. In this study, an improved supervised machine learning algorithm, namely a Grey Principal Component Analysis (G-PCA) was proposed to evaluate the operators’ thermal comfort. The comprehensive dataset was first attained and constructed from the proposed 32 indicators, which recorded each tested object’s EEG and physiological features, core body temperature, skin temperature, and subjective assessments. The accuracy of the proposed model was demonstrated by comparing it with the results predicted via existing indicator sets (PMV and 7-point skin temperature) and modelling algorithms (BP and PCA BP). The results showed that the prediction accuracy of the PMV model, 7-point skin temperature, the 32 indicators were found to be 79.4%, 82.8%, 96.1%, utilising the G-PCA WNN algorithm, and the prediction accuracy of BP, PCA BP, G-PCA WNN is 82.3%, 89.9%, 96.1%, based on the 32 indicators. A conclusion could be drawn that the proposed 32 indicators can incorporate a more comprehensive range of thermal comfort information, and the improved G-PCA WNN thermal comfort prediction model achieved the best prediction performance among the compared algorithms and models.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2024.113963 5072953:DBE5FQ7V openalex: W4391755697
Keywords: Enclosed cabin environment; Neural network model; Real-time prediction; Self-adaptive model; Thermal comfort; _important; _z:class:countries; _z:class:themes; _z:no_pdf; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11109 Physiological Responses to Heat Stress in Humans; oa:topic:T11244 Impact of Climate Change on Human Health; openalex:n:1; openalex:yes; selected_for:Predictive models for classroom conditions 2024

Developing a deep neural network model for predicting ventilation rates in public housing buildings in Hong Kong - Dai, Ho Kam; Shi, Yifu; Chen, Chun (Energy and Buildings, 2024)
In Hong Kong, 45 % of the population live in public housing buildings. This study aimed to develop deep neural network (DNN) models for efficiently predicting the ventilation rates in public housing buildings in Hong Kong in the era of modular flat design. First, a database of ventilation rates in Cheung Tai House, a representative public housing building, under 23 wind conditions and 32 different ventilation settings, was obtained by means of computational fluid dynamic (CFD) and multi-zone airflow network models. On-site measurements were conducted in two residential units to validate the numerical models. The database was then used to train the DNN models for the 32 ventilation settings, respectively, for predicting the ventilation rate. The trained DNN models can accurately predict the ventilation rates in Cheung Tai House with a mean absolute percentage error (MAPE) of 4.3 %. The trained DNN models were further validated by numerical simulation results for Hung Fuk Estate and field measurement results for Chun Yeung Estate. The results show that the trained DNN models based on the Cheung Tai House database could predict the ventilation rates of other public housing buildings reasonably well, with a MAPE of 10 % regardless of the building’s structural shape.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2024.113993 5072953:N2KMIA55 openalex: W4391906572
Keywords: Computational fluid dynamics; Deep neural network model; Modular flat design; Multi-zone airflow network model; Public housing; _z:class:countries; _z:class:themes; _z:no_pdf; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:n:1; openalex:yes

Using AI to Automate Literature Reviews - Haßler, Björn; Hassan, Mustafa; Klune, Christopher (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10529049 ZenodoArchiveConcept: 10529048 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1003 2129771:JC66TBWQ 2405685:BVD8JX7V
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon; evidence_review

Belize: Making an Impact to Improve Lives Selected Results in IDB Group-supported Projects on Climate Change and Education (2024)
Two of the development challenges that Belize has recently worked on, with support from the IDB Group, are vulnerability to climate change and educational quality. The measures implemented on both fronts have allowed relevant achievements. In terms of climate resilience, flooding has been significantly reduced, as a result of investments in infrastructure and, especially, in nature-based solutions. Regarding the quality of education, progress has been made with innovative pedagogical models and teaching in STEAM areas (science, technology, engineering, arts and mathematics).
openalex: W4391693336
Keywords: C:Belize; _z:class:countries; _z:class:themes; oa:topic:T10119 Sustainability Transitions and Resilience in Social-Ecological Systems; oa:topic:T10439 Adaptation to Climate Change in Agriculture; oa:topic:T12656 Impact of Climate Change on Human Migration; openalex:import; openalex:yes

Published research on the human health implications of climate change between 2012 and 2021: cross sectional study - Bartlett, Victoria; Doernberg, Harry; Mooghali, Maryam; Gupta, Ravi; Wallach, John R.; Nyhan, Kate; Chen, Kai; Ross, Joseph S. (BMJ Medicine, 2024)
Objective To better understand the state of research on the effects of climate change on human health, including exposures, health conditions, populations, areas of the world studied, funding sources, and publication characteristics, with a focus on topics that are relevant for populations at risk. Design Cross sectional study. Data sources The National Institute of Environmental Health Sciences climate change and human health literature portal, a curated bibliographical database of global peer reviewed research and grey literature was searched. The database combines searches of multiple search engines including PubMed, Web of Science, and Google Scholar, and includes added-value expert tagging of climate change exposures and health impacts. Eligibility criteria Inclusion criteria were peer reviewed, original research articles that investigated the health effects of climate change and were published in English from 2012 to 2021. After identification, a 10% random sample was selected to manually perform a detailed characterisation of research topics and publication information. Results 10 325 original research articles were published between 2012 and 2021, and the number of articles increased by 23% annually. In a random sample of 1014 articles, several gaps were found in research topics that are particularly relevant to populations at risk, such as those in the global south (134 countries established through the United Nations Office for South-South Cooperation) (n=444; 43.8%), adults aged 65 years or older (n=195; 19.2%), and on topics related to human conflict and migration (n=25; 2.5%) and food and water quality and security (n=148; 14.6%). Additionally, fewer first authors were from the global south (n=349; 34.4%), which may partly explain why research focusing on these countries is disproportionally less. Conclusions Although the body of research on the health effects of climate change has grown substantially over the past decade, including those with a focus on the global south, a disproportionate focus continues to be on countries in the global north and less at risk populations. Governments are the largest source of funding for such research, and governments, particularly in the global north, need to re-orient their climate and health research funding to support researchers in the global south and to be more inclusive of issues that are relevant to the global south.
openalex: W4391722099
Keywords: _z:class:countries; openalex:citedBy; openalex:import; selected_for:effects of climate ch...on learning...LMICs 2024; tagged

Youth Response to Climate Change: Learning from Indigenous Land-Based Camp at the Northern Saskatchewan Indigenous, Canada - Datta, Prarthona; Datta, Ranjan; Lewis, Kevin; Hurlbert, Margot (EXPLORE, 2024)
openalex: W4392087410
Keywords: C:Canada; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10348 Indigenous Health Disparities and Decolonization; oa:topic:T12614 Health and Well-being of Arctic Indigenous Peoples; oa:topic:T12656 Impact of Climate Change on Human Migration; openalex:import; openalex:yes

Integrating conceptual and machine learning models to enhance daily-Scale streamflow simulation and assessing climate change impact in the watersheds of the Godavari basin, India - Reddy, Nagireddy Masthan; Saravanan, Subbarayan; Paneerselvam, Balamurugan (Environmental Research, 2024)
This study examined and addressed climate change's effects on hydrological patterns, particularly in critical places like the Godavari River basin. This study used daily gridded rainfall and temperature datasets from the Indian Meteorological Department (IMD) for model training and testing, 70% and 30%, respectively. To anticipate future hydrological shifts, the study harnessed the EC-Earth3 data, presenting an innovative methodology tailored to the unique hydrological dynamics of the Godavari River basin. The Sacramento model provided initial streamflow estimates for Kanhargaon, Nowrangpur, and Wairagarh. This approach melded traditional hydrological modeling with advanced multi-layer perceptron (MLP) capabilities. When combined with parameters like lagged rainfall, lagged streamflow, potential evapotranspiration (PET), and temperature variations, these initial outputs were further refined using the Sac-MLP model. A comparison with Sacramento revealed the superior performance of the Sac-MLP model. For instance, during training, the Nash Sutcliffe efficiency (NSE) values for the Sac-MLP witnessed an improvement from 0.610 to 0.810 in Kanhargaon, 0.580 to 0.692 in Nowrangpur, and 0.675 to 0.849 in Wairagarh. The results of the testing further corroborated these findings, as evidenced by the increase in the NSE for Kanhargaon from 0.890 to 0.910. Additionally, Nowrangpur and Wairagarh experienced notable improvements, with their NSE values rising from 0.629 to 0.785 and 0.725 to 0.902, respectively. Projections based on EC-Earth3 data across various scenarios highlighted significant shifts in rainfall and temperature patterns, especially in the far future (2071–2100). Regarding the relative change in annual streamflow, Kanhargaon projections under SSP370 and SSP585 for the far future indicate increases of 584.38% and 662.74%. Similarly, Nowrangpur and Wairagarh are projected to see increases of 98.27% and 114.98%, and 81.68% and 108.08%, respectively. This study uses EC-Earth3 estimates to demonstrate the Sac-MLP model's accuracy and importance in climate change water resource planning. The unique method for region-specific hydrological analysis provides vital insights for sustainable water resource management. This research provides a deeper understanding of climate-induced hydrological changes and a robust modeling approach for accurate predictions in changing environmental conditions.
openalex: W4391812592
Keywords: _z:class:countries; oa:sdg:13 Climate action; oa:topic:T10330 Hydrological Modeling and Water Resource Management; oa:topic:T10930 Global Flood Risk Assessment and Management; oa:topic:T11490 Hydrological Modeling using Machine Learning Methods; openalex:import; openalex:n:1; openalex:yes

Why disability inclusion is important for climate resilience - King, Molly M. (2024)
openalex: W4391337198
Keywords: _z:class:countries; openalex:import; openalex:yes

Supervised Machine Learning Approaches for Predicting Key Pollutants and for the Sustainable Enhancement of Urban Air Quality: A Systematic Review - Essamlali, Ismail; Nhaila, Hasna; Khaïli, Mohamed El (Sustainability, 2024)
Urban air pollution is a pressing global issue driven by factors such as swift urbanization, population expansion, and heightened industrial activities. To address this challenge, the integration of Machine Learning (ML) into smart cities presents a promising avenue. Our article offers comprehensive insights into recent advancements in air quality research, employing the PRISMA method as a cornerstone for the reviewing process, while simultaneously exploring the application of frequently employed ML methodologies. Focusing on supervised learning algorithms, the study meticulously analyzes air quality data, elucidating their unique benefits and challenges. These frequently employed ML techniques, including LSTM (Long Short-Term Memory), RF (Random Forest), ANN (Artificial Neural Networks), and SVR (Support Vector Regression), are instrumental in our quest for cleaner, healthier urban environments. By accurately predicting key pollutants such as particulate matter (PM), nitrogen oxides (NOx), carbon monoxide (CO), and ozone (O3), these methods offer tangible solutions for society. They enable informed decision-making for urban planners and policymakers, leading to proactive, sustainable strategies to combat urban air pollution. As a result, the well-being and health of urban populations are significantly improved. In this revised abstract, the importance of frequently employed ML methods in the context of air quality is explicitly emphasized, underlining their role in improving urban environments and enhancing the well-being of urban populations.
openalex: W4391131339
Keywords: _z:class:countries; evidence_review; openalex:citedBy; openalex:import; selected_for:effects of climate ch...on learning...LMICs 2024; tagged

Introducing the next iteration of our sensor box - Haßler, Björn; Bablok, Bernhard (2024)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10456801 ZenodoArchiveConcept: 10456800 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1064 2129771:FNTQ646H 4874017:G95V88FS 5072953:8SMU77AC 5072953:MMXK965C
Keywords: _publish; _r:AddedByMyEducationEvidence; _z:class:countries; _z:class:themes

Emissions of Volatile Organic Compounds from Human Occupants in a Student Office: Dependence on Ozone Concentration - Qu, Yuekun; Xie, Di; Liu, Yingjun (ACS Environmental Au, 2024)
Keywords: _z:class:countries

The effects of cool roofs on health, environmental, and economic outcomes in rural Africa: study protocol for a community-based cluster randomized controlled trial - Bunker, Aditi; Compoaré, Guillaume; Sewe, Maquins Odhiambo; Laurent, Jose Guillermo Cedeno; Zabré, Pascal; Boudo, Valentin; Ouédraogo, Windpanga Aristide; Ouermi, Lucienne; Jackson, Susan T.; Arisco, Nicholas; Vijayakumar, Govind; Yildirim, Ferhat Baran; et al. (Trials, 2024)
High ambient air temperatures in Africa pose significant health and behavioral challenges in populations with limited access to cooling adaptations. The built environment can exacerbate heat exposure, making passive home cooling adaptations a potential method for protecting occupants against indoor heat exposure.
openalex: W4390908494 KerkoCite.ItemAlsoKnownAs: 5072953:FKAKUTLN 5072953:JEITJCWJ 5072953:QFAE9T62
Keywords: C:Burkina Faso; Climate change adaptation; Cool roofs; Heat exposure; Passive home cooling; Randomized controlled trial; Sub-Saharan Africa; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11244 Impact of Climate Change on Human Health; openalex:n:1; openalex:yes

Decolonizing Climate Change Adaptations from Indigenous Perspectives: Learning Reflections from Munda Indigenous Communities, Coastal Areas in Bangladesh - Datta, Ranjan; Kairy, Barsha (Sustainability, 2024)
This study explores the imperative need for decolonizing climate change adaptation strategies by focusing on Indigenous knowledge and perspectives. Focusing on the Munda Indigenous communities residing in the coastal areas of Bangladesh, the research offers critical insights into the intricate relationship between Indigenous wisdom and sustainable climate adaptation. By engaging with the Munda Indigenous people and their traditions, this study explores how traditional ecological knowledge and practices can inform and enhance contemporary climate adaptation efforts. Following the decolonial theoretical research framework, this research used participatory research methods and collaboration with the Munda Indigenous community. In this study, we shared our learning reflections to uncover unique approaches to climate resilience, including traditional community-based disaster risk reduction and cultural practices that foster social cohesion. These insights challenge the prevailing Western-centric climate adaptation paradigms, emphasizing recognizing and valuing Indigenous voices in climate discourse. The research underscores the significance of empowering Indigenous communities as key stakeholders in climate adaptation policy and decision-making. It calls for shifting from top-down, colonial approaches towards more inclusive, culturally sensitive strategies. The Munda Indigenous communities’ experiences offer valuable lessons that can inform broader efforts to address climate change, fostering resilience and harmonious coexistence between people and their environment. This study advocates for integrating Indigenous knowledge, practices, and worldviews into climate adaptation frameworks to create more effective, equitable, and sustainable solutions for the challenges posed by climate change.
openalex: W4390913855
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10439 Adaptation to Climate Change in Agriculture; oa:topic:T10747 Community Resilience to Natural Disasters; oa:topic:T12656 Impact of Climate Change on Human Migration; openalex:import; openalex:yes

Decolonizing Climate Change Adaptations from Indigenous Perspectives: Learning Reflections from Munda Indigenous Communities, Coastal Areas in Bangladesh - Datta, Ranjan; Kairy, Barsha (Sustainability, 2024)
This study explores the imperative need for decolonizing climate change adaptation strategies by focusing on Indigenous knowledge and perspectives. Focusing on the Munda Indigenous communities residing in the coastal areas of Bangladesh, the research offers critical insights into the intricate relationship between Indigenous wisdom and sustainable climate adaptation. By engaging with the Munda Indigenous people and their traditions, this study explores how traditional ecological knowledge and practices can inform and enhance contemporary climate adaptation efforts. Following the decolonial theoretical research framework, this research used participatory research methods and collaboration with the Munda Indigenous community. In this study, we shared our learning reflections to uncover unique approaches to climate resilience, including traditional community-based disaster risk reduction and cultural practices that foster social cohesion. These insights challenge the prevailing Western-centric climate adaptation paradigms, emphasizing recognizing and valuing Indigenous voices in climate discourse. The research underscores the significance of empowering Indigenous communities as key stakeholders in climate adaptation policy and decision-making. It calls for shifting from top-down, colonial approaches towards more inclusive, culturally sensitive strategies. The Munda Indigenous communities’ experiences offer valuable lessons that can inform broader efforts to address climate change, fostering resilience and harmonious coexistence between people and their environment. This study advocates for integrating Indigenous knowledge, practices, and worldviews into climate adaptation frameworks to create more effective, equitable, and sustainable solutions for the challenges posed by climate change.
openalex: W4390913855
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10439 Adaptation to Climate Change in Agriculture; oa:topic:T10747 Community Resilience to Natural Disasters; oa:topic:T12656 Impact of Climate Change on Human Migration; openalex:import; openalex:yes

Thermal modeling for control applications of 60,000 homes in North America using smart thermostat data - Vallianos, Charalampos; Candanedo, José; Athienitis, Andreas (Energy and Buildings, 2024)
As smart thermostats become increasingly available in residential buildings, there is an opportunity to use measured building data to calibrate models for community and district applications, instead of relying on high-fidelity simulations. This study used smart thermostat data from 60,000 houses in North America to create single-zone models. The model structure was defined with an automated forward selection procedure. 61% of the final models were classified as good fits and the structure of 80% of them was of 5th-order (5 thermal capacitances). An investigation of the 24-hour prediction error of the models showed that the ones classified as good fits are accurate enough for day-ahead predictions and Model Predictive Control (MPC) applications. An analysis of the model parameters suggested no strong correlation between them and the available metadata. The time constants of the houses were estimated, providing valuable information about the houses thermal inertia. Building models that can accurately capture and leverage building thermal inertia are ideal candidates for MPC and energy flexibility applications.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2023.113811 5072953:BDEU3AD2 openalex: W4389265746
Keywords: Building simulation; Building thermal dynamics; Grey-box models; Model Predictive Control (MPC); _z:class:countries; _z:class:themes; _z:no_pdf; oa:sdg:11 Sustainable cities and communities; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10603 Demand Response in Smart Grids; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:n:1; openalex:yes

Predicting indoor 3D airflow distribution using artificial neural networks with two different architectures - Zheng, Yulin; Xu, Xiangguo (Energy and Buildings, 2024)
To meet the thermal comfort requirements of room occupants, a fast and accurate method for predicting indoor high-resolution 3D airflow distribution is necessary, which can be combined with heating, ventilation, and air conditioning (HVAC) systems to adjust the indoor environment. Artificial neural networks (ANN) can establish complex mappings between variables with nonlinear relationships. The aim of this study was to verify the feasibility of an ANN for the fast and accurate prediction of indoor 3D airflow distribution. Considering two prediction strategies, ANN A and B were constructed. The inputs of both ANNs were the air supply velocity, air supply direction, and section location. ANN A output the airflow distribution of the entire room directly, whereas ANN B output the airflow distribution of the characteristic sections first and then the airflow distribution of other sections according to the contribution of the characteristic sections. The two ANNs’ performances on training and testing datasets were compared. Both ANNs performed well in the training and interpolation cases. However, their performances decreased rapidly in the extrapolation cases. In the case of a large gap between the input and output dimensions of the ANNs, the two-step prediction strategy improved the prediction accuracy, accelerated convergence, and alleviated data imbalance problems. The prediction time of ANN A and B was 0.89 s and 12.38 s, respectively. The ANN can predict indoor high-resolution 3D airflow distribution quickly and accurately, and can add functions that include identifying internal heat sources and air supply inlet position changes. ANN combined with HVAC could allow real-time control to regulate indoor airflow.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2023.113841 5072953:GBH3ABMT openalex: W4389956152
Keywords: Artificial neural network (ANN); Computational fluid dynamics (CFD); Indoor high-resolution 3D airflow distribution; Two-step prediction; _z:class:countries; _z:class:themes; _z:no_pdf; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10990 Airborne Transmission of Respiratory Viruses; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:n:1; openalex:yes

Re-storying schools as “research sites” of climate change in the Chthulucene : diffractively reading through the land of a primary school in South Africa - Reynolds, Rose-Anne; Murris, Karin (The Journal of Environmental Education, 2024)
Inspired by Karen Barad’s agential realism and Donna Haraway’s use of the Chthulucene, our paper profoundly troubles and unsettles the humanist subject that has been the cause of so much trouble. Re-turning to a government primary school in Cape Town as the “research site,” we adopt temporal and spatial diffraction as a postqualitative research methodology. The colonial practices related to land ownership, are not in the past, but remain in its be(com)ing. Land “use” in South Africa during Apartheid, was, and still is, a form of violence. Thinking-with Neimanis and McLauchlan, we understand a school as not separate from the phenomenon of climate change, but as one of its sites and as a feminist project. A diffractive image articulates aesthetically and politically how the land as the more-than-human is a significant part of the phenomenon and queers school as a concept and “research site.”
openalex:W4390807577 mag: KerkoCite.ItemAlsoKnownAs: 10.1080/00958964.2023.2259831 5072953:VCGJCITM
Keywords: C:South Africa; _z:class:countries; _z:class:themes; _z:no_pdf; oa:topic:T10738 Exploration of Posthumanist Performativity in Social Sciences; oa:topic:T11506 Participation of Children in Research and Policy; oa:topic:T12295 Foucauldian Governmentality and Neoliberalism Studies; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

University Students’ Perception of Community Information Centres as a Vehicle for Climate Change Awareness Creation in Ghana. - Abednego, Adjei Baffour; Adu-Agyei, Nana Obeng; Pawar, V P; Nkrumah, Collins (International Journal of Research and Scientific Innovation, 2024)
Information has a significant role in the growth of people and societies. Yet access to information is unequal across communities, particularly in rural areas in developing countries. Given this, people’s consciousness of climatic change differs by several factors including location and the type of medium employed. This paper examines community information centres as a vehicle for climate change awareness creation in Ghana. The paper adopted a quantitative approach with 205 participants randomly chosen from six public universities. The finding shows that selling of traditional medicines dominates information centres’ activities. Environmental health and climate change education occupy infinitesimal place in these centres’ activities with climate change occupying the very bottom. The study also shows that using local language, providing a platform for grassroot education, integrating scientific and indigenous knowledge, etc. are some of the ways these centres can be used to promote climate change consciousness. The results also disclose that community information centres face the problems of limited resources, lack of interest, unreliable power source etc. Regarding how to manage these challenges, the majority of the participants proposed the role of government in providing resources, community sensitisation, an alternative power source, among others. The paper concludes that although proper attention has not been given to climate change awareness creation in information centres’ activities in Ghana, these informational hubs can be a medium to raise climate change awareness in the disadvantaged and marginalised rural communities in which they are situated to facilitate local adaptation.
openalex:W4390951275 mag: KerkoCite.ItemAlsoKnownAs: 10.51244/ijrsi.2023.1012058 5072953:DDXDDKQJ
Keywords: C:Ghana; _z:class:countries; _z:class:themes; _z:no_pdf; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Psychological Ill-Being Caused By Climate Change Among Persons With Disabilities "PWD" In The Kingdom Of Saudi Arabia - القديمي, فاطمة بنت يحيى حسن (مجلة الجامعة الإسلامية للعلوم التربوية والاجتماعية, 2024)
openalex: W4392249639
Keywords: _z:class:countries; openalex:import; openalex:yes

Climate, Environment and Education (as child’s play) What? Why? How? - Bangay, Colin (2024)
KerkoCite.ItemAlsoKnownAs: 5072953:U9FP27JD

Ways to Think About Education Systems Risk Analysis at a Country Level - Bangay, Colin (Foreign, Commonwealth & Development Office, UK, 2024)
KerkoCite.ItemAlsoKnownAs: 5072953:HKXACYAG

Mapping climate mitigation policy literature using machine learning: disparities between scientific attention, policy density, and emissions - Callaghan, Max; Banisch, Lucy; Doebbeling-Hildebrandt, Niklas; Edmondson, Duncan; Flachsland, Christian; Lamb, William; Levi, Sebastian; Müller-Hansen, Finn; Posada, Eduardo; Vasudevan, Shraddha (2024)
KerkoCite.ItemAlsoKnownAs: 5072953:7XN7EAGW 5072953:FD2VCUFD
Keywords: _z:class:countries

Unintended consequences of English school stock energy-efficient retrofit on cognitive performance of children under climate change - Dong, J.; Schwartz, Y.; Korolija, I.; Mumovic, D. (Building and Environment, 2024)
School building stock retrofit forms a key part of UK’s commitment to net-zero carbon target by 2050. However, with a changing climate, the retrofit of school buildings may have unintended consequences on classroom thermal environments and cognitive performance of children in non-heating seasons. This paper aims to quantify the impact of school stock retrofit in accordance with increasingly tightening energy efficiency regulatory requirements on cognitive performance of English children, while also exploring the potential adaptation measures under climate change. The results indicate that English schools that undergo envelope insulation exhibit higher Cognitive Performance Loss (CPL) of children compared to their original conditions. Passive climate adaptation measures, especially increased daytime ventilation rate was found to be an effective strategy for mitigating the impact of climate change on cognitive performance. However, the benefits of passive measures will diminish as the climate warms, while air conditioning will be required to maintain cognitive performance loss at relatively low levels. In addition to the reduction of heating load, envelope insulation can provide benefits for English schools in cooler climatic regions from both cognitive performance and energy point of view. The study calls for the CPL to be added as one of the key performance indicators when considering the long-term impact of climate change on schools. This would enable policy makers and relevant stakeholders to make more holistic decisions regarding school stock retrofit while ensuring that classrooms are conducive to learning.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.buildenv.2023.111107 5072953:RXETR3RL
Keywords: _z:class:countries

The orchestration of a sustainable development agenda in the European Higher Education Area - Kushnir, Iryna; Eta, Elizabeth Agbor; Mbah, Marcellus Forh; Kennedy, Charlotte-Rose (International Journal of Sustainability in Higher Education, 2024)
Publisher: Emerald Publishing Limited KerkoCite.ItemAlsoKnownAs: 10.1108/IJSHE-12-2022-0394 5072953:887LZGTD openalex: W4384305696
Keywords: _z:class:countries; _z:class:themes; oa:keyword:european higher education area; oa:keyword:sustainable development; oa:keyword:sustainable development agenda; oa:topic:T11300 Global Governance in Education Policy Research; oa:topic:T11835 Sustainability Education in Higher Education Institutions; oa:topic:T12545 Education for Global Citizenship in a Globalized World; openalex:n:1; openalex:yes

The orchestration of a sustainable development agenda in the European Higher Education Area - Kushnir, Iryna; Eta, Elizabeth Agbor; Mbah, Marcellus Forh; Kennedy, Charlotte-Rose (International Journal of Sustainability in Higher Education, 2024)
Publisher: Emerald Publishing Limited KerkoCite.ItemAlsoKnownAs: 10.1108/IJSHE-12-2022-0394 5072953:887LZGTD openalex: W4384305696
Keywords: _z:class:countries; _z:class:themes; oa:keyword:european higher education area; oa:keyword:sustainable development; oa:keyword:sustainable development agenda; oa:topic:T11300 Global Governance in Education Policy Research; oa:topic:T11835 Sustainability Education in Higher Education Institutions; oa:topic:T12545 Education for Global Citizenship in a Globalized World; openalex:n:1; openalex:yes

The orchestration of a sustainable development agenda in the European Higher Education Area - Kushnir, Iryna; Eta, Elizabeth Agbor; Mbah, Marcellus Forh; Kennedy, Charlotte-Rose (International Journal of Sustainability in Higher Education, 2024)
KerkoCite.ItemAlsoKnownAs: 10.1108/IJSHE-12-2022-0394 5072953:887LZGTD openalex: W4384305696
Keywords: _z:class:countries; _z:class:themes; oa:keyword:european higher education area; oa:keyword:sustainable development; oa:keyword:sustainable development agenda; oa:topic:T11300 Global Governance in Education Policy Research; oa:topic:T11835 Sustainability Education in Higher Education Institutions; oa:topic:T12545 Education for Global Citizenship in a Globalized World; openalex:n:1; openalex:yes

The added value of partnerships in implementing the UN sustainable development goals - Leal Filho, Walter; Dibbern, Thais; Dinis, Maria Alzira Pimenta; Cristofoletti, Evandro Coggo; Mbah, Marcellus; Mishra, Ashish; Clarke, Amelia; Samuel, Naima; Apraiz, Julen Castillo; Abubakar, Ismaila Rimi (Journal of Cleaner Production, 2024)
Publisher: Elsevier KerkoCite.ItemAlsoKnownAs: 10.1016/j.jclepro.2024.140794 5072953:FTYPRUUB openalex: W4390972518
Keywords: _z:class:countries; _z:class:themes; oa:sdg:17 Partnerships for the goals; oa:topic:T11168 Foreign Aid and Development Policies; oa:topic:T12013 Measurement and Evaluation of Sustainable Development; oa:topic:T12786 Frugal Innovation in Emerging Markets; openalex:n:1; openalex:yes

The added value of partnerships in implementing the UN sustainable development goals - Leal Filho, Walter; Dibbern, Thais; Dinis, Maria Alzira Pimenta; Cristofoletti, Evandro Coggo; Mbah, Marcellus; Mishra, Ashish; Clarke, Amelia; Samuel, Naima; Apraiz, Julen Castillo; Abubakar, Ismaila Rimi (Journal of Cleaner Production, 2024)
KerkoCite.ItemAlsoKnownAs: 10.1016/j.jclepro.2024.140794 5072953:FTYPRUUB openalex: W4390972518
Keywords: _z:class:countries; _z:class:themes; oa:sdg:17 Partnerships for the goals; oa:topic:T11168 Foreign Aid and Development Policies; oa:topic:T12013 Measurement and Evaluation of Sustainable Development; oa:topic:T12786 Frugal Innovation in Emerging Markets; openalex:n:1; openalex:yes

Examining thermal comfort levels and ASHRAE Standard-55 applicability: A case study of free-running classrooms in Abuja, Nigeria - Mustapha, T.D.; Hassan, A.S.; Khozaei, F.; Onubi, H.O. (Indoor and Built Environment, 2024)
Keywords: _z:class:countries

School Buildings Infrastructure in East Africa - Nambatya, Mauricia (Google Docs, 2024)
School Buildings Infrastructure in East Africa Author: Mauricia Nambatya https://doi.org/10.53832/opendeved.1136 Within East Africa, school buildings are similar in design and materials used in construction. The most commonly used walling materials are fired or burnt bricks because they are loca...
KerkoCite.ItemAlsoKnownAs: 2129771:55SZ56YG 4874017:2NX3AJB9
Keywords: evidence_review

Climate change risk assessment of rainfall and temperature in the West Bank, Palestine - Shadeed, Sameer; Alawna, Sandy (International Journal of Global Warming, 2024)

Machine learning evidence map reveals global differences in adaptation action - Sietsma, Anne J.; Theokritoff, Emily; Biesbroek, Robbert; Canosa, Iván Villaverde; Thomas, Adelle; Callaghan, Max; Minx, Jan C.; Ford, James D. (One Earth, 2024)
Keywords: _z:class:countries

Dataset of indoor air parameter measurements relating to indoor air quality and thermal comfort in South African primary school classrooms of various building infrastructure types - Van Der Walt, Rita Elise; Grobbelaar, Sara Susanna; Booysen, Marthinus Johannes (Data in Brief, 2024)
In the resource-constrained South African education sector, infrastructure considered temporary or a backup in other countries is used as permanent classrooms, primarily but not exclusively in lower-income areas. Children's cognitive performance and comfort are directly impacted by indoor air quality. Temperature, relative humidity, particulate matter and CO2 levels, substantial determinants of air quality and thermal comfort, have not been investigated across different classroom building and infrastructure types. We measure these parameters with 11-min intervals in 24 classrooms at schools in Stellenbosch, South Africa. These classrooms consist of a range of different infrastructure types. Container classrooms with and without insulation, mobile (prefabricated) classrooms, and brick classrooms of different configurations are included. Measurements are concurrently sampled over ten months (249 days, still ongoing) across multiple seasons with relevant metadata, including ambient weather conditions, school days and times, and electricity availability in the (South) African context, which impacts air conditioning usage. This dataset provides valuable insights into true learning conditions in South African classrooms.
openalex: W4390938962 KerkoCite.ItemAlsoKnownAs: 2129771:YNAE9CTV 2129771:YNAE9CTV 2129771:YNAE9CTV 2129771:YNAE9CTV 2129771:YNAE9CTV 10.1016/j.dib.2024.110045 5072953:3W35N8CY 5072953:FZJPX8JY 5072953:J25A6NN2
Keywords: Brick classrooms; C:South Africa; Carbon dioxide; Developing country; Indoor air quality; Learning environment; Particulate matter; Portable classrooms; Thermal environment; _z:class:countries; _z:class:themes; evidence_review; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11692 Effects of Noise Pollution on Health and Well-being; oa:topic:T11988 Sustainable Construction and Green Building; openalex:n:1; openalex:yes

Literature review: Indoor climate versus building characteristics in tropical climates - Vito (2024)
KerkoCite.ItemAlsoKnownAs: 4874017:Z2LYEL2L 5072953:UDSI84N2
Keywords: _z:class:countries; _z:class:themes

Causal loop diagram (Wikipedia, 2023)
A causal loop diagram (CLD) is a causal diagram that aids in visualizing how different variables in a system are causally interrelated. The diagram consists of a set of words and arrows. Causal loop diagrams are accompanied by a narrative which describes the causally closed situation the CLD describes. Closed loops, or causal feedback loops, in the diagram are very important features of CLDs. The words with arrows coming in and out represent variables, or quantities whose value changes over time and the links represent a causal relationship between the two variables (i.e., they do not represent a material flow). A link marked + indicates a positive relation where an increase in the causal variable leads, all else equal, to an increase in the effect variable, or a decrease in the causal variable leads, all else equal, to a decrease in the effect variable. A link marked - indicates a negative relation where an increase in the causal variable leads, all else equal, to a decrease in the effect variable, or a decrease in the causal variable leads, all else equal, to an increase in the effect variable. A positive causal link can be said to lead to a change in the same direction, and an opposite link can be said to lead to change in the opposite direction, i.e. if the variable in which the link starts increases, the other variable decreases and vice versa. The words without arrows are loop labels. As with the links, feedback loops have either positive (i.e., reinforcing) or negative (i.e., balancing) polarity. CLDs contain labels for these processes, often using numbering (e.g., B1 for the first balancing loop being described in a narrative, B2 for the second one, etc.), and phrases that describe the function of the loop (i.e., "haste makes waste"). A reinforcing loop is a cycle in which the effect of a variation in any variable propagates through the loop and returns to reinforce the initial deviation (i.e. if a variable increases in a reinforcing loop the effect through the cycle will return an increase to the same variable and vice versa). A balancing loop is the cycle in which the effect of a variation in any variable propagates through the loop and returns to the variable a deviation opposite to the initial one (i.e. if a variable increases in a balancing loop the effect through the cycle will return a decrease to the same variable and vice versa). Balancing loops are typically goal-seeking, or error-sensitive, processes and are presented with the variable indicating the goal of the loop. Reinforcing loops are typically vicious or virtuous cycles. Example of positive reinforcing loop: The amount of the Bank Balance will affect the amount of the Earned Interest, as represented by the top blue arrow, pointing from Bank Balance to Earned Interest. Since an increase in Bank balance results in an increase in Earned Interest, this link is positive, which is denoted with a "+". The Earned interest gets added to the Bank balance, also a positive link, represented by the bottom blue arrow. The causal effect between these variables forms a positive reinforcing loop, represented by the green arrow, which is denoted with an "R".
Page Version ID: 1192291490 KerkoCite.ItemAlsoKnownAs: 2129771:6DPJ2Y3W
Keywords: evidence_review

The next generation of machine learning for tracking adaptation texts - Sietsma, Anne J.; Ford, James D.; Minx, Jan C. (Nature Climate Change, 2023)
Machine learning presents opportunities for tracking evidence on climate change adaptation, including text-based methods from natural language processing. In theory, such tools can analyse more data in less time, using fewer resources and with less risk of bias. However, the first generation of adaptation studies have delivered only proof of concepts. Reviewing these first studies, we argue that future efforts should focus on creating more diverse datasets, investigating concrete hypotheses, fostering collaboration and promoting ‘machine learning literacy’, including understanding bias. More fundamentally, machine learning enables a paradigmatic shift towards automating repetitive tasks and makes interactive ‘living evidence’ platforms possible. Broadly, the adaptation community is failing to prepare for this shift. Flagship projects of organizations such as the IPCC could help to lead the way.
openalex: W4390273618 KerkoCite.ItemAlsoKnownAs: 5072953:3P98PU49 5072953:5CC2RIQH 5072953:9N8TXRGU 5440726:VR85NTPZ
Keywords: Climate-change impacts; Interdisciplinary studies; Research data; _z:class:countries; _z:no_pdf; openalex:citedBy; openalex:import; selected_for:effects of climate ch...on learning...LMICs 2024; tagged

Cultivating Adaptation: A Study of FPO Farmer Preferences for Climate-Smart Training in the Western Zone of Tamil Nadu, India - Malarkodi, M.; Kanaka, S.; Premavathi, P.; Tamilselvi, C.; Agila, Rosana de Jesús Eras; Sridhar, Praveen (Asian Journal of Agricultural Extension, Economics and Sociology, 2023)
The Tamil Nadu government actively supports farmer development through frequent training programs. These programs, incorporating both classroom sessions and field visits, are targeted towards farmer members of Farmer Producer Organizations (FPOs) and conducted at regular intervals. Recognizing the importance of understanding farmers' motivations and preferences, the training centers conducted a study involving 80 FPO farmer respondents from Coimbatore and Nilgiris districts. Using rank-based quotient (RBQ) analysis, the researchers explored the reasons behind farmers' participation in the training programs. Additionally, conjoint analysis revealed their preferred training mode. The study identified a two-day program, held once a year from 10 am to 5 pm and combining classroom training with field visits, as the most popular option. Interestingly, the number of days was the key deciding factor for program attendance, while having experienced farmers as trainers or guest speakers emerged as the primary reason for participating. This research offers valuable insights for optimizing future training programs to better cater to the needs and preferences of farmers, ultimately maximizing their benefits and fostering their development.
openalex: W4390504911
Keywords: C:India; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10367 Agricultural Innovation and Livelihood Diversification; oa:topic:T13358 Livestock Farming and Rural Development Practices; oa:topic:T13508 Agricultural Development and Policy in South Asia; openalex:import; openalex:yes

Knowledge and (un)certainty in climate change education in India - Puttick, Steven; Chandrachud, Paloma; Chopra, R. N.; Khosla, Radhika; Robson, James; Singh, Sandeep; Talks, Isobel (British Educational Research Journal, 2023)
Abstract This paper explores teachers' conceptions of climate change knowledge, contributing to the growing body of work on the geographies of climate change. The paper focuses on the data generated through in‐depth semi‐structured interviews with a sample of 48 teachers in India to address the research question: What discourses about climate change knowledge are being constructed by teachers in India? We argue that teachers' lesson planning and searches for information are at the forefront of the changing ways in which individuals engage with, find out and construct meaning about climate change. These teachers' beliefs about climate change are very strongly held, even in the face of a perceived lack of expertise or understanding: climate change is described as the ‘need of the hour’, which this work understands as not only involving material impacts and processes but also important epistemological, collaborative needs through which education might contribute to public reasoning about climate change. Through this analysis we present a ‘certainty problematic’ as a heuristic device that foregrounds tensions between the inherent uncertainty of knowledge and (against climate denialism) certainty about anthropogenic climate change.
openalex: W4390111446
Keywords: C:India; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; oa:topic:T12343 Geography Education and Spatial Thinking; openalex:import; openalex:yes

Mental health and wellbeing outcomes of climate change mitigation and adaptation strategies: A systematic review - Flores, Elaine C.; Brown, Laura J.; Kakuma, Ritsuko; Eaton, Julian; Dangour, Alan D. (Environmental Research Letters, 2023)
Abstract Climate change has already impacted the health and wellbeing of ∼5 billion people globally. However, the potential influence of climate change mitigation and adaptation strategies on mental health and wellbeing outcomes in low-and-middle-income countries (LMICs) remains insufficiently understood. We aimed to determine the effect of these strategies on mental health and wellbeing outcomes among LMIC beneficiaries. We carried out a systematic review to identify intervention and case studies published from 2013 to 2022, searching OVID Medline, Embase, PsycINFO, Global Health, Cochrane Library, GreenFile, Web of Science, and a subset of studies from the ‘Global Adaptation Mapping Initiative’ database. We included controlled, quasi-experimental, pilot, and focussed case studies reporting mental health or wellbeing outcomes assessments of climate change mitigation and adaptation strategies. We categorised studies by design, geographic region, target population, setting, environmental hazard, strategy type and primary outcomes. PROSPERO registry: CRD42021262711. A total of 9532 studies were initially retrieved, and 15 studies involving 12 255 participants met the inclusion criteria. Among these, twelve studies described evidence from single-adaptation strategies in nine LMICs, while three reported mitigation programmes. Only two randomised evaluations assessed common mental disorders such as depression, trauma or anxiety using validated scales. Most studies evaluated broader wellbeing at the community and individual levels. Nine studies (53.3%) reported significant beneficial changes in mental health or wellbeing outcomes among beneficiaries, while six (46.7%) obtained mixed results linked to local and sociocultural factors. The interventions ‘practical significance and overall impact remained unclear due to the heterogeneous reporting in program effectiveness, gaps in effect size assessments or qualitative insights. Our review highlights the scarcity and limited nature of the current evidence, underscoring the need for further equitable research. The ongoing global climate and mental health crises press us to fully understand and address these strategies’ psychosocial impacts and translate these findings into effective policy and transdisciplinary action as an opportunity to prevent and ameliorate significant, long-term problems in the population’s mental health and wellbeing.
openalex: W4389660070
Keywords: _z:class:countries; evidence_review; openalex:citedBy; openalex:import; selected_for:effects of climate ch...on learning...LMICs 2024; tagged

A Rapid Review of Impact Assessment of Climate Change on Health and Mental Well-Being in Africa - Oladimeji, Kelechi Elizabeth; Zungu, Lindiwe; Chocko, Ronnie; Hyera, Francis Leonard Mpotte; Nyatela, Athini; Gumede, Siphamandla; Dwarka, Depika; Lalla-Edward, Samanta Tresha (New Voices in Psychology, 2023)
Despite widespread global attention, the potential threats to human health posed by climate change in Africa still need to be further understood. Although there is mounting concern that climate change is a serious risk to human health, less evidence shows a direct causal relationship between climate change and health risks in Africa. In this rapid review, we discuss our synthesis of available evidence on the health implications of climate change with a focus on Africa. PubMed was systematically searched for relevant articles from 2020 to 2023 using a search strategy. Only eligible articles published in the English language with full article access were included for review using the population concept context (PCC) criteria by Joanna Briggs Institute (JBI). After removing duplicates, the selection process began with title and abstract screening, followed by screening full-text articles. Of the 3272 articles retrieved, only 10 were eligible for synthesis. We found mainly reported climate exposures to range from drought, concerning rainfall patterns, and increasing temperatures reported to cause morbidity and mortality through health risks: respiratory diseases, vector-borne diseases, cardiovascular diseases and mental health concerns. Africa still has a huge shortage of available evidence, particularly research focusing on the health implications, including mental health of climate change and interventions to prevent climate change-related health consequences. While the limited global evidence indicates that climate change results in an increased risk to public health, there are gaps in demonstrating the causal links between climate change and societal mental health impacts in Africa. There is also an urgent need for more research on effectively addressing climate hazards that threaten the African continent's public health and well-being.
openalex: W4391697555
Keywords: _z:class:countries; evidence_review; openalex:citedBy; openalex:import; selected_for:effects of climate ch...on learning...LMICs 2024; tagged

Knowledge and Perceptions of Climate Change among the Science Students at the University of South Africa - Chelule, Paul Kiprono; Dhlamini, Thembekile Smangele; Munganga, Justin Wazute (2023)
Background:. Knowledge and positive perception of climate change are crucial for public participation in activities that contain climate change. Limited studies, particularly in South Africa have reported on the knowledge and perceptions of climate change by university students.
Study Aim: This study aimed to assess the level of knowledge and perceptions of climate change by the science students at the University of South Africa (UNISA).
Methods: This was a quantitative cross sectional survey, undertaken among science students using questionnaire emailed to 500 students in the School of Science through Unisa email system. Bivariate logistic regression was used to test the association between socio-demographics, level of knowledge and perceptions of climate change.
Results: A total of 420 students participated in the study. They were predominantly male (70.3%), mostly younger than 35 years of age. Most of the respondents were in the 2nd (34.7%) and 3rd (33.8%) year of study. Majority of respondents (97.9%) knew and perceived (93.6%) that climate change was happening. Overall, 93.8% of respondents had an excellent knowledge and basic concepts of climate change.
Conclusion: The majority of students were knowledgeable and had positive perceptions about the basic concepts of climate change. However, the year of study was not significantly associated with positive perceptions of climate change. There is need to include climate change modules in South African university curriculum.
openalex:W4389902586 mag: KerkoCite.ItemAlsoKnownAs: 10.20944/preprints202312.1341.v1 5072953:H666SU9D
Keywords: C:South Africa; _z:class:countries; _z:class:themes; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Lots of snakes but where are the ladders? Building environment-smart learning friendly schools responsive to extreme weather - Bangay, Colin (2023)
KerkoCite.ItemAlsoKnownAs: 2129771:TD64LG7P 2129771:TD64LG7P 2129771:TD64LG7P 2129771:TD64LG7P 5072953:WIAFW4QF
Keywords: _z:class:countries; _z:class:themes; evidence_review_2

Building the evidence base for climate-smart education systems: Introducing a new interest group - Tammi, Anna-Maria; Bangay, Colin (2023)
KerkoCite.ItemAlsoKnownAs: 5072953:JN2GW52U
Keywords: _z:class:countries; _z:class:themes

Assessment of Climate Change Anxiety in High School Youths of Kwale County, Kenya - Mutua, Patrick M.; Kauti, Matheaus K.; Mwangangi, Leonard; Nzilani, Musyoka Sonnia (African Journal of Climate Change and Resource Sustainability, 2023)
Climate change anxiety refers to negative cognitive, emotional, behavioural, and functional responses to experiences of climate change and has implications on mental health. The current study sought to determine how climate change anxiety relates to cognitive-emotional and functional impairments as well as with experience of climate change and behavioural engagement in youths. The study surveyed 388 youths (aged 13-24 years) in high schools in Kwale County, Kenya. Data were analysed in XLSTAT software using Pearson's correlation and considered significant for values of p ≤ 0.05. Over 60 % of the youths had more than "Sometimes" suffered cognitive-emotional impairment, while 63 % were more than "Sometimes" inflicted with functional impairment. Additionally, 61 % of the respondents more than "Sometimes" reported having had a climate change experience. However, 71 % of the youths were more than "Sometimes" engaged in climate change behavioural activities. There were no significant gender differences in the scores. Cognitive-emotional impairment (M = 2.507, SD = 1.267) was significantly (P = 0.0048) associated with behavioural engagement in climate change (M = 3.019, SD = 1.403). Youths attending day schools scored significantly (P = 0.022) higher in functional impairment (M = 2.897, SD = 1.182) than students in boarding schools (M = 2.535, SD = 1.395). Youths aged 13-17 years were substantially more affected by climate change anxiety than those aged 18-24 years. This study identifies a population at risk with high exposure and vulnerability to the health impacts of climate change. The study suggests the need for policies to address climate change anxiety in youths in schools and the use of the youths' pro-environmental behavioural engagements in climate change to improve their adaptive capacity
openalex:W4389390039 mag: KerkoCite.ItemAlsoKnownAs: 10.37284/ajccrs.2.1.1610 5072953:B9Z58EQ3
Keywords: C:Kenya; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; oa:topic:T13536 Conceptualization and Measurement of Time Perspective; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Climate change and mental health: impact on people with disabilities - Vig, Shinu; Dwivedi, Sunita (Mental Health and Social Inclusion, 2023)
Purpose This paper aims to examine why people with disabilities (PWDs) are at risk due to climate change. It also discusses the linkage between climate change events and the mental health of the disabled population. Design/methodology/approach This paper follows a qualitative approach. Findings Climate change can affect the mental well-being of PWDs in several ways such as increased vulnerability, displacement-related trauma, social isolation, loss of independence, climate anxiety and eco-grief. Practical implications The paper has practical implications for policymakers. Because climate change has a disproportionate impact on PWDs, there is an urgent need to include them in climate action, both as beneficiaries and decision-makers. Originality/value The paper attempts to explore the measures that can be taken for prevention and mitigation of impacts on the mental health of PWDs.
openalex: W4389326575
Keywords: _z:class:countries; openalex:import; openalex:yes

Hearing Loss and Disorders: The Repercussions of Climate Change - Sherratt, Sue (American Journal of Audiology, 2023)
Climate change is considered to be the greatest threat to human health in the 21st century, and its effects are accelerating. Extensive research has clearly demonstrated its increasing impact across the continuum of health conditions. Despite this, there has been limited attention to the ramifications of climate change on hearing loss and hearing disorders. This lack of consideration is somewhat surprising as the environment itself and its changing nature have a substantial effect on hearing.Tackling climate change could be the greatest global health opportunity of the 21st century. To address this issue, this tutorial provides a general introduction to climate change and its three major elements (pollution, infectious diseases, and extreme weather events) and their effects on health. The substantial consequences of climate change for the incidence, development, and exacerbation of hearing loss and disorders are clearly described and detailed.The challenge of responding to this very real and escalating threat to hearing requires a combination of prevention, advocacy, and education. These three roles place audiologists in the perfect position to take action on the far-reaching effects of climate change on hearing loss and disorders. To respond to this challenge and to fulfill these roles, several strategies, ranging from the individual level to the global level, are delineated for audiologists to incorporate into their practice.
openalex: W4387446041
Keywords: _z:class:countries; openalex:import; openalex:yes

Climate-resilient school buildings - Hassler, Bjoern (2023)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10203951 ZenodoArchiveConcept: 10203950 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1031 2129771:FVMXNR7R 5072953:L6TCKG52
Keywords: _r:AddedByMyEducationEvidence; _z:class:countries; _z:class:themes

Project updates for Climate, Environment and Education Adaptation Research (CLEEAR) Tanzania Steering Committee - Villavicencio, Xuzel; Hassler, Bjoern (2023)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10203975 ZenodoArchiveConcept: 10203974 openalex:W4388970860 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1032 2129771:6V9PMAJB 5072953:87V9QL4T 5072953:VASXMNQS
Keywords: C:Tanzania; _r:AddedByMyEducationEvidence; _z:class:countries; _z:class:themes; openalex:import; openalex:n:1; openalex:yes

Managing School Plant Planning for Climate Change in Public Secondary Schools in Rivers State, Nigeria: A Prerequisite for the Attainment of Sustainable Educational Development - Sunday, Osaat Dinah; Chinenye, Akani Gift (Journal of Advances in Education and Philosophy, 2023)
This study examined managing school plant planning for climate change in the attainment of sustainable educational development for public secondary schools in Rivers State. Two research questions and two hypotheses guided the study. The descriptive design was adopted. The population of the study comprised all the 542 public junior and senior secondary schools in Rivers State. A sample of 304 principals representing 56% of the population served as the study respondents. This sample was selected using the stratified random sampling technique. A validated Likert-modified 4-scale 16 item instrument titled: ‘Managing School Plant Planning for Climate Change in Public Secondary Schools Questionnaire (MSPPCCPSSQ)’ was used for data collection and its reliability coefficient was established at 0.82 using the Cronbach Alpha Correlation coefficient. Mean and standard deviation were used to analyze the research questions while the z-test statistics was used to test the hypotheses at 0.05 level of significance. The findings of this study revealed that discouraging deforestation while encouraging afforestation where trees acting as wind breakers are planted; communicating effectively with students by promoting students’ engagements by means of enlightening students on the importance of respecting green spaces such as school gardens, parks are some of the ways of managing school plant planning for climate change in the attainment of sustainable educational development in public secondary schools in Rivers State, Nigeria. Based on these findings, the researcher recommended that Rivers State government should endeavor to champion the course of initiating proactive ways and policies in managing school plant planning for public secondary schools aimed at curbing the negative effects of climate change in Rivers State.
openalex:W4388767437 mag: KerkoCite.ItemAlsoKnownAs: 10.36348/jaep.2023.v07i11.004 5072953:ARI9AEB7
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Global Research on Natural Disasters and Human Health: a Mapping Study Using Natural Language Processing Techniques - Ye, Xin; Lin, Hugo You‐Hsien (Current Environmental Health Reports, 2023)
openalex: W4388646885
Keywords: _z:class:countries; openalex:citedBy; openalex:import; selected_for:effects of climate ch...on learning...LMICs 2024; tagged

Improving Australian climate change adaption strategies: learning from international experience - Perugia, Francesca; Rowley, Steven; Swapan, Mohammad Shahidul Hasan (2023)
This research explores climate change adaptation practices, strategies and policies implemented internationally that could be adopted to support the sustainable development of cities and towns across Australia. Adaptation strategies focus on reducing the impact of climate change effects while promoting sustainable development.Adaptation is framed as a shared responsibility between governments at all levels, businesses, communities and individuals. Within this overarching framework, each level of government has a specific role.Australia lacks a strong overarching direction in climate change adaptation, including legislation and funding. In a 2019 assessment of adaptation plans for 54 countries, Australia was the lowest performer. This poor performance can be linked to the narrow scope of Australia's approach to adaptation, including the lack of political leadership and the division of powers and allocation of responsibilities in the three tiers of government.The research interrogated urban adaption strategies in three international case studies and found all three case studies emphasise active community participation and leadership in devising and delivering their adaption strategies.The research found that Australian cities and towns should incorporate three main strategic approaches for effective climate change adaptation: long-term investment and holistic approaches building community resilience to deal with the impacts of climate change innovation in structural solutions that respect and reinforce the local ecological system as a way to build resilience.
openalex: W4388599677
Keywords: C:Australia; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10747 Community Resilience to Natural Disasters; oa:topic:T12656 Impact of Climate Change on Human Migration; openalex:import; openalex:yes

Improving Australian climate change adaption strategies: learning from international experience - Perugia, Francesca; Rowley, Steven; Swapan, Mohammad Shahidul Hasan (2023)
This research explores climate change adaptation practices, strategies and policies implemented internationally that could be adopted to support the sustainable development of cities and towns across Australia. Adaptation strategies focus on reducing the impact of climate change effects while promoting sustainable development.Adaptation is framed as a shared responsibility between governments at all levels, businesses, communities and individuals. Within this overarching framework, each level of government has a specific role.Australia lacks a strong overarching direction in climate change adaptation, including legislation and funding. In a 2019 assessment of adaptation plans for 54 countries, Australia was the lowest performer. This poor performance can be linked to the narrow scope of Australia's approach to adaptation, including the lack of political leadership and the division of powers and allocation of responsibilities in the three tiers of government.The research interrogated urban adaption strategies in three international case studies and found all three case studies emphasise active community participation and leadership in devising and delivering their adaption strategies.The research found that Australian cities and towns should incorporate three main strategic approaches for effective climate change adaptation: long-term investment and holistic approaches building community resilience to deal with the impacts of climate change innovation in structural solutions that respect and reinforce the local ecological system as a way to build resilience.
openalex: W4388599677
Keywords: C:Australia; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10747 Community Resilience to Natural Disasters; oa:topic:T12656 Impact of Climate Change on Human Migration; openalex:import; openalex:yes

Benefits of using ISSB in school buildings - Nambatya, Mauricia (Open Development & Education, 2023)
An output of the Open Development & Education, https://opendeved.net/
CallNumber: opendeved.1034 ZenodoArchiveID: 10257225 ZenodoArchiveConcept: 10257224 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1034 2129771:3KUTI3BB 5072953:R996U75H
Keywords: _r:AddedByMyEducationEvidence; _z:class:countries; _z:class:themes; evidence_review_2

Is indoor environmental quality in my school classroom safe? - Warwocki, Pawel (2023)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10079928 ZenodoArchiveConcept: 10079927 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1028 2129771:F6PT9SPQ 5072953:YRX5T4BV
Keywords: _r:AddedByMyEducationEvidence; _z:class:countries; _z:class:themes

The Influence of Religious Affiliation and Church Attendance on Climate Change Awareness, Perception, and Action: The Role of Churches through Environmental Education in Nigeria - Nche, George C. (Didaktika: Jurnal Kependidikan, 2023)
Churches can serve as platforms for environmental education, fostering a sense of responsibility towards the environment among their congregations.This study examined the influence of religious affiliation and attendance on climate change awareness, perception, action and perceived role of the church through environmental education in Nigeria. Churchgoers from Catholic, Anglican, and Pentecostal churches from the six geopolitical zones of Nigeria completed the Climate Change Awareness Questionnaire (CCAQ); Climate Change Perception Questionnaire (CCPQ); Churches’ Role Perception Scale (CRPS); and Climate Change Action Assessment Scale (CCAAS) and also provided relevant demographic information. Results of statistical analysis indicated that there was a significant difference between the religious denominations in climate change awareness, perception, action and perceived role of the church. The results also showed that more frequency of attendance to church activities was associated with increased climate change awareness, perception of climate change, climate change action, and perceived role of the church in addressing climate change. Churches must continue incorporating environmental teachings into their religious practices and advocating for environmentally-friendly behaviors among members as ways of contributing to the campaign against climate change.
openalex:W4391054823 mag: KerkoCite.ItemAlsoKnownAs: 10.58230/27454312.453 5072953:3CKKCKCW
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T12656 Impact of Climate Change on Human Migration; oa:topic:T13059 Influence of Religion on Environmental Concern and Activism; oa:topic:T13636 Pentecostalism and its Cultural Impact; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Real-time indoor thermal comfort prediction in campus buildings driven by deep learning algorithms - Ma, Zherui; Wang, Jiangjiang; Ye, Shaoming; Wang, Ruikun; Dong, Fuxiang; Feng, Yingsong (Journal of Building Engineering, 2023)
Thermal comfort prediction is vital in achieving a good indoor environment and efficient energy management. However, thermal comfort is strongly nonlinear and dynamically changing over time, making it difficult to predict thermal comfort accurately. Two real-time thermal comfort prediction models on multi-time scales are proposed based on deep learning algorithms. The indirect prediction model for thermal comfort integrates the bidirectional long and short-term memory network to predict real-time environmental parameters. It subsequently combines the thermal comfort calculation method with the predicted environmental parameters to obtain the predicted thermal comfort value. The indirect prediction model for thermal comfort combines the bidirectional long and short-term memory network to realize real-time prediction of environmental parameters and then calculates thermal comfort by the thermal comfort calculation method to realize indirect thermal comfort prediction. The other is the direct prediction model of thermal comfort, which is realized using the bidirectional long short-term memory network for real-time thermal comfort prediction. The two real-time prediction models are compared and analyzed for 10-min, 30-min, and 60-min scales. Experimental results show that the prediction accuracy of the indirect prediction model is better than the direct prediction model, but the robustness of the indirect prediction model is lower than the direct prediction model. In addition, the accuracy of the thermal comfort prediction model on the small time scale is higher than that on the large time scale, in which the RMSE and MAE reached 0.0551 and 0.0543 (10-min scale), respectively. Therefore, the proposed thermal comfort prediction models can be integrated into the control model of heating, ventilation and air conditioning systems, providing a reference for optimizing indoor thermal comfort.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.jobe.2023.107603 5072953:HJEERC9K 5072953:JMVG6NNN openalex: W4385973216
Keywords: Bidirectional long short-term memory network; Direct prediction; Indirect prediction; Prediction uncertainty; Thermal comfort; _important; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:indoor thermal comfort prediction; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11109 Physiological Responses to Heat Stress in Humans; openalex:n:1; openalex:yes; selected_for:Predictive models for classroom conditions 2024

Real-time indoor thermal comfort prediction in campus buildings driven by deep learning algorithms - Ma, Zherui; Wang, Jiangjiang; Ye, Shaoming; Wang, Ruikun; Dong, Fuxiang; Feng, Yingsong (Journal of Building Engineering, 2023)
Thermal comfort prediction is vital in achieving a good indoor environment and efficient energy management. However, thermal comfort is strongly nonlinear and dynamically changing over time, making it difficult to predict thermal comfort accurately. Two real-time thermal comfort prediction models on multi-time scales are proposed based on deep learning algorithms. The indirect prediction model for thermal comfort integrates the bidirectional long and short-term memory network to predict real-time environmental parameters. It subsequently combines the thermal comfort calculation method with the predicted environmental parameters to obtain the predicted thermal comfort value. The indirect prediction model for thermal comfort combines the bidirectional long and short-term memory network to realize real-time prediction of environmental parameters and then calculates thermal comfort by the thermal comfort calculation method to realize indirect thermal comfort prediction. The other is the direct prediction model of thermal comfort, which is realized using the bidirectional long short-term memory network for real-time thermal comfort prediction. The two real-time prediction models are compared and analyzed for 10-min, 30-min, and 60-min scales. Experimental results show that the prediction accuracy of the indirect prediction model is better than the direct prediction model, but the robustness of the indirect prediction model is lower than the direct prediction model. In addition, the accuracy of the thermal comfort prediction model on the small time scale is higher than that on the large time scale, in which the RMSE and MAE reached 0.0551 and 0.0543 (10-min scale), respectively. Therefore, the proposed thermal comfort prediction models can be integrated into the control model of heating, ventilation and air conditioning systems, providing a reference for optimizing indoor thermal comfort.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.jobe.2023.107603 5072953:HJEERC9K 5072953:JMVG6NNN openalex: W4385973216
Keywords: Bidirectional long short-term memory network; Direct prediction; Indirect prediction; Prediction uncertainty; Thermal comfort; _important; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:indoor thermal comfort prediction; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11109 Physiological Responses to Heat Stress in Humans; openalex:n:1; openalex:yes; selected_for:Predictive models for classroom conditions 2024

Improving Australian climate change adaption strategies: learning from international experience - Perugia, Francesca; Rowley, Steven; Swapan, Mohammad Shahidul Hasan (AHURI final report, 2023)
openalex: W4387696955
Keywords: C:Australia; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T14509 Spatial Microsimulation Models for Policy Analysis; openalex:import; openalex:yes

Improving Australian climate change adaption strategies: learning from international experience - Perugia, Francesca; Rowley, Steven; Swapan, Mohammad Shahidul Hasan (AHURI final report, 2023)
openalex: W4387696955
Keywords: C:Australia; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T14509 Spatial Microsimulation Models for Policy Analysis; openalex:import; openalex:yes

Heating energy demand estimation of the EU building stock: Combining building physics and artificial neural networks - Veljkovic, Ana; Pohoryles, Daniel A.; Bournas, Dionysios A. (Energy and Buildings, 2023)
The aim of this study is to present a novel data-driven approach developed for space heating energy demand calculation of the whole EU building stock. To develop a computationally efficient bottom-up model that takes into account building physics parameters and details of the building stock make-up, an artificial neural network (ANN) is trained on a dataset of precise building-physics models. For this purpose, 2025 building energy simulations were performed in this study, ensuring representativeness for the entire EU, in terms of building stock properties (3 building geometries and 27 combinations of building envelope properties) and climatic conditions (25 weather files). The developed model is the first comprehensive hybrid (ANN and building physics) approach based on a condensed selection of input features, yet covering a wide range of climatic and building stock values, hence suitable for consideration of the spatial, temporal and multinational scale of the EU building stock. A unique building stock model was developed for this study at the EU regional level. The performance of the ANNs was validated by assessing the RMSE and R2 against the training (85%), testing (15%) and total dataset (100%, i.e. 2025 data points), to ensure adequate robustness, accuracy and generalisation capacity. As to the application of the ANN model on the building stock of 27 EU countries, a good accordance between ANN model results and measured consumption over the nine years from 2011 to 2019, was obtained, with an average overestimation by 9.3% (standard deviation (SD) = 5%), which confirmed the adequacy of the adopted methodology. Additional consideration of the occupant behaviour resulted in average overestimating the actual measurements by only 2.4% (SD = 4.7%). In addition to the EU and country level, the added value of the implemented bottom-up approach is its ability to assess the heating energy demand at regional level. Overall, the presented approach can be considered accurate and reliable to be used in future research on the long-term impact of building renovation with respect to energy savings and reductions of greenhouse gas emissions.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2023.113474 5072953:8VB7Z8ID openalex: W4386024563
Keywords: Building physics; EU building stock; Neural network; Space heating; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:energy demand estimation; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:n:1; openalex:yes; selected_for:Predictive models for classroom conditions 2024

Real-time energy consumption prediction method for air-conditioning system based on long short-term memory neural network - Zhao, Yifan; Li, Wei; Zhang, Jili; Jiang, Changwei; Chen, Siyu (Energy and Buildings, 2023)
With increasing energy consumption, how to achieve the energy-saving operation of air-conditioning systems is crucial for improving the energy efficiency of buildings. The accurate and reliable energy consumption prediction of air-conditioning systems can be useful for optimizing the energy supply and equipment operation strategies. However, most existing studies focus on the prediction of the long-term energy consumption of air-conditioning systems, which usually exceeds the individual control time steps of the air-conditioning system. If the energy consumption of air-conditioning systems in the next control step can be predicted, then the least energy-consuming operating strategy can be selected at the beginning of each control step by relying on the predicted energy consumption, thereby achieving greater energy conservation. This paper proposes a real-time energy consumption prediction model for air-conditioning systems based on a long short-term memory neural network. The correlation between the energy consumption of air-conditioning system and input variables can be obtained by calculating the Spearman correlation coefficient. The predicted model results show that the normalized root mean square error of the prediction model is 0.0429 when the indoor air temperature, condenser inlet temperature, and historical energy consumption are set as inputs to predict the energy consumption of the air-conditioning system for the next 15 min. Meanwhile, the energy consumption at a certain indoor temperature setpoint can be predicted by the prediction model to aid in selecting a more appropriate indoor temperature setpoint, which can reduce energy consumption by optimizing the operation strategy of the air-conditioning system at each control step.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2023.113527 5072953:EPHFNR2Q openalex: W4386514378
Keywords: Air-conditioning system; C:Mali; Energy consumption; LSTM neural network; Prediction model; _z:class:countries; _z:class:themes; _z:no_pdf; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11529 Refrigeration Systems and Technologies; oa:topic:T11954 Energy Efficiency in Manufacturing and Industry Sector; openalex:n:1; openalex:yes

International development in a contested world: ending extreme poverty and tackling climate change – A White Paper on International Development (2023)
Keywords: _z:class:countries

PM2.5 Observations of Outdoor and Indoor Environment at Dwarka, New Delhi, India - Malik, Shristy; Rao, A. S.; Dhaka, Surendra K. (MAPAN, 2023)
Measurement of PM2.5 is carried out simultaneously outdoors as well as indoors using a Compact and Useful PM2.5 Instrument (CUPI) from Nov 2018 to Oct 2019. A high-time resolution data (~ 2 min interval) was recorded at Dwarka (West Delhi), New Delhi, to investigate the difference between outdoor and indoor ambient particulate matter. Year-long observations provide an opportunity to decipher that indoor PM2.5 concentration increases significantly from mid-November 2018 to mid-December 2018. During this high concentration occurrence of PM2.5, outdoor concentration was higher in the range of 100–200 µg/m3 than indoor. Indoor pollution was less by 30–50% in comparison to the outdoor environment. Analyses reveal that during a high pollution period, intermittently for a short period, outdoor PM2.5 was less, which coincides with clear weather days suggesting that indoor pollution did not disperse due to a closed environment. Diurnal variation of PM2.5 clearly shows high concentration stays until 12:00 noon in both indoor and outdoor environments, which reduces in the afternoon and again picks up in the evening. Diurnal variation of solar radiation showed a consistent increase from 9 am to 2 pm, while relative humidity declined considerably from 10 am to 4 pm (local time); these two factors correspond to less concentration in both indoor and outdoor environments. However, there is no significant difference between outdoor and indoor concentration during summer and monsoon season.
KerkoCite.ItemAlsoKnownAs: 5072953:PSPPNADD 5072953:ZTZG5U9E
Keywords: C:India; _z:class:countries; _z:no_pdf

Climate Change and Its Implications on School Education in Kenya - Ogendi, George Mokua (2023)
Climate change is the greatest challenge of the 21st century. It is threatening all aspects of societal life. The right to education of children is negatively impacted by these climate-induced challenges. This chapter presents findings of a study on the effects of climate change on the education of the younger generation. The study used a mixed research design method and was done within Kisii Municipality, Kenya. The findings were that climate change and its effects have brought about increased waterborne diseases, reduced available income for families, and compromised living standards, thereby negatively impacting on children's education. To address the effects of climate change, however, provision of appropriate education can go a long way in mitigating these climatic challenges. Secondly, topics on climate change should be included in the school curriculum.
openalex:W4386160772 mag: KerkoCite.ItemAlsoKnownAs: 10.4018/978-1-6684-9099-0.ch007 5072953:V2TDV5X9
Keywords: C:Kenya; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:climate change; oa:keyword:school education; oa:sdg:13 Climate action; oa:topic:T10747 Community Resilience to Natural Disasters; oa:topic:T12656 Impact of Climate Change on Human Migration; oa:topic:T14296 Climate Change and Sustainable Development; openalex:import; openalex:n:1; openalex:yes

Integrating Climate Change Education Into the Curriculum in Kenya - Syallow, Maureen; Dimba, Magdalene; King'ori, Esther Muthoni (2023)
The effects of climate change are a major global concern. In Kenya, the impact of climate change has been felt in perennial droughts which sometimes result into conflict as communities fight for pasture and water. In a bid to address climate change issues, Kenya has developed policies that focus on mitigation and adaptation measures borrowed from ideas outlined in global climate change strategies. One such strategy is the employment of education as a tool to create awareness on climate change issues. This chapter will examine the climate change policies developed by bodies in charge of higher education in Kenya. The chapter will further analyze attempts that have been made to integrate climate change education into curricula. In addition, the chapter will trace the history of discourse that saw the introduction of climate change education in institutions of higher learning. Finally, the chapter will analyze pedagogical strategies that can be employed in teaching climate change content.
openalex:W4386174507 mag: KerkoCite.ItemAlsoKnownAs: 10.4018/978-1-6684-9099-0.ch002 5072953:H8IKIES8
Keywords: C:Kenya; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:climate change; oa:keyword:climate change education; oa:sdg:13 Climate action; oa:topic:T12343 Geography Education and Spatial Thinking; oa:topic:T12656 Impact of Climate Change on Human Migration; oa:topic:T13839 Volunteer Tourism and Global Development Impacts; openalex:import; openalex:n:1; openalex:yes

Climate Change and Disability Inclusion in Uzbekistan (2023)
openalex: W4388189107
Keywords: _z:class:countries; openalex:import; openalex:yes

Indoor Air Quality Implications of Germicidal 222 nm Light - Barber, Victoria P.; Goss, Matthew B.; Franco Deloya, Lesly J.; LeMar, Lexy N.; Li, Yaowei; Helstrom, Erik; Canagaratna, Manjula; Keutsch, Frank N.; Kroll, Jesse H. (Environmental Science & Technology, 2023)
Keywords: _z:class:countries

Optimising multi-factor assistance in a deep learning-based electricity forecasting model with climate resilience: an Australian case study - Yang, Weijia; Sparrow, Sarah; Wallom, David (2023)
With the increasing incidence of power blackouts attributed to climate change, climate-resilient load forecasting is increasingly necessary to enable timely network reconfiguration during extreme weather events. This paper proposes a generalised multi-factor Deep Learning (DL) model to forecast electricity load in Distribution Networks (DNs) during extreme climate periods. We optimise factors that affect forecast accuracy, including input matrix structures, calendar effects, and correlation-based preceding temperatures. The novel input feature selection decreases the Mean Absolute Percentage Error (MAPE) by 30.73% when compared to using instantaneous temperature alone. The model has been developed based on three real DNs in Victoria, Australia, during the wildfire seasons of 2015-2020. The sensitivity to large- scale climate variability, such as El Niño or La Niña, has also been assessed, showing minimal impact. Our model achieves an average forecast MAPE of 2.95%, ensuring that reconfiguration events mitigate rather than exasperate high load conditions during periods of extreme stress.
openalex: W4391342067
Keywords: C:Australia; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10424 Electricity Market Operation and Optimization; oa:topic:T11052 Electricity Price and Load Forecasting Methods; openalex:import; openalex:n:1; openalex:yes

Optimising multi-factor assistance in a deep learning-based electricity forecasting model with climate resilience: an Australian case study - Yang, Weijia; Sparrow, Sarah; Wallom, David (2023)
With the increasing incidence of power blackouts attributed to climate change, climate-resilient load forecasting is increasingly necessary to enable timely network reconfiguration during extreme weather events. This paper proposes a generalised multi-factor Deep Learning (DL) model to forecast electricity load in Distribution Networks (DNs) during extreme climate periods. We optimise factors that affect forecast accuracy, including input matrix structures, calendar effects, and correlation-based preceding temperatures. The novel input feature selection decreases the Mean Absolute Percentage Error (MAPE) by 30.73% when compared to using instantaneous temperature alone. The model has been developed based on three real DNs in Victoria, Australia, during the wildfire seasons of 2015-2020. The sensitivity to large- scale climate variability, such as El Niño or La Niña, has also been assessed, showing minimal impact. Our model achieves an average forecast MAPE of 2.95%, ensuring that reconfiguration events mitigate rather than exasperate high load conditions during periods of extreme stress.
openalex: W4391342067
Keywords: C:Australia; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10424 Electricity Market Operation and Optimization; oa:topic:T11052 Electricity Price and Load Forecasting Methods; openalex:import; openalex:n:1; openalex:yes

The impact of climate change on the resilience of banking systems in selected Sub-Saharan economies - Amo-Bediako, Emmanuel; Takawira, Oliver; Choga, Ireen (International Journal of Applied Economics, Finance and Accounting, 2023)
Climate change is seen as a peril to the overall financial system, yet this revelation is in its infant stage. On that note, this study investigates the impact of climate change shocks on banking system resilience in selected Sub-Saharan economies. The study relies on a quantitative research method by first employing a Generalized Auto Regressive Conditional Heteroskedasticity (GARCH) (1,1) model to forecast the volatility series of the climate change variables. Further, the study applies the panel ARDL model to disseminate the longand short-term associations between the obtained conditional variances of climate change parameters and banking system resilience within a time frame of 1996-2017 for 29 selected economies. The results show that banking systems in SSA are resilient to temperature shocks in the long-term. However, the study finds that the banking systems in SSA are not resilient to both precipitation and greenhouse gas shocks in the long-term. For the short-term impact assessment, the study finds that banking systems in SSA are resilient to only precipitation shocks. The study concludes that banking sectors in SSA should vigorously conduct stress-testing on climate-related financial risks and also design forward-looking strategies as well as climate change risk management procedures in the wake of climate change events.
Keywords: _z:class:countries

Spatio-temporal interpretable neural network for solar irradiation prediction using transformer - Gao, Yuan; Miyata, Shohei; Matsunami, Yuki; Akashi, Yasunori (Energy and Buildings, 2023)
Deep learning models have been increasingly applied in the field of solar radiation prediction. However, the characteristics of a deep learning black box model restrict its application in practical scenarios such as model predictive control. Because energy system controllers may be unable to make final decisions based solely on the predictions of a black-box model. This study considers both the temporal and spatial dependencies of solar radiation predictions through unfolding sequences and applying a transformer model As the results indicate, the transformer model used can improve the mean absolute percent error by approximately 20.9% and the mean squared error by 14.3% compared to the baseline recurrent neural network model. At the same time, detailed case studies show that the transformer model heavily considers humidity and temperature when predicting the more significant outcomes Finally, the detailed results of a one-step analysis prove that the change in weight of the transformer model is related to the change in outdoor weather conditions.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2023.113461 5072953:ZT667M7S openalex: W4386034952
Keywords: Building energy management; Interpretable deep learning; Solar irradiation prediction; Transformer; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:solar irradiation prediction; oa:sdg:7 Affordable and clean energy; oa:topic:T10468 Photovoltaic Maximum Power Point Tracking Techniques; oa:topic:T11052 Electricity Price and Load Forecasting Methods; oa:topic:T11276 Machine Learning Methods for Solar Radiation Forecasting; openalex:n:1; openalex:yes

Identifying gaps on health impacts, exposures, and vulnerabilities to climate change on human health and wellbeing in South America: a scoping review - Palmeiro-Silva, Yasna K.; Lescano, Andrés G.; Flores, Elaine C.; E, Yamileth Astorga; Rojas, Luis; Chavez-Hermosilla, Mario; Mora-Rivera, Wendel; Hartinger, Stella M. (The Lancet Regional Health - Americas, 2023)
There is an important gap in regional information on climate change and health, limiting the development of science-based climate policies in South American countries. This study aims to identify the main gaps in the existing scientific literature on the impacts, exposure, and vulnerabilities of climate change on population health. A scoping review was performed guided by four sub-questions focused on the impacts of climate change on physical and mental health, exposure and vulnerability factors of population to climate hazards. The main findings showed that physical impacts mainly included infectious diseases, while mental health impacts included trauma, depression, and anxiety. Evidence on population exposure to climate hazards is limited, and social determinants of health and individual factors were identified as vulnerability factors. Overall, evidence on the intersection between climate change and health is limited in South America and has been generated in silos, with limited transdisciplinary research. More formal and systematic information should be generated to inform public policy.None.
openalex: W4386122878
Keywords: _z:class:countries; evidence_review; openalex:citedBy; openalex:import; selected_for:effects of climate ch...on learning...LMICs 2024; tagged

Prediction of window opening behavior and its impact on HVAC energy consumption at a residential dormitory using Deep Neural Network - Pandey, Pratik Raj; Dong, Bing (Energy and Buildings, 2023)
Individuals globally spend about 88–92% of their entire time in the indoor environment. The implementation of regularly scheduled systems operation is common in many commercial and residential building types. Occupant Behavior (OB) is highly stochastic, making it difficult to depict the human factor using simple schedules. In the present work, window-opening tendencies were found to be highest in summer and transition seasons and lowest during winter. The Air Changes per Hour (ACH) value obtained from blower door testing was compared with the average ACH value obtained from the mass balance equation. These ACH values were imported to the EnergyPlus model. A three-hidden layered deep neural network was developed to predict the window's state at 16 residential dorms. The data was collected from August 2021 to May 2022 to train and test the DNN models. 48 windows’ operations were measured during this timeframe and 48 DNN models were created with an average accuracy of 96.71% and an average True Positive Rate (TPR) of 0.9136. Bedroom windows were found to be more time-dependent than living room windows. Incorporating time components into the bedroom window opening models can increase the TPR by 0 to 6%. The models were then integrated into the Energy Plus simulation engine using the newly introduced Python API to simulate the total HVAC energy consumption during the occupied heating season of 2021–2022. The DNN coupled model predicts 16,350 kWh energy is lost through windows from eight homes in an occupied heating season.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2023.113355 5072953:PXYQW8KW openalex: W4384156628
Keywords: Artificial intelligence; Deep Neural Network; Energy loss through windows; Occupant behavior; Residential dorms; Window operation; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:hvac energy consumption; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T12256 Impact of Workspace Environment on Work Performance; openalex:n:1; openalex:yes

Understanding the complex dynamics of climate change in south-west Australia using Machine Learning - Yadav, Alka; Das, Sourish; Bakar, K. Shuvo; Chakrabarti, A. (Physica A: Statistical Mechanics and its Applications, 2023)
The climate system is an excellent example of a “complex system” since there is an interplay and inter-relation of several climate variables. Variables such as the Standardized Precipitation Index (SPI) are used to indicate the drought climate condition – a negative (or positive) value of SPI would imply a dry (or wet) state in a region. It is difficult to identify the factors influencing the SPI or their inter-relations (including feedback loops). Here, we aim to study the complex dynamics that SPI has with the sea surface temperature (SST), El Niño Southern Oscillation (ENSO) (aka., NINO 3.4) and Indian Ocean Dipole (IOD), using a machine learning approach. Our findings are: (i) IOD was negatively correlated to SPI till 2008; (ii) until 2004, SST was negatively correlated with SPI; (iii) from 2005 to 2014, the SST had swung between negative and positive correlations; (iv) since 2014, we observed that the regression coefficient (δ) corresponding to SST has always been positive; (v) the SST has an upward trend, and the positive upward trend of δ implied that SPI has been positively correlated with SST in recent years; and finally, (vi) the current value of SPI has a significant positive correlation with a past SPI value with a periodicity of about 7.5 years. Examining the complex dynamics, we used a statistical machine learning approach to construct an inferential network of these climate variables, which revealed that SST and NINO 3.4 directly couples with SPI, whereas IOD indirectly couples with SPI through SST and NINO 3.4. The system also indicated that Nino 3.4 significantly negatively affects SPI. If Nino 3.4 increases (decreases), the SPI drops (increases) considerably, leading to more drought (wet) conditions. Interestingly, there was a structural change in the complex dynamics of the four climate variables of NINO 3.4, IOD, SST, and SPI, sometime in 2008. Though a simple 12-month moving average of SPI over 58 years (1961–2018) has a negative trend towards drought, the complex dynamics of SPI with other climate variables indicate a wet season for south-west Australia.
openalex: W4385880672
Keywords: C:Australia; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:topic:T10029 Climate Change and Variability Research; oa:topic:T10466 Numerical Weather Prediction Models; oa:topic:T11186 Global Drought Monitoring and Assessment; openalex:import; openalex:yes

Understanding the complex dynamics of climate change in south-west Australia using Machine Learning - Yadav, Alka; Das, Sourish; Bakar, K. Shuvo; Chakrabarti, A. (Physica A: Statistical Mechanics and its Applications, 2023)
The climate system is an excellent example of a “complex system” since there is an interplay and inter-relation of several climate variables. Variables such as the Standardized Precipitation Index (SPI) are used to indicate the drought climate condition – a negative (or positive) value of SPI would imply a dry (or wet) state in a region. It is difficult to identify the factors influencing the SPI or their inter-relations (including feedback loops). Here, we aim to study the complex dynamics that SPI has with the sea surface temperature (SST), El Niño Southern Oscillation (ENSO) (aka., NINO 3.4) and Indian Ocean Dipole (IOD), using a machine learning approach. Our findings are: (i) IOD was negatively correlated to SPI till 2008; (ii) until 2004, SST was negatively correlated with SPI; (iii) from 2005 to 2014, the SST had swung between negative and positive correlations; (iv) since 2014, we observed that the regression coefficient (δ) corresponding to SST has always been positive; (v) the SST has an upward trend, and the positive upward trend of δ implied that SPI has been positively correlated with SST in recent years; and finally, (vi) the current value of SPI has a significant positive correlation with a past SPI value with a periodicity of about 7.5 years. Examining the complex dynamics, we used a statistical machine learning approach to construct an inferential network of these climate variables, which revealed that SST and NINO 3.4 directly couples with SPI, whereas IOD indirectly couples with SPI through SST and NINO 3.4. The system also indicated that Nino 3.4 significantly negatively affects SPI. If Nino 3.4 increases (decreases), the SPI drops (increases) considerably, leading to more drought (wet) conditions. Interestingly, there was a structural change in the complex dynamics of the four climate variables of NINO 3.4, IOD, SST, and SPI, sometime in 2008. Though a simple 12-month moving average of SPI over 58 years (1961–2018) has a negative trend towards drought, the complex dynamics of SPI with other climate variables indicate a wet season for south-west Australia.
openalex: W4385880672
Keywords: C:Australia; C:India; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:topic:T10029 Climate Change and Variability Research; oa:topic:T10466 Numerical Weather Prediction Models; oa:topic:T11186 Global Drought Monitoring and Assessment; openalex:import; openalex:yes

Climate, environment and schools in Tanzania - Fab Inc; Laterite (2023)
KerkoCite.ItemAlsoKnownAs: 5072953:7AEEJ3QV
Keywords: C:Tanzania; _z:class:countries; _z:class:themes

Educators' Perceptions of Climate Change Education in Pakistan & Students’ Readiness - Saeed, Atif (Pakistan journal of educational research, 2023)
This qualitative study aims to investigate the outlook of geography educators in Pakistan. It involves a group of around twelve participants, primarily aiming to understand their viewpoints regarding the goals of climate change education; it also explores how these viewpoints influence their teaching approaches, especially when dealing with contentious topics in geography education. The research delves into the complex educational landscape related to climate change education in Pakistan. The study's results reveal that educators' perspectives on the objectives of climate change education significantly impact their willingness to address controversial subjects in their classrooms. Additionally, the study reveals that educators' beliefs concerning their students' academic abilities significantly influence their strategies for addressing contentious aspects of climate change education, resulting in tailored approaches for various student demographics. This study provides valuable insights into the mindset of Pakistani educators concerning climate change education. It sheds light on the factors that inform their pedagogical decision-making. By examining these dynamics, the study aims to contribute to the discourse on climate change education in Pakistan, addressing the unique challenges and opportunities posed by this critical global issue. This research underscores the importance of comprehensive and inclusive climate change education that equips all students to engage with environmental issues effectively. Such an approach holds the potential to foster a more equitable and impactful education system, not only in Pakistan but also in other regions globally
openalex: W4388799298
Keywords: C:Pakistan; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T12343 Geography Education and Spatial Thinking; oa:topic:T12904 Agricultural Education and School Gardening Research; openalex:import; openalex:yes

Monitoring, evaluation and learning (MEL) in farmer field schools on food security and adaptation to climate change: pilot testing of a framework in Malawi - Berg, Henk van den; Chikomola, Anderson; Bondo, Austin; Ameny, Thomas; Okoth, J.; Kamwendo, Noella; Dicke, Marcel; Kirichu, Samuel (Food Security, 2023)
The farmer field school (FFS) has been promoted as an approach for educating farmers on making adaptive farming decisions. In Malawi, the FFS has been used to enhance food security within the context of adaptation to climate change. Monitoring, evaluation and learning (MEL) extends the learning cycle from the core of the FFS to the project level to facilitate learning and adaptation for improvement of interventions. This study’s objectives were to test the utility of a MEL framework for the FFS, and to explore the effects of the FFS. The framework differentiated between four capital domains. Data were collected from 33 FFS groups at 2–4 years after the start of the FFS, using spider diagramming, focus group discussions, and direct observation. These tools demonstrated their feasibility and acceptability for use by practitioners at the district level and provided cross-verification of results, whereas limitations included the risk of biased results, e.g. due to vested interests of respondents. The MEL methods can be adapted for use in other FFS programmes and other contexts through modification of the framework’s targets or questions. The effects of the FFS were evident for most targets in the human, social and natural domains, whilst effects for some targets in the financial domain were smaller. Effects that were indicative of food security and adaptation to climate change included improvements in adaptive capacity, experimentation, crop cultivation practices, crop diversification, collective actions, food sources and meals, and savings.
openalex:W4386982759 mag: KerkoCite.ItemAlsoKnownAs: 10.1007/s12571-023-01386-0 5072953:MJWTDTUM
Keywords: C:Malawi; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10367 Agricultural Innovation and Livelihood Diversification; oa:topic:T11610 Impact of Food Insecurity on Health Outcomes; oa:topic:T12896 Evaluation of Environmental Impact in Agriculture; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Perception of Climate Change at Ain Shams Medical Campus: A Survey of Egyptian Medical Students - Yousef, Shaimaa; Momen, Mohamed; Abdellatif, Aya (The Egyptian Journal of Community Medicine, 2023)
openalex:W4387041105 KerkoCite.ItemAlsoKnownAs: 10.21608/ejcm.2023.220870.1264 5072953:FKN564PA
Keywords: C:Egypt; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T11244 Impact of Climate Change on Human Health; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Climate Change and Transatlantic Slavery: Uncomfortable parallels, uncertain futures - Niles, Keron (Pan-African Conversations, 2023)
The article examines the causes and effects of climate change and juxtaposes these with the transatlantic slave trade to glean what lessons, if any, can be learnt. It further explores any systemic linkages between transatlantic slavery and climate change, and proffers sustainable recommendations for mitigating the current dilemmas associated with slavery and climate change. To this end, this study finds that the effects of transatlantic slavery and climate change reveal multi-generational impacts related to a lack of representation, the disproportionate distribution of benefits and costs, cultural losses, and a lack of frameworks to facilitate compensation to those adversely affected. The article concludes by underscoring useful measures that can be adopted to combat the proliferation of similar problems in the future.
Number: 2
Keywords: _z:class:countries

Prototype Design of Automatic Switching Speed of Exhaust Fan For Indoor Air Quality Control With Warning Alarm System Based on IoT - Adziimaa, Ahmad Fauzan; Ardiatmajaya, Egik; Utami, Riski Mulyaning (2023 International Conference on Electrical and Information Technology (IEIT), 2023)
Keywords: _z:class:countries

Terminal evaluation of the project “Strengthening capacities of agricultural producers to cope with climate change for increased food security through the Farmer Field School approach in Mozambique” (2023)
openalex:W4386640060 KerkoCite.ItemAlsoKnownAs: 10.4060/cc6976en 5072953:NG4G2AIU
Keywords: C:Mozambique; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:farmer field school approach; oa:sdg:2 Zero hunger; oa:topic:T12896 Evaluation of Environmental Impact in Agriculture; openalex:import; openalex:n:1; openalex:yes

Improving learning through classroom experience in Tanzania – Presentation - Pattni, Ravina; Villavicencio Peralta, Xuzel; Toyinbo, Oluyemi; Proctor, Jamie; Forbes, Catriona; Atherton, Paul; Haßler, Björn (Laterite, Fab Inc, Open Development & Education, 2023)
This conference paper was delivered at UKFIET 2023 (Oxford). IT was a joint presentation between Laterite, Fab Inc, and Open Development & Education, as well as FCDO.
ZenodoArchiveID: 10044115 ZenodoArchiveConcept: 10044114 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1025 2129771:ICBNFIUW 2129771:JNMJ2AAW 2129771:U5GXRKUD 5072953:V6YBP2PG
Keywords: C:Tanzania; _r:AddedByMyEducationEvidence; _z:class:countries; _z:class:themes

Trialling environmental sensors in Tanzanian schools – First pilot - Toyinbo, Oluyemi; Villavicencio, Xuzel; Haßler, Björn (2023)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10257287 ZenodoArchiveConcept: 10257286 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1035 2129771:NFNWZX3A 5072953:FZCR8IW7
Keywords: C:Tanzania; _publish; _r:AddedByMyEducationEvidence; _z:class:countries; _z:class:themes

Conducting surveys in Tanzanian schools – Second pilot - Villavicencio, Xuzel; Haßler, Björn; Toyinbo, Oluyemi (2023)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10257420 ZenodoArchiveConcept: 10257419 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1036 2129771:EZ9EFDFS 5072953:YFY9R5AI
Keywords: C:Tanzania; _r:AddedByMyEducationEvidence; _z:class:countries; _z:class:themes

The impact of climate change on cognitive performance of children in English school stock: A simulation study - Dong, Jie; Schwartz, Yair; Korolija, Ivan; Mumovic, Dejan (Building and Environment, 2023)
Children in England spend around 30% of their time in schools to gain knowledge and skills. Climate change could impact schools' thermal environments and children's learning performance by impairing their cognitive ability. This study presents an evaluation approach to investigating and quantifying climate change's impact on the cognitive performance of children across English school stocks. The study also evaluates the potential of possible strategies for mitigating the impacts of climate change. The results show that future climates are projected to increase cognitive performance loss of children in school archetypes representative of school stocks, with variations based on regional climate characteristics. Increasing ventilation rates proves to be an effective means of reducing cognitive performance loss, while its effectiveness diminishes as outdoor temperatures rise in the future. Thus, the introduction of air conditioning becomes a potentially more beneficial strategy, despite the associated increase in cooling energy demand. Moreover, higher ventilation rates in air-conditioned classrooms can further improve children's cognitive performance. The use of cognitive performance loss as a Key Performance Indicator (KPI) allows for better communication and understanding of climate change risks faced by schools among building and non-building experts. The proposed evaluation approach remains adjustable and can be continuously updated and enhanced as new insights from psychological research emerge.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.buildenv.2023.110607 2129771:DHHN5N8V 4874017:ZSQG47I2
Keywords: Building stock modelling; Climate adaptation; Climate change; Climate resilience; Cognitive performance; School; evidence_review

Optimizing the control of Venetian blinds with artificial neural networks to achieve energy savings and visual comfort - Nicoletti, Francesco; Kaliakatsos, Dimitrios; Parise, Mirco (Energy and Buildings, 2023)
Solar shading devices, such as Venetian blinds, are effective in controlling heat and light gain in buildings. This study focuses on developing an Artificial Neural Network (ANN) to automate the management of Venetian blinds in order to find a balance between energy savings and visual comfort. Typically, automatic control strategies rely on cut-off angles or maintaining appropriate indoor illuminance. However, finding the optimal trade-off between solar gain and daylight is challenging, particularly in regions with temperate or tropical climates. To this end, this paper proposes a novel approach to identify the best slat arrangement. The optimal angle is determined by simulating all possible slat angles using EnergyPlus and selecting the one that maximizes an objective function. The ANN is trained to recognize this angle as a function of variables that can be easily measured in situ. The resulting building’s behavior is tested on EnergyPlus using the output provided by the ANN. The results demonstrate that the target angle can be identified with high reliability, even for windows with different orientation and in other cities. The energy savings for heating/cooling are up to 37.7 %/38.7 %. The UDI200-800 increases by up to 38.5 % at the expense of a slight increase in lighting consumptions (13.5 %).
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2023.113279 5072953:T9LHX7GY openalex: W4381051659
Keywords: Artificial neural networks; Building management system; Optimal angle; Solar radiation; Venetian blinds; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:venetian blinds; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:n:1; openalex:yes

Modelling urban dwellers’ indoor heat stress to enhance heat-health warning and planning - Yi, Choo-yoon; Peng, Chengzhi; Robinson, Darren (Building and Environment, 2023)
Due to climate change, the intensity, duration and frequency of heatwaves are likely to increase in the coming years. Excessive heat events can increase local urban heat island intensity affecting the health and wellbeing of urban dwellers vulnerable to heat stress. Heat-Health Warning Systems (HHWSs) have been developed to warn the public of impending heat events and to advise on preventable negative health outcomes. However, metrics upon which action triggers are made in HHWSs rely on reported critical outcomes, such as heat-related excess death. Thus, human exposure to heat is underestimated in current metrics and consequently, their capacity to prevent heat-related health risks remains uncertain, particularly indoors. This study investigates how indoor heat stress in urban dwellings at a city-scale can be modelled to enhance Heat-Health Warning and Planning. First, the effects of housing typologies on indoor thermal conditions are quantified in a local urban microclimate context. We then model the dynamic relationships between outdoor climate and indoor heat exposure to identify specific outdoor climatic thresholds as action triggers for alerting urban dwellers’ indoor heat stress. Based on urban microclimate data available for a city of Birmingham UK, a proof-of-principle study is presented. The result shows the presence of large variances in the heat-health action triggers across different housing typologies. This is further extended to consider the Birmingham climate projection scenarios provided by the UKCP18. Compared to the current UK Heat-Health Alert Service, we show how indoor heat stress warnings may look like and the implications for long-term heat-health planning.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.buildenv.2023.110623 5072953:XIJ4Q5AL 5072953:XU2AEQSL openalex: W4384775158
Keywords: Building typologies; Heat-health plan; Heat-health warning systems (HHWSs); Heatwaves; Indoor heat stress; Urban heat island; _important; _z:class:countries; _z:class:themes; oa:keyword:heat stress; oa:keyword:indoor heat stress; oa:sdg:13 Climate action; oa:topic:T10190 Health Effects of Air Pollution; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11244 Impact of Climate Change on Human Health; openalex:n:1; openalex:yes; selected_for:Predictive models for classroom conditions 2024

Modelling urban dwellers’ indoor heat stress to enhance heat-health warning and planning - Yi, Choo-yoon; Peng, Chengzhi; Robinson, Darren (Building and Environment, 2023)
Due to climate change, the intensity, duration and frequency of heatwaves are likely to increase in the coming years. Excessive heat events can increase local urban heat island intensity affecting the health and wellbeing of urban dwellers vulnerable to heat stress. Heat-Health Warning Systems (HHWSs) have been developed to warn the public of impending heat events and to advise on preventable negative health outcomes. However, metrics upon which action triggers are made in HHWSs rely on reported critical outcomes, such as heat-related excess death. Thus, human exposure to heat is underestimated in current metrics and consequently, their capacity to prevent heat-related health risks remains uncertain, particularly indoors. This study investigates how indoor heat stress in urban dwellings at a city-scale can be modelled to enhance Heat-Health Warning and Planning. First, the effects of housing typologies on indoor thermal conditions are quantified in a local urban microclimate context. We then model the dynamic relationships between outdoor climate and indoor heat exposure to identify specific outdoor climatic thresholds as action triggers for alerting urban dwellers’ indoor heat stress. Based on urban microclimate data available for a city of Birmingham UK, a proof-of-principle study is presented. The result shows the presence of large variances in the heat-health action triggers across different housing typologies. This is further extended to consider the Birmingham climate projection scenarios provided by the UKCP18. Compared to the current UK Heat-Health Alert Service, we show how indoor heat stress warnings may look like and the implications for long-term heat-health planning.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.buildenv.2023.110623 5072953:XIJ4Q5AL 5072953:XU2AEQSL openalex: W4384775158
Keywords: Building typologies; Heat-health plan; Heat-health warning systems (HHWSs); Heatwaves; Indoor heat stress; Urban heat island; _important; _z:class:countries; _z:class:themes; oa:keyword:heat stress; oa:keyword:indoor heat stress; oa:sdg:13 Climate action; oa:topic:T10190 Health Effects of Air Pollution; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11244 Impact of Climate Change on Human Health; openalex:n:1; openalex:yes; selected_for:Predictive models for classroom conditions 2024

Mechanisms of urban blue-green infrastructure on winter microclimate using artificial neural network - Fei, Fan; Wang, Yan; Wang, Luyao; Fukuda, Hiroatsu; Yao, Wanxiang; Zhou, Yue; Dong, Xiaohan (Energy and Buildings, 2023)
In response to climate change, urban blue-green infrastructure (UBGI) improves the microclimate of the built environment. In previous research, UBGI (consisting of water and greenery) is found to be a cold source in the summer, alleviating urban thermal stress. However, studies on the heating effect of UBGI in the winter are limited. This effect can improve environmental temperature, which is beneficial to human thermal comfort in the cold season. Therefore, this study conducted the objective and subjective evaluation of the winter microclimate of UBGI through field measurement and questionnaire in China’s cold regions. The coupling mechanisms of UBGI on winter microclimate were quantified by using the artificial neural network (ANN), and the thermal demand characteristic of UBGI users was established. The study results showed that the heating effect of water and greenery was most significant at a distance of 4 m from the water in the winter. Neural network-predicted models are established to discuss coupling mechanisms in depth. The new microclimate influence (MI) model of coupling mechanisms was proposed based on the ANN. In addition, when the air temperature was 9.07–14.75℃, the UBGI not only satisfied the thermal comfort demand but also had a greater comfort level than general urban underlying surfaces did. The universal thermal climate index (UTCI) evaluation based on the coupling mechanisms for UBGI users was obtained. This study offers scientific guidance and reference for the planning and redevelopment of UBGI.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2023.113188 5072953:IM52JB9Z openalex: W4378417862
Keywords: Artificial neural network; C:China; Mechanisms; Urban blue-green infrastructure; _z:class:countries; _z:class:themes; _z:no_pdf; microclimate influence (MI) model; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10692 Impact of Urban Green Space on Public Health; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; openalex:n:1; openalex:yes

Mechanisms of urban blue-green infrastructure on winter microclimate using artificial neural network - Fei, Fan; Wang, Yan; Wang, Luyao; Fukuda, Hiroatsu; Yao, Wanxiang; Zhou, Yue; Dong, Xiaohan (Energy and Buildings, 2023)
In response to climate change, urban blue-green infrastructure (UBGI) improves the microclimate of the built environment. In previous research, UBGI (consisting of water and greenery) is found to be a cold source in the summer, alleviating urban thermal stress. However, studies on the heating effect of UBGI in the winter are limited. This effect can improve environmental temperature, which is beneficial to human thermal comfort in the cold season. Therefore, this study conducted the objective and subjective evaluation of the winter microclimate of UBGI through field measurement and questionnaire in China’s cold regions. The coupling mechanisms of UBGI on winter microclimate were quantified by using the artificial neural network (ANN), and the thermal demand characteristic of UBGI users was established. The study results showed that the heating effect of water and greenery was most significant at a distance of 4 m from the water in the winter. Neural network-predicted models are established to discuss coupling mechanisms in depth. The new microclimate influence (MI) model of coupling mechanisms was proposed based on the ANN. In addition, when the air temperature was 9.07–14.75℃, the UBGI not only satisfied the thermal comfort demand but also had a greater comfort level than general urban underlying surfaces did. The universal thermal climate index (UTCI) evaluation based on the coupling mechanisms for UBGI users was obtained. This study offers scientific guidance and reference for the planning and redevelopment of UBGI.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2023.113188 5072953:IM52JB9Z openalex: W4378417862
Keywords: Artificial neural network; Mechanisms; Urban blue-green infrastructure; _z:class:countries; _z:class:themes; _z:no_pdf; microclimate influence (MI) model; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10692 Impact of Urban Green Space on Public Health; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; openalex:n:1; openalex:yes

Graph neural network-based spatio-temporal indoor environment prediction and optimal control for central air-conditioning systems - Zhang, Jing; Xiao, Fu; Li, Ao; Ma, Tianyou; Xu, Kan; Zhang, Hanbei; Yan, Rui; Fang, Xing; Li, Yuanyang; Wang, Dan (Building and Environment, 2023)
Model-based optimal control has proven its effectiveness in optimizing the performance of central air-conditioning systems in terms of thermal comfort and energy efficiency. It was often assumed that temperature distribution in the entire air-conditioned space is uniform and can be represented by a single or averaged measurement in optimization. However, actual distribution in the air-conditioned space is usually uneven, which can affect thermal comfort and indoor air quality. The dynamics of air conditioning systems and their interactions with the built environment exist in both time and space domains. Conventional data-driven approaches typically concentrate on the temporal correlations only among building operation data, while neglecting the spatial correlations. This study proposed a spatio-temporal data-driven methodology for optimal control of central air conditioning systems, which aims to address the challenging issue of uneven spatial distributions of environmental parameters in air-conditioned space. The methodology consists of graph-based multi-source data integration, graph neural network-based indoor environment modeling and spatio-temporal model-based online optimal control. The proposed methodology is tested on real air handling unit-variable air volume (AHU-VAV) system in a high-rise office building through a cloud-based platform. Spatio-temporal data from building automation system (BAS), internet of things (IoT) devices and building information modeling (BIM) are integrated and organized as graph structure. Graph neural network models are developed for predicting the evolution of indoor air temperature distribution under different control settings. The developed graph neural network-recurrent neural network (GNN-RNN) model architectures show enhanced accuracy than conventional deep learning models (i.e., convolutional neural network-recurrent neural network (CNN-RNN), Dense-RNN). And the cloud-based online test demonstrates that the proposed model-based control strategy improves the percentage of time achieving Grade I thermal comfort from 36.5% (i.e., existing control strategy) to 81.3%.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.buildenv.2023.110600 5072953:VRBHK3GI openalex: W4383497835
Keywords: Air conditioning system; Graph neural network; Indoor environment; Machine learning; Optimal control; _z:class:countries; _z:class:themes; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T12120 Low-Cost Air Quality Monitoring Systems; openalex:n:1; openalex:yes

Building performance simulation in the brave new world of artificial intelligence and digital twins: A systematic review - de Wilde, Pieter (Energy and Buildings, 2023)
In an increasingly digital world, there are fast-paced developments in fields such as Artificial Intelligence, Machine Learning, Data Mining, Digital Twins, Cyber-Physical Systems and the Internet of Things. This paper reviews and discusses how these new emerging areas relate to the traditional domain of building performance simulation. It explores the boundaries between building simulation and these other fields in order to identify conceptual differences and similarities, strengths and limitations of each of these areas. The paper critiques common notions about these new domains and how they relate to building simulation, reviewing how the field of building performance may evolve and benefit from the new developments.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2023.113171 5072953:RCUUUF9P openalex: W4377023743
Keywords: Artificial intelligence; Building performance simulation; Cyber-physical system; Data mining; Digital twin; Internet of things; Machine learning; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:digital twins; oa:sdg:11 Sustainable cities and communities; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11006 Building Information Modeling in Construction Industry; oa:topic:T11211 3D Geospatial Modelling Techniques; openalex:n:1; openalex:yes

People with Disabilities Needed in Fight Against Climate Change (Climate Change and Law Collection, 2023)
openalex: W4385428232 KerkoCite.ItemAlsoKnownAs: 10.1163/9789004322714_cclc_2020-0150-0760 5072953:WMUBTFY7 5440726:FIWZ73QK
Keywords: _z:class:countries; openalex:import; openalex:yes

A Case Study on PV-Aided Net Zero-Energy Building: the Daycare in IKCU - Djana, Loic Rebnodji; Güngör, Şahin (Scientific Research Communications, 2023)
At the core of our growing societies, energy supply stands as one of the major concerns today, and it will be an inevitable challenge for our near future. As the nations are looking to find solutions for the transition from fossil fuels – depleting at a high rate – to alternative energy sources, solar energy through PV cells is getting attention as an affordable and easily implemented option especially for power supply in commercial and residential buildings. This work consists in analyzing the possibility to cover the entire energy needs of a building via PV solar cells for the case of a constructed daycare. In this case study, HVAC energy requirement has been calculated by the TS825 standard. The standard specifies a method for calculating the net heating/ventilation energy need and provides the rules for calculating the maximum allowable temperature in buildings. First, dimensions of the investigated building are taken and characteristics affecting the thermal insulation are assessed. Then, other energy needs, mainly lighting and electrical devices, are computed in the analysis as internal electricity needs. The scope of this work extends to the assessment of indoor air quality for occupants of building, which is an important aspect in our case study where the occupants are children. ASHRAE standards 62.1 is utilized for this purpose. The standard specifies minimum ventilation rates and other measures intended to provide acceptable indoor air quality to human occupants and that minimizes adverse health effects. The results are obtained for monthly varying solar exposition in the specified area where the building is located to provide supply for the determined energy demand via solar energy. Finally, monocrystalline PV panel system has been proposed with proper orientation and adequate power potential. Based on the obtained results, as well as the economical aspect, inferences and suggestions are made for improvements.
Keywords: _z:class:countries

The Impact of Social Media Influence on Attitudes toward Sustainable Consumption “A Mediation Analysis of Climate Change Awareness” An applied Study on Higher Education Students in Egypt - Mussa, Mona Hamed (المجلة العلمية للدراسات التجارية والبيئية, 2023)
openalex:W4388162043 mag: KerkoCite.ItemAlsoKnownAs: 10.21608/jces.2023.321481 5072953:ZXSTI7V9
Keywords: C:Egypt; _z:class:countries; _z:class:themes; oa:keyword:climate change awareness”; oa:sdg:13 Climate action; oa:topic:T10609 Impact of Social Media on Consumer Behavior; oa:topic:T10880 Drivers and Impacts of Green Consumer Behavior; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

A Raspberry Pi Zero-based Basestation for environmental data collection - Haßler, Björn; Hassan, Mansour; Mahamane, Amina (Open Development & Education, 2023)
original-date: 2023-07-15T20:50:01Z KerkoCite.ItemAlsoKnownAs: 4874017:C873IPY5 5072953:8DCZBFEV
Keywords: _z:class:countries; _z:class:themes

Enhancing community resilience to climate change disasters: Learning experience within and from sub‐Saharan black immigrant communities in western Canada - Acharibasam, John Bosco; Datta, Ranjan (Sustainable Development, 2023)
Abstract Enhancing community capacity towards resilience is key to reducing climate disaster risk, especially in Black immigrant communities in Canada. While there are many extreme climate change events occurring, such as hailstorms, floods, snowstorms, forest fires, droughts, and heat waves in western Canada, there is no known study that has explored resilience within sub‐Saharan African immigrant communities to climate disaster risks in western Canada. All these extreme climate change events have devastated Black populations threatening their ability to cope with disaster risks. Following a decolonial phenomenology methodological framework research approach; our study explores sub‐Saharan African immigrant communities' adaptation strategies to address climate disaster risk in western Canada. In this research, our main purpose was to investigate whether community resilience strategies implemented by the two provinces (Saskatchewan and Alberta) meet the unique needs of sub‐Saharan African Immigrants. By exploring local communities' perspectives on climate change, we highlighted the relevance of inclusivity in climate capacity building to reduce disaster risk and cope with climate change‐related disasters in the localities. Our findings revealed that personal experiences with climate change risks significantly influenced communities' strength and resilience and contributed to their resilience strategies. We view this paper as a first step in developing a community‐led climate change resilience research agenda that will have a practical application for the community in the face of climate change in Canada.
openalex: W4384407272
Keywords: C:Canada; _z:class:countries; _z:class:themes; oa:keyword:climate change disasters; oa:keyword:community resilience; oa:sdg:13 Climate action; oa:topic:T10439 Adaptation to Climate Change in Agriculture; oa:topic:T10747 Community Resilience to Natural Disasters; oa:topic:T12656 Impact of Climate Change on Human Migration; openalex:import; openalex:yes

Conducting a systematic review in six weeks – experiences with and evaluation of an intensive team pilot project - Ames, Heather; Kornør, Hege; Evensen, Line Holtet; Lidal, Ingeborg Beate; Hafstad, Elisabet; Hestevik, Christine Hillestad; Jardim, Patricia Sofia Jacobsen; Hval, Gyri (Research Square (Research Square), 2023)
Abstract Background Evidence synthesis organisations worldwide are trying to meet commissioners’ need for rapid responses to their evidence synthesis commissions. In this project we piloted an intensive process, working to complete an evidence synthesis within six-weeks, rather than the standard lead time of 4-6 months. There were three objectives: 1) To develop a plan for and conduct an evidence synthesis in six weeks or less (“intensive pilot”) 2) To register time used for the intensive pilot 3) To evaluate the intensive pilot process and identify barriers, facilitators, learning points, areas for improvement or future implementation ideas. Methods The two project teams divided the pilot into three phases: Pre-planning, planning and intensive. During the pre-planning phase commissions were identified and researchers were recruited. During the planning phase the team interacted with the commissioner, completed the evidence synthesis protocol, and planned how they were going to work together during the intensive phase. During the intensive phase the team implemented their plan and completed the evidence synthesis they were assigned. We held reflective meetings and kept evaluator notes throughout the process. Results The team was able to achieve the project objectives. They developed and implemented a plan for conducting an evidence synthesis in six weeks. They registered their times use. During the pilot process the team reflected on and evaluated the process itself to identify barriers, facilitators, learning points, areas for improvement or future implementation ideas. The involved researchers preferred working in this intensive way. They felt that time use was more effective, and they were more focused. However, there are implications for project leadership and implementation that should be considered before implementing an intensive approach in future evidence synthesis projects. Conclusions The involved researchers preferred working intensively with one evidence synthesis over being involved with many projects at the same time. They felt that time use was more effective, and they were able to complete the tasks in a focused way. However, there are several implications for project management, leadership and further implementation that should be considered before implementing an intensive approach in future evidence syntheses.
openalex: W4383371218
Keywords: _z:class:countries; evidence_review; openalex:citedBy; openalex:import; selected_for:effects of climate ch...on learning...LMICs 2024; tagged

Human-AI Collaboration to Identify Literature for Evidence Synthesis - Spillias, Scott; Tuohy, P; Andreotta, Matthew; Annand-Jones, R; Boschetti, Fabio; Cvitanovic, Christopher; Duggan, Joe; Fulton, Elizabeth A.; Karcher, Denis B.; Paris, Cécile; Shellock, Rebecca; Trebilco, Rowan (Research Square (Research Square), 2023)
Abstract Systematic approaches to evidence synthesis can improve the rigour, transparency, and replicability of a traditional literature review. However, these systematic approaches are time and resource intensive. We evaluate the ability of OpenAI’s ChatGPT to undertake two initial stages of evidence syntheses (searching peer-reviewed literature and screening for relevance) and develop a novel collaborative framework to leverage the best of both human and AI intelligence. Using a scoping review of community-based fisheries management as a case study, we find that with substantial prompting, the AI can provide critical insight into the construction and content of a search string. Thereafter, we evaluate five strategies for synthesising AI output to screen articles based on predefined inclusion criteria. We find low omission rates (< 1%) of relevant literature by the AI are achievable, which is comparable to that of human screeners. These findings show that generalised AI tools can assist reviewers with evidence synthesis to accelerate the implementation and improve the reliability of a review.
openalex: W4383198986
Keywords: _z:class:countries; openalex:citedBy; openalex:import; selected_for:effects of climate ch...on learning...LMICs 2024; tagged

Sensorboard for use with Raspberry Pi GPIO / Raspberry Pi Zero - Haßler, Björn (Open Development & Education, 2023)
original-date: 2023-07-02T18:34:24Z KerkoCite.ItemAlsoKnownAs: 2129771:ESH93VPP 2129771:MTELHIJ6 4874017:UT3RFH6H 5072953:IPNLB2ZZ
Keywords: _z:class:countries; _z:class:themes

The importance of climate-friendly school buildings in Africa - Nambatya, Mauricia (2023)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10257528 ZenodoArchiveConcept: 10257527 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1039 2129771:RTMQSBV6 5072953:YQ4CAK73
Keywords: _r:AddedByMyEducationEvidence; _z:class:countries; _z:class:themes

Efficient and Accurate Peer-to-Peer Training of Machine Learning Based Home Thermal Models - Boubouh, Karim; Basmadjian, Robert; Ardakanian, Omid; Maurer, Alexandre; Guerraoui, Rachid (Proceedings of the 14th ACM International Conference on Future Energy Systems, 2023)
KerkoCite.ItemAlsoKnownAs: 10.1145/3575813.3597453 5072953:EJDZF6J2 openalex: W4380885277
Keywords: _important; _z:class:countries; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10603 Demand Response in Smart Grids; oa:topic:T10998 Microchannel Heat Transfer and Cooling Technology; openalex:n:1; openalex:yes; selected_for:Predictive models for classroom conditions 2024

Pakistani Chemistry Teachers’ Understanding, Beliefs, and Teaching Practice About Climate Change - Gill, A. Malcolm; Ellis, Todd; Henderson, Charles (Journal of research in science, mathematics and technology education, 2023)
Teachers’ personal beliefs and understanding about science topics play a vital role in students learning. This is especially relevant for the teaching of climate change which is a scientifically complicated topic that can also be influenced by personal and political views. Semi-structured interviews were conducted with thirteen Pakistani chemistry teachers (grades 10 & 12) to understand their knowledge about the science of climate change as well as their beliefs and practices related to the teaching of climate change. We found that teachers believe it is important to teach climate change in schools. They report that they teach climate change with relevant topics and do not face any obstacles doing so. No consensus was found regarding the appropriate grade levels and disciplines in which climate change should be taught. We also found that teachers have insufficient scientific knowledge about climate change (e.g., they think that any change in environment is climate change and climate change is related to pollution and ozone layer depletion). Our results suggest that there is a need to include climate change in in-service refresher courses and preservice teacher training programs, so the teachers have better understanding of the science of climate change. Further, there should be more climate change content in high school chemistry and biology.
openalex: W4381800962
Keywords: C:Pakistan; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10072 Enhancing Science Education through Inquiry and Argumentation; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:yes

Building energy model calibration using a surrogate neural network - Herbinger, Florent; Vandenhof, Colin; Kummert, Michaël (Energy and Buildings, 2023)
Energy studies of buildings are becoming more widespread as stakeholders strive to improve energy efficiency and reduce carbon emissions. As a result, there is an increased need for novel numerical techniques to automatically calibrate building energy models (BEMs) for these energy studies. In this paper, a new automated building calibration methodology was developed, which uses a surrogate (i.e., meta) multilayer perceptron artificial neural network (ANN) to infer unknown building parameters. Typically, in the field of BEM calibration, surrogate models are used as a time-saving technique. Instead of running the building simulation software during each iteration of an optimization search, a surrogate model can approximate the output of the BEM very quickly, leading to much faster optimization of the unknown building parameters. However, we show that, once trained, the surrogate model itself can be used to find the unknown building parameters. Since the surrogate model is differentiable, gradient descent can be used to find the building parameters that minimize the error between true and predicted metered energy consumption. Previous surrogate modeling approaches for calibrating BEMs map only the unknown building parameters to the BEM’s output. As a result, they are blind to the effects of other crucial variables like weather and the building’s schedules. On the other hand, our surrogate ANN model accounts for these other predictors of energy consumption. With this advantage, our method was able to outperform a powerful black box optimizer when finding 14 unknown building parameter values in a controlled case study with hourly energy data. In a real metered data case study, our ANN method and the black box optimizer performed similarly on average, but our method had less variance in performance across trials.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2023.113057 5072953:5A7LQJ52 openalex: W4364374537
Keywords: Artificial neural network; Building energy model calibration; Building energy modeling; Emulators; Machine learning; Metamodeling; Surrogate modeling; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:energy model calibration; oa:keyword:surrogate neural network; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10848 Multiobjective Optimization in Evolutionary Algorithms; oa:topic:T11052 Electricity Price and Load Forecasting Methods; openalex:n:1; openalex:yes

School: a second home for the children - Warwocki, Pawel (2023)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10257503 ZenodoArchiveConcept: 10257502 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1037 2129771:NW5NJAGB 5072953:DMUSFIEG
Keywords: _r:AddedByMyEducationEvidence; _z:class:countries; _z:class:themes

3D printed case for pico datalogger (rev1.00) - Haßler, Björn (Open Development & Education, 2023)
original-date: 2023-05-22T21:47:38Z KerkoCite.ItemAlsoKnownAs: 4874017:233BSSUN 5072953:PB4VBPAH
Keywords: _z:class:countries; _z:class:themes

Pico board for data-logging with power-management and micro-sd storage - Bablok, Bernhard; Haßler, Björn (Open Development & Education, 2023)
Pico board for data-logging with power-management and micro-sd storage
original-date: 2023-05-22T21:54:19Z KerkoCite.ItemAlsoKnownAs: 4874017:B3Y6NMI2 5072953:SKBI9Q4Y
Keywords: _z:class:countries; _z:class:themes

Pico Datalogger with Integrated Power-Management - Haßler, Björn; Bablok, Bernhard (Open Development & Education, 2023)
Pico board for data-logging with power-management and micro-sd storage
original-date: 2023-05-22T21:54:19Z KerkoCite.ItemAlsoKnownAs: 4874017:QY8LE6GK 5072953:X4MIRGWZ
Keywords: _z:class:countries; _z:class:themes

Climate change knowledge, attitude and perception of undergraduate students in Ghana - Ofori, Benjamin Y.; Ameade, Evans Paul Kwame; Ohemeng, Fidelia; Musah, Yahaya; Quartey, Jones K.; Owusu, Erasmus H. (PLOS Climate, 2023)
Anthropogenic climate change is a serious global environmental issue that threatens food and water security, energy production, and human health and wellbeing, ultimately jeopardizing the attainment of the UN Sustainable Development Goals (SDGs). A good understanding of climate change is essential for societies to adapt to or mitigate it. Yet, studies reveal that most people have limited knowledge, misconceptions and misunderstanding about climate change. Sub-Saharan Africa is projected to experience disproportionately higher adverse effects of climate change, but there is paucity of information about climate change knowledge in the region. Here, we assessed climate change knowledge, attitude and perception of undergraduate students in Ghana and the influential factors using a cross-sectional study and semi-structured questionnaire. The study population was full-time undergraduate students at the University of Ghana, Legon. The data was analyzed using descriptive statistics, logistic regressions, t-test and One-Way ANOVA. The results revealed that a strong majority of the respondents believe that climate change is real and largely human-induced, and they expressed concern about it. Yet, students lack basic knowledge and had some misconceptions about the causes and consequences of climate change. The overall knowledge score of the students on climate change was average (66.9%), although majority (92%) of the respondents claimed they had adequate (75–85%) knowledge of climate change. Our data also showed that respondents’ level of education, programme of study, ethnicity, religion and mother’s occupation had statistically significant association with their knowledge, perception and attitude on aspects of climate change. Our findings highlight knowledge gaps in climate change among undergraduate students in Ghana, underscoring the need to integrate climate change science into the education curricula at all levels of pre-tertiary schools and university for both the science and non-science programme.
openalex:W4379739985 mag: KerkoCite.ItemAlsoKnownAs: 10.1371/journal.pclm.0000215 5072953:2SJ36FBC
Keywords: C:Ghana; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change knowledge; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; oa:topic:T12503 Social Acceptance of Renewable Energy Innovation; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Optimizing overheating, lighting, and heating energy performances in Canadian school for climate change adaptation: Sensitivity analysis and multi-objective optimization methodology - Baba, Fuad Mutasim; Ge, Hua; Zmeureanu, Radu; Wang, Liangzhu (Building and Environment, 2023)
This paper aims to develop long-term adaptation strategies for the existing Canadian school buildings under extreme current and future climates using a developed methodology based on global and local sensitivity analysis and Multi-Objective Optimization Genetic Algorithm. The calibrated simulation model based on indoor and outdoor measured temperature for a school of interest is used to evaluate the optimization strategies. This paper aims to search for the optimum school building design under three simultaneous conflicting objective functions: (1) the minimization of overheating hours to less than 40 h as required by Building Bulletin BB101 building code by using passive mitigation measures, (2) the minimization of heating energy use to less than 15 kW/m2 according to passive house requirements and thus the reduction of greenhouse gas emissions, and (3) the minimization of artificial lighting energy use to less than the current lighting energy use by maximization of daylighting usage without exceeding acceptable glare index in classrooms. Ten building design variables are selected, which could generate approximately 300,000 solutions. The developed methodology reduced the numbers to 14,400 solutions and found seven Pareto solutions that comply with the three objectives and their constraints. High energy-efficient building envelope, appropriate window-wall ratio and window type, natural ventilation during the day, and night cooling can play a key role in achieving the objectives under current weather conditions. An additional cool roof and external overhang will be needed in the medium-term future climate, and an additional movable screen shading will be needed in the long-term future climate.
openalex: W4366767050
Keywords: _z:class:countries; _z:class:themes; evidence_review_2; oa:keyword:climate change adaptation; oa:sdg:13 Climate action; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:import; openalex:yes

Sensors OpenSCAD: An OpenSCAD library for common environmental sensors - Haßler, Björn (Open Development & Education, 2023)
original-date: 2023-05-29T22:31:22Z KerkoCite.ItemAlsoKnownAs: 4874017:GEW7P34M 5072953:F96VVYDV
Keywords: _z:class:countries; _z:class:themes

Sensor Sripboard (v1) - Haßler, Björn (Open Development & Education, 2023)
original-date: 2023-05-26T21:42:45Z KerkoCite.ItemAlsoKnownAs: 4874017:ZMRE5TTV 5072953:5Y4J246T
Keywords: _z:class:countries; _z:class:themes

A New Correlation for Single-Sided Natural Ventilation Rate Based on Full-Scale Experimental Study in Mogao Grottoes, Dunhuang, China - Zhang, Junjie; Yan, Zengfeng; Zhang, Zhengmo; Bi, Wenbei; Yao, Shanshan (Buildings, 2023)
Although research on the natural ventilation of single-sided buildings is progressing, research on the natural ventilation of the Mogao Grottoes, which have special shapes and structures, is relatively limited. The purpose of this paper is to develop a correlation for calculating the natural ventilation rates of such grottoes. Field experiments were carried out on two typical caves to measure their meteorological parameters and natural ventilation rates to verify the validity of the proposed correlation. The results show that our correlation has good reliability and stability when predicting the natural ventilation rates of the caves. First, the new correlation has a small average deviation of 16.35%. The average deviations in the natural ventilation rates predicted by seven established correlations are as low as 17.85% and as high as 59.39%, revealing a large gap compared with the correlation proposed herein. Second, the maximum deviation in the outputs of the proposed correlation is only 7.70% between each case. Finally, a comparison between the calculated results and the values measured in Cave 328 shows that the correlation is also suitable for large-volume caves. The developed correlation provides theoretical support and a scientific method for preventive protection and a quantitative analysis method for the study of natural ventilation in caves.
Keywords: _z:class:countries

How to build an IoT device with low-power sleep - Haßler, Björn (2023)
ZenodoArchiveID: 7881014 ZenodoArchiveConcept: 7881013 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.0289 2129771:3SCPTDDX 4874017:UW4EFIA6 4874017:XJ6UULLS 5072953:33JW9RSY 5072953:CEW5TSEB 5072953:X2WWYHJB
Keywords: _r:AddedByZotZen; _z:class:countries; _z:class:themes

Continuing Education for Climate Change: A Study of Australian Urban Planners’ Current Practices and Developing Competence - Hurlimann, Anna; Cobbinah, Patrick Brandful; Bush, Judy; Gaisie, Eric (Journal of Planning Education and Research, 2023)
Despite the critical need for urban planners to address climate change, there is a limited understanding of planning professionals’ perceptions of their climate change competency. This paper reports results from a survey of Australian urban planning professionals, identifying their perceived climate change knowledge, skills, competencies, and everyday practice. The urban planning professionals surveyed had high levels of perceived climate change knowledge, but only a small number incorporate climate change impacts into their professional work. They had limited access to information and tools needed for climate change planning in their practice. Areas for further competency development through continuing education are identified.
openalex: W4376118267
Keywords: C:Australia; _z:class:countries; _z:class:themes; oa:keyword:australian urban planners; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10119 Sustainability Transitions and Resilience in Social-Ecological Systems; oa:topic:T12143 Understanding Human Connection to Places; openalex:import; openalex:yes

Continuing Education for Climate Change: A Study of Australian Urban Planners’ Current Practices and Developing Competence - Hurlimann, Anna; Cobbinah, Patrick Brandful; Bush, Judy; Gaisie, Eric (Journal of Planning Education and Research, 2023)
Despite the critical need for urban planners to address climate change, there is a limited understanding of planning professionals’ perceptions of their climate change competency. This paper reports results from a survey of Australian urban planning professionals, identifying their perceived climate change knowledge, skills, competencies, and everyday practice. The urban planning professionals surveyed had high levels of perceived climate change knowledge, but only a small number incorporate climate change impacts into their professional work. They had limited access to information and tools needed for climate change planning in their practice. Areas for further competency development through continuing education are identified.
openalex: W4376118267
Keywords: C:Australia; _z:class:countries; _z:class:themes; oa:keyword:australian urban planners; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10119 Sustainability Transitions and Resilience in Social-Ecological Systems; oa:topic:T12143 Understanding Human Connection to Places; openalex:import; openalex:yes

Dilated causal convolutional neural networks for forecasting zone airflow to estimate short-term energy consumption - Tully, Joseph; Haight, Ryan; Hutchinson, Brian; Huang, Sen; Lee, Joon-Yong; Katipamula, Srinivas (Energy and Buildings, 2023)
This paper investigates the use of dilated causal convolutional neural networks for fine-grained temporal forecasting of building zone states. Specifically, we build and evaluate models using a small set of exogenous features (e.g., external temperature) to autoregressively predict zone airflow setpoints every minute for a 24-h prediction window. We carefully explore the trade-off between generality and specificity in these models, training and evaluating them based on zone, zone type, month, season, and combinations thereof. When evaluated for a commercial office building in Eastern Washington with 16 zones served by variable air volume air handling units, we find that the highest performance comes from a zone-specific, season-agnostic approach; with it, we obtain an R2 of 0.704 (averaged over zones) and an average normalized root mean square error (nRMSE) of 0.111. In contrast, the most general model (trained across all zones and seasons) yields an R2 of only 0.416 and a nRMSE of 0.168, while a baseline zone-specific reduced order model obtains 0.443 R2 and 0.159 nRMSE. We also report on factors affecting airflow forecasting performance, on the ability of models trained on a specific zone to generalize to other zones, and on the capability of those models trained on a specific month to generalize to other months.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2023.112890 5072953:QY4E8D3C openalex: W4321073092
Keywords: Airflow setpoint; C:Mali; Deep learning; Dilated causal convolution; Neural networks; Time series forecasting; Transactive control and coordination; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:causal convolutional neural networks; oa:keyword:forecasting zone airflow; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11052 Electricity Price and Load Forecasting Methods; oa:topic:T12120 Low-Cost Air Quality Monitoring Systems; openalex:n:1; openalex:yes

Planting seeds of change: the Tanzanian students and teachers taking climate action into their own hands - Keevill, Kerensa (Aga Khan Foundation UK, 2023)
KerkoCite.ItemAlsoKnownAs: 2129771:M8HN6LGJ 2129771:M8HN6LGJ 2129771:M8HN6LGJ 2129771:M8HN6LGJ 4874017:3F5P67FP 5072953:8C4ANKFE
Keywords: C:Tanzania; _z:class:countries; _z:class:themes; evidence_review_2

Perception and Knowledge of Algerian Students about Climate Change and Its Putative Relationship with the COVID-19 Pandemic: A Preliminary Cross-Sectional Survey - Lounis, Mohamed; Madani, Azzeddine; Boutebal, Saad Eddine (Climate, 2023)
Background: Climate changes (CC) is one of the most important insidious crises affecting all countries in the world in the 21st century, including Algeria, and it is projected to affect many people in the future. Mitigation of the effects of this phenomenon will certainly involve environmental education, especially among university students. Therefore, evaluating their level of knowledge could help us understand to what extent they are prepared to contribute in the global efforts to fight against this catastrophe. Objective: The current study aims to investigate the perception and knowledge of Algerian students about climate change and its potential relationship with the COVID-19 pandemic. Methods: An online cross-sectional survey was conducted on a sample of 204 Algerian students by adopting snowball sampling during the academic year (2022/2023), with a questionnaire based on Google Forms. Data were analyzed using SPSS software. Results: The results obtained showed that 95.6% of the students asked had heard about this phenomenon and more than 90% perceived that it was really happening. The level of knowledge is significantly associated with age, where students aged between 20 and 30 years old had a lower level of knowledge than those over 30 years old (OR = 0.22, p = 0.027). Furthermore, students of the Humanities have shown the lowest level of knowledge compared to those of other domains. Regarding their attitude, only 31.8% of the asked students declared that they changed their attitude positively during the COVID-19 pandemic. The change in attitude and concern is statistically associated neither with the level of knowledge and perception nor COVID-19 affection, psychological impact, and uptake of the COVID-19 vaccine. Conclusion: The study concluded that there was a high level of awareness and a medium level of knowledge about CC among Algerian university students. However, most of them were either very worried or a little worried about this phenomenon. It was also suggested that the average level of knowledge about cause and effect and pandemic resistance could be attributed to the scientific study path of students from the study sample. The results of this study could be used as a baseline for future research into CC knowledge and perception in Algeria.
openalex:W4366598792 mag: KerkoCite.ItemAlsoKnownAs: 10.3390/cli11040090 5072953:XEJ6NSFN
Keywords: C:Algeria; _z:class:countries; _z:class:themes; oa:keyword:algerian students; oa:keyword:climate change; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11244 Impact of Climate Change on Human Health; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Knowledge, perception, and practices regarding climate change among students of Al-Azhar University for Girls in Cairo, Egypt - Elsharkawy, Safaa Abdelfattah; Elsheikh, Asmaa Abdelghany; Refaat, Laila Abdel Raheem (Journal of Public Health, 2023)
Abstract Aim To assess knowledge, perception, and practices regarding climate change (CC) among university students and to investigate the relationships between knowledge levels and reported practices in response to CC. Subject and methods A cross-sectional study was conducted among 768 undergraduate students from the practical and theoretical faculties of Al-Azhar University for Girls in Cairo. Results Most (82.6%) students had heard the term CC and believed it affected their communities. Approximately 57.8% of the students possessed good knowledge about the causes and impacts of CC. The utilization of renewable energy sources, reduction of industrial pollution, and proper waste disposal were mentioned by over 90% of the students as measures to cope with CC. The most popular practices among participants were using energy-efficient lightbulbs (89.2%), short distance walking rather than riding (65.4%), and using public transportation rather than private cars (65%). There were significant positive relationships between the students’ knowledge and practice of environmentally friendly actions. In addition, participants’ residence, faculty, and information sources were significantly related to their knowledge. Conclusions Most of the university students were aware of CC and strongly agreed with the general mitigation measures, but they had insufficient knowledge and inadequate practices. CC education focusing on its causes and explaining its relationship with daily activities is highly recommended for youth so that they can adopt climate-friendly practices.
openalex:W4365150252 mag: KerkoCite.ItemAlsoKnownAs: 10.1007/s10389-023-01901-9 5072953:VVMCV7C4
Keywords: C:Egypt; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; oa:topic:T12503 Social Acceptance of Renewable Energy Innovation; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

DARE: Distill and Reinforce Ensemble Neural Networks for Climate-Domain Processing - Xiang, Kun; Fujii, Akihiro (Entropy, 2023)
Natural-language processing is well positioned to help stakeholders study the dynamics of ambiguous Climate Change-related (CC) information. Recently, deep neural networks have achieved good results on a variety of NLP tasks depending on high-quality training data and complex and exquisite frameworks. This raises two dilemmas: (1) the networks are highly reliant on powerful hardware devices and processing is time-consuming, which is not only inconducive to execution on edge devices but also leads to resource consumption. (2) Obtaining large-scale effective annotated data is difficult and laborious, especially when it comes to a special domain such as CC. In this paper, we propose a CC-domain-adapted BERT distillation and reinforcement ensemble (DARE) model for tackling the problems above. Specifically, we propose a novel data-augmentation strategy which is a Generator-Reinforced Selector collaboration network for countering the dilemma of CC-related data scarcity. Extensive experimental results demonstrate that our proposed method outperforms baselines with a maximum of 26.83% on SoTA and 50.65× inference time speed-up. Furthermore, as a remedy for the lack of CC-related analysis in the NLP community, we also provide some interpretable conclusions for this global concern.
openalex: W4365146569
Keywords: _z:class:countries; openalex:citedBy; openalex:import; selected_for:effects of climate ch...on learning...LMICs 2024; tagged

The effect of classroom environment on literacy development - Rance, Gary; Dowell, Richard C.; Tomlin, Dani (npj Science of Learning, 2023)
The physical characteristics of a child’s learning environment can affect health, wellbeing and educational progress. Here we investigate the effect of classroom setting on academic progress in 7–10-year-old students comparing reading development in “open-plan” (multiple class groups located within one physical space) and “enclosed-plan” (one class group per space) environments. All learning conditions (class group, teaching personnel, etc.) were held constant throughout, while physical environment was alternated term-by-term using a portable, sound-treated dividing wall. One hundred and ninety-six students underwent academic, cognitive and auditory assessment at baseline and 146 of these were available for repeat assessment at the completion of 3 school terms, allowing within-child changes across an academic year to be calculated. Reading fluency development (change in words read-per-minute) was greater for the enclosed-classroom phases (P < 0.001; 95%CI 3.7, 10.0) and the children who showed the greatest condition difference (i.e. slower rate of development in the open-plan) were those with the worst speech perception in noise and/or poorest attention skills. These findings highlight the important role classroom setting plays in the academic development of young students.
KerkoCite.ItemAlsoKnownAs: 10.1038/s41539-023-00157-y 2129771:VSJF6CNU 4874017:K96RFSZZ
Keywords: Education; Human behaviour; evidence_review

Digital twin with Machine learning for predictive monitoring of CO2 equivalent from existing buildings - Arsiwala, Arva; Elghaish, Faris; Zoher, Mohammed (Energy and Buildings, 2023)
The revolution of the industry 4.0 presents a new era of digital transformation for the construction industry, advancing towards the concept of digital twins, while on the other hand it faces the global challenge of reducing carbon emissions from operational assets. The current research gap in the application of digital twins for achieving net zero were reviewed in this study, highlighting its potentials for enhancement in the built environment, and emphasizing the need for demonstration of a use-case analysis for its adoption by the industry. This research presents a digital twin solution to automate the monitoring and controlling of equivalent carbon dioxide (eCO2) emissions from existing assets through the integration of IoT, BIM, and artificial intelligence across a comprehensive solution, further validating its workability through a real-life use case analysis. The study revealed the significance of BIM and IoT, as essential components of a digital twin to visualise critical spatial information for enhanced facility management specifically for monitoring of indoor air quality of spaces, while also coalescing an AI-supported system to predict carbon emissions from the collected data through integration of machine learning features across the digital twin. The output of the entire solution is displayed as an interactive dashboard for observing trends and patterns, enabling stakeholders to implement effective data-driven retrofitting strategies. This research is a fundamental initiation for implementing digital twins to monitor emissions from existing assets, a step towards achieving the net zero targets.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2023.112851 5072953:6WX2IENS openalex: W4319967909
Keywords: Artificial Intelligence (AI); BIM; Big Data (BD); Carbon emission; Digital Twin; Internet of things (IoT); Net zero; Sustainability; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:co2; oa:sdg:9 Industry; innovation and infrastructure; oa:topic:T10763 Industry 4.0 and Digital Transformation in Manufacturing; oa:topic:T11006 Building Information Modeling in Construction Industry; oa:topic:T11211 3D Geospatial Modelling Techniques; openalex:n:1; openalex:yes

Children's exposure to indoor and outdoor black carbon and particulate matter air pollution at school in Rwanda, Central-East Africa - Kalisa, Egide; Kuuire, Vincent; Adams, Matthew (Environmental Advances, 2023)
Schoolchildren are a high-risk population, and their exposure to air pollution at school has been documented in high-income countries. As a result, school siting policies to protect children from air pollution have been established in those countries. Such policies are, however, non-existent in Africa where the air pollution problem is growing and gravely under-studied due to the lack of funding to install reliable ground-level monitoring networks and lack of air quality standards. The present study, the first of its kind to be conducted in Africa, measured Black Carbon (BC) and its related sources: fossil fuels (BCff) and biomass burning (BCbb). BC and fine particles (PM2.5) were measured simultaneously indoors and outdoors at schools over a 12-month period in Rwanda. The annual concentrations of BC in classrooms (8.15 µg/m3) and outdoor schoolyards (9.22 µg/m3) were higher than simultaneous concentrations recorded at Kigali urban background site (7.78 μg m3). The annual mean PM2.5 concentrations in classrooms and outdoor school were more than eight times higher than the World Health Organization's safe limits. The results demonstrated a more than two-fold increase in the concentrations of BCff during drop-off hours compared to off-peak hours, indicating the dominant contribution of vehicles queuing on the school premises. However, higher indoor than outdoor BC levels were recorded in some instances, 2 hours after an outdoor peak during drop-off times. The exposure peaks inside the classrooms were more pronounced for BC than PM2.5.The highest reduction of 24% and 19% were observed for BCff during weekends and school holidays in classrooms compared to regular days. No reduction was observed for BCbb concentrations. This study shows that BC and PM2.5 levels are considerably higher in schoolyards, and that further investigation of air pollution exposure at schools is warranted in Africa to promote improved drop-off/pick-up behaviors at and around school environments.
KerkoCite.ItemAlsoKnownAs: 2129771:6KYKJ43E 2129771:6KYKJ43E 2129771:6KYKJ43E 2129771:6KYKJ43E 10.1016/j.envadv.2022.100334 4874017:NF94Y9M4 5072953:HUMVFJAG openalex: W4313530581
Keywords: Africa; C:Rwanda; Drop-off and pick up times; Indoor and outdoor air pollution; School air pollution; _z:class:countries; _z:class:themes; evidence_review_2; oa:keyword:particulate matter air pollution; oa:topic:T10190 Health Effects of Air Pollution; oa:topic:T11336 Indoor Air Pollution in Developing Countries; oa:topic:T12120 Low-Cost Air Quality Monitoring Systems; openalex:n:1; openalex:yes

Topic modelling the mobility response to heat and drought - Zander, Kerstin K.; Baggen, Hunter S.; Garnett, Stephen T. (Climatic Change, 2023)
Abstract We conducted a systematic literature review of peer-reviewed full text articles on the nexus between human mobility and drought or heat published between 2001 and 2021, inclusive. We identified 387 relevant articles, all of which were analysed descriptively using a dictionary-based approach and by using an unsupervised machine learning–based Latent Dirichlet Allocation (LDA) model. Most articles were in response to droughts (71%), but heat and extreme temperature became more prominent after 2015. The drought-related literature focuses geographically on African and Southern Asian countries, while heat-related research has mainly been conducted in developed countries (mostly in the USA and Australia). For both hazards, European countries are under-represented. The LDA model identified 46 topics which were clustered into five major themes. One cluster (14% of all articles) included literature on heat-related mobility, mostly data-driven models, including amenity migration. The other four clusters included literature on drought, primarily on farming societies and the agricultural sector with three of those clusters making up 63% of all articles, with the common overarching focus on climate migration and food security. One of the four drought clusters focused on social dysfunction in relation to droughts. A sentiment analysis showed articles focusing on voluntary mobility as part of adaptation to drought and heat were more positive than articles focusing on migration triggered by droughts and heat. Based on the topics and the article characterisation, we identified various research gaps, including migration in relation to urban droughts, heat in farming societies and in urban societies of developing countries, planned retreat from hot to cooler places, and the inability or barriers to doing so. More research is also needed to understand the compound effect of drought and heat, and the social and psychological processes that lead to a mobility decision.
openalex: W4362608060
Keywords: _z:class:countries; openalex:citedBy; openalex:import; selected_for:effects of climate ch...on learning...LMICs 2024; tagged

International Society of Physical Medicine and Rehabilitation position statement on climate change and disability - Alexander, Marcalee; Gosney, Jim; O’Connell, Colleen; Khan, Fary; Laíns, Jorge (Journal of the International Society of Physical and Rehabilitation Medicine, 2023)
Climate change is the greatest public health threat of the 21st century. Moreover, people with the lived experience of disabilities, a population physiatrists commonly treat, are among the most vulnerable to acute disasters such as floods and wildfires and excessive heat. In this position statement, we recommend actions that physiatrists and rehabilitation professionals should take at micro, meso, and macro levels to assist in mitigation and adaptation to the effects of climate change on the world.
openalex: W4361836005
Keywords: _z:class:countries; openalex:import; openalex:yes

How Teacher’s Climate Change Belief Influences Classroom Management Practices for Students’ Climate Change Awareness In Nigerian Schools - Igu, Ntasiobi C. N.; Anochiwa, Roseline; Ogba, Francisca; Nwinyinya, Emeka; Eze, Beatrice A; Ogar, Joseph; Obih, Solomon; Ugbogu, Chikwendu (Polish Journal of Environmental Studies, 2023)
openalex:W4361298819 KerkoCite.ItemAlsoKnownAs: 10.15244/pjoes/159429 5072953:INHAMZNK
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change awareness; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

A systematic review of ambient heat and sleep in a warming climate - Chevance, Guillaume; Minor, Kelton; Vielma, Constanza; Campi, Emmanuel; O’Callaghan-Gordo, Cristina; Basagaña, Xavier; Ballester, Joan; Bernard, Paquito (medRxiv (Cold Spring Harbor Laboratory), 2023)
Abstract Background Earlier reviews documented the effects of a broad range of climate change outcomes on sleep but have not yet evaluated the effect of ambient temperature. This systematic review aims to identify and summarize the literature on ambient temperature and sleep outcomes in a warming world. Methods For this systematic review, we searched online databases (PubMed, Scopus, JSTOR, GreenFILE, GeoRef and PsycARTICLES) together with relevant journals for studies published before February 2023. We included articles reporting associations between objective indicators of ambient temperature and valid sleep outcomes measured in real-life environments. We included studies conducted among adults, adolescents, and children. A narrative synthesis of the literature was then performed. Findings The present systematic review shows that higher outdoor or indoor ambient temperatures, expressed either as daily mean or night-time temperature, are negatively associated with sleep quality and quantity worldwide. The negative effect of higher ambient temperatures on sleep is stronger in the warmest months of the year, among vulnerable populations and in the warmest areas of the world. This result appears consistent across several sleep indicators and measures. Interpretation Although this work identified several methodological limitations of the extant literature, a strong body of evidence from both this systematic review and previous experimental studies converge on the negative impact of elevated temperatures on sleep quality and quantity. In absence of solid evidence on fast adaptation to the effects of heat on sleep, rising temperatures induced by climate change pose a planetary threat to human sleep and therefore human health, performance and wellbeing.
openalex: W4361213721
Keywords: _z:class:countries; evidence_review; openalex:citedBy; openalex:import; selected_for:effects of climate ch...on learning...LMICs 2024; tagged

(Adapting to the) Impacts of climate (change): Temperature, Light, Sound, Air - Haßler, Björn (OpenDevEd, 2023)
ZenodoArchiveID: 7823061 ZenodoArchiveConcept: 7823060 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.0287 2129771:CQKQ898B 4874017:XNCB6KR8 5072953:IDMZ2T5A 5072953:WN2QRCCG
Keywords: _r:AddedByZotZen; _z:class:countries; _z:class:themes; ⚠️ Invalid DOI

Comparative Analysis of Comfort Temperature of School Children and Their Teachers - Munonye, Charles; Ngobili, Michael; Umeora, Chukwunonso; Oluchi, Ifebi; Maduka, Nkechi; Onwuzuligbo, Chijioke (Research & Development, 2023)
Thermal comfort in learning environments influences the student’s focus and learning productivity. This study aims to evaluate and compare the adaptive thermal comfort of schoolchildren and their teachers in naturally ventilated primary schools in some selected cities in Imo State Nigeria. To achieve these objectives, the study analyzed the data collected from 330 pupils and 44 teachers in six surveyed classrooms in two types of classroom buildings. The recorded data in the surveyed classrooms consisted of four environmental factors and two personal factors. At the same time, the subjects filled out the questionnaires asking them about thermal sensation and thermal preferences against the classrooms’ thermal requirements. The results of the measurements showed that the indoor mean air temperature, relative humidity, and air velocity were 29.1°C, 71.2%, and 0.19m/s, respectively. The mean thermal sensation votes of the children were +0.16 while that of their teachers was +0.58. The preferred temperatures were 27.4°C and 29.4°C for the schoolchildren and the teachers, respectively. Furthermore, the comfort range of the students was between 25.8°C - 31.6°C, and that of the teachers was between 28.0°C - 29.9°C. Based on the results of this study conducted in primary school buildings located in warm and humid climates, the thermal comfort perception of children and adults differ. This information will serve as a guide to professionals in the built environment, especially architects when designing primary school buildings in the warm and humid climates.
openalex: W4380897799 KerkoCite.ItemAlsoKnownAs: 2129771:J9TERRN6 2129771:J9TERRN6 10.11648/j.rd.20230401.15 5072953:FP8NL8Q5 5072953:ZFR6WRQW
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; evidence_review_2; oa:keyword:comfort temperature; oa:sdg:13 Climate action; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; openalex:n:1; openalex:yes

Visual Comfort and Discomfort in public boarding secondary Schools in Nairobi City County, Kenya - Magero, Cynthia Vugudza; Nyamari, Jackim; Mutisya, Redempta (East African Journal of Health and Science, 2023)
Indoor light quality is the intensity and amount of illumination of interior spaces. Technological developments have led to the utilisation of artificial natural light. Illumination is crucial in the visibility of tasks. Quality of light can influence the visual comfort and ocular health of the students. Although Kenya lacks lighting standards for schools, ISO and CIE provide international guidelines on optimal illumination for various facilities. This study was conducted on public boarding secondary schools in Nairobi City County to assess the visual comfort or discomfort of students in classrooms. The study utilised a cross-sectional descriptive study design. Four hundred twenty-three students were randomly sampled from 8 schools. Illumination levels were measured in 38 classrooms using a calibrated Benetech GM1010 light metre and compared to levels recommended by ISO and CIE. A self-administered semi-structured questionnaire was used to collect data on students’ visual comfort or discomfort. Data was analysed using SPSS version 23. Descriptive data were analysed using frequencies, while inferential data were analysed using chi-square. The study established that 15% of the respondents experience visual comfort during the day, 13.5% at night, and 12.7% both day and night. Fourteen classrooms achieved the recommended illumination level at 7:30, 20 at 13:00 hours, and 10 at 18:00 hours. Recorded levels ranged from 56.71 lux to 1289.93 lux. The study found a statistically significant association between visual comfort and factors such as existing eye problems, presence of blinds or curtains, number of windows, presence of whiteboards, classroom orientation and student sitting positions. The study recommends that public secondary schools need to ensure quality indoor illumination in their facilities to enhance the visual comfort of students in learning facilities.
Number: 1 KerkoCite.ItemAlsoKnownAs: 2129771:TE2WX7X5 2129771:TE2WX7X5 2129771:TE2WX7X5 2129771:TE2WX7X5 10.37284/eajhs.6.1.1123 4874017:9V2UUXLE 5072953:K8N7Z4IX openalex: W4323569394
Keywords: C:Kenya; Environmental Factors; Indoor Illumination; Indoor Lighting in Schools; Visual Comfort; _z:class:countries; _z:class:themes; evidence_review_2; oa:keyword:public boarding secondary schools; oa:sdg:11 Sustainable cities and communities; oa:topic:T11963 Impact of Nighttime Light Data on Various Fields; oa:topic:T12950 Learning Environments in Education; openalex:n:1; openalex:yes

Considerations for relational research methods for use in Indigenous contexts: implications for sustainable development - Mbah, Marcellus F.; Bailey, Megan; Shingruf, Ayesha (International Journal of Social Research Methodology, 2023)
KerkoCite.ItemAlsoKnownAs: 10.1080/13645579.2023.2185345 5072953:A9C83KA6 openalex: W4323314977
Keywords: _z:class:countries; _z:class:themes; oa:keyword:indigenous contexts; oa:keyword:relational research methods; oa:topic:T10348 Indigenous Health Disparities and Decolonization; oa:topic:T11944 Participatory Visual Research Methods in Social Science; oa:topic:T12196 Empowerment and Collaboration in Community Health; openalex:n:1; openalex:yes

Considerations for relational research methods for use in Indigenous contexts: implications for sustainable development - Mbah, Marcellus F.; Bailey, Megan; Shingruf, Ayesha (International Journal of Social Research Methodology, 2023)
KerkoCite.ItemAlsoKnownAs: 10.1080/13645579.2023.2185345 5072953:A9C83KA6 openalex: W4323314977
Keywords: _z:class:countries; _z:class:themes; oa:keyword:indigenous contexts; oa:keyword:relational research methods; oa:topic:T10348 Indigenous Health Disparities and Decolonization; oa:topic:T11944 Participatory Visual Research Methods in Social Science; oa:topic:T12196 Empowerment and Collaboration in Community Health; openalex:n:1; openalex:yes

Assessment of Climate Change Awareness among Secondary School Teachers in Ebonyi State, Nigeria (Journal of Education and Practice, 2023)
Climate change is an area that is currently in dire need of a wide range of publicity especially among teachers in secondary schools. This is because teachers’ awareness of Climate Change may result to multiplier effects where families and communities benefit when students share what they have learned especially in relation to causes, adaptation and mitigation. The study was therefore carried out to assess the extent of climate change awareness among secondary school teachers in Ebonyi State. The researcher employed survey design for the stud. Three research questions and three null hypotheses guided the study. A 24 item self made questionnaire titled ““Climate Change Awareness Questionnaire” (CCAQ) were administered to a sample of 300 teachers from eight secondary schools from communities with visible impacts of climate change in Ebonyi State. The researcher employed purposive and random sampling methods in drawing the sample. Mean ( ) score was used to answer the research questions while t-test of difference between two means of independent samples was used to analyze the hypotheses. The findings revealed that the extent of awareness on the causes, impacts and adaptation/mitigation strategies of climate change among the secondary school teachers in Ebonyi State is very little. Based on the findings, the researcher recommended mainstreaming climate change throughout secondary education system in Ebonyi State among others. Keywords: Climate change, awareness, teachers, students, Ebonyi State, School Administration DOI: 10.7176/JEP/14-8-01 Publication date: March 31 st 2023
openalex:W4362512459 KerkoCite.ItemAlsoKnownAs: 10.7176/jep/14-8-01 5072953:HR54FHIG
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change awareness; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; openalex:import; openalex:n:1; openalex:yes

Climate change and disability: a physical medicine and rehabilitation (PM&R) perspective - Amatya, Bhasker; Khan, Fary (Journal of the International Society of Physical and Rehabilitation Medicine, 2023)
Climate change phenomena, such as droughts, floods, heat waves, hurricanes, and wildfires, have a deleterious effect on nature and the health of the people, especially on vulnerable population cohorts, such as persons with disabilities (PwD). PwD are disproportionately affected by the health effects of climate change and experience a greater burden due to various physiological, socio-economic and health-related factors. Rehabilitation professionals as trusted care providers/educators have an integral role in global efforts to educate, advocate and protect vulnerable people from the adverse impact of climate change. They are in a distinctive position as they are experts in understanding the complex medical, physiological and psychosocial needs of PwD. Although the impact of climate change on health is widely documented, the literature on the effect of climatic factors on PwD is sparse. Further, specific rehabilitation and disability-inclusive climate action plans are yet to be developed and/or implemented globally. As the climate-change-related health burdens continue to grow the critical importance of rehabilitation services is apparent. The challenge ahead is to build a structured people-centered approach to building rehabilitation-inclusive climate-resilient health systems to improve the adaptive capacity and resilience of the most susceptible people with distinct healthcare needs.
openalex: W4361836010
Keywords: _z:class:countries; openalex:import; openalex:yes

Evaluation of projected soil organic carbon stocks under future climate and land cover changes in South Africa using a deep learning approach - Odebiri, Omosalewa; Mutanga, Onisimo; Odindi, John; Naicker, Rowan; Slotow, Rob; Mngadi, Mthembeni (Journal of Environmental Management, 2023)
Environmental degradation and carbon emissions have become a major global concern. This has forced policymakers to consider strategic and long-term contingencies to increase carbon sequestration capacity and mitigate the effects of climate change. Soil organic carbon (SOC) provides a reliable long-lasting mechanism to ameliorate climate change and regulate carbon fluxes. However, unanticipated rates of climate change coupled with the dynamic nature of land-use transformation threatens current mitigation approaches and can jeopardise carbon stock assimilation. To effectively manage and protect SOC stocks, large-scale projections that accurately model both current and future SOC pools are necessary. Hence, this study modelled the effects of simulated climate and land-cover change on SOC inventories across South Africa up to the year 2050. A digital soil mapping strategy in concert with a deep neural network (DNN) was used to model current SOC stocks distribution. Subsequently, WorldClim general circulation models and a space-for-time substitution (SFTS) method were used to derive future SOC stocks under four shared socio-economic emission pathways. Results show a relatively high accuracy with RMSE of 7.44 t/h for current stocks, while future stocks ranged from 11.37 to 13.56 t/h. Depending on emission rates, results showed a reduction in SOC inventories, with overall SOC stocks declining from 5.64 Pg to between 4.97 and 5.38 Pg by 2050. Meanwhile, forests, which account for approximately 1.2 Pg of total SOC in South Africa, were found to have lost more than 1% of their total coverage by 2050. These findings provide a glimpse into the state of South Africa's current and future SOC stock inventories and the influence of climate and land-use change. These findings are valuable to among others policymakers, land use managers and climate change experts in assessing the long-term feasibility of South Africa's existing SOC management protocols and land-use planning agenda. However, to adequately protect future SOC stocks, current land-use planning frameworks need to be re-adjusted to prioritize pressing environmental concerns.
openalex:W4313731734 mag: KerkoCite.ItemAlsoKnownAs: 10.1016/j.jenvman.2022.117127 5072953:H4V9M8QQ
Keywords: C:South Africa; _z:class:countries; _z:class:themes; _z:no_pdf; oa:sdg:13 Climate action; oa:topic:T10004 Soil Carbon Dynamics and Nutrient Cycling in Ecosystems; oa:topic:T10770 Digital Soil Mapping Techniques; oa:topic:T12467 Rangeland Degradation and Pastoral Livelihoods; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Evaluation of projected soil organic carbon stocks under future climate and land cover changes in South Africa using a deep learning approach - Odebiri, Omosalewa; Mutanga, Onisimo; Odindi, John; Naicker, Rowan; Slotow, Rob; Mngadi, Mthembeni (Journal of Environmental Management, 2023)
Environmental degradation and carbon emissions have become a major global concern. This has forced policymakers to consider strategic and long-term contingencies to increase carbon sequestration capacity and mitigate the effects of climate change. Soil organic carbon (SOC) provides a reliable long-lasting mechanism to ameliorate climate change and regulate carbon fluxes. However, unanticipated rates of climate change coupled with the dynamic nature of land-use transformation threatens current mitigation approaches and can jeopardise carbon stock assimilation. To effectively manage and protect SOC stocks, large-scale projections that accurately model both current and future SOC pools are necessary. Hence, this study modelled the effects of simulated climate and land-cover change on SOC inventories across South Africa up to the year 2050. A digital soil mapping strategy in concert with a deep neural network (DNN) was used to model current SOC stocks distribution. Subsequently, WorldClim general circulation models and a space-for-time substitution (SFTS) method were used to derive future SOC stocks under four shared socio-economic emission pathways. Results show a relatively high accuracy with RMSE of 7.44 t/h for current stocks, while future stocks ranged from 11.37 to 13.56 t/h. Depending on emission rates, results showed a reduction in SOC inventories, with overall SOC stocks declining from 5.64 Pg to between 4.97 and 5.38 Pg by 2050. Meanwhile, forests, which account for approximately 1.2 Pg of total SOC in South Africa, were found to have lost more than 1% of their total coverage by 2050. These findings provide a glimpse into the state of South Africa's current and future SOC stock inventories and the influence of climate and land-use change. These findings are valuable to among others policymakers, land use managers and climate change experts in assessing the long-term feasibility of South Africa's existing SOC management protocols and land-use planning agenda. However, to adequately protect future SOC stocks, current land-use planning frameworks need to be re-adjusted to prioritize pressing environmental concerns.
openalex:W4313731734 mag: KerkoCite.ItemAlsoKnownAs: 10.1016/j.jenvman.2022.117127 5072953:H4V9M8QQ
Keywords: C:South Africa; _z:class:countries; _z:class:themes; _z:no_pdf; oa:sdg:13 Climate action; oa:topic:T10004 Soil Carbon Dynamics and Nutrient Cycling in Ecosystems; oa:topic:T10770 Digital Soil Mapping Techniques; oa:topic:T12467 Rangeland Degradation and Pastoral Livelihoods; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Design and Experiments of a Naturally-Ventilated Radiation Shield for Ground Temperature Measurement - Liu, Qingquan; Jin, Wei; Yang, Jie; Zhu, Huanan; Dai, Wei (Atmosphere, 2023)
Temperature sensors may produce a measurement error of up to 1 °C because of the influence of solar radiation. In order to obtain a relatively minimal temperature error, a new temperature observation system was proposed in this paper for measuring surface air temperatures. Firstly, a radiation shield was designed with two aluminum plates, eight vents, and a multi-layer structure which is able to resist direct solar radiation, reflected radiation, and upwelling long-ware radiation, as well as ensuring the temperature sensor probe could work effectively. Then, the effect of different solar radiation intensities, wind speeds, scattered radiation intensities, long-wave radiation intensities, and underlying surface reflectivity levels on radiation error was calculated through a computational fluid dynamics (CFD) method. The mapping relationship was established between the various influencing factors and the solar radiation error. A back-propagation (BP) network algorithm was used to fit the discrete data obtained from the simulation to obtain the solar radiation error correction equation. Finally, the solar radiation error correction equation was verified. Outdoor experiments were conducted to confirm this system’s measurement accuracy. According to the experimental findings, the root-mean-square error was only 0.095 °C, which is a relatively high degree by which to reduce the temperature error. In addition, the average difference between the corrected value of the temperature observation system and the reference value was barely 0.084 °C.
Number: 3 openalex: W4323663661
Keywords: _z:class:countries; computational fluid dynamics; naturally-ventilated radiation shield; neural network; oa:keyword:ground temperature measurement; oa:keyword:radiation shield; oa:sdg:7 Affordable and clean energy; oa:topic:T10466 Numerical Weather Prediction Models; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T12019 Radiometric Calibration and Performance Monitoring; openalex:n:1; openalex:yes; radiation error; temperature sensor

Comparative Analysis of Comfort Temperature of School Children and Their Teachers - Munonye, Charles; Ngobili, Michael; Umeora, Chukwunonso; Oluchi, Ifebi; Maduka, Nkechi; Onwuzuligbo, Chijioke (Research & Development, 2023)
Thermal comfort in learning environments influences the student’s focus and learning productivity. This study aims to evaluate and compare the adaptive thermal comfort of schoolchildren and their teachers in naturally ventilated primary schools in some selected cities in Imo State Nigeria. To achieve these objectives, the study analyzed the data collected from 330 pupils and 44 teachers in six surveyed classrooms in two types of classroom buildings. The recorded data in the surveyed classrooms consisted of four environmental factors and two personal factors. At the same time, the subjects filled out the questionnaires asking them about thermal sensation and thermal preferences against the classrooms’ thermal requirements. The results of the measurements showed that the indoor mean air temperature, relative humidity, and air velocity were 29.1°C, 71.2%, and 0.19m/s, respectively. The mean thermal sensation votes of the children were +0.16 while that of their teachers was +0.58. The preferred temperatures were 27.4°C and 29.4°C for the schoolchildren and the teachers, respectively. Furthermore, the comfort range of the students was between 25.8°C - 31.6°C, and that of the teachers was between 28.0°C - 29.9°C. Based on the results of this study conducted in primary school buildings located in warm and humid climates, the thermal comfort perception of children and adults differ. This information will serve as a guide to professionals in the built environment, especially architects when designing primary school buildings in the warm and humid climates.
Number: 1 KerkoCite.ItemAlsoKnownAs: 10.11648/j.rd.20230401.15 2129771:8S89IW2F 4874017:RQ3YAIN6
Keywords: evidence_review

Understanding the complex dynamics of climate change in south-west Australia using Machine Learning - Yadav, Alka; Das, Sourish; Bakar, K Shuvo; Chakraborti, Anirban (2023)
The Standardized Precipitation Index (SPI) is used to indicate the meteorological drought situation - a negative (or positive) value of SPI would imply a dry (or wet) condition in a region over a period. The climate system is an excellent example of a complex system since there is an interplay and inter-relation of several climate variables. It is not always easy to identify the factors that may influence the SPI, or their inter-relations (including feedback loops). Here, we aim to study the complex dynamics that SPI has with the SST, NINO 3.4 and Indian Ocean Dipole (IOD), using a machine learning approach. Our findings are: (i) IOD was negatively correlated to SPI till 2008; (ii) until 2004, SST was negatively correlated with SPI; (iii) from 2005 to 2014, the SST had swung between negative and positive correlations; (iv) since 2014, we observed that the regression coefficient ($\delta$) corresponding to SST has always been positive; (v) the SST has an upward trend, and the positive upward trend of $\delta$ implied that SPI has been positively correlated with SST in recent years; and finally, (vi) the current value of SPI has a significant positive correlation with a past SPI value with a periodicity of about 7.5 years. Examining the complex dynamics, we used a statistical machine learning approach to construct an inferential network of these climate variables, which revealed that SST and NINO 3.4 directly couples with SPI, whereas IOD indirectly couples with SPI through SST and NINO 3.4. The system also indicated that Nino 3.4 has a significant negative effect on SPI. Interestingly, there seems to be a structural change in the complex dynamics of the four climate variables, some time in 2008. Though a simple 12-month moving average of SPI has a negative trend towards drought, the complex dynamics of SPI with other climate variables indicate a wet season for western Australia.
openalex: W4321650125
Keywords: C:Australia; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10029 Climate Change and Variability Research; oa:topic:T13650 Scientific Computing and Data Analysis with Python; oa:topic:T14329 Climate Change and Environmental Science; openalex:import; openalex:yes

Understanding the complex dynamics of climate change in south-west Australia using Machine Learning - Yadav, Alka; Das, Sourish; Bakar, K Shuvo; Chakraborti, Anirban (2023)
The Standardized Precipitation Index (SPI) is used to indicate the meteorological drought situation - a negative (or positive) value of SPI would imply a dry (or wet) condition in a region over a period. The climate system is an excellent example of a complex system since there is an interplay and inter-relation of several climate variables. It is not always easy to identify the factors that may influence the SPI, or their inter-relations (including feedback loops). Here, we aim to study the complex dynamics that SPI has with the SST, NINO 3.4 and Indian Ocean Dipole (IOD), using a machine learning approach. Our findings are: (i) IOD was negatively correlated to SPI till 2008; (ii) until 2004, SST was negatively correlated with SPI; (iii) from 2005 to 2014, the SST had swung between negative and positive correlations; (iv) since 2014, we observed that the regression coefficient ($\delta$) corresponding to SST has always been positive; (v) the SST has an upward trend, and the positive upward trend of $\delta$ implied that SPI has been positively correlated with SST in recent years; and finally, (vi) the current value of SPI has a significant positive correlation with a past SPI value with a periodicity of about 7.5 years. Examining the complex dynamics, we used a statistical machine learning approach to construct an inferential network of these climate variables, which revealed that SST and NINO 3.4 directly couples with SPI, whereas IOD indirectly couples with SPI through SST and NINO 3.4. The system also indicated that Nino 3.4 has a significant negative effect on SPI. Interestingly, there seems to be a structural change in the complex dynamics of the four climate variables, some time in 2008. Though a simple 12-month moving average of SPI has a negative trend towards drought, the complex dynamics of SPI with other climate variables indicate a wet season for western Australia.
openalex: W4321650125
Keywords: C:Australia; C:India; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10029 Climate Change and Variability Research; oa:topic:T13650 Scientific Computing and Data Analysis with Python; oa:topic:T14329 Climate Change and Environmental Science; openalex:import; openalex:yes

How Endogenous Cultural Institutions May (Not) Shape Farmers’ Climate Adaptation Practices: Learning from Rural Cameroon - Kimengsi, Jude Ndzifon; Silberberger, Magdalene (Society & Natural Resources, 2023)
Climate change is high on the science and policy agenda of sub-Saharan Africa (SSA), requiring context-specific adaptation. Studies on endogenous cultural institutions (ECIs) in climate adaptation are fragmented, impeding policy orientation. This suggests the need for complementary evidence on ECIs to inform adaptation practice. Through a sample of 158 households in rural Cameroon, we contribute to bridge this gap, by: (1) exploring socio-political factors shaping peasant farmers’ compliance with agro-based ECIs, and (2) estimating the effect of ECI compliance on farmers’ adaptation practices. Our estimation revealed the following: While political factors do not sufficiently explain compliance, state influence, mirrored through the application of formal rules negatively affects ECI compliance. Traditional rain forecast significantly explains climate adaptation; however, the pouring of libation does not. The age of peasant farmers also positively affects compliance with ECIs. We conclude that compliance with ECIs manifest in climate adaptation in varying proportions.
openalex:W4319310740 mag: KerkoCite.ItemAlsoKnownAs: 10.1080/08941920.2023.2175283 5072953:CZ47Q3DV
Keywords: C:Cameroon; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:climate adaptation practices; oa:sdg:13 Climate action; oa:topic:T10367 Agricultural Innovation and Livelihood Diversification; oa:topic:T10439 Adaptation to Climate Change in Agriculture; oa:topic:T12656 Impact of Climate Change on Human Migration; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

‘As a farmer you've just got to learn to cope’: Understanding dairy farmers' perceptions of climate change and adaptation decisions in the lower South Island of Aotearoa-New Zealand - Griffin, Christina; Wreford, Anita; Cradock-Henry, Nicholas (Journal of Rural Studies, 2023)
The impacts and implications of climate change – such as floods, droughts, heavy rainfall and increased regulation – are affecting dairy farming practices in the lower South Island (Te Waipaounamu) of Aotearoa-New Zealand. Adapting to these changes, in an equitable and transformational manner, is dependent on understanding the underlying root causes of vulnerability alongside local knowledge and values. We apply an intersectional values-based and contextual analysis to describe how past and present processes of agrarian change interact across different farmer identities to influence adaptive pathways. Local knowledge, place-based experience, values and perceptions of fairness intersect with different facets of a farmer's identity – such as financial capacity, land ownership status, debt arrangements, age and gendered participation – to enable or constrain adaptive action. Notably, notions of fairness, whether real or perceived, vary across farmer groups, and influence the kinds of adaptation activities that dairy farmers are willing, or potentially able, to engage in. The results call for more contextualised engagement with farming communities, and highlight the need to build a shared understanding of the complex historical, social, economic, cultural and environmental drivers of past, present and future change, in this highly productive, yet risky, agricultural landscape.
openalex: W4322101951
Keywords: C:New Zealand; _z:class:countries; _z:class:themes; oa:keyword:dairy farmers; oa:topic:T10367 Agricultural Innovation and Livelihood Diversification; oa:topic:T10439 Adaptation to Climate Change in Agriculture; oa:topic:T12098 Rural Development and Change in Agricultural Landscapes; openalex:import; openalex:yes

An occupant-centric control strategy for indoor thermal comfort, air quality and energy management - Wang, Zu; Calautit, John Kaiser; Tien, Paige; Wei, Shuangyu; Zhang, Wuxia; Wu, Yupeng; Xia, Liang (Energy and Buildings, 2023)
Recently, Occupant-Centric Control (OCC) strategies have gained mounting interest. Previous studies made use of OCC strategies for adjusting the operation of heating/cooling systems, improving indoor thermal comfort and governing mechanical ventilation systems. However, a very limited number of studies have applied OCC strategies to natural ventilation systems. Further, the feasibility of establishing OCC strategies for controlling indoor thermal comfort, energy use and specifically air quality has received much less attention and investigation. This paper presented an Occupant-Centric Heating and Natural Ventilation Control (OCHNVC) strategy for enhancing indoor thermal comfort, building energy performance and indoor air quality. Firstly, real-time profiles of occupant behavior and window opening in a case study building were collected using artificial intelligence (AI)-powered cameras and deep vision algorithms. Secondly, shallow artificial-neural-networks predictive models were established for forecasting the responses of the studied building to different levels of occupant behavior and window opening behavior. Thirdly, an OCHNVC strategy tailored to the studied room was proposed and applied to the studied room. The strategy could lower heating energy consumption by between 0.6 % and 29.0 % and improve the level of indoor thermal comfort by between 0 % and 58.8 %, relative to a conventional control strategy. Moreover, the conventional window control strategy only maintained indoor CO2 concentrations below 1000 ppm for 59.7 % of the period that occupants were within the studied room, while the proposed controller could do so for 89.2 % of the period. Future works shall focus on experimentally deploying the strategy to real buildings and evaluating its performance.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2023.112899 5072953:5RQJKZMD openalex: W4321073692
Keywords: _important; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:indoor thermal comfort; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:n:1; openalex:yes; selected_for:Predictive models for classroom conditions 2024

An occupant-centric control strategy for indoor thermal comfort, air quality and energy management - Wang, Zu; Calautit, John Kaiser; Tien, Paige; Wei, Shuangyu; Zhang, Wuxia; Wu, Yupeng; Xia, Liang (Energy and Buildings, 2023)
Recently, Occupant-Centric Control (OCC) strategies have gained mounting interest. Previous studies made use of OCC strategies for adjusting the operation of heating/cooling systems, improving indoor thermal comfort and governing mechanical ventilation systems. However, a very limited number of studies have applied OCC strategies to natural ventilation systems. Further, the feasibility of establishing OCC strategies for controlling indoor thermal comfort, energy use and specifically air quality has received much less attention and investigation. This paper presented an Occupant-Centric Heating and Natural Ventilation Control (OCHNVC) strategy for enhancing indoor thermal comfort, building energy performance and indoor air quality. Firstly, real-time profiles of occupant behavior and window opening in a case study building were collected using artificial intelligence (AI)-powered cameras and deep vision algorithms. Secondly, shallow artificial-neural-networks predictive models were established for forecasting the responses of the studied building to different levels of occupant behavior and window opening behavior. Thirdly, an OCHNVC strategy tailored to the studied room was proposed and applied to the studied room. The strategy could lower heating energy consumption by between 0.6 % and 29.0 % and improve the level of indoor thermal comfort by between 0 % and 58.8 %, relative to a conventional control strategy. Moreover, the conventional window control strategy only maintained indoor CO2 concentrations below 1000 ppm for 59.7 % of the period that occupants were within the studied room, while the proposed controller could do so for 89.2 % of the period. Future works shall focus on experimentally deploying the strategy to real buildings and evaluating its performance.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2023.112899 5072953:5RQJKZMD openalex: W4321073692
Keywords: _important; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:indoor thermal comfort; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:n:1; openalex:yes; selected_for:Predictive models for classroom conditions 2024

Prediction of rainfall response to the 21st-century climate change in Ghana using machine learning empirical statistical downscaling - Arthur, Frank H.; Boateng, Daniel; Baidu, Michael; Aryee, Jeffrey N. A. (Authorea (Authorea), 2023)
openalex:W4317894222 mag: KerkoCite.ItemAlsoKnownAs: 10.22541/essoar.167458059.91056213/v1 5072953:9JWSWHFW 5072953:IFPRA9AC
Keywords: C:Ghana; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:rainfall response; oa:sdg:13 Climate action; oa:topic:T11052 Electricity Price and Load Forecasting Methods; oa:topic:T11490 Hydrological Modeling using Machine Learning Methods; oa:topic:T13650 Scientific Computing and Data Analysis with Python; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Mapping climate risk for education planning in the Caribbean - Centre (UNOSAT), United Nations Satellite (ArcGIS StoryMaps, 2023)
A project by CDEMA, OpenDevEd and UNOSAT
KerkoCite.ItemAlsoKnownAs: 4874017:7WQGXXZC 5072953:IYQCIV97
Keywords: _z:class:countries; _z:class:themes

The role of the scientific community in strengthening disability-inclusive climate resilience - Stein, Penelope J. S.; Stein, Michael Ashley; Groce, Nora; Kett, Maria (Nature Climate Change, 2023)
Despite the trajectory towards climate catastrophe, governments are failing to take disability-inclusive climate action. We discuss how the scientific community could advance and hasten the development of disability-inclusive climate resilience, and which areas should be prioritized.
openalex: W4313888059
Keywords: _z:class:countries; openalex:import; openalex:yes

Student knowledge and perceptions of climate change and environmental sustainability at the Faculty of Health Sciences, University of Cape Town, South Africa - Irlam, James; Razzack, Z; Rother, H-A (African Journal of Health Professions Education, 2023)
Background. Climate change and polluting healthcare systems are significant threats to public health. Education about planetary health and environmentally sustainable healthcare is needed to equip health professionals to meet these challenges.Objectives. To assess the knowledge, perceptions and understanding of climate change and environmental sustainability among undergraduate health sciences students at the Faculty of Health Sciences (FHS), University of Cape Town (UCT).
Methods. Two student-led focus groups helped to design a cross-sectional survey of all undergraduate health sciences students. The survey findings were analysed quantitatively and thematically.Results. The 264 respondents included 211 medical and 53 health and rehabilitation students. Two-thirds of respondents (64.4%) claimed awareness but little understanding of climate change, which was understood mainly as changes in weather and climate patterns (40%) as a result of human activities (96.6%). Most (72%) were aware of the concept of environmental sustainability, but with little understanding. Students’ main sources of information about climate change were the internet (84.1%) and social media (77.3%). Two-thirds believed that climate change will highly impact their patients’ health and quality of life. Most (58.3%) thought that health professionals can help to prevent climate change by educating patients and promoting sustainable lifestyles. Nearly half (47.3%) thought it important to teach climate change and environmental sustainability in the curriculum.
Conclusion. Climate change and environmental sustainability have been poorly incorporated into current FHS, UCT curricula. Students acknowledged that these concepts are important and should be taught. The FHS should integrate planetary health and environmental sustainability into its curricula, in line with global efforts.
openalex:W4362566146 mag: KerkoCite.ItemAlsoKnownAs: 10.7196/ajhpe.2023.v15i1.1659 5072953:QSKZ9FJC
Keywords: C:South Africa; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:environmental sustainability; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11244 Impact of Climate Change on Human Health; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Training Needs on Climate Change Adaptation Measures in Crop and Livestock Production among Field Extension Workers in the Southeast Agro-Ecological Zone of Nigeria - Agomuo, C.I.; Umunakwe, P.C.; Ejiogu, A. O.; Ubeh, E.O. (Middle East Journal of Agriculture Research, 2023)
The study examined the training needs on climate change adaptation measures in crop and livestock production among field extension workers in the Southeast agro-ecological zone of Nigeria. Specifically, the study identified trainings on climate change adaptation in crop and livestock production received by field extension staff, training needs on climate change adaptation on livestock and crop production among the workers and the constraints faced by the workers in disseminating climate change adaptation measures. A sample of 210 field extension workers proportionately selected from three out of five states in the Southeast agro-ecological zone of Nigeria participated in the study. Data were obtained using structured questionnaire and were described using mean score and frequency. Results showed that the field extension staff were still in their economically active ages (X¯= 43), mostly female (64%) and well-educated. It was further revealed that the extension staff had worked for an average of 14 years. On the trainings on climate change adaptation measures in crop received by the staff, the result indicated that intercropping/mixed cropping (96.5%), early maturing varieties and higher yielding crops (96.5%) dominated whereas training on mixed livestock faming (91.4%) and use of improved livestock breeds (91.0%) prevailed in the livestock area. It was further indicated that the field extension workers needed training on communication skills (X¯= 3.6), erosion detection techniques and preventive & control measures for onward dissemination to farmers (X¯ = 3.5). The constraints to the dissemination of climate change adaptation measures included inadequate agricultural information/database/library for easy access to extension workers (X¯ = 2.8) and weak linkage system between research and extension for prompt innovation and information exchange (X¯ = 2.5). The study recommended the organization of routine training on climate change adaptation for field extension workers in the agro-ecological zone.
openalex:W4390203465 KerkoCite.ItemAlsoKnownAs: 10.36632/mejar/2023.12.2.21 5072953:C4RF98TU 5072953:LDXQAKHF
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T11259 Sustainable Diets and Environmental Impact; openalex:import; openalex:n:1; openalex:yes

Assessing and mitigating overheating risk in existing Canadian school buildings under extreme current and future climates - Baba, Fuad Mutasim; Ge, Hua; Wang, Liangzhu; Zmeureanu, Radu (Energy and Buildings, 2023)
Canadian buildings have been primarily designed to withstand cold and long winters, not hot summers. With climate change and the increase in the intensity and severity of heatwaves, it has become important to investigate overheating in buildings. However, there are limited studies on assessing and mitigating the overheating risk in existing buildings that house vulnerable populations in cold climates, especially in Canada. This paper provides a framework for the systematic assessment of overheating risks and the development of passive mitigation strategies to reduce the overheating risks without increasing cooling energy consumption under current and future climates with simulation models that are calibrated based on measured indoor air temperatures and outdoor weather conditions. The framework is applied to a school building built in 1958. The calibrated building model achieved an RMSE of less than 0.6 °C compared with measurements, a Maximum-Absolute-Difference of less than 1.9 °C, and a 1 °C Percentage-Error of less than 10 %. The simulation results from the calibrated model predicted 110 overheating hours during the year 2020. The use of exterior blind roll or a combination of night cooling and other mitigation measures that reduce solar heat gain can achieve acceptable thermal conditions. In 2044 (the future extreme midterm year), night cooling with the exterior blind roll shading would be required during extreme heat events. Whereas during 2090 (the future long-term extreme year), additional mitigation measures such as a cool roof may be required to achieve an acceptable level of thermal conditions in the school.
openalex: W4310906470
Keywords: C:Canada; _z:class:countries; _z:class:themes; evidence_review_2; oa:keyword:canadian school buildings; oa:keyword:overheating risk; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11244 Impact of Climate Change on Human Health; openalex:import; openalex:yes

Optimizing Overheating, Lighting, and Heating Energy Performances in Canadian School for Climate Change Adaptation: Sensitivity Analysis and Multi-Objective Optimization Methodology - Baba, Fuad Mutasim; Ge, Hua; Zmeureanu, Radu; Wang, Liangzhu (Social Science Research Network, 2023)
This paper aims to develop long-term adaptation strategies for the existing Canadian school buildings under extreme current and future climates using a developed methodology based on global and local sensitivity analysis and Multi-Objective Optimization Genetic Algorithm. The calibrated simulation model based on indoor and outdoor measured temperature for a school of interest is used to evaluate the optimization strategies. This paper aims to search for the optimum school building design under three simultaneous conflicting objective functions: (1) the minimization of overheating hours to less than 40 hours as required by BB101 building code by using passive mitigation measures, (2) the minimization of heating energy use to less than 15 kW/m2 according to passive house requirements and thus the reduction of greenhouse gas emissions, and (3) the minimization of artificial lighting energy use to less than the current lighting energy use by maximization of daylighting usage without exceeding acceptable glare index in classrooms. Ten building design variables are selected, which could generate approximately 300,000 solutions. The developed methodology reduced the numbers to 14,400 solutions and found seven Pareto solutions that comply with the three objectives and their constraints. High energy-efficient building envelope, appropriate window-wall ratio and window type, natural ventilation during the day, and night cooling can play a key role in achieving the objectives under current weather conditions. An additional cool roof and external overhang will be needed in the medium-term future climate, and an additional movable screen shading will be needed in the long-term future climate.
openalex: W4361018614
Keywords: _z:class:countries; _z:class:themes; evidence_review_2; oa:keyword:climate change adaptation; oa:sdg:13 Climate action; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; openalex:import; openalex:yes

Effects of Indoor Plants on Occupants’ Emotional-State, Performance, and Perceived Comfort in an Open-Plan Seating Space - Budaniya, Mukesh; Mishra, Asit; Rai, Aakash; Dasgupta, Mani Sankar (2023)
Keywords: _z:class:countries

Climate change adaptation in agriculture: Learning from an international labour mobility programme in Australia and the Pacific Islands region - Dun, Olivia; Klocker, Natascha; Farbotko, Carol; McMichael, Celia (Environmental Science & Policy, 2023)
Climate change is expected to seriously affect agricultural livelihoods and food security in all Pacific Island countries. The United Nations Food and Agriculture Organisation contends that, to adapt, both ‘modern’ and Indigenous agricultural practices and knowledge are needed. A challenge lies in combining agricultural knowledge systems and enabling adaptive knowledge to be shared amongst Pacific Islanders. Opportunities to integrate different types of agricultural knowledge (including ‘modern’ and Indigenous) are needed. This paper argues that international labour mobility programmes provide an avenue for knowledge exchange that can support climate change adaptation in agriculture. It presents empirical evidence from research with 33 Pacific Islanders who grow crops in their home countries and were employed in Australia’s Seasonal Worker Programme (SWP). We demonstrate how SWP participation opened new possibilities for climate change adaptation in agriculture in the Pacific Islands. Adaptive knowledge stems from SWP workers’ exposure to different agricultural skills and ideas in Australia, combined with their knowledge and experience of crop production in their countries of origin. SWP participation created opportunities for workers to draw on different agricultural skills and knowledge on return to the Pacific Islands. The ability for SWP workers to then exchange adaptive knowledge with other Pacific Islanders is enabled by their social relationships, the likes of which an official agricultural extension officer might not have to the same degree. So far, such adaptive agricultural knowledge and skills exchanges are serendipitous. There is scope to explicitly build climate change knowledge exchange into agriculture-focused international labour mobility schemes.
openalex: W4310017060
Keywords: C:Australia; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change adaptation; oa:topic:T10367 Agricultural Innovation and Livelihood Diversification; oa:topic:T10439 Adaptation to Climate Change in Agriculture; oa:topic:T12656 Impact of Climate Change on Human Migration; openalex:import; openalex:yes

Health impact studies of climate change adaptation and mitigation measures – A scoping review - Luyten, Axel; Winkler, Mirko S.; Ammann, Priska; Dietler, Dominik (The Journal of Climate Change and Health, 2023)
Climate change affects both mental and physical health. Besides limiting the extent and consequences of climate change, mitigation and adaptation measures can have additional and potentially unintended health impacts. This scoping review outlines how health effects of climate mitigation and adaptation measures have been studied in the scientific literature. We conducted a systematic literature search in the databases PubMed, Scopus and Web of Science without time restriction. All peer-reviewed articles reporting quantified health impacts linked to specific climate change adaptation and mitigation measures were included. Overall, the 89 included articles considered only a narrow range of health determinants and health outcomes. Adaptation- and mitigation-related articles most frequently investigated the environmental health determinants air temperature and air pollution, respectively. Non-communicable diseases were predominantly studied while other relevant health outcome categories, such as mental health, food- and nutrition-related issues, and communicable diseases were rarely reported. The scarcity of studies focusing on the social health determinants and providing stratified health impacts among vulnerable population groups in assessments points to an inadequate consideration of health equity aspects. Increased efforts to quantify health impacts more comprehensively and to identify underlying vulnerability factors among specific population groups seem needed. This information could provide policymakers with more accurate evidence to address health equity aspects, limit adverse health impacts and promote health co-benefits of climate change adaptation and mitigation measures.
openalex: W4308629203
Keywords: _z:class:countries; evidence_review; openalex:citedBy; openalex:import; selected_for:effects of climate ch...on learning...LMICs 2024; tagged

Prevalence of stress, anxiety and depression in the context of climate change among newly recruited contract teachers in Morocco - Meskini, Nadia; Lamtai, Mouloud; Sfendla, Anis; Madhi, Youssef El; Ahami, Ahmed Omar Touhami; Ouahidi, Moulay Laarbi (E3S Web of Conferences, 2023)
Teaching has been identified as one of a highly stressful jobs. As known, this job is linked to development of neuropsychiatric. However, there is a little background about the assessment of these problems among Moroccan teachers. This study aims to measure the prevalence of stress, anxiety and depression among 150 newly recruited contractual primary teachers in KHEMISSET city using three international scales. The perceived stress scale (PSS) for stress, the hospital anxiety and depression scale (HADS) and The Mini International Neuropsychiatric Interview (MINI) for anxiety and depression. The results show that 95.9% of the teachers are stressed. In contrast, among these teachers newly recruited 94.9% and 72.4% do not suffer from depression and anxiety, respectively. Additionally, there was no significant difference in the stress, anxiety and depression scores between male and female teachers (p > 0.05). The prevalence of stress, anxiety, and depression among newly recruited contract teachers in Morocco, specifically in the context of climate change, can be influenced by various factors. In conclusion, this study suggest that teachers are more susceptible to stress, depression and anxiety and suitable steps should be taken to enhance the mental health of these teachers, thus guaranteeing good quality education.
openalex:W4385957493 mag: KerkoCite.ItemAlsoKnownAs: 10.1051/e3sconf/202341201073 5072953:FHGX54SS
Keywords: C:Morocco; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10795 Impact of Burnout on Healthcare Professionals and Students; oa:topic:T12947 Salutogenesis and Sense of Coherence in Health; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

The Impact of Climate Change on Quality Education Delivery: A Case Study of Four Selected Secondary Schools in Kabwe District, Zambia - Mpanza, Charity Tumeo; Muluka, Webby (International Journal of Research and Innovation in Social Science, 2023)
The study was an attempt to establish the impact of climate change on quality education delivery in selected four secondary schools in Kabwe district of central province in Zambia. Two objectives were at the heart of the study, namely: to establish effects of climate change commonly experienced in Kabwe district and to investigate how such effects affect provision of quality education in the selected four secondary schools within the district. 128 participants comprising 40 teachers, 80 pupils and 8 school administrators were purposively selected from four different secondary schools in Kabwe district. A survey using structured interviews and questionnaires were used. On challenges associated with effects of climate change commonly experienced in Kabwe district, the study established the following: impassable access roads to schools due to floods, destruction of homes, school buildings, obliteration of field crops and livestock due to heavy rains and droughts, and escalation of diseases and stress. On how the afore mentioned challenges affect quality education delivery, the study established the following: high absenteeism rate among pupils, deprivation of pupils with quality physical learning environment, increased hunger and reduced attention span in pupils, and compromised health of pupils. The study has proposed the following interventions: upscale tree planting programs, parents-teachers associations in concerned schools to aggressively lobby local authorities to maintain strategic roads in townships and residential areas leading to schools, to continue promoting use of eco-friendly practices such as conservation farming, strict control of both forest and charcoal burning, ban open air trash burning.
openalex:W4381622474 mag: KerkoCite.ItemAlsoKnownAs: 4874017:9ZF8ZVJ2 2129771:HDDW7DGQ 4874017:9ZF8ZVJ2 2129771:HDDW7DGQ 2129771:HDDW7DGQ 10.47772/ijriss.2023.70621 5072953:4ZNH56C7
Keywords: C:Zambia; _z:class:countries; _z:class:themes; _z:no_pdf; evidence_review_2; oa:keyword:quality education delivery; oa:sdg:2 Zero hunger; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Content and Teaching Methods Regarding Climate Change: South African Curricula Perspective - Msezane, Sıkhulıle Bongınkosı (2023)
The purpose of this chapter is to explore teaching methods showing the impact of climate change on the environment and human health. This study used a qualitative research design to explore potential climate change teaching strategies because climate change not only negatively impacts the environment, but also negatively impacts human health. The chapter will examine instructional strategies for teaching learners in Grades 10 to 12 about climate change using appropriate examples from the document analysis. To find the best climate change teaching strategies to implement in the classroom, documents will be purposefully sampled. Climate change teaching strategies will be helpful to both teachers and learners. Climate change practitioners, textbook authors, and educational policymakers will all benefit from these instructional strategies which can be applied in any school setting anywhere in the world.
openalex:W4387679727 mag: KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-031-25960-9_48-1 5072953:PGCX7AVW
Keywords: C:South Africa; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:climate change; oa:keyword:teaching methods; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:n:1; openalex:yes

Enhancing the review process in global environmental assessments: The case of the IPCC - Palutikof, Jean; Boulter, Sarah; Field, Christopher B.; Mach, Katharine J.; Manning, Martin; Mastrandrea, Michael D.; Meyer, Leo M.; Minx, Jan; Pereira, Joy Jacqueline; Plattner, Gian‐Kasper; Ribeiro, Suzana Kahn; Sokona, Youba; et al. (Environmental Science & Policy, 2023)
External review is a fundamental component of Global Environmental Assessments, ensuring their processes are comprehensive, objective, open and transparent, and are perceived as such. Here, we focus on review of Intergovernmental Panel on Climate Change (IPCC) Assessment Reports. The review process has received little scrutiny, although review comments and author responses are public. Here we analyse review documents from the Fourth and Fifth Assessments, focusing primarily on Working Group II. We address three questions: Is the review representative? Is it comprehensive? Is it insightful? Overall we found the review process to be fit for purpose, although there are outstanding issues. First, the overwhelming majority of reviewers are from developed countries, although evidence suggests participation by developing country reviewers increased between the Fourth and Fifth Assessments. Second, earlier sections of chapters are more densely reviewed than later ones. This is true even when executive summaries are removed from analysis. In consequence, some sections on specialised topics may escape in-depth review. Thirdly, those review comments which are received make a valid and valuable contribution to the scientific development of chapters. We suggest how outstanding issues could be addressed, including through enhanced reviewer recognition, a wider role for review editors, adherence to mandated page lengths from early in the process, reviewer training, and consistency in reporting to allow systematic evaluation. Making such changes will result in more transparent, consistent and representative processes delivering reviews which effectively contribute to the credibility and legitimacy of future Global Environmental Assessments and, ultimately, their recognition and contribution.
openalex: W4309079633
Keywords: _z:class:countries; evidence_review; openalex:citedBy; openalex:import; selected_for:effects of climate ch...on learning...LMICs 2024; tagged

Self-Generating Training Model (SGTM) Algorithm to Estimate Groundwater Level in Consensus with Climate Change Impact Study in Cauvery Delta Zone, Tamil Nadu, India - Raj, A. Stanley; Angelena, J.P.; Damodharan, R.; Kumar, D. Senthil (2023)
Cauvery Delta Zone is present in the eastern part of Tamil Nadu, popularly known as ‘rice bowl’ of Tamil Nadu. It constitutes of about 11.1% of total area of the state. It lies between 10.00 and 11.30° N latitude and 78.15°–79.45° E longitude. Cauvery Delta Zone includes the districts of Thanjavur, Thiruvarur, Nagapattinam, Mayiladuthurai, Perambalur and some parts of Pudhukottai and Cuddalore Districts. This zone plays a vital role not only in rice production but also in other varieties of crops and raw materials for industries. It receives more than 50% of rainfall in North East monsoon. Variation in rainfall in this zone causes serious environmental effects. Sources of groundwater recharge zones are mostly influenced by rainfall variability. In this research work, the connection between the climate change impact and rainfall variability has been studied and the successive study has been made. The temporal trends of rainfall variability are studied extensively to predict the future scenario using the Self-Generating Training Model (SGTM) algorithm. This work is potentially helpful for farmers to identify the threatening zones and can understand the fluctuations in groundwater level due to implications of climate change.
openalex: W4387917520
Keywords: C:India; _z:class:countries; _z:class:themes; oa:keyword:estimate groundwater level; oa:topic:T10330 Hydrological Modeling and Water Resource Management; oa:topic:T11186 Global Drought Monitoring and Assessment; oa:topic:T11490 Hydrological Modeling using Machine Learning Methods; openalex:import; openalex:n:1; openalex:yes

Schools, Religion and Teaching about Climate Change and Sustainable Development – Indonesia and Nigeria - Salter, Emma (2023)
openalex:W4386625040 mag: KerkoCite.ItemAlsoKnownAs: 10.5040/9781350297296.ch-19 5072953:T599JSXV
Keywords: C:Indonesia; C:Nigeria; _z:class:countries; _z:class:themes; _z:no_pdf; oa:topic:T13059 Influence of Religion on Environmental Concern and Activism; oa:topic:T13456 Role of Faith-Based Organizations in Development and Social Services; openalex:import; openalex:n:1; openalex:yes

The Potential of Artificial Intelligence for Achieving Healthy and Sustainable Societies - Sırmaçek, Beril; Gupta, Shivam; Mallor, Fermı́n; Azizpour, Hossein; Ban, Yifang; Eivazi, Hamidreza; Fang, Haowen; Golzar, Farzin; Leite, Iolanda; Melsión, Gaspar Isaac; Smith, Kevin; Nerini, Francesco Fuso; et al. (2023)
In this chapter we extend earlier work (Vinuesa et al., Nat Commun 11, 2020) on the potential of artificial intelligence (AI) to achieve the 17 Sustainable Development Goals (SDGs) proposed by the United Nations (UN) for the 2030 Agenda. The present contribution focuses on three SDGs related to healthy and sustainable societies, i.e., SDG 3 (on good health), SDG 11 (on sustainable cities), and SDG 13 (on climate action). This chapter extends the previous study within those three goals and goes beyond the 2030 targets. These SDGs are selected because they are closely related to the coronavirus disease 19 (COVID-19) pandemic and also to crises like climate change, which constitute important challenges to our society.
openalex: W4368249643
Keywords: _z:class:countries; openalex:citedBy; openalex:import; selected_for:effects of climate ch...on learning...LMICs 2024; tagged

Civic Education Teachers' Perspectives on Climate Change and Climate Change Education among Selected Peri-Urban Schools in Lusaka District, Zambia - Szanajda, Andrew; Li, Yu Jie (International Journal of Humanities, Social Sciences and Education, 2023)
openalex:W4385500979 KerkoCite.ItemAlsoKnownAs: 10.20431/2349-0381.1007017 5072953:7PWUJHR8
Keywords: C:Zambia; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change education; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Carbon dioxide concentration levels and thermal comfort in primary school classrooms: what pupils and teachers do - Zapata-Lancaster, Maria Gabriela; Ionas, Miltiadis; Toyinbo, Oluyemi; Smith, Thomas Aneurin (Sustainability, 2023)
The current climate emergency concerns and the COVID-19 pandemic demand urgent action to maintain healthy indoor environments in energy efficient ways. Promoting good indoor environments, in particular, increasing ventilation levels, has been a prominent strategy to mitigate the risk of COVID-19 transmission indoors. However, this strategy could be detrimental to thermal comfort, particularly during the heating season in buildings located in temperate climate zones. This paper presents research conducted in two primary schools in South Wales (UK) where the temperature, relative humidity and the carbon dioxide (CO2) concentration levels were monitored. The study monitored six classrooms and two communal spaces in the two schools during the academic year 2021/2022, the first academic year back to teaching and learning in school buildings after home-schooling and educational disruptions due to COVID-19 lockdowns. The study investigated the actions taken by teachers and pupils to balance the thermal comfort needs while minimising CO2 concentration levels. We conducted user studies to explore the comfort perceptions by pupils and teachers in relation to the thermal conditions and the freshness of air in the monitored classrooms. The paper identifies opportunities where end-users, teachers and pupils engaged with the management of the indoor environmental conditions and adopted actions to balance the requirement of reducing CO2 concentration levels while promoting thermal comfort. This research offers lessons and insights related to end-users’ agency and their understanding of indoor environments and thermal experience in schools.
KerkoCite.ItemAlsoKnownAs: 2129771:CALH3X97 2129771:CALH3X97 10.3390/su15064803 4874017:NUNNPT8A 5072953:P4CXHH47 openalex: W4323664266
Keywords: CO_2 concentration indoors; _z:class:countries; _z:class:themes; evidence_review_2; monitoring; oa:keyword:primary school classrooms; oa:sdg:13 Climate action; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10990 Airborne Transmission of Respiratory Viruses; oa:topic:T11002 Indoor Air Quality and Health Effects; openalex:n:1; openalex:yes; school buildings; thermal comfort

Determining the adaptive thermal comfort and preference votes of children in public primary schools in the hot semi-arid climatic zone of Nigeria - Abdullah, I.A.; Salisu, A.S.; Dahiru, A. (J. Human Centered Technol, 2023)
Keywords: _z:class:countries; evidence_review_2

The effect of commercial building orientations on indoor climate in tropical environments: A new insight on thermal comfort studies - Akpan, A. (Curr Landscape Ecol Rep, 2023)
Keywords: _z:class:countries

Guidance note on using implementation research in education - Allison, C. (London: Foreign, Commonwealth & Development Office, prepared for Building Evidence in Education (BE2), 2023)
KerkoCite.ItemAlsoKnownAs: 2129771:V6II42S9 2129771:V7SJPNUZ
Keywords: evidence_review

Design guidance for education facilities: prioritization for Advanced Indoor Air Quality - ASHRAE; Setty, Raj; Ruch, Christopher; Metzger, Corey; Hasenkox, Kyle; Hammelman, Keith; Maor, Itzhak (2023)
KerkoCite.ItemAlsoKnownAs: 4874017:4FRFAYMY 5072953:FAGHTYPR
Keywords: _z:class:countries; _z:class:themes

Interdependence between climate change and migration: Does agriculture, geography, and development level matter in sub‐Saharan Africa? - Bannor, Frank; Magambo, Isaiah Hubert; Mahabir, Jugal; Tshitaka, Jeanluc Mubenga (South African Journal of Economics, 2023)
Concerns about the human effects of climate change have contributed to forecasts of how populations in drought-prone and flood-prone areas would respond to these events. Empirical studies have predicted that human migration has been among the critical resilient strategy in responding to the impact of climate change. To obtain a more comprehensive understanding of the climate–migration relationship, the impacts of climate change on international migration flows from sub-Saharan Africa nations to South Africa are investigated empirically in this paper. The study employed static and dynamic models and panel data from 35 countries in sub-Saharan Africa, spanning 1990 to 2017. The findings are as follows: (1) The analysis shows that historical temperature has a positive and statistically significant effect on outmigration in agriculture-dependent nations. (2) The analysis shows that agricultural value added as a share in gross domestic product has a negative and statistically significant effect on outmigration in agriculture-dependent nations. (3) The results also show that geographic location and development level of a country, in addition to dependency on agriculture, are key factors in the climate change–international migration nexus. Policy implications are discussed.
openalex: W4366997629
Keywords: _snowballing:openalex; _z:class:countries; openalex:n:1; openalex:yes

Holistic overview of natural ventilation and mixed mode in built environment of warm climate zones and hot seasons - Bienvenido-Huertas, David; De La Hoz-Torres, María Luisa; Aguilar, Antonio J.; Tejedor, Blanca; Sánchez-García, Daniel (Building and Environment, 2023)
The climate change leads to periods of extreme events (i.e. reduction of cold seasons, heat waves, overheating, urban heat island among others) that affect the performance of residential and tertiary buildings with high occupancy (i.e. hospitals, schools, commercial centres, offices etc). However, most of low-carbon policies do not consider the ventilation as a mitigation measure. In fact, a lack of studies on natural ventilation (NV) and mixed-mode (MM) strategies was detected, especially for warm regions or areas with hot and humid climates. This paper aims to carry out a bibliometric analysis from 1928 to 2023, to observe the evolution of the topic. After identifying the main research clusters (thermal comfort, energy efficiency, indoor air quality and simulation tools) by science mapping, the most relevant publications of the last 20 years were assessed (2003–2023). The results of this study revealed that only 1.51 % of the scientific documents in 95 years corresponded to an extensive literature review, although epidemic or disease outbreaks led to peaks of production in this topic. This emphasizes the importance of observing what was done and how was implemented over the years. Regarding the clusters, some relevant aspects can be highlighted: (i) non-homogeneity of studies on NV or MM related to building type; (ii) interregional projects should be drawn up to check the effectiveness of NV and MM, especially when other architectural techniques are adopted (i.e. solar chimneys, window wall ratio –WWR-, thermally activated building structures –TABS- etc); (iii) the optimization of simulation tools should be based on the incorporation of BIM and generative design for NV and MM.
KerkoCite.ItemAlsoKnownAs: 5072953:24YYVSKW 5072953:2M65XVSM
Keywords: Built environment; Energy efficiency; IAQ; Mixed mode; Natural ventilation; Simulation; Software; Thermal comfort; _z:class:countries; _z:no_pdf

Effectiveness of carbon pricing–A systematic review and meta-analysis of the ex-post literature - Döbbeling-Hildebrandt, N.; Miersch, K.; Khanna, T.; Bachelet, M.; Bruns, S. B.; Callaghan, M.; Edenhofer, O.; Flachsland, C.; Forster, P.; Kalkuhl, M. (2023)
KerkoCite.ItemAlsoKnownAs: 5072953:L9FD3JCY 5072953:YVAYYGBL
Keywords: _z:class:countries

Exploring the use of indigenous building materials to achieve thermal comfort in a hot, humid climate: The case of south Eastern Nigeria - Egbum, P.S.; Anaebo, C.; David, C.; Barnaby, J. (African Journal of Educational Management, Teaching and Entrepreneurship Studies, 2023)
Keywords: _z:class:countries

Thermal energy storage enhanced windcatcher system for hybrid cooling and ventilation in buildings - Eso, Olamide (2023)
KerkoCite.ItemAlsoKnownAs: 4874017:ZDP45MEY 5072953:CSIQDIMN
Keywords: _z:class:countries; _z:class:themes

Climate, Enviroment and Education - Fab Inc; Laterite; Open Development and Education (2023)
Presentation for the Tanzania Education Donors-Partners working group – session on Education, Climate and Environment.
KerkoCite.ItemAlsoKnownAs: 2129771:FKT25FYV 5072953:D9AMRVQH
Keywords: C:Tanzania; _z:class:countries; _z:class:themes

An introduction to statistical learning with applications in python - G., James; Witten, D.; Hastie, T.; Tibshirani, R.; Taylor, J. (Springer Texts in Statistics, 2023)
Keywords: _z:class:countries

Ergonomics of the thermal environment — Instruments for measuring and monitoring physical quantities - I.S.O. (2023)
Keywords: _z:class:countries

Holistic approach towards a sustainable urban renewal: Thermal comfort perspective of urban housing in Kigali, Rwanda - Irakoze, A.; Lee, K.; Kim, K.H. (Buildings, 2023)
Keywords: _z:class:countries

Experimental study of the unconstrained melting of a phase change material for air-conditioning applications - Iskandar, Shamir H.; Cofré-Toledo, Jonathan; Cataño, Francisco A.; Ortega-Aguilera, Roberto; Vasco, Diego A. (International Journal of Refrigeration, 2023)
Keywords: _z:class:countries; _z:no_pdf

A literature review of cross ventilation in buildings - Jiang, Zitao; Kobayashi, Tomohiro; Yamanaka, Toshio; Sandberg, Mats (Energy and Buildings, 2023)
There is a growing body of literature that recognizes that natural ventilation plays a vital role in indoor air quality, thermal comfort and building energy consumption. This paper systematically reviews the previously published research of the most efficient and typical natural ventilation type - cross ventilation, aiming to present the main research topics in contemporary research and provide an agenda for future studies. The methodologies, airflow pattern, ventilation models and influencing parameters of cross ventilation were comprehensively summarized and discussed. The chained analysis and data-driven methods are the potential approaches to study cross ventilation more efficiently. The comparisons of different ventilation models of cross ventilation help to better understand the basic mechanisms that drive the cross ventilation airflow.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2023.113143 4874017:3K8PVHUI 5072953:PUP2YURT openalex: W4372402124
Keywords: _z:class:countries; _z:class:themes; oa:keyword:cross ventilation; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10990 Airborne Transmission of Respiratory Viruses; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:n:1; openalex:yes

The impact of climate change on cognitive performance of children in English school stock: A simulation study - Jie, Dong; Schwartz, Yair; Korolija, Ivan; Mumovic, Dejan (Building and Environment, 2023)
Children in England spend around 30% of their time in schools to gain knowledge and skills. Climate change could impact schools’ thermal environments and children’s learning performance by impairing their cognitive ability. This study presents an evaluation approach to investigating and quantifying climate change’s impact on the cognitive performance of children across English school stocks. The study also evaluates the potential of possible strategies for mitigating the impacts of climate change. The results show that future climates are projected to increase cognitive performance loss of children in school archetypes representative of school stocks, with variations based on regional climate characteristics. Increasing ventilation rates proves to be an effective means of reducing cognitive performance loss, while its effectiveness diminishes as outdoor temperatures rise in the future. Thus, the introduction of air conditioning becomes a potentially more beneficial strategy, despite the associated increase in cooling energy demand. Moreover, higher ventilation rates in air-conditioned classrooms can further improve children’s cognitive performance. The use of cognitive performance loss as a Key Perfor mance Indicator (KPI) allows for better communication and understanding of climate change risks faced by schools among building and non-building experts. The proposed evaluation approach remains adjustable and can be continuously updated and enhanced as new insights from psychological research emerge.
Keywords: _z:class:countries; evidence_review_2

Windows of opportunities: orientation, sizing and pv-shading of the glazed area to reduce cooling energy demand in Sub-Sahara Africa - Kabanshi, A.; Choonya, G.; Ameen, A.; Liu, W.; Mulenga, E. (Energies, 2023)
Keywords: _z:class:countries

UK higher education sector's response to the war in Ukraine - Kushnir, Iryna; Milani, Zara; Mbah, Marcellus Forh (Journal of Applied Research in Higher Education, 2023)
Publisher: Emerald Publishing Limited KerkoCite.ItemAlsoKnownAs: 10.1108/JARHE-08-2023-0384 5072953:WZPEY7KA openalex: W4389718784
Keywords: _z:class:countries; _z:class:themes; oa:topic:T10762 Mental Health of Refugees and Immigrants; oa:topic:T13086 The Sustainability and Future of Unrecognized Quasi-States; oa:topic:T14372 Impacts of Warfare on Environment and Food Security; openalex:n:1; openalex:yes

UK higher education sector's response to the war in Ukraine - Kushnir, Iryna; Milani, Zara; Mbah, Marcellus Forh (Journal of Applied Research in Higher Education, 2023)
KerkoCite.ItemAlsoKnownAs: 10.1108/JARHE-08-2023-0384 5072953:WZPEY7KA openalex: W4389718784
Keywords: C:Ukraine; _z:class:countries; _z:class:themes; oa:topic:T10762 Mental Health of Refugees and Immigrants; oa:topic:T13086 The Sustainability and Future of Unrecognized Quasi-States; oa:topic:T14372 Impacts of Warfare on Environment and Food Security; openalex:n:1; openalex:yes

Mapping universities-communities partnerships in the delivery of the sustainable development goals - Leal Filho, Walter; Dibbern, Thais; Trevisan, Laís Viera; Cristofoletti, Evandro Coggo; Dinis, Maria Alzira Pimenta; Matandirotya, Newton; Sierra, Javier; Shulla, Kalterina; Buttriss, Gary; Decosta, Patrick L. (Frontiers in Environmental Science, 2023)
Publisher: Frontiers Media SA KerkoCite.ItemAlsoKnownAs: 10.3389/fenvs.2023.1246875 5072953:VCPIYR8Q openalex: W4385725090
Keywords: _z:class:countries; _z:class:themes; oa:keyword:sustainable development; oa:keyword:sustainable development goals; oa:sdg:17 Partnerships for the goals; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11806 Impact of Service-Learning in Higher Education; oa:topic:T11835 Sustainability Education in Higher Education Institutions; openalex:n:1; openalex:yes

Mapping universities-communities partnerships in the delivery of the sustainable development goals - Leal Filho, Walter; Dibbern, Thais; Trevisan, Laís Viera; Cristofoletti, Evandro Coggo; Dinis, Maria Alzira Pimenta; Matandirotya, Newton; Sierra, Javier; Shulla, Kalterina; Buttriss, Gary; Decosta, Patrick L. (Frontiers in Environmental Science, 2023)
Publisher: Frontiers Media SA KerkoCite.ItemAlsoKnownAs: 10.3389/fenvs.2023.1246875 5072953:VCPIYR8Q openalex: W4385725090
Keywords: _z:class:countries; _z:class:themes; oa:keyword:sustainable development; oa:keyword:sustainable development goals; oa:sdg:17 Partnerships for the goals; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11806 Impact of Service-Learning in Higher Education; oa:topic:T11835 Sustainability Education in Higher Education Institutions; openalex:n:1; openalex:yes

Mapping universities-communities partnerships in the delivery of the sustainable development goals - Leal Filho, Walter; Dibbern, Thais; Trevisan, Laís Viera; Cristofoletti, Evandro Coggo; Dinis, Maria Alzira Pimenta; Matandirotya, Newton; Sierra, Javier; Shulla, Kalterina; Buttriss, Gary; Decosta, Patrick L. (Frontiers in Environmental Science, 2023)
KerkoCite.ItemAlsoKnownAs: 10.3389/fenvs.2023.1246875 5072953:VCPIYR8Q openalex: W4385725090
Keywords: _z:class:countries; _z:class:themes; oa:keyword:sustainable development; oa:keyword:sustainable development goals; oa:sdg:17 Partnerships for the goals; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11806 Impact of Service-Learning in Higher Education; oa:topic:T11835 Sustainability Education in Higher Education Institutions; openalex:n:1; openalex:yes

Indoor exposure to polycyclic aromatic hydrocarbons associated with solid fuel use in rural China - Li, Shiyin; Men, Yatai; Luo, Zhihan; Huang, Wenxuan; Xing, Ran; Sun, Chao; Shen, Guofeng (Environmental Geochemistry and Health, 2023)
Keywords: _z:class:countries; _z:no_pdf

Energy retrofit of public office building through liquid desiccant assisted dedicated outdoor air system with fuel cell in Korea - Lim, Hansol; Cheon, Seong-Yong; Cho, Hye-Jin; Jeong, Jae-Weon; Su, Yuehong (Applied Thermal Engineering, 2023)
Keywords: _z:class:countries; _z:no_pdf

Post occupancy evaluation of ventilation coefficient desired for thermal comfort in educational facilities - Mba, E.J.; Okeke, F.O.; Ezema, E.C.; Oforji, P.I.; Ozigbo, C.A. (Journal of Human, Earth, and Future, 2023)
Keywords: _z:class:countries

Community Health Education for Health Crisis Management: The Case of COVID-19 in Cameroon - Mbah, Marcellus; Bang, Henry; Ndi, Humphrey; Ndzo, Judwin Alieh (Community Health Equity Research & Policy, 2023)
The current coronavirus disease 2019 (COVID-19) pandemic has led Cameroon’s government to implement public health measures aimed at preventing its spread. This paper investigates how community health education on the virus was being carried out, what gaps exist and what further action could be taken. A survey instrument was used to gather data among a total of 179 Cameroonians recruited via opportunistic and snowball sampling methods. According to our findings, gaps exist. These include the need for adequate community health education on COVID-19, maximising multilingualism and indigenous cultural assets and disbanding misconceptions on the pandemic, as well as stigmatisation. The paper culminates by underlining the significance of an integrated approach to confront the pandemic. This approach captures the need to frame but also firm up community health education architecture on COVID-19 that captures inputs from different stakeholders, including indigenous knowledge holders, for collective wellbeing.
KerkoCite.ItemAlsoKnownAs: 10.1177/0272684X211031106 5072953:JRMK8IXQ openalex: W3174855276
Keywords: C:Cameroon; _z:class:countries; _z:class:themes; oa:keyword:health crisis management; oa:sdg:3 Good health and well-being; oa:topic:T10410 Modeling the Dynamics of COVID-19 Pandemic; oa:topic:T10833 Factors Affecting Vaccine Hesitancy and Acceptance; oa:topic:T11581 Ebola Virus Research and Outbreaks; openalex:n:1; openalex:yes

Heat adaptation proposal - MEER (2023)
KerkoCite.ItemAlsoKnownAs: 2129771:J7TBYU2H 4874017:VDZ3JQFF
Keywords: evidence_review

Coaching ourselves: how peer-learning empowers managers and workers to achieve climate solutions - Molthan-Hill, Petra; Mintzberg, H.; Ibrahim, S. E.; Johnston, K.; LeNir, P.; Mbah, M.; Morsing, M.; Leigh, J. S. A. (2023)
KerkoCite.ItemAlsoKnownAs: 10.5465/AMPROC.2023.14150symposium 5072953:93G422IW openalex: W4385218363
Keywords: _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; openalex:n:1; openalex:yes

Coaching ourselves: how peer-learning empowers managers and workers to achieve climate solutions - Molthan-Hill, Petra; Mintzberg, H.; Ibrahim, S. E.; Johnston, K.; LeNir, P.; Mbah, M.; Morsing, M.; Leigh, J. S. A. (2023)
KerkoCite.ItemAlsoKnownAs: 10.5465/AMPROC.2023.14150symposium 5072953:93G422IW openalex: W4385218363
Keywords: _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; openalex:n:1; openalex:yes

Coaching ourselves: how peer-learning empowers managers and workers to achieve climate solutions - Molthan-Hill, Petra; Mintzberg, H.; Ibrahim, S. E.; Johnston, K.; LeNir, P.; Mbah, M.; Morsing, M.; Leigh, J. S. A. (2023)
KerkoCite.ItemAlsoKnownAs: 10.5465/AMPROC.2023.14150symposium 5072953:93G422IW openalex: W4385218363
Keywords: _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; openalex:n:1; openalex:yes

An overview of implications and suggestions for reducing temperature rise in buildings located in the tropics - Munonye, C.; Ifebi, O.; Maduka, N.; Ngobili, M. (Research & Development, 2023)
Keywords: _z:class:countries

Investigation of indoor air pollutants in different environmental settings and their health impact: a case study of Dehradun, India - Nandan, Abhishek; Mondal, Prasenjit; Kumar, Sandeep; Siddiqui, Nihal Anwar; Sinha, Shambhavi; Subramani, Sudalai; Singh, Akshi Kunwar; Raja, Sivashankar; Hussain, Chaudhery Mustansar (Air Quality, Atmosphere & Health, 2023)
The air we breathe both indoors and in the external environment significantly affects human health and life. The legal systems across the globe, including the United Nations programs, have taken measures to protect the right to clean air as a basic human right. Urbanization and modern lifestyles have changed the dynamics of need and usage of products and allied activities. However, the scope of this study is focused on the investigation of indoor air quality (IAQ). This study is perhaps the first ever attempt to investigate the indoor air pollutant in different environmental setup based on building code specially for nonindustrial indoor environments, i.e., office buildings, public buildings (schools, hospitals, theatres, restaurants), and private dwellings in Dehradun, India. Air pollutants measured in this study include particulate matter (PM10), carbon dioxide (CO2), carbon monoxide (CO), ozone (O3), sulfur dioxide (SO2), nitrogen dioxide (NO2), volatile organic compounds (VOCs), and formaldehyde (HCHO). In order to identify the exposure level of indoor air pollutants on human health, chronic daily intake has been calculated. In residential building occupancies, the concentration of particulates is higher in indoor air, and the key sources are kitchen activities such as the operation of gas stoves for cooking. In educational buildings, significant pollutants present are CO2, formaldehyde, and respirable suspended particulate matter (RSPM), predominantly due to characteristic available ventilation systems. Compared to other indoor occupancies, institutional buildings related to health science have significant sources of indoor pollutants generated from biomedical waste, medical equipment, and instruments.
KerkoCite.ItemAlsoKnownAs: 2129771:HXMX2D6G 2129771:HXMX2D6G 5072953:2YFHX2RT 5072953:S4HWLZ9Z
Keywords: Air pollution; C:India; Chronic daily intake; Indoor air quality; Ventilation; _z:class:countries; _z:no_pdf; evidence_review_2

The indoor climate of hospitals in tropical countries: A systematic review - Nyembwe, J.-P.K.B.; Ogundiran, J.O.; Chenari, B.; Simões, N.A.V.; Silva, M. (Energies, 2023)
Keywords: _z:class:countries

Comparative Assessment of The Thermal Comfort in Naturally Evolving Buildings in Hot and Dry Sahelian Climate: Case of The City of Ouagadougou in Burkina Faso - Ouedraogo, A.L.S.-N.; Hema, C.; Neya, I.; Nshimiyimana, P.; Yamegueu, D.; Coulibaly, Y.; Kabore, M.; A. (Journal of Materials Science and Surface Engineering, 2023)
Keywords: _z:class:countries

Short-Term Prediction for Indoor Temperature Control Using Artificial Neural Network - Park, Byung Kyu; Kim, Charn-Jung (Energies, 2023)
KerkoCite.ItemAlsoKnownAs: 10.3390/en16237724 5072953:N5XQFZYW openalex: W4388928717
Keywords: _z:class:countries; _z:class:themes; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10320 Neural Network Fundamentals and Applications; oa:topic:T12093 Dynamic Modeling of Plant Form and Growth; openalex:n:1; openalex:yes; selected_for:Predictive models for classroom conditions 2024

A systematic review highlights that there are multiple benefits of urban agriculture besides food - Pradhan, Prajal; Callaghan, Max; Hu, Yuanchao; Dahal, Kshitij; Hunecke, Claudia; Reußwig, Fritz; Lotze-Campen, Hermann; Kropp, Jürgen P. (Global Food Security, 2023)
Keywords: _z:class:countries

What can the education sector do to adapt to the forthcoming impacts of climate change? - Proctor, Jamie (2023)
Practitioner experience and reflections on what can be done specifically within the education sector to adapt and reduce the negative impacts of climate change on education.
KerkoCite.ItemAlsoKnownAs: 4874017:YDW5WRTT 5072953:6LKQUEDS
Keywords: _z:class:countries; _z:class:themes

Attention to climate change only temporarily diverted by COVID-19 - Repke, Tim; Callaghan, Max; Lamb, William F.; Lück, Sarah; Müller-Hansen, Finn; Minx, Jan C. (2023)
Keywords: _z:class:countries

To aspirate or not to aspirate – impact of active versus passive ventilation on urban heat (island) indicators - Ridder, K.; Maiheu, B.; Lauwaet, D. (Urban Climate, 2023)
Keywords: _z:class:countries

Using mobile air quality station data to identify critical areas in the city of Rio de Janeiro regarding pollutant concentrations - Rodrigues, João Rogério Borges Amorim; Dantas, Guilherme; Siciliano, Bruno; Silva, Cleyton Martins Da; Arbilla, Graciela (Revista Brasileira de Ciências Ambientais, 2023)
Recent studies have shown that tropospheric ozone, fine particulate matter and nitrogen dioxide are the urban air pollutants of major concern regarding human health effects. Monitoring air quality is a challenge in several cities, such as Rio de Janeiro, where the number of fixed-site air quality monitoring stations and their spatial distribution are insufficient to assess the extent of atmospheric pollutants. However, despite this lack of resources, the data obtained by mobile stations are a valuable means of determining which areas are experiencing critical air quality conditions, and provide key information for an air quality management program. The main purpose of this study was to conduct a critical analysis of data obtained by the Municipal Department of Environment and Climate (SMAC) mobile station in the period 2010–2018. Concentrations determined for particulate matter with a diameter ≤2.5 µm (PM2.5), O3, NO2, SO2 and CO showed that PM2.5 and O3 are the pollutants of major concern, and that the north of the city has higher air quality indices for these compounds. In addition, the south-west district had relatively high ozone levels, probably owing to low concentrations of NO2 in a volatile organic compound (VOC)-limited ozone formation regime. These factors should be considered by the municipal government in future discussions of control strategies for managing the city’s air quality. This study also shows the value of mobile stations in making a preliminary survey of pollutant concentrations, mainly in countries with limited financial investment in air quality management.
Keywords: _z:class:countries

Critical Review of the Literature on Thermal Comfort in Educational Buildings: Study of the Influence of the COVID-19 Pandemic - Romero, P.; Miranda, M.T.; Montero, I.; Sepúlveda, F.J.; Valero-Amaro, V. (Indoor Air, 2023)
Keywords: _z:class:countries

Progress on climate action: a multilingual machine learning analysis of the global stocktake - Sietsma, Anne J.; Groenendijk, Rick W.; Biesbroek, Robbert (Climatic Change, 2023)
Keywords: _z:class:countries

The First Generation of Machine Learning Applications for Tracking Climate Change Adaptation - Sietsma, Anne Jelmar (University of Leeds, 2023)
Keywords: _z:class:countries

Predicting indoor air temperature and thermal comfort in occupational settings using weather forecasts, indoor sensors, and artificial neural networks - Sulzer, Markus; Christen, Andreas; Matzarakis, Andreas (Building and Environment, 2023)
We present an approach to generate location-specific forecasts of indoor temperature (Ti) and thermal comfort and issue indoor heat warnings for occupational settings. Indoor forecasts are generated using standard outdoor weather forecasting products and an artificial neural network (ANN) trained on-site using local indoor measurements from a low-cost sensor system measuring Ti and indoor physiologically equivalent temperature (PETi). The outcomes are hourly indoor Ti and PET i forecasts. Different ANN-based forecast products using different predictors were concurrently tested at 121 workplaces in agricultural, industrial, storage, and office buildings using data for an entire annual cycle. A forecast was considered skillful when the Ti and PETi forecast was <2 K from actual measurements. The best-performing model used the predictors time of year, week, and day; solar position; and outdoor weather forecast variables to train and run an ANN to predict Ti or PETi. It had an annual average mean absolute forecast error of 0.87 K for Ti and 0.99 K for PET i over the next 24 h, with Pearson correlation coefficients of 0.98 and 0.97, respectively. Overall, 91% of Ti forecasts and 88% of PET i forecasts were skillful. Indoor forecasts showed larger errors in the summer than in the winter. We conclude that combining indoor data with weather forecasts using ANNs could be implemented widely to provide locationspecific indoor weather forecasts to improve and localize heat and health warning systems.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.buildenv.2023.110077 5072953:KPRMWQ9H openalex: W4319868632
Keywords: _important; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:indoor air temperature; oa:keyword:weather forecasts; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11244 Impact of Climate Change on Human Health; openalex:n:1; openalex:yes; selected_for:Predictive models for classroom conditions 2024

Enhancing environmental sustainability and green design: a guide for teacher colleges - TESP (2023)
KerkoCite.ItemAlsoKnownAs: 2129771:GIRKIUNP 2129771:GIRKIUNP 4874017:8AUMC9SS 5072953:V4UELA3B
Keywords: _z:class:countries; _z:class:themes; evidence_review_2

Indoor environmental quality, pupils’ health, and academic performance—A literature review - Toyinbo, O. (Buildings, 2023)
Keywords: _z:class:countries

Education and climate change – What retrofits could make classroom environments more conducive to learning? - Toyinbo, Oluyemi; Villavicencio, Xuzel (2023)
An output of the Open Development & Education, https://.opendeved.net/
ZenodoArchiveID: 8392534 ZenodoArchiveConcept: 8392533 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.0297 10.53832/opendeved.1014 2129771:WSD6C5HV 5072953:NESBVC9C
Keywords: _r:AddedByMyEducationEvidence; _z:class:countries; _z:class:themes

Exploration of Climate Change Awareness among Students at a South African Public University - Uwizeyimana, DE; Sekgobela, C (International Journal of Social Science Research and Review, 2023)
This study aimed to explore climate change awareness among students at a South African public university. The quantitative research method was applied in this study. Due to Covid-19 protocol requirements, a semi-structured electronic questionnaire was used to collect data from students at one South African public university whose name is withheld due to confidentiality requirements. One of the main findings of this study is that most respondents from this particular South African public university are aware that climate change is indeed happening. However, most participants in this research needed to be made aware of the international conventions that deal with climate change or climate change. These findings call for intensifying climate change awareness among South African university students across all media outlets. The study recommends that climate change and climate change awareness and combatting strategies be part and parcel of social and economic development programmes at local, national, continental, and global levels. It is vital to ensure that all citizens in general, as well as university students who are likely to be future leaders of communities and countries, have access to scientifically proven evidence on climate change and its impacts from reliable sources, some of which are highlighted in this study.
Keywords: _z:class:countries

Influence of building attributes on thermal comfort in naturally ventilated hospital wards in the hot-humid tropics of southeast Nigeria - Uzuegbunam, F.O.; Aja, F.N.; Ibem, E.O. (International Journal of Building Pathology and Adaptation, 2023)
Keywords: _z:class:countries

The “Improving Learning Through Classroom Experience” Study - Open Development & Education - Villavicencio Peralta,, Xuzel; Megogo Bokamba, Tania Elena (2023)
The Improvement Learning Through Classroom Experience (ILCE) is a programme that focuses on the relationship between natural conditions and school learning outcomes
KerkoCite.ItemAlsoKnownAs: 2129771:B3X8LHIP 4874017:76IP43B8 5072953:9ZQ3NZP5 5072953:9ZTUVJC9
Keywords: _publish; _z:class:countries; _z:class:themes

Possible Retrofit Interventions for Classrooms (infographic) - Villavicencio Peralta, Xuzel; Toyinbo, Oluyemi (2023)
KerkoCite.ItemAlsoKnownAs: 4874017:HEPNSHEQ 5072953:G44KLXMH
Keywords: _z:class:countries; _z:class:themes

What retrofits could make classroom environments more conducive to learning? - Villavicencio, Xuzel; Toyinbo, Oluyemi (2023)
This slide deck relates to a presentation given by OpenDevEd at The Education and Development Forum in Oxford (UKFIET 2023), as part of the sub-theme “Conflict, crisis, climate, and migration”. This presentation was part of the symposium called Climate, environment and education outcomes – Preliminary findings and practical experience from East and West Africa.
KerkoCite.ItemAlsoKnownAs: 2129771:HFX4BA8D 5072953:SAEMQCES
Keywords: _z:class:countries; _z:class:themes

Quantifying the influence of climate variability on armed conflict in Africa, 2000–2015 - Wang, Qian; Hao, Mengmeng; Helman, David; Ding, Fangyu; Jiang, Dong; Xie, Xiaolan; Chen, Shuai; Ma, Tian (Environment, Development and Sustainability, 2023)
Abstract Global climate change, expected to be one of the most severe challenges that human beings have ever encountered, has had far-reaching impacts on ecosystems and humans, among which the potentially increasing chance of violent conflict has raised attention recently. However, several years of research have produced no consensus regarding whether climate variability affects the risk of armed conflict and how it may affect conflict. In this study, we built a geographically disaggregated method to explore the relationship between climate variability from normal climate conditions and armed conflicts both on a local and regional scale. With the 10,993 conflict records acquired in 25 African countries over 16 years from 2000 to 2015, we estimated the effects of temperature and wet day variability on conflicts in agricultural and non-agricultural areas, respectively, on gridded 1° resolution. The results showed that deviations from the normal climate have a systematical impact on the risk of conflict: The risk of violence rises with increasing deviations from the temperature norms in both non-agricultural and agricultural areas. Regarding the rainfall variability, in non-agricultural areas, the risk of violence grows with increasing anomalous wet days, either more or fewer days than the annual average, while in agricultural areas, increases in violence risk only exhibit under the impact of fewer wet days than the annual average. We expect these findings would provide empirical support for policymakers and relevant organizations who need to prepare additional law enforcement and/or peacekeeping resources when climatic anomalies are detected.
Keywords: _z:class:countries

How do countries frame climate change? A global comparison of adaptation and mitigation in UNFCCC National Communications - Wright, Sarah Judith; Sietsma, Anne; Korswagen, Stefanie; Athanasiadis, Ioannis N.; Biesbroek, Robbert (Regional Environmental Change, 2023)
Abstract Self-reporting is an important mechanism of the UNFCCC to collect information about what countries are doing to achieve their climate change mitigation and adaptation targets and how much progress has been made. Here we empirically test four hypotheses about what countries prioritise in their self-reporting through the National Communications. Using quantitative text analysis methods (structural topic modelling and keyness statistics), we analyse over 600 submissions (from 1994 to 2019) and find evidence that vulnerable countries highlight impacts, vulnerability, and adaptation rather than mitigation targets, whereas high-emitting countries tend to focus their messaging more on mitigation. Despite the Paris Agreement being considered a “watershed moment”, we find no statistically significant increase in focus on climate solutions post-Paris, and no significant increase in attention to adaptation. Our global assessment and the methods used offer a novel perspective to understand what gets framed as important by governments. Finally, we provide reflections on how self-reporting mechanisms can be used for global stocktaking of progress on climate action.
Keywords: _z:class:countries

Implementing natural ventilation and daylighting strategies for thermal comfort and energy efficiency in office buildings in Burkina Faso - Zoure, A.N.; Genovese, P.V. (Energy Reports, 2023)
Keywords: _z:class:countries

An Investigation of Thermal Comfort in Classrooms in the Tropical Savanna Climate - Mustapha, Tajudeen; Hassan, Ahmad; Abdul Nasir, Muhammad; Onubi, Hilary (Journal of Advanced Research in Applied Sciences and Engineering Technology, 2022)
Studying the thermal environment in classrooms is essential due to its impact on students' health, teaching, learning, and productivity. In the Nigerian context, there is a general lack of thermal comfort studies, and none specifically relate to secondary school settings. This study aims to investigate students' perceptions of the indoor thermal environment and to determine the optimum temperature in naturally ventilated classrooms in the tropical savanna climate. Field investigations were conducted in free-running classrooms in Abuja to evaluate occupants' thermal comfort and perceptions. The study involves 901 pupils from 21 classrooms. Data were obtained through physical measurements of thermal comfort variables and a questionnaire survey on occupants' perceptions of the indoor thermal environment. The objective assessment indicated that 86% of the classrooms were inconsistent with the ASHRAE standard–55. Although 60% of the pupils were satisfied with their thermal environment, 78% preferred a cooler than neutral temperature. The result revealed a comfort temperature of 28.9 oC. The results extend the literature on thermal comfort in classrooms to the tropical savannah climate of the west African sub-region, which has received little attention in earlier research. The findings provide foundation data for developing a comfort standard for classrooms in the zone.
KerkoCite.ItemAlsoKnownAs: 10.37934/araset.29.1.6275 2129771:BFL237GS 4874017:XFJ6HDUH
Keywords: evidence_review

Predicting Climate Change Related Extreme Natural Disasters Using Machine Learning in Zambia - Phiri, David; Chembe, Christopher (Zambia ICT Journal, 2022)
One of the most important concerns affecting humanity today is climate change that has led to increased frequency of natural disasters that threaten social and economic stability to populations. Zambia’s vulnerability to the threat of disasters remains high because the country still lacks an effective Early Warning System (EWS). This study recognises the need to evaluate various Machine Learning (ML) algorithms, that have been successfully implemented in disaster prediction, in order to develop a model for Zambia. Six ML algorithms, namely; Logistic Regression (LR), Random Forest (RF), K-Nearest Neighbor (KNN), Gaussian Naive Bayes (GNB), Decision Tree (DT), and Support Vector Machine (SVM), have been compared from which the best performing is chosen. The historical climate data is obtained from the Zambia Meteorological Department (ZMD) while historical natural disasters data was obtained online because it is not locally available. The study results show that LR and SVM algorithms performed better than the others, both scoring 73.0% accuracy, respectively. LR is chosen to produce the final model because it has a shorter computational time compared to SVM. The model is then incorporated in a web service and android application for deployment. However, the high number of outliers, missing values and highly imbalanced classes affect the performance of the model. ML data cleaning and feature engineering techniques, such as Data Imputation and Oversampling Techniques, are applied but certain challenges still persist because these tools have their own flaws. Therefore, the model’s performance in a real-world data environment is likely to be affected.
openalex:W4313414138 mag: KerkoCite.ItemAlsoKnownAs: 10.33260/zictjournal.v6i1.128 5072953:2IZA52UE 5072953:2WA5PT34
Keywords: C:Zambia; _z:class:countries; _z:class:themes; _z:no_pdf; oa:sdg:13 Climate action; oa:topic:T10747 Community Resilience to Natural Disasters; oa:topic:T10930 Global Flood Risk Assessment and Management; oa:topic:T13650 Scientific Computing and Data Analysis with Python; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

An investigation of thermal comfort in classrooms in the tropical Savanna climate - Mustapha, Tajudeen Dele; Hassan, Ahmad Sanusi; Nasir, Muhammad Hafeez Abdul; Onubi, Hilary Omatule (Journal of Advanced Research in Applied Sciences and Engineering Technology, 2022)
Studying the thermal environment in classrooms is essential due to its impact on students' health, teaching, learning, and productivity. In the Nigerian context, there is a general lack of thermal comfort studies, and none specifically relate to secondary school settings. This study aims to investigate students' perceptions of the indoor thermal environment and to determine the optimum temperature in naturally ventilated classrooms in the tropical savanna climate. Field investigations were conducted in free-running classrooms in Abuja to evaluate occupants' thermal comfort and perceptions. The study involves 901 pupils from 21 classrooms. Data were obtained through physical measurements of thermal comfort variables and a questionnaire survey on occupants' perceptions of the indoor thermal environment. The objective assessment indicated that 86% of the classrooms were inconsistent with the ASHRAE standard–55. Although 60% of the pupils were satisfied with their thermal environment, 78% preferred a cooler than neutral temperature. The result revealed a comfort temperature of 28.9 oC. The results extend the literature on thermal comfort in classrooms to the tropical savannah climate of the west African sub-region, which has received little attention in earlier research. The findings provide foundation data for developing a comfort standard for classrooms in the zone.
Number: 1 openalex:W4313580688.json KerkoCite.ItemAlsoKnownAs: 2129771:SCM2XDX6 2129771:SCM2XDX6 2129771:SCM2XDX6 2129771:SCM2XDX6 10.37934/araset.29.1.6275 4874017:X7YWDRM9 5072953:FV66BCLI 5072953:KS9NTX56
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; evidence_review_2; oa:keyword:thermal comfort; oa:keyword:tropical savanna climate; oa:sdg:13 Climate action; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T12950 Learning Environments in Education; thermal sensation

Climate change and sustainable development perceptions of university students in Lahore, Pakistan - Nadeem, Obaidullah; Nawaz, Mariyum (International Research in Geographical and Environmental Education, 2022)
The main aim of this study is to assess university students’ perceptions of climate change (CC) and sustainable development (SD). It also reviews existing curricula of various degree programs and obtains students’ opinion on how to integrate these concepts into the curricula and improve teaching methods and students’ learning. In total, 400 students from two of the oldest and renowned public sector higher education institutions (HEIs) in Lahore, Pakistan participated in this study. The results revealed that students have better perceptions of CC than of SD even though very few degree programs cover these concepts in their curriculum. Generally, the students perceived that human beings’ interference with the natural settings through their development actions is the main reason for climate change. They prefer environmental protection over economic growth. It is concluded that the integration of courses on CC and SD and promoting action-oriented case study research in the curriculum of the degree programs being offered by the HEIs can help improve learning. Hence, the HEIs of developing countries with similar socio-economic contexts need to do more to train our future generation of professionals to facilitate achieving the goal of sustainable development.
openalex: W4311691595
Keywords: C:Pakistan; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:sustainable development; oa:keyword:sustainable development perceptions; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; oa:topic:T11835 Sustainability Education in Higher Education Institutions; openalex:import; openalex:yes

German Flood Deaths Highlight Climate Change Risks for People with Disabilities (2022)
openalex: W4311557334
Keywords: _z:class:countries; openalex:import; openalex:yes

Improving Learning Through Classroom Experience in East Africa: Temperature, Lighting, and Sound Quality – Inception report - Haßler, Björn; Villavicencio Peralta, Xuzel Ana; Macharia, Grace; Toyinbo, Oluyemi; Nambatya, Mauricia; Mtebe, Joel; Schaffer, Jens; Wargocki, Pawel; Adam, Taskeen (Open Development & Education, 2022)
KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.0286 2129771:44YQ4VEG 2129771:GSFGV6IU 5072953:CQXY9UJD openalex: W4365398634
Keywords: Author:OpenDevEd; C:Tanzania; _r:AddedByZotZen; _z:class:countries; _z:class:themes; evidence_review; oa:keyword:classroom experience; oa:topic:T10162 Transformative Potential of Blended Learning in Education; oa:topic:T12950 Learning Environments in Education; oa:topic:T13412 Impact of Interactive Whiteboards in Education; openalex:n:1; openalex:yes

Climate change and sustainability education in India and the place for arts-based practice: reflections from East Kolkata Wetlands - Jones, Verity; Mitra, Saptarshi; Gupta, Nobina (London Review of Education, 2022)
In 2019 India was ranked seventh most affected nation by climate change, yet 65 per cent of the Indian population had not heard of climate change. India’s revised National Education Policy mentions climate change and environmental issues as part of its work towards reaching the United Nation’s Sustainable Development Goals. However, to date, climate education in India has tended to remain the responsibility of the secondary science teacher in many schools where resources are limited. Following calls for a more holistic and multidisciplinary approach – where students can link environmental issues with their lives – we reflect on three arts-based climate education exemplars with students from the East Kolkata Wetlands (EKW) (n = 150, 10–17-year-olds). We consider how these frame climate change and sustainable education as a collective learning experience, rather than as scientific concepts alone. We respond to Szczepankiewicz et al.’s model for climate education and propose that teacher training in the EKW context can be conceptualised through a three-stage, interconnected approach to pedagogy: building concepts, learning through hands-on activities and building communities is central. We suggest that these three generalisable tenets of student teacher practice should be explored in other areas of ecological fragility, as well as in spaces of economic insecurity.
openalex: W4312222934
Keywords: C:India; _z:class:countries; _z:class:themes; oa:keyword:east kolkata wetlands; oa:keyword:sustainability education; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T12950 Learning Environments in Education; oa:topic:T12997 Experiential Education and Adventure Therapy; openalex:import; openalex:yes

Healthy indoor air is our fundamental need: the time to act is now - Morawska, Lidia; Marks, Guy B; Monty, Jason (Medical Journal of Australia, 2022)
A ccording to estimates by the World Health Organization, polluted outdoor air kills over 7 million people annually. In 2021, the WHO published new air quality guidelines to serve as the basis for setting or updating national ambient air quality standards. This document can also be the basis for setting national indoor air standards, as the recommended air pollution levels apply both to outdoor and indoor air. Will national jurisdictions update their indoor air quality (IAQ) standards? The shocking reality is that most countries, including Australia, do not have any IAQ standards or even plans to establish them. The handful of countries that have standards do not have the means and procedures to enforce them; therefore, they do not serve their purpose.
Keywords: _important; _z:class:countries

Indoor air quality and learning: evidence from a large field study in primary schools - Palacios, Juan; Eichholtz, Piet; Kok, Nils; Duran, Nicolas (2022)
Governments devote a large share of public budgets to construct, repair, and modernize school facilities. However, evidence on whether investments in the physical state of schools translate into better student outcomes is scant. In this study, we report the results of a large field study on the implications of poor air quality inside classrooms − a key performance measure of school mechanical ventilation systems. We continuously monitor the air quality (i.e., CO2), together with a rich set of indoor environmental parameters in 216 classrooms in the Netherlands. We link indoor air quality conditions to the outcomes on semi-annual nationally standardized tests of 5,500 children, during a period of five school terms (from 2018 to 2020). Using a fixed-effects strategy, relying on within-pupil changes in air quality conditions and test results, we document that exposure to poor indoor air quality during the school term preceding a test is associated with significantly lower test results: a one standard deviation increase in the school-term average daily peak of CO2 leads to a 0.11 standard deviation decrease in subsequent test scores. The estimates based on plausibly exogenous variation driven by mechanical ventilation system breakdown events confirm the robustness of the results. Our results add to the ongoing debate on the determinants of student human capital accumulation, highlighting the role of school infrastructure in shaping learning outcomes.
KerkoCite.ItemAlsoKnownAs: 2129771:3L6RGSNQ 2129771:3L6RGSNQ 10.2139/ssrn.4296077 4874017:GFF6PS5F 5072953:F7X6I96S openalex: W4318613216
Keywords: Academic Performance; C:Netherlands; Education; Human Capital; Indoor Air Quality; School Infrastructure; _z:class:countries; _z:class:themes; evidence_review_2; oa:keyword:indoor air quality; oa:topic:T12950 Learning Environments in Education; openalex:n:1; openalex:yes

An Occupant-Centric Control Strategy for Indoor Thermal Comfort, Air Quality and Energy Management - Wang, Zu; Calautit, John Kaiser; Tien, Paige Wenbin; Wei, Shuangyu; Zhang, Wuxia; Wu, Yupeng; Xia, Liang (2022)
Recently, Occupant-Centric Control (OCC) strategies have gained mounting interest. Previous studies made use of OCC strategies for adjusting the operation of heating/cooling systems, improving indoor thermal comfort and governing mechanical ventilation systems. However, a very limited number of studies have applied OCC strategies to natural ventilation systems. Further, the feasibility of establishing OCC strategies for controlling indoor thermal comfort, energy use and specifically air quality has received much less attention and investigation. This paper presented an Occupant-Centric Heating and Natural Ventilation Control (OCHNVC) strategy for enhancing indoor thermal comfort, building energy performance and indoor air quality. Firstly, real-time profiles of occupant behavior and window opening in a case study building were collected using artificial intelligence (AI)-powered cameras and deep vision algorithms. Secondly, shallow artificial-neural-networks predictive models were established for forecasting the responses of the studied building to different levels of occupant behavior and window opening behavior. Thirdly, an OCHNVC strategy tailored to the studied room was proposed and applied to the studied room. The strategy could lower heating energy consumption by between 0.6% and 29.0% and improve the level of indoor thermal comfort by between 0% and 58.8%, relative to a conventional control strategy. Moreover, the conventional window control strategy only maintained indoor CO2 concentrations below 1,000 ppm for 59.7% of the period that occupants were within the studied room, while the proposed controller could do so for 89.2% of the period. Future works shall focus on experimentally deploying the strategy to real buildings and evaluating its performance.
KerkoCite.ItemAlsoKnownAs: 10.2139/ssrn.4293660 5072953:6JM8D7BH openalex: W4318815365
Keywords: Buildings; Deep learning; HVAC temperature setpoint control; Indoor air quality; Occupant-Centric control; Thermal comfort; _z:class:countries; _z:class:themes; _z:not_duplicate; artificial intelligence; oa:keyword:indoor thermal comfort; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; openalex:n:1; openalex:yes

An Occupant-Centric Control Strategy for Indoor Thermal Comfort, Air Quality and Energy Management - Wang, Zu; Calautit, John Kaiser; Tien, Paige Wenbin; Wei, Shuangyu; Zhang, Wuxia; Wu, Yupeng; Xia, Liang (2022)
Recently, Occupant-Centric Control (OCC) strategies have gained mounting interest. Previous studies made use of OCC strategies for adjusting the operation of heating/cooling systems, improving indoor thermal comfort and governing mechanical ventilation systems. However, a very limited number of studies have applied OCC strategies to natural ventilation systems. Further, the feasibility of establishing OCC strategies for controlling indoor thermal comfort, energy use and specifically air quality has received much less attention and investigation. This paper presented an Occupant-Centric Heating and Natural Ventilation Control (OCHNVC) strategy for enhancing indoor thermal comfort, building energy performance and indoor air quality. Firstly, real-time profiles of occupant behavior and window opening in a case study building were collected using artificial intelligence (AI)-powered cameras and deep vision algorithms. Secondly, shallow artificial-neural-networks predictive models were established for forecasting the responses of the studied building to different levels of occupant behavior and window opening behavior. Thirdly, an OCHNVC strategy tailored to the studied room was proposed and applied to the studied room. The strategy could lower heating energy consumption by between 0.6% and 29.0% and improve the level of indoor thermal comfort by between 0% and 58.8%, relative to a conventional control strategy. Moreover, the conventional window control strategy only maintained indoor CO2 concentrations below 1,000 ppm for 59.7% of the period that occupants were within the studied room, while the proposed controller could do so for 89.2% of the period. Future works shall focus on experimentally deploying the strategy to real buildings and evaluating its performance.
KerkoCite.ItemAlsoKnownAs: 10.2139/ssrn.4293660 5072953:6JM8D7BH openalex: W4318815365
Keywords: Buildings; Deep learning; HVAC temperature setpoint control; Indoor air quality; Occupant-Centric control; Thermal comfort; _z:class:countries; _z:class:themes; _z:not_duplicate; artificial intelligence; oa:keyword:indoor thermal comfort; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; openalex:n:1; openalex:yes

Analysis of input parameters for deep learning-based load prediction for office buildings in different climate zones using eXplainable Artificial Intelligence - Chung, Woong June; Liu, Chunde (Energy and Buildings, 2022)
Simplification of input variables can increase the applicability of Artificial Intelligence (AI) in building load prediction. The most essential inputs for AI therefore need to be identified via a significance level test. In this study, the significance of the input parameters was evaluated using the standardized regression coefficient (SRC) and Explainable AI methods, i.e., Local Interpretable Model-agnostic Explanations (LIME) and SHapley Additive exPlanations (SHAP). To consider various types of office buildings operating under different climates, the constraints of the U.S. Department of Energy reference buildings with the Latin hypercube sampling were used to generate two thousand building models for each of five climate zones classified by the Köppen and Geiger system. The number and types of essential inputs for deep learning-based building load prediction were identified based on SRC, LIME, and SHAP. By comparison, the SHAP method gave the smallest number of essential inputs for accurate load prediction. In addition, the types of essential inputs varied with different climates. This study presented the potential elimination of weather sensors with time variables depending on the climate conditions. It would help building practitioners and non-experts to determine the essential inputs to build up a simple but accurate deep learning-based building system.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2022.112521 5072953:AN67QK2Q openalex: W4298006992
Keywords: Artificial intelligence; Building load predictions; Local interpretable model-agnostic explanations; Long Short-term memory networks; SHapley additive explanations; The köppen and geiger climate classification system; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:load prediction; oa:sdg:13 Climate action; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11052 Electricity Price and Load Forecasting Methods; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:n:1; openalex:yes

Primary school students and climate change–an interview study in Finland and Tanzania - Sjöblom, Pia; Wolff, Lili-Ann; Vuorenpää, Sari; Grahn, Rebecka (Journal of Cleaner Production, 2022)
Climate change is a complex and wicked problem, which needs to be addressed through relevant climate change education. However, the preconditions for combatting climate change differ in different parts of the world, depending on physical, cultural and social circumstances. The diversity of circumstances also influences the implementation of climate change in education. Therefore, in this article we have chosen to examine climate change education (CCE) based on an interview study in two distinct school contexts. More specifically, the cases aim to explore Finnish and Tanzanian primary students' views on climate change. A hermeneutical approach guided the analysis, and a significant result was that most of the students understood the severity of climate change. Nevertheless, some misconceptions regarding both causes, consequences and mitigation of climate change were also obvious. In addition, the analysis revealed interesting variations in the students' reasoning, which relate to their different contexts. Unquestionably, the sample size in this study is limited, and further research is needed for a more detailed picture of Finnish and Tanzanian students’ views.
openalex:W4308741334 mag: KerkoCite.ItemAlsoKnownAs: 10.1016/j.jclepro.2022.135099 5072953:23IV8WAW
Keywords: C:Finland; C:Tanzania; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:climate change–an; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Implementation of Teacher Capacitation Programs to Integrate Climate Change Education: The Case Study of Geography Teaching in South African Secondary Schools - Mavuso, Mzuyanda Percival; Olawumi, Kayode Babatunde; Khalo, Xolani; Kafu-Quvane, Babalwa; Mzilikazi, Busiswa (International Journal of Learning, Teaching and Educational Research, 2022)
Countries all over the world are experiencing the devastating havoc of climate change. Drastic efforts directed at integrating climate change education into the school curriculum in South African Secondary schools have been unsuccessful due to a lack of training support for teachers teaching Climate Change Education in secondary schools. The purpose of this paper was to explore the role of teacher capacitation programs in assisting Geography teacher to integrate climate change education in their lessons. Shulman’s Model of Pedagogical Reasoning served as theoretical lenses for the study. Five secondary schools out of twenty which participated in the five days’ training program conducted by one higher education institution were purposefully selected. Data for the study was generated through one-on-one semi-structured interviews conducted with five participating Geography teachers in the selected schools according to the geographical location and close proximity to the training provider. It emerged from the data that teachers were lacking content and pedagogical knowledge on Climate Change Education and this capacitation program assisted in bridging that gap. The study concludes that training programs were according to selected Geography teachers’ views responsible for the improved pedagogical practices in the classroom. It is therefore recommended that teacher professional development programs on Climate Change Education for Geography teachers be organized on a continuous basis.
openalex:W4310990179 mag: KerkoCite.ItemAlsoKnownAs: 10.26803/ijlter.21.11.5 5072953:PEA64VQ5
Keywords: C:South Africa; _z:class:countries; _z:class:themes; oa:keyword:climate change education; oa:keyword:geography teaching; oa:keyword:teacher capacitation programs; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T12904 Agricultural Education and School Gardening Research; oa:topic:T14482 Innovations in Education Technology and Pedagogy; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Review of low-cost sensors for indoor air quality: Features and applications - Ródenas García, Milagros; Spinazzé, Andrea; Branco, Pedro T.B.S.; Borghi, Francesca; Villena, Guillermo; Cattaneo, Andrea; Di Gilio, Alessia; Mihucz, Victor G.; Gómez Álvarez, Elena; Lopes, Sérgio Ivan; Bergmans, Benjamin; Orłowski, Cezary; et al. (Applied Spectroscopy Reviews, 2022)
Humans spend the majority of their time indoors, where they are potentially exposed to hazardous pollutants. Within this context, over the past few years, there has been an upsurge of low-cost sensors (LCS) for the measurement of indoor air pollutants, motivated both by recent technological advances and by increased awareness of indoor air quality (IAQ) and its potential negative health impacts. Although not meeting the performance requirements for reference regulatory-equivalent monitoring indoors, LCS can provide informative measurements, offering an opportunity for high-resolution monitoring, emission source identification, exposure mitigation and managing IAQ and energy efficiency, among others. This article discusses the strengths and limitations that LCS offer for applications in the field of IAQ monitoring; it provides an overview of existing sensor technologies and gives recommendations for different indoor applications, considering their performance in the complex indoor environment and discussing future trends.
Keywords: _important; _z:class:countries

Students establish micro-forest to conserve the environment (2022)
The Aga Khan Education Services (AKES) of Tanzania has joined hands with the Aga Khan Foundation Tanzania (AKF) and the Ismaili Civic’s joint climate resilience initiative by supporting the establishment of a micro-forest in efforts aimed to reduce carbon footprint and conserve the environment.
KerkoCite.ItemAlsoKnownAs: 4874017:KMVLWY23 5072953:M7PV5GQJ
Keywords: C:Tanzania; _z:class:countries; _z:class:themes

The impact of climate change related extreme weather events on people with pre-existing disabilities and chronic conditions: a scoping review - Lindsay, Sally; Hsu, Shaelynn; Ragunathan, Sharmigaa; Lindsay, John B. (Disability and Rehabilitation, 2022)
Purpose People with disabilities experience a disproportionate impact of extreme weather events and there is a critical need to better understand the impact that climate change has for them. Most previous reviews focus on the risk of acquiring a new disability or injury after a climate-related event and not the impact on people with pre-existing disabilities or chronic conditions, which is the purpose of this study.Methods We conducted a scoping review while searching seven international databases that identified 45 studies meeting our inclusion criteria.Results The studies included in our review involved 2 337 199 participants with pre-existing disabilities and chronic conditions across 13 countries over a 20-year period. The findings demonstrated the following trends: (1) the impact on physical and mental health; (2) the impact on education and work; (3) barriers to accessing health and community services (i.e., lack of access to services, lack of knowledge about people with disabilities, communication challenges, lack of adequate housing); and (4) coping strategies (i.e., social supports and connecting to resources) and resilience.Conclusions Our findings highlight the critical need for rehabilitation clinicians and other service providers to explore opportunities to support their clients in preparing for climate-related emergencies.
openalex: W4310053773
Keywords: _z:class:countries; openalex:import; openalex:yes

Effects from Exposures to Human Bioeffluents and Carbon Dioxide - Zhang, Xiaojing; Mishra, Asit; Wargocki, Pawel (2022)
Keywords: _z:class:countries

Learning continuity in response to climate emergencies: preliminary insights on supporting learning continuity following the 2022 Pakistan floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Kaye, Tom; Perry, Freya (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0134 4874017:R257YPYJ 5072953:UXHFMYPM
Keywords: C:Pakistan; _z:class:countries; _z:class:themes

Level of Awareness of Climate Change Concepts and Issues Among Pre-Service Chemistry Teachers at Mufulira College of Education in Zambia - TEBEKA, JOHN (Journal of Global Ecology and Environment, 2022)
The aim of this study was to investigate the level of awareness of climate change concepts and issues among the pre-service chemistry teachers at Mufulira College of Education in Zambia. The study was motivated by the need to enable teachers and learners address climate change challenges which are among the issues facing the world today. The study used a qualitative survey targeted at all the 334 pre-service chemistry teachers from Mufulira College of Education as at 2021 when the research was carried out. However, data was only collected from 303 participants who completed questionnaires, representing a response rate of over 90%. The survey explored the students’ awareness levels on the different causes of climate change, the impact of climate change on the environment and the students’ ability to recognize the different mitigation measures of climate change. The study established that on average 60% of the students could only go as far as recalling concepts and issues of climate change but could not critically explain how climate change was caused and why it was a threat to the environment. At the same time climate change issues and concepts did not form part of the priorities for assessment in the pre-service chemistry curriculum at the selected college. It is recommended that a policy is created that ensures that climate change issues and concepts are given the attention they deserve. There is need to urgently develop teaching and learning materials on climate change education for the pre-service chemistry education curriculum.
openalex:W4308841902 mag: KerkoCite.ItemAlsoKnownAs: 10.56557/jogee/2022/v16i47926 5072953:RQA2WU35
Keywords: C:Zambia; _z:class:countries; _z:class:themes; oa:keyword:climate change concepts; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11835 Sustainability Education in Higher Education Institutions; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Experimental Investigation and Optimization of a Glazed Transpired Solar Collector - Teodosiu, Catalin Ioan; Sima, Catalin; Croitoru, Cristiana; Bode, Florin (Applied Sciences, 2022)
Solar air collectors are increasingly used nowadays due to their important potential in reducing the energy consumption of buildings. In this context, glazed transpired solar collectors (GTCs) represent an interesting solution, but this type of solar air collector is less studied. Consequently, the objective of this work is to thoroughly assess the performance of a GTC prototype under real long-term climatic conditions. First, the design of the GTC is optimized based on methodically experimental tests. The results show that the GTC configuration with a 30 mm air gap among the absorber and the glazing leads to improved heat transfer efficiency and superior global effectiveness, regardless of airflow rates through the solar air collector. This optimized GTC configuration is further studied by integration within the façade of a full-scale experimental building (container-type, light structure). Comparative experimental studies are then carried out concerning the heating energy consumption and ventilation load of the experimental building without/with GTC implemented in the ventilation system, under Bucharest real weather conditions. The data achieved indicate that the GTC prototype is capable of substantially reducing the ventilation load: up to 25% for low solar radiation (below 200 W/m2) and over 50% (achieving even 90%) for moderate solar radiation (between 250 and 380 W/m2). Finally, for high solar radiation (over 400 W/m2), the GTC outlet air temperature exceeds the interior temperature set-point (22 °C) of the experimental building.
Keywords: _z:class:countries

Reflecting on climate change education (CCE) initiatives for mitigation and adaptation in South Africa - Sibanda, Arorisoe; Manik, Sadhana (Environmental Education Research, 2022)
South Africa remains the largest emitter of carbon dioxide, a greenhouse gas, in Africa. As such despite the glowing government policy documents addressing climate change, efforts towards achieving the targets of the sustainable development goals (especially SDG 13) at grassroots level remain significant. We identified relevant published articles and grey literature on CCE. A thematic analysis of these publications focused on identifying the common CCE initiatives being actioned in SA. The major themes on CCE in respect of mitigation and adaption included: CCE initiatives promoted and articulated through the media, school community projects, the development of the school and higher education curricula for CCE, the development of associated teaching materials and guides. The findings revealed that despite the evidence of robust education initiatives for climate change mitigation and adaptation in published reports, there was greater emphasis on short term responses at the expense of long-term mitigation efforts.
openalex:W4308587747 mag: KerkoCite.ItemAlsoKnownAs: 10.1080/13504622.2022.2140781 5072953:WI3RM395
Keywords: C:South Africa; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:climate change; oa:keyword:climate change education; oa:sdg:13 Climate action; oa:topic:T10119 Sustainability Transitions and Resilience in Social-Ecological Systems; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Teaching about climate change: Possibilities and challenges in Australian adult literacy programs - Yasukawa, Keiko (Journal of Adolescent & Adult Literacy, 2022)
Abstract Australia's natural environment poses challenges for human inhabitants and will continue to pose novel challenges in an era of climate change. However, the resources that people can access to respond to climate change are diverse and unequally distributed. While this suggests a role for education, especially for those who are most socially and economically vulnerable, integrating climate change literacy into educational programs is not straightforward in all sectors. Studies have shown that increased standardization of curricula constrain teacher autonomy and pose dilemmas for teachers faced with tensions between curricular requirements and their professional judgment about appropriate pedagogy and curricula. This article considers the possibility of educational intervention for socially and economically disadvantaged adults with limited English language and literacy skills by investigating how a group of teachers in accredited literacy courses viewed their role in addressing climate change and environmental literacy in their literacy classes.
openalex: W4308261794
Keywords: C:Australia; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T12545 Education for Global Citizenship in a Globalized World; oa:topic:T14007 Place-Based Education in Rural Communities; openalex:import; openalex:yes

Teaching about climate change: Possibilities and challenges in Australian adult literacy programs - Yasukawa, Keiko (Journal of Adolescent & Adult Literacy, 2022)
Abstract Australia's natural environment poses challenges for human inhabitants and will continue to pose novel challenges in an era of climate change. However, the resources that people can access to respond to climate change are diverse and unequally distributed. While this suggests a role for education, especially for those who are most socially and economically vulnerable, integrating climate change literacy into educational programs is not straightforward in all sectors. Studies have shown that increased standardization of curricula constrain teacher autonomy and pose dilemmas for teachers faced with tensions between curricular requirements and their professional judgment about appropriate pedagogy and curricula. This article considers the possibility of educational intervention for socially and economically disadvantaged adults with limited English language and literacy skills by investigating how a group of teachers in accredited literacy courses viewed their role in addressing climate change and environmental literacy in their literacy classes.
openalex: W4308261794
Keywords: C:Australia; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T12545 Education for Global Citizenship in a Globalized World; oa:topic:T14007 Place-Based Education in Rural Communities; openalex:import; openalex:yes

Decolonizing Climate Change Education: Evidence from an Empirical Study in Ghana (Journal of Education and Practice, 2022)
Climate change education plays a significant role in the fight against climate change. Yet the knowledges of Indigenous Peoples who have been disproportionately impacted and are at the frontlines of climate change have not been given enough attention in climate change education. To enhance the capacity of communities to adapt to climate change, calls are increasing for climate change education to be decolonized. Contributing to this call, the researcher partnered with a rural community, Boania, in Northern Ghana to integrate Indigenous Ecological Knowledge into environmental and climate change education in a rural primary school. A community-based research approach and an Indigenous research methodology in the form of two-eyed seeing were adopted to guide the project. The purpose of the study was to decolonize environmental and climate change education by integrating Indigenous Ecological Knowledge into programs. It emerged that the consideration of holistic Indigenous epistemologies in climate change education re-emphasized our inseparability from non-humans and improved the children’s knowledge about the community’s local environment. Additionally, decolonizing the concept of climate change created the space for acknowledging community-led climate adaptation efforts. Broadly, the study provided a model for decolonizing climate change education in Ghana. Keywords:community-based research; climate change education; decolonization; Indigenous Ecological Knowledge; Indigenous epistemologies DOI: 10.7176/JEP/13-32-06 Publication date: November 30 th 2022
openalex:W4310633966 mag: KerkoCite.ItemAlsoKnownAs: 2129771:7ZAXFZX7 2129771:7ZAXFZX7 10.7176/jep/13-32-06 5072953:4KPXTX6I
Keywords: C:Ghana; _z:class:countries; _z:class:themes; evidence_review_2; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T14007 Place-Based Education in Rural Communities; openalex:import; openalex:n:1; openalex:yes

Retrofitting measures for climate resilience: Enhancing the solar performance of Malaysian school buildings with passive design concepts - Alwi, Najah Md; Flor, J-F; Anuar, Nur Hidayah Khairul; Mohamad, J; Hanafi, N N H; Muhammad, N H; Zain, M H K M; Nasir, M R M (IOP Conference Series: Earth and Environmental Science, 2022)
Climate-sensitive school buildings can enhance students’ learning performance and reduce the building’s overall energy consumption. This paper reports on a post-occupancy study of contemporary school buildings in Malaysia, assessing problems of solar heat gain. The research aims to propose retrofitting measures based on passive design principles adapted specifically for the Malaysian tropical climate to strengthen the resilience of local school buildings in a global climate emergency. On-site measurements in two different schools provided the empirical basis for the design modifications. The monitoring procedure included site observations, extended temperature and humidity measurements, and daylight analysis. A virtual classroom model was generated based on the on-site measurements, and a parametric simulation study was conducted to evaluate the proposed retrofit measures’ effectiveness. The model variables were evaluated and compared to identify the passive design elements that significantly impact heat gains and thermal comfort. The results showed that increasing roof overhangs to 1500 mm for additional shading, sensitive selection of roof materials and colours of white-painted zinc roof, and reduction of window-to-wall ratio by 30% to the operable windows helps to reduce solar gains by 6% to improve comfort conditions within the classrooms. Overall, the study provided evidence of how passive solar building design would benefit the climate resilience of Malaysian schools.
openalex: W4310789718
Keywords: C:Malaysia; _z:class:countries; _z:class:themes; evidence_review_2; oa:keyword:climate resilience; oa:keyword:malaysian school buildings; oa:sdg:13 Climate action; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:import; openalex:yes

Retrofitting measures for climate resilience: Enhancing the solar performance of Malaysian school buildings with passive design concepts - Alwi, Najah Md; Flor, J-F; Anuar, Nur Hidayah Khairul; Mohamad, J; Hanafi, N N H; Muhammad, N H; Zain, M H K M; Nasir, M R M (IOP Conference Series: Earth and Environmental Science, 2022)
Climate-sensitive school buildings can enhance students’ learning performance and reduce the building’s overall energy consumption. This paper reports on a post-occupancy study of contemporary school buildings in Malaysia, assessing problems of solar heat gain. The research aims to propose retrofitting measures based on passive design principles adapted specifically for the Malaysian tropical climate to strengthen the resilience of local school buildings in a global climate emergency. On-site measurements in two different schools provided the empirical basis for the design modifications. The monitoring procedure included site observations, extended temperature and humidity measurements, and daylight analysis. A virtual classroom model was generated based on the on-site measurements, and a parametric simulation study was conducted to evaluate the proposed retrofit measures’ effectiveness. The model variables were evaluated and compared to identify the passive design elements that significantly impact heat gains and thermal comfort. The results showed that increasing roof overhangs to 1500 mm for additional shading, sensitive selection of roof materials and colours of white-painted zinc roof, and reduction of window-to-wall ratio by 30% to the operable windows helps to reduce solar gains by 6% to improve comfort conditions within the classrooms. Overall, the study provided evidence of how passive solar building design would benefit the climate resilience of Malaysian schools.
openalex: W4310789718 KerkoCite.ItemAlsoKnownAs: 10.1088/1755-1315/1102/1/012014 2129771:BW22RJ67 4874017:97DE7AX9 5072953:AET5KVED
Keywords: C:Malaysia; _z:class:countries; _z:class:themes; evidence_review; oa:keyword:climate resilience; oa:keyword:malaysian school buildings; oa:sdg:13 Climate action; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:import; openalex:yes

Representations of Humans, Climate Change, and Environmental Degradation in School Textbooks in Ghana and Malawi - Ress, Susanne; Kendall, Nancy; Friedson-Ridenour, Sophia; Ampofo, Yaa Oparebea (Comparative Education Review, 2022)
Youth in sub-Saharan Africa are extremely vulnerable to the negative consequences of climate change and environmental degradation. The interest in education for sustainable development (ESD) to support African youth in learning about and adapting to climate change is growing in response. This study examines the messages about human-earth relationships, environmental change, and responsibilities for mitigation that are presented in official grade 8 Ghana and Malawi textbooks. Utilizing a political ecology framework, it shows that the curricula normalize an anthropocentric earth view that disappears global power dynamic, neglects widespread commodification of scarce resources, fails to question the developmentalist dream of endless growth, and translates local ecological contexts into universal commodities. We discuss the need to develop educational theories and practices that account for the complexity and deep contextuality of human-earth relationship if we hope to help students around the world envision alternative ways more likely to ensure species survival.
openalex:W4308734415 mag: KerkoCite.ItemAlsoKnownAs: 10.1086/722101 5072953:983CDNKW
Keywords: C:Ghana; C:Malawi; C:Mali; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:climate change; oa:topic:T10119 Sustainability Transitions and Resilience in Social-Ecological Systems; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

A review of thermal comfort in primary schools and future challenges in machine learning based prediction for children - Lala, Betty; Hagishima, Aya (Buildings, 2022)
Children differ from adults in their physiology and cognitive ability. Thus, they are extremely vulnerable to classroom thermal comfort. However, very few reviews on the thermal comfort of primary school students are available. Further, children-focused surveys have not reviewed the state-of-the-art in thermal comfort prediction using machine learning (AI/ML). Consequently, there is a need for discussion on children-specific challenges in AI/ML-based prediction. This article bridges these research gaps. It presents a comprehensive review of thermal comfort studies in primary school classrooms since 1962. It considers both conventional (non-ML) studies and the recent AI/ML studies performed for children, classrooms, and primary students. It also underscores the importance of AI/ML prediction by analyzing adaptive opportunities for children/students in classrooms. Thereafter, a review of AI/ML-based prediction studies is presented. Through an AI/ML case-study, it demonstrates that model performance for children and adults differs markedly. Performance of classification models trained on ASHRAE-II database and a recent primary students’ dataset shows a 29% difference in thermal sensation and 86% difference in thermal preference, between adults and children. It then highlights three major children-specific AI/ML challenges, viz., “illogical votes”, “multiple comfort metrics”, and “extreme class imbalance”. Finally, it offers several technical solutions and discusses open problems.
Number: 11 openalex: W4309462869 KerkoCite.ItemAlsoKnownAs: 2129771:QBBL2FSI 2129771:QBBL2FSI 10.3390/buildings12112007 4874017:UZL8PAXY 5072953:H3CYMR6M 5072953:VL2ICVVU
Keywords: _important; _z:class:countries; _z:class:themes; children thermal comfort; class imbalance; classroom thermal environment; evidence_review_2; illogical votes; machine learning; oa:keyword:thermal comfort; oa:sdg:4 Quality education; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T12950 Learning Environments in Education; openalex:n:1; openalex:yes; primary school students; selected_for:Predictive models for classroom conditions 2024; thermal comfort

Sampling Volatile Organic Compound Emissions from Consumer Products: A Review - Haug, Helen; Klein, Luise; Sauerwald, Tilman; Poelke, Birte; Beauchamp, Jonathan; Roloff, Alexander (Critical Reviews in Analytical Chemistry, 2022)
Volatile organic compounds (VOCs) are common constituents of many consumer products. Although many VOCs are generally considered harmless at low concentrations, some compound classes represent substances of concern in relation to human (inhalation) exposure and can elicit adverse health effects, especially when concentrations build up, such as in indoor settings. Determining VOC emissions from consumer products, such as toys, utensils or decorative articles, is of utmost importance to enable the assessment of inhalation exposure under real-world scenarios with respect to consumer safety. Due to the diverse sizes and shapes of such products, as well as their differing uses, a one-size-fits-all approach for measuring VOC emissions is not possible, thus, sampling procedures must be chosen carefully to best suit the sample under investigation. This review outlines the different sampling approaches for characterizing VOC emissions from consumer products, including headspace and emission test chamber methods. The advantages and disadvantages of each sampling technique are discussed in relation to their time and cost efficiency, as well as their suitability to realistically assess VOC inhalation exposures.
KerkoCite.ItemAlsoKnownAs: 5072953:BP68FKPR 5072953:NYJZC3IU
Keywords: Emission test chamber; VOCs; _z:class:countries; _z:no_pdf; headspace; indoor air quality; inhalation exposure

Published Research on the Human Health Implications of Climate Change from 2012-2019: a Cross-Sectional Study - Bartlett, Victoria; Gupta, Ravi; Wallach, John R.; Nyhan, Kate; Chen, Kai; Ross, Joseph S. (medRxiv (Cold Spring Harbor Laboratory), 2022)
Abstract Importance Climate change is one of the most pressing global public health issues and is increasingly gaining attention from governments and researchers as a critical policy and research focus. While research on the effects of climate change on human health has grown significantly over the past few decades, there remain known gaps in research on non-physical health topics, like mental health, and in research on low-income countries. Objective To better understand the current state of research on the human health effects of climate change, including exposures, health conditions, populations, areas of the world studied, funding sources, and publication characteristics, with a focus on topics that are relevant for vulnerable populations. Evidence Review We searched the National Institute of Environmental Health Sciences (NIEHS) Climate Change and Human Health Literature Portal, a curated bibliographic database of global peer-reviewed research and gray literature on the science of climate impact on human health, to identify peer-reviewed original research investigating the health effects of climate change published from 2012 to 2019. The database combines searches of multiple search engines including PubMed, Web of Science, and Google Scholar and includes added-value expert tagging of climate change exposures and health impacts. We filtered our search by year published, limited to original research articles published in English. After identifying all original research articles, we selected a 5% random sample to manually perform a detailed characterization of research topics and publication information. Findings There were 7082 original research articles published between 2012 and 2019, and the number of articles increased by 23% annually. In our random sample of 348 articles, we found that there were several gaps in research topics that are particularly relevant to vulnerable populations, such as those in the Global South (159; 45.7%) and the elderly (55; 15.8%). Additionally, fewer first authors were from the Global South (110; 31.6%), which may in part explain why there is disproportionally less research focusing on these countries. Conclusions and Relevance Our results help elucidate gaps in research that, once addressed, may help us better understand and mitigate some of the most devastating effects of climate change on human health.
openalex: W4302283472
Keywords: _z:class:countries; openalex:citedBy; openalex:import; selected_for:effects of climate ch...on learning...LMICs 2024; tagged

Global Disability Justice In Climate Disasters: Mobilizing People With Disabilities As Change Agents - Engelman, Alina; Craig, Leyla; Iles, Alastair (Health Affairs, 2022)
Disabled people are highly susceptible to climate change impacts and disasters, yet they often remain sidelined or largely invisible. Policy makers, humanitarian agencies, and governments need to address the climate-related vulnerabilities that disabled people encounter during acute events and in the course of more creeping forms of climate change. As deaf researchers, we call for integrating disability justice into climate and disaster preparedness policies and practices worldwide. A disability justice approach can embrace the strengths that disabled people bring to disaster planning and climate mitigation and advocacy efforts. In this article we present case studies from different global regions to illustrate how disability is overlooked in responding to climate-related health impacts and disaster planning. We also draw particular attention to mutual aid networks led by disabled people in adapting to climate-related health impacts. We then suggest questions to help policy makers and practitioners integrate disability justice into their work. Above all, disabled people, organizations, and service providers should take ownership over the process of developing policies and actions to better prevent, prepare for, and respond to climate disasters.
openalex: W4300690178
Keywords: _z:class:countries; openalex:import; openalex:yes

Resilience of persons with disabilities to climate induced landslide hazards in the vulnerable areas of Mount Elgon, Uganda - Ssennoga, Martin; Kisira, Yeeko; Mugagga, Frank; Nadhomi, Daniel (International Journal of Disaster Risk Reduction, 2022)
The resilience of persons with disabilities in landslide-prone areas is not well understood. Moreover, these disasters are persistent and this information is vital in enhancing socioeconomic transformation of the livelihoods of Persons with disabilities. We anchored the resilience of Persons with disabilities to landslide hazards on four factors, namely; risk exposure, socioeconomic capacity, the individual functioning capacity, and the individual's housing infrastructure. The objectives of the study were (i) to assess the level of resilience of Persons with disabilities to landslides and (ii) to explore the significant sociodemographic factors that underpin the resilience of Persons with disabilities to landslides. We used a cross-sectional design and snowball sampling to access the households respondents for interviews. The analysis included descriptive analysis and inferential statistics computed using in Statistical Package for Social Sciences (SPSS) Version 23 and Microsoft Excel version 2016. The geometric mean method was used to assess the level of resilience. The Chisquare and Kendals' Tau-b were used to ascertain the underpinning sociodemographic factors to the resilience of Persons with disabilities. Results revealed that the overall resilience was low. Sex, education level, and access to disaster training significantly controlled resilience among Persons with disabilities. We conclude that Persons with disabilities in landslideprone areas have low resilience and receive little attention with respect to rescue and recovery amidst these recurrent hazards in the area. There is a need to boost the resilience of Persons with disabilities, especially the housing infrastructure and functioning capacity taking into account their social networks to build the socioeconomic and preparedness wings of disaster resilience among Persons with disabilities.
openalex: W4292074941
Keywords: _z:class:countries; openalex:import; openalex:yes

Human temperature regulation under heat stress in health, disease, and injury - Cramer, Matthew N.; Gagnon, Daniel; Laitano, Orlando; Crandall, Craig G. (Physiological Reviews, 2022)
Download figureDownload PowerPoint
KerkoCite.ItemAlsoKnownAs: 10.1152/physrev.00047.2021 2129771:8G2SQFX9 4874017:VWTCAZVD
Keywords: core temperature; environment; evidence_review; exercise; skin blood flow; sweating; vasodilation

Temperature and cardiovascular hospitalization in persons with and without disabilities: Invisible population in climate change discourse - Kim, Sera; Lee, Jong-Tae (Environmental health perspectives, 2022)
BACKGROUND AND AIM: The adverse health effects of non-optimal temperatures are disproportionately distributed in the population due to differential susceptibility and adaptive capacity to heat and cold. Although persons with disabilities (PwD) can be one of the susceptible populations, they have been neglected in the climate change discourse. This study aimed to investigate the association of ambient temperature with cardiovascular hospitalization in persons with and without disabilities. METHODS: This study used the National Health Insurance Service-National Sample Cohort established by South Korea. Using nationwide data from 2003 to 2013, we conducted a space-time-stratified case-crossover study using a conditional Poisson regression with a distributed lag nonlinear model to investigate the association between daily mean temperature and cardiovascular hospitalization. The extreme and moderate heat (99th and 95th temperature percentile, respectively) and cold (1st and 5th temperature percentile, respectively) effects on hospitalization over ten days were estimated using the minimum hospitalization temperature (MHT) as a reference. All analyses were conducted separately by the existence of a disability. RESULTS: A J-shaped association between temperature and cardiovascular hospitalization was found with the MHT at 22.2°C and 15.9°C in persons with and without disabilities, respectively. In persons without disabilities, the effects of hot temperatures were acute and lasted several days, while the effects of cold temperatures appeared after 2-3 days. In PwD, the effects of hot temperatures lasted up to 10 days, while the effects of cold temperatures appeared immediately with the following deficit in hospitalizations. The cumulative cold effects over ten days were higher in PwD than their non-disabled counterparts, although the cumulative heat effects did not show a significant difference. CONCLUSIONS: PwD were more susceptible to cold-related hospitalizations compared to their non-disabled counterpart. Precision adaptation strategies to heat and cold that considers susceptibility in PwD are needed. KEYWORDS: Temperature; Climate change; Health equity; Disability
openalex: W4320065789
Keywords: _z:class:countries; openalex:import; openalex:yes

Using Machine Learning to Predict the Effect of Non-renewable Energy Sources on Climate Change in India - Sharma, Neha; De, Prithwis Kumar (2022)
Chapter 5 makes an attempt to predict trends in average land temperature due to CO2 emissions from all the non-renewable energy resources like “coal”, “oil”, “natural gas”, and “flaring”. The chapter illustrates the step-by-step process of time series analysis that is used to forecast temperature values. Predictions with the help of a machine learning model reveal that if no significant and immediate steps are implemented, emissions from these sources of energy will continue to rise in the near future at the current rate of consumption and production. The findings indicate that the average land temperature in India is predicted to rise by 0.2 degrees Celsius in the coming years.
openalex: W4296193082
Keywords: C:India; _z:class:countries; _z:class:themes; oa:topic:T11052 Electricity Price and Load Forecasting Methods; oa:topic:T11276 Machine Learning Methods for Solar Radiation Forecasting; openalex:import; openalex:yes

Towards Resilient Agriculture to Hostile Climate Change in the Sahel Region: A Case Study of Machine Learning-Based Weather Prediction in Senegal - Nyasulu, Chimango; Diattara, Awa; Traoré, Assitan; Dème, Abdoulaye; Ba, Cheikh Oumar (Agriculture, 2022)
To ensure continued food security and economic development in Africa, it is very important to address and adapt to climate change. Excessive dependence on rainfed agricultural production makes Africa more vulnerable to climate change effects. Weather information and services are essential for farmers to more effectively survive the increasing occurrence of extreme weather events due to climate change. Weather information is important for resource management in agricultural production and helps farmers plan their farming activities in advance. Machine Learning is one of the technologies used in agriculture for weather forecasting and crop disease detection among others. The objective of this study is to develop Machine Learning-based models adapted to the context of daily weather forecasting for Rainfall, Relative Humidity, and Maximum and Minimum Temperature in Senegal. In this study, we made a comparison of ten Machine Learning Regressors with our Ensemble Model. These models were evaluated based on Mean Absolute Error, Mean Squared Error, Root Mean Squared Error and Coefficient of Determination. The results show that the Ensemble Model performs better than the ten base models. The Ensemble Model results for each parameter are as follows; Relative Humidity: Mean Absolute Error was 4.0126, Mean Squared Error was 29.9885, Root Mean Squared Error was 5.4428 and Coefficient of Determination was 0.9335. For Minimum Temperature: Mean Absolute Error was 0.7908, Mean Squared Error was 1.1329, Root Mean Squared Error was 1.0515 and Coefficient of Determination was 0.9018. For Maximum Temperature: Mean Absolute Error was 1.2515, Mean Squared Error was 2.8038, Root Mean Squared Error was 1.6591 and Coefficient of Determination was 0.8205. For Rainfall: Mean Absolute Error was 0.2142, Mean Squared Error was 0.1681, Root Mean Squared Error was 0.4100 and Coefficient of Determination was 0.7733. From the present study, it has been observed that the Ensemble Model is a feasible model to be used for Rainfall, Relative Humidity, and Maximum and Minimum Temperature forecasting.
openalex:W4296107732 mag: KerkoCite.ItemAlsoKnownAs: 10.3390/agriculture12091473 5072953:7TCSEVF2 5072953:JENMI9XB
Keywords: C:Senegal; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:resilient agriculture; oa:keyword:weather prediction; oa:sdg:2 Zero hunger; oa:topic:T11052 Electricity Price and Load Forecasting Methods; oa:topic:T11490 Hydrological Modeling using Machine Learning Methods; oa:topic:T13650 Scientific Computing and Data Analysis with Python; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Wearables for Measuring Health Effects of Climate Change–Induced Weather Extremes: Scoping Review - Koch, Mara; Matzke, Ina; Huhn, Sophie; Gunga, Hanns‐Christian; Maggioni, Martina Anna; Munga, Stephen; Obor, David; Sié, Ali; Boudo, Valentin; Bunker, Aditi; Dambach, Peter; Bärnighausen, Till; et al. (Jmir mhealth and uhealth, 2022)
Although climate change is one of the biggest global health threats, individual-level and short-term data on direct exposure and health impacts are still scarce. Wearable electronic devices (wearables) present a potential solution to this research gap. Wearables have become widely accepted in various areas of health research for ecological momentary assessment, and some studies have used wearables in the field of climate change and health. However, these studies vary in study design, demographics, and outcome variables, and existing research has not been mapped.In this review, we aimed to map existing research on wearables used to detect direct health impacts and individual exposure during climate change-induced weather extremes, such as heat waves or wildfires.We conducted a scoping review according to the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews) framework and systematically searched 6 databases (PubMed [MEDLINE], IEEE Xplore, CINAHL [EBSCOhost], WoS, Scopus, Ovid [MEDLINE], and Google Scholar). The search yielded 1871 results. Abstracts and full texts were screened by 2 reviewers (MK and IM) independently using the inclusion and exclusion criteria. The inclusion criteria comprised studies published since 2010 that used off-the-shelf wearables that were neither invasive nor obtrusive to the user in the setting of climate change-related weather extremes. Data were charted using a structured form, and the study outcomes were narratively synthesized.The review included 55,284 study participants using wearables in 53 studies. Most studies were conducted in upper-middle-income and high-income countries (50/53, 94%) in urban environments (25/53, 47%) or in a climatic chamber (19/53, 36%) and assessed the health effects of heat exposure (52/53, 98%). The majority reported adverse health effects of heat exposure on sleep, physical activity, and heart rate. The remaining studies assessed occupational heat stress or compared individual- and area-level heat exposure. In total, 26% (14/53) of studies determined that all examined wearables were valid and reliable for measuring health parameters during heat exposure when compared with standard methods.Wearables have been used successfully in large-scale research to measure the health implications of climate change-related weather extremes. More research is needed in low-income countries and vulnerable populations with pre-existing conditions. In addition, further research could focus on the health impacts of other climate change-related conditions and the effectiveness of adaptation measures at the individual level to such weather extremes.
openalex: W4288048593
Keywords: _z:class:countries; evidence_review; openalex:citedBy; openalex:import; selected_for:effects of climate ch...on learning...LMICs 2024; tagged

Assessing the Validity and Reliability of Adapted Classroom Climates Instrument for Malaysian Rural Schools Using PLS-SEM - Dolinting, Priscilla Petrus; Pang, Vincent (International Journal of Education, Psychology and Counseling, 2022)
The association between classroom climate qualitity and students’ academic achievement has been well researched. The relationship of a student to the classroom climate can be viewed from the seminal work of Moos (1974) in classifying the dimensions between individual relationship and the surrounding environment into “relationship”, “personal growth” as well as “systems maintenance and change”. Students’ perspective on their classroom climate can be used as a mechanism for classroom assessment to provide useful information regarding the strengths and weaknesses as well as an opportunity for teacher’s reflection in teaching practices. Hence, the main objective of this study is to produce empirical evidence of the validity and reliability of the item in Malay version of What is Happening in This Class? (WIHIC) questionnaire in the context of Malaysian rural secondary schools which is used to study students’ perceptions of their mathematics learning experiences in the classroom. PLS-SEM approach with aided by Smart PLS version 3.2.8 software was used to examine the internal consistency reliability, convergent validity, discriminant validity. The translated questionnaire was administered to 338 students of rural secondary schools in Sabah, Malaysia by using the multi-stage cluster sampling. Results showed a PLS-SEM measurement model with 48-items demonstrating good convergent and discriminant validity and reliability. This finding concluded that all items in the Malay version of WIHIC are valid and reliable to be used in future study. Lastly, the current study supports the use of WIHIC for educational practices improvement that could be beneficial to stakeholders such as teachers, administrators and policy makers.
openalex: W4320067347
Keywords: C:Malaysia; _z:class:countries; _z:class:themes; evidence_review_2; oa:keyword:adapted classroom climates instrument; oa:keyword:malaysian rural schools; oa:topic:T13873 Web-Based Learning Systems; oa:topic:T14182 E-Learning in Higher Education; openalex:import; openalex:yes

A low-cost air quality monitoring system based on Internet of Things for smart homes - Taştan, Mehmet (Journal of Ambient Intelligence and Smart Environments, 2022)
Global climate change and COVID-19 have changed our social and business life. People spend most of their daily lives indoors. Low-cost devices can monitor indoor air quality (IAQ) and reduce health problems caused by air pollutants. This study proposes a real-time and low-cost air quality monitoring system for smart homes based on Internet of Things (IoT). The developed IoT-based monitoring system is portable and provides users with real-time data transfer about IAQ. During the COVID-19 period, air quality data were collected from the kitchen, bedroom and balcony of their home, where a family of 5 spend most of their time. As a result of the analyzes, it has been determined that indoor particulate matter is mainly caused by outdoor infiltration and cooking emissions, and the CO2 value can rise well above the permissible health limits in case of insufficient ventilation due to night sleep activity. The obtained results show that the developed measuring devices may be suitable for measurement-based indoor air quality management. In addition, the proposed low-cost measurement system compared to existing systems; It has advantages such as modularity, scalability, low cost, portability, easy installation and open-source technologies.
Keywords: _important; _z:class:countries

Assessment of coastal variations due to climate change using remote sensing and machine learning techniques: A case study from west coast of India - Pradeep, Jibin; Shaji, E.; S, Subeesh Chandran C; Ajas, H; Chandra, S.S. Vinod; Dev, S.G. Dhanil; Babu, D. S. Suresh (Estuarine, Coastal and Shelf Science, 2022)
Climate change and other environmental disturbances are causing sea level rise all over the world. Due to sea-level rise and other unprecedented atmospheric phenomena caused by climate change, Indian coasts are vulnerable to coastal erosion. The Kerala coast, at the southern tip of India's west coast, has experienced a sea change in the last decade. To address coastal variations, we investigate coastal erosion, coastal accretion, and shoreline changes (from 2006 to 2020) along this coast between Pozhiyoor and Anchuthengu (58 km). To monitor the status and predict changes along the coast, remote sensing, GIS, field checks, and machine learning tools were used. The data analysis reveals that the shoreline configuration, rate of beach accretion, and erosion have all changed significantly. When the rate of erosion in the 58-km-long coastal stretch was examined, it was discovered that approximately 42 km face acute erosion, 13 km face accretion, and approximately 3 km face neither accretion nor erosion and remain in equilibrium. According to the estimates, approximately 2.62 km2 of land has been eroded away from the shore over a 14-year period, while 0.7 km2 of land has been accreted. At locations where the influence of river discharge or groynes is minimal, the normal rate of accretion in the stretch is around 1–2 m/y. Nonetheless, the rate of accretion increased to 5–8 m/y where groynes or river mouths, or both, have a significant influence on shoreline stability. The normal rate of erosion in the stretch under consideration, however, is around 5 m/y. With a rate of 10.59 m/y, Pozhiyoor had the highest erosion rate. According to the data, the rate of erosion is faster between Pozhikkara and Veli. The increase in shoreline changes is primarily may be due to increased cyclone occurrences in the Arabian Sea, the formation of swell waves, changes in wave energy, and sea level rise due to climate change. The slow rate of sediment discharge by rivers, groyne construction, groyne spacing, groyne length, long shore currents, and preferential northward sediment transport all play a role in the formation and destruction of beaches along India's west coast. Using machine learning techniques, a prediction model for the year 2027 was created using data from the previous 14 years (2006–2020). According to the model, almost the entire stretch will experience severe erosion, with the rate remaining consistently high between Shanghumugham and Anchuthengu. As a result, soft and appropriate engineering solutions are required for coastal stability all along the beach, particularly at these two locations after a feasibilty study.
openalex: W4284888618
Keywords: C:India; _z:class:countries; _z:class:themes; oa:keyword:coastal variations; oa:keyword:remote sensing; oa:sdg:14 Life below water; oa:topic:T10647 Coastal Dynamics and Climate Change Impacts; oa:topic:T10779 Importance of Mangrove Ecosystems in Coastal Protection; oa:topic:T11061 Dynamics of Ocean Surface Waves and Wind Interaction; openalex:import; openalex:yes

Progressive Trends in Implementing Climate Change Courses in Higher Education Curriculum at Symbiosis International University, Pune, India - Rao, Prakash; Patil, Yogesh P. (2022)
openalex: W4307012495
Keywords: C:India; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:higher education curriculum; oa:keyword:implementing climate change courses; oa:topic:T10119 Sustainability Transitions and Resilience in Social-Ecological Systems; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11835 Sustainability Education in Higher Education Institutions; openalex:import; openalex:yes

Exploring Curriculum for the Integration of Disaster Risk Reduction and Climate Change: The Case of Planning Schools in India - Roy, Anil K.; Kaliyath, Ajith; Ghosh, Debjani (Environment and Urbanization ASIA, 2022)
This article explores the urban planning curriculum of the three selected planning schools in India. They are the School of Planning and Architecture (SPA), New Delhi; Department of City and Regional Planning, Indian Institute of Technology (IIT), Kharagpur; and the Faculty of Planning, CEPT University, Ahmedabad. It uses content analysis to understand the deepening of research, skill formation and the possible change in pedagogy due to growing concerns about climate change (CC) and disaster risk reduction (DRR) in the urban area. The concerned programme coordinators and heads of the departments have also been consulted to find out the general approach to integrating CC and DRR knowledge into their planning curricula. An account of research outreach of faculty members, student dissertations and institutional publication in the CC and DRR has also been presented to illustrate research outreach with the community. It has been found that these schools need to deepen further their engagement with the domain of CC and DRR.
openalex: W4306318284
Keywords: C:India; _z:class:countries; _z:class:themes; oa:keyword:disaster risk reduction; oa:keyword:planning schools; oa:sdg:13 Climate action; oa:topic:T10439 Adaptation to Climate Change in Agriculture; oa:topic:T10747 Community Resilience to Natural Disasters; oa:topic:T10930 Global Flood Risk Assessment and Management; openalex:import; openalex:yes

No Teacher is an Island: A case study on the enablers and barriers for effective school-based teacher professional development in Sierra Leone - Lurvink, Anne-Fleur; Bangura, Zainab; Fortune, Alhaji; George, Alex H.; Godwin, Katie; Mason-Sesay, Miriam; Moseray, David; Tholley, Ibrahim; Turay, Emmanuel B.; Haßler, Björn (OpenDevEd, 2022)
ZenodoArchiveID: 7004902 ZenodoArchiveConcept: 7004901 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.0284 2129771:N665IBBE 2129771:XEJUQ9H6
Keywords: Author:OpenDevEd; _bjoern_cv; _r:AddedByZotZen; _r:ImportedToMyEducationEvidence; evidence_review

State of the Climate in 2021 - Blunden, Jessica; Boyer, Timothy P. (Bulletin of the American Meteorological Society, 2022)
Abstract Editors note: For easy download the posted pdf of the State of the Climate in 2021 is a low-resolution file. A high-resolution copy of the report is available by clicking here . Please be patient as it may take a few minutes for the high-resolution file to download.
openalex: W4295886659
Keywords: _z:class:countries; openalex:cites; openalex:import

Methods, data sources and applications of the Artificial Intelligence in the Energy Poverty context: A review - López-Vargas, Ascensión; Ledezma-Espino, Agapito; Sanchis-de-Miguel, Araceli (Energy and Buildings, 2022)
Energy Poverty (EP) is a widespread problem in Europe. EP detection is hampered by a lack of data and global metrics. Recently, innovative approaches using Artificial Intelligent (AI) techniques have been increasingly applied for the EP alleviation. In this work, studies focused on the application of AI on EP were studied. It was identified that there is not a high number of works that apply AI to fight against EP (considering this problem as a multidimensional phenomenon). Artificial Neural Networks-based algorithms and Decision Trees were the most used algorithms in the reviewed literature focused on EP alleviation. However, several AI applications focused on partial aspects of the EP or on areas intimately related to EP (low-income, high-energy price and low-energy efficiency of buildings) that allow the characterization of the problem in an efficient way have been published in recent years; the last 7 years published literature have been reviewed in this work. It was found that Neural Networks algorithms were the most used models for low-income, energy price and poor energy efficiency characterizations. Support Vector Machines-based algorithms were the most popular AI method applied on energy consumption related problems. Deep learning was the most popular technique for detecting energy billing irregularities and unpaid energy bills.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2022.112233 5072953:9QVPJ6BT openalex: W4281665463
Keywords: Artificial intelligence; Energy poverty; Fuel poverty; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:energy poverty context; oa:topic:T10603 Demand Response in Smart Grids; oa:topic:T11336 Indoor Air Pollution in Developing Countries; oa:topic:T13429 Electricity Theft Detection in Smart Grids; openalex:n:1; openalex:yes

Trained Climate Change Educators: Are Secondary School Pupils Getting Quality Climate Change Education? Views from Teachers and Pupils in Lusaka, Zambia - Mubanga, Kabwe Harnadih; Mazyopa, Kelly; Chirwa, B. B.; Musonda-Mubanga, Annie; Kayumba, Rebecca (European Journal of Development Studies, 2022)
Zambia like many other countries has not been spared from the destructive impacts of climate change. Climate change awareness creation is pivotal to adaptation and mitigation strategies. Effective dissemination of knowledge among the citizens during formal school years and later on in teacher training programs is crucial to that end. This paper investigates the quality of climate change education that students receive in secondary schools as well as the adequacy of the content taught from the teachers’ and pupils’ perspectives. It further investigated teachers’ and pupils’ opinions on the effects of embracing compulsory climate change education in secondary schools and teacher training colleges and universities. It is based on responses from secondary school students and teachers in Lusaka District. A descriptive survey design utilizing a structured questionnaire was administered to 152 randomly selected respondents drawn from 8 secondary schools within Lusaka. Data analysis involved chi-square tests and thematic analysis of respondents’ qualitative responses. Results also show that the level of climate change knowledge among secondary school teachers in Lusaka was not significantly low (χ2 = 9.488, n = 152, df = 4). Factors such as tertiary level qualification and teaching subject combination emerged as some of the major reasons for varying degrees of climate change knowledge among teachers and pupils respectively. It was recommended that the Ministry of Education should undertake climate change capacity building among teachers through the introduction of compulsory climate change training programs for all teachers at the college or university level, as well as comprehensive and compulsory climate change subject training at secondary school. Curriculum formulation agencies such Curriculum Development Centre and the Ministry of Education should work with teachers and university lecturers to come up with a detailed but easy-to-understand climate change curriculum content.
openalex:W4294265772 mag: KerkoCite.ItemAlsoKnownAs: 10.24018/ejdevelop.2022.2.4.127 5072953:HJVZENVD
Keywords: C:Zambia; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change educators; oa:keyword:quality climate change education; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Climate change resilient agricultural practices: A learning experience from indigenous communities over India - Aich, Amitava; Dey, Dipayan; Roy, Arindam (PLOS sustainability and transformation, 2022)
The impact of climate change on agricultural practices is raising question marks on future food security of billions of people in tropical and subtropical regions. Recently introduced, climate-smart agriculture (CSA) techniques encourage the practices of sustainable agriculture, increasing adaptive capacity and resilience to shocks at multiple levels. However, it is extremely difficult to develop a single framework for climate change resilient agricultural practices for different agrarian production landscape. Agriculture accounts for nearly 30% of Indian gross domestic product (GDP) and provide livelihood of nearly two-thirds of the population of the country. Due to the major dependency on rain-fed irrigation, Indian agriculture is vulnerable to rainfall anomaly, pest invasion, and extreme climate events. Due to their close relationship with environment and resources, indigenous people are considered as one of the most vulnerable community affected by the changing climate. In the milieu of the climate emergency, multiple indigenous tribes from different agroecological zones over India have been selected in the present study to explore the adaptive potential of indigenous traditional knowledge (ITK)-based agricultural practices against climate change. The selected tribes are inhabitants of Eastern Himalaya (Apatani), Western Himalaya (Lahaulas), Eastern Ghat (Dongria-Gondh), and Western Ghat (Irular) representing rainforest, cold desert, moist upland, and rain shadow landscape, respectively. The effect of climate change over the respective regions was identified using different Intergovernmental Panel on Climate Change (IPCC) scenario, and agricultural practices resilient to climate change were quantified. Primary results indicated moderate to extreme susceptibility and preparedness of the tribes against climate change due to the exceptionally adaptive ITK-based agricultural practices. A brief policy has been prepared where knowledge exchange and technology transfer among the indigenous tribes have been suggested to achieve complete climate change resiliency.
openalex: W4288435621
Keywords: C:India; _z:class:countries; _z:class:themes; oa:keyword:indigenous communities; oa:keyword:resilient agricultural practices; oa:sdg:2 Zero hunger; oa:topic:T10439 Adaptation to Climate Change in Agriculture; oa:topic:T12093 Dynamic Modeling of Plant Form and Growth; oa:topic:T12253 Urban Agriculture and Community Development; openalex:import; openalex:yes

Modelling hydrological responses under climate change using machine learning algorithms – semi-arid river basin of peninsular India - Naidu, G. Sireesha; Pratik, M.; Rehana, S. (2022)
Evolutionary algorithms and allied fields are getting more visibility as well as familiarity due to their numerous flexibilities such as handling high-dimensional non-linear problems and more. This book will help budding researchers to formulate their research problems, and comprises 10 chapters: three on optimization, five on machine learning algorithms, one on Internet of Things, and one on remote sensing.In Focus–a book series that showcases the latest accomplishments in water research. Each book focuses on a specialist area with papers from top experts in the field. It aims to be a vehicle for in-depth understanding and inspire further conversations in the sector.
openalex: W4391700651
Keywords: C:India; _z:class:countries; _z:class:themes; oa:topic:T10330 Hydrological Modeling and Water Resource Management; oa:topic:T10930 Global Flood Risk Assessment and Management; oa:topic:T11490 Hydrological Modeling using Machine Learning Methods; openalex:import; openalex:yes

A Narrative Literature Review of Natural Language Processing Applied to the Occupational Exposome - Schoene, Annika Marie; Basinas, Ioannis; Tongeren, Martie van; Ananiadou, Sophia (International Journal of Environmental Research and Public Health, 2022)
The evolution of the Exposome concept revolutionised the research in exposure assessment and epidemiology by introducing the need for a more holistic approach on the exploration of the relationship between the environment and disease. At the same time, further and more dramatic changes have also occurred on the working environment, adding to the already existing dynamic nature of it. Natural Language Processing (NLP) refers to a collection of methods for identifying, reading, extracting and untimely transforming large collections of language. In this work, we aim to give an overview of how NLP has successfully been applied thus far in Exposome research.We conduct a literature search on PubMed, Scopus and Web of Science for scientific articles published between 2011 and 2021. We use both quantitative and qualitative methods to screen papers and provide insights into the inclusion and exclusion criteria. We outline our approach for article selection and provide an overview of our findings. This is followed by a more detailed insight into selected articles.Overall, 6420 articles were screened for the suitability of this review, where we review 37 articles in depth. Finally, we discuss future avenues of research and outline challenges in existing work.Our results show that (i) there has been an increase in articles published that focus on applying NLP to exposure and epidemiology research, (ii) most work uses existing NLP tools and (iii) traditional machine learning is the most popular approach.
openalex: W4285495954
Keywords: _z:class:countries; openalex:citedBy; openalex:import; selected_for:effects of climate ch...on learning...LMICs 2024; tagged

Education for Sustainable Development: A Study on the Attitude and Concerns on Climate Change Issues among Elementary School Teachers of Odisha, India - Mohapatra, Shashwoti; Mallik, Kapileswar; Satapathy, M. K. (Asian journal of education and social studies, 2022)
From fatal heat waves and cruel droughts to devastating floods and fast depleting water tables, climate change is the greatest destructor in the current time creating a threat to all living organisms including human being. Teachers being the agents of social change have an important role to play in moulding the behaviour of children to cope with the climate change stress. The present study was carried out with 462 (222 pre-service and 240 in-service) elementary school teachers taking a Likert type five point attitude scale with 30 items having six dimensions viz., science of climate change, causes of climate change, impacts of climate change, mitigation, national initiatives and policies and politics of climate change.
From the study, it was noted that though both pre-service and in-service teachers had favourable attitude towards climate change issues, pre-service teachers had higher level of concern than in-service teachers as reflected from their attitude scores. Dimension wise pre-service and in-service teachers had favourable attitude towards science of climate change, causes of climate change, impacts of climate change and mitigation, and negative attitude towards national initiatives and policies and politics of climate change. Urban teachers were more favourable than rural teachers in first four dimensions studied.
However, among in-service teachers rural teachers were more concerned on issues such as impacts of climate change and causes of climate change than on science of climate change, mitigation, national initiatives, policies and politics of climate change. Among pre-service teachers, there was no significant difference in the attitude scores between science and arts teachers, and male and female teachers. However, urban teachers had more favourable attitude than rural teachers. Among in-service teachers, there was significant difference in the attitude scores as far as subject (science/arts) and residence (urban/rural) are concerned. Rural in-service teachers had more favourable attitude than urban teachers.
The correlation between knowledge and attitude showed a positive relationship which reflected that with increase in knowledge there was increase in concern. The relationship between age and attitude showed that with increase in teacher’s age concern for climate change increased.
openalex: W4285095005
Keywords: C:India; _z:class:countries; _z:class:themes; oa:keyword:climate change issues; oa:keyword:sustainable development; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11835 Sustainability Education in Higher Education Institutions; openalex:import; openalex:yes

PersonalisedComfort: a personalised thermal comfort model to predict thermal sensation votes for smart building residents - Rehman, Saif Ur; Javed, Abdul Rehman; Khan, Mohib Ullah; Nazar Awan, Mubashar; Farukh, Adees; Hussien, Aseel (Enterprise Information Systems, 2022)
KerkoCite.ItemAlsoKnownAs: 10.1080/17517575.2020.1852316 5072953:V39UXIL7 openalex: W3109877856
Keywords: _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:personalisedcomfort thermal personalisedcomfort model; oa:keyword:smart building residents; oa:keyword:thermal sensation votes; oa:sdg:11 Sustainable cities and communities; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10603 Demand Response in Smart Grids; oa:topic:T12120 Low-Cost Air Quality Monitoring Systems; openalex:n:1; openalex:yes

Inter-Organizational Bench-Learning to Respond to Climate Change and Reduce Trade-Offs in Urban Drinking Water Supply: The Case of Grade 2B Municipalities in Oromia National Regional State, Ethiopia - Debela, Bacha Kebede (SAGE Open, 2022)
Most studies on drinking water supply seem to focus on efficiency analysis and have failed to analyze effectiveness, cost-effectiveness, and trade-offs in performance management. Using Data Envelopment Analysis (DEA) and Free Disposal Hull (FDH) novel reference technologies, we analyzed the efficiency, effectiveness, and cost-effectiveness, and the social, economic and ecological performance (TBL elements) of 29 municipalities in drinking water supply, in Oromia National Regional State. The results from 42 (efficiency), 173 (effectiveness), and 37 (cost-effectiveness) DEA and FDH models on production model criterion and TBL elements reveal that performance of many municipalities was weak, and the municipalities encountered trade-offs on the production model criterion and TBL elements. We argue that inter-organizational bench-learning can improve performance, reduce trade-offs, and respond to the effect of climate change on the drinking water supply. To this end, we argue for the need to map peers for inter-organizational bench-learning. We identified five inter-organizational bench-learning strategies and drew implications. The article contributes to performance management literature and the debate on sustainable development.
openalex:W4296510869 mag: KerkoCite.ItemAlsoKnownAs: 10.1177/21582440221123926 5072953:I8EI9AIJ
Keywords: C:Ethiopia; _z:class:countries; _z:class:themes; oa:keyword:urban drinking water supply; oa:topic:T10357 Efficiency Analysis in Production and Resource Allocation; oa:topic:T10596 Maternal and Child Nutrition in Developing Countries; oa:topic:T10969 Optimal Operation of Water Resources Systems; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

A review on occupancy prediction through machine learning for enhancing energy efficiency, air quality and thermal comfort in the built environment - Zhang, Wuxia; Wu, Yupeng; Calautit, John Kaiser (Renewable and Sustainable Energy Reviews, 2022)
The occupants' presence, activities, and behaviour can significantly impact the building's performance and energy efficiency. Currently, heating, ventilation, and airconditioning (HVAC) systems are often run based on assumed occupancy levels and fixed schedules, or manually set by occupants based on their comfort needs. However, the unpredictability and variability of occupancy patterns can lead to over/under the conditioning of space when using such approaches, affecting indoor air quality and comfort. As a result, machine learning-based models and methodologies are progressively being used to forecast occupancy behaviour and routines in buildings, which may subsequently be used to aid in the design and operation of building systems. The present work reviews recent studies employing machine learning methods to predict occupancy behaviour and patterns, with a special focus on its related applications and benefits to building systems, improving energy efficiency, indoor air quality and thermal comfort. The review provides insight into the workflow of a machine learning-based occupancy prediction model, including data collection, prediction, and validation. An organised evaluation of the applicability or suitability of the different data collection methods, machine learning algorithms, and validation methods was carried out.
Publisher: Elsevier BV KerkoCite.ItemAlsoKnownAs: 10.1016/j.rser.2022.112704 5072953:4H3KXJPC 5072953:BWJRN86L 5072953:DNAK72FD 5072953:FPEXE6LT openalex: W4292166922
Keywords: Building model simulation; Energy efficiency; Machine learning; Occupancy detection; Occupancy prediction; Thermal comfort; _important; _z:class:countries; _z:class:themes; oa:keyword:occupancy prediction; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; oa:topic:T12120 Low-Cost Air Quality Monitoring Systems; openalex:n:1; openalex:yes; selected_for:Predictive models for classroom conditions 2024

A review on occupancy prediction through machine learning for enhancing energy efficiency, air quality and thermal comfort in the built environment - Zhang, Wuxia; Wu, Yupeng; Calautit, John Kaiser (Renewable and Sustainable Energy Reviews, 2022)
The occupants' presence, activities, and behaviour can significantly impact the building's performance and energy efficiency. Currently, heating, ventilation, and airconditioning (HVAC) systems are often run based on assumed occupancy levels and fixed schedules, or manually set by occupants based on their comfort needs. However, the unpredictability and variability of occupancy patterns can lead to over/under the conditioning of space when using such approaches, affecting indoor air quality and comfort. As a result, machine learning-based models and methodologies are progressively being used to forecast occupancy behaviour and routines in buildings, which may subsequently be used to aid in the design and operation of building systems. The present work reviews recent studies employing machine learning methods to predict occupancy behaviour and patterns, with a special focus on its related applications and benefits to building systems, improving energy efficiency, indoor air quality and thermal comfort. The review provides insight into the workflow of a machine learning-based occupancy prediction model, including data collection, prediction, and validation. An organised evaluation of the applicability or suitability of the different data collection methods, machine learning algorithms, and validation methods was carried out.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.rser.2022.112704 5072953:4H3KXJPC 5072953:BWJRN86L 5072953:DNAK72FD 5072953:FPEXE6LT openalex: W4292166922
Keywords: Building model simulation; Energy efficiency; Machine learning; Occupancy detection; Occupancy prediction; Thermal comfort; _important; _z:class:countries; _z:class:themes; oa:keyword:occupancy prediction; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; oa:topic:T12120 Low-Cost Air Quality Monitoring Systems; openalex:n:1; openalex:yes; selected_for:Predictive models for classroom conditions 2024

Time series-based deep learning model for personal thermal comfort prediction - Chennapragada, Aniruddh; Periyakoil, Divya; Das, Hari Prasanna; Spanos, Costas J. (Proceedings of the Thirteenth ACM International Conference on Future Energy Systems, 2022)
Personal thermal comfort models are crucial for the future of human-in-the-loop HVAC control in energy-efficient buildings. Individual comfort models, compared to average population responses, can provide the personalization required for successful control. In this work, we frame the thermal preference prediction task as a multivariate, multi-class classification problem and use deep learning and time-series-based approach for thermal preference prediction. We combine l1 regularization with a Regularized Long Short-Term Memory network (R-LSTM) to leverage the attentional mechanisms of such a model while counteracting overfitting. We run experiments on fourteen different subjects and find promising accuracy, F1 and AUC results, outperforming state-of-the-art machine learning approaches applied for the same task.
KerkoCite.ItemAlsoKnownAs: 10.1145/3538637.3539617 5072953:QHIN3L6X 5072953:WKNRDQMZ openalex: W4283264750
Keywords: LSTM; _z:class:countries; _z:class:themes; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11019 Image Enhancement Techniques; openalex:n:1; openalex:yes; thermal comfort prediction; time-series models

Time series-based deep learning model for personal thermal comfort prediction - Chennapragada, Aniruddh; Periyakoil, Divya; Das, Hari Prasanna; Spanos, Costas J. (Proceedings of the Thirteenth ACM International Conference on Future Energy Systems, 2022)
Personal thermal comfort models are crucial for the future of human-in-the-loop HVAC control in energy-efficient buildings. Individual comfort models, compared to average population responses, can provide the personalization required for successful control. In this work, we frame the thermal preference prediction task as a multivariate, multi-class classification problem and use deep learning and time-series-based approach for thermal preference prediction. We combine l1 regularization with a Regularized Long Short-Term Memory network (R-LSTM) to leverage the attentional mechanisms of such a model while counteracting overfitting. We run experiments on fourteen different subjects and find promising accuracy, F1 and AUC results, outperforming state-of-the-art machine learning approaches applied for the same task.
KerkoCite.ItemAlsoKnownAs: 10.1145/3538637.3539617 5072953:QHIN3L6X 5072953:WKNRDQMZ openalex: W4283264750
Keywords: LSTM; _z:class:countries; _z:class:themes; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11019 Image Enhancement Techniques; openalex:n:1; openalex:yes; thermal comfort prediction; time-series models

Nigerian teachers' self‐reported climate science literacy and expressed training needs on climate change concepts: Prospects of job‐embedded situative professional development - Eze, Emmanuel; Nwagu, Eric K. N.; Onuoha, Joseph C. (Science Education, 2022)
Abstract The assessment of Nigerian teachers' climate science literacy and training needs on climate change concepts (i.e., causes, impacts, and solutions) are absent. This study relates teachers' climate science literacy and their expressed training needs in other climate change concepts and places teachers in groups. Following a descriptive survey design, 410 teachers were randomly sampled from 8338 public secondary school teachers in Enugu State, southeastern Nigeria. A researcher‐developed instrument passing validity and reliability tests was used for this study. We implemented frequencies, mean, t test, ANOVA, k ‐means cluster analyses, and Pearson's correlation for the analyses of collected data and tested all hypotheses at a p < 0.05 level of significance. Teachers reported low to moderate climate science literacy and expressed high training needs on climate change concepts. Lower climate science literacy was related to higher expressed training needs. Four groups of teachers ensued from our cluster analyses. Sadly, teachers who possess little or less climate science literacy and expressed less or no training needs in climate change causes, impacts, and solutions constitute over half of the respondents of this study (53.90%). These are mostly science teachers. This situation, if unreversed, may lead to the transfer of misconceptions and inaccurate information on climate change to students. Our findings support the prospects of school−university partnerships, coaching, mentoring, study groups, and co‐teaching for job‐embedded situative approaches to teachers' professional development (PD) to replace an endless wait for inadequate and irregular training opportunities from the government. Questions about the climate science literacy of teacher educators also arise.
openalex:W4283692342 mag: KerkoCite.ItemAlsoKnownAs: 10.1002/sce.21743 5072953:SB4HBBE6
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:climate change; oa:keyword:climate change concepts; oa:keyword:climate science literacy; oa:keyword:nigerian teachers; oa:sdg:13 Climate action; oa:topic:T10072 Enhancing Science Education through Inquiry and Argumentation; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Overcrowded Classrooms: Effect on Teaching and Learning Process in Public Secondary Schools in Ilemela Municipality, Tanzania - Likuru, Laurian; Mwila, Prospery (Asian Journal of Education and Social Studies, 2022)
With parents, teachers, and policymakers, reducing class size is a favoured education policy approach. Cursory studies had suggested that overcrowded classroom results in relatively modest in students’ academic achievement. Underpinned by the Social Cognitive Theory, this study assessed how overcrowded classrooms affect the teaching and learning process in Ilemela Municipality, Mwanza -Tanzania. The study adopted a mixed research approach and convergent parallel research design. The sample consisted of 110 respondents including 1 MSEO, 1 Quality Assurance, 8 heads of school 40 teachers and 60 students. Structured questionnaires and interview guide were used as research instruments. Data were analysed through descriptive statistics and thematic analysis. The synthesis of the findings revealed that classrooms in Ilemela municipality are overcrowded –against the access bargain of 45 students per class; students exceeded 90 within a single stream. On the basis of the findings it was concluded that overcrowded classrooms has an effect on the teaching and learning process, since it limits the application and implementation of competence based curriculum and supportive classroom management practices which aid effectiveness of teaching and learning process. The study recommends that there is a need to enforce the policy on classroom size and to construct more classroom school so as to remedy the situation.
KerkoCite.ItemAlsoKnownAs: 10.9734/ajess/2022/v30i230744 2129771:G8N2T7B3 4874017:43V4L2JZ 5343980:9HBWPUT5
Keywords: evidence_review

Climate change knowledge, concerns and experiences in secondary school learners in South Africa - Kutywayo, Alison; Chersich, Matthew; Naidoo, Nicolette; Scorgie, Fiona; Bottoman, Likho; Mullick, Saiqa (Jàmbá: Journal of Disaster Risk Studies, 2022)
Climate change poses a major threat to the future of today's youth. Globally, young people are at the forefront of climate change activism. Their ability to engage, however, depends on the level of knowledge of climate change and concern about the topic. We sought to examine levels of knowledge and concerns about climate change among youth in South Africa, and their experiences of heat exposure. Ten questions on climate change knowledge, concerns and experiences were nested within a cross-sectional survey conducted in a cluster randomised trial among 924 secondary school learners in 14 public schools in low-income Western Cape areas. Learners' mean age was 15.8 years and they were predominately female. While 72.0% of respondents knew that climate change leads to higher temperatures, only 59.7% agreed that human activity is responsible for climate change, and 58.0% believed that climate change affects human health. Two thirds (68.7%) said that climate change is a serious issue and 65.9% indicated action is needed for prevention. Few learners indicated climate change events had affected them, although many reported difficulties concentrating during hot weather (72.9%). Female learners had lower knowledge levels than male learners, but more frequent heat-related symptoms. Learners scoring high on knowledge questions expressed the most concern about climate change and had the highest heat impacts. Many youth seem unaware that climate change threatens their future. Heat-related symptoms are common, likely undermining educational performance, especially as temperatures escalate. More is needed to mainstream climate change into South African school curricula.
openalex:W4282944628 mag: KerkoCite.ItemAlsoKnownAs: 10.4102/jamba.v14i1.1162 5072953:QMURAEXR
Keywords: C:South Africa; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:secondary school learners; oa:sdg:13 Climate action; oa:topic:T10119 Sustainability Transitions and Resilience in Social-Ecological Systems; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Climate change knowledge, concerns and experiences in secondary school learners in South Africa - Kutywayo, Alison; Chersich, Matthew; Naidoo, Nicolette; Scorgie, Fiona; Bottoman, Likho; Mullick, Saiqa (Jàmbá: Journal of Disaster Risk Studies, 2022)
Climate change poses a major threat to the future of today's youth. Globally, young people are at the forefront of climate change activism. Their ability to engage, however, depends on the level of knowledge of climate change and concern about the topic. We sought to examine levels of knowledge and concerns about climate change among youth in South Africa, and their experiences of heat exposure. Ten questions on climate change knowledge, concerns and experiences were nested within a cross-sectional survey conducted in a cluster randomised trial among 924 secondary school learners in 14 public schools in low-income Western Cape areas. Learners' mean age was 15.8 years and they were predominately female. While 72.0% of respondents knew that climate change leads to higher temperatures, only 59.7% agreed that human activity is responsible for climate change, and 58.0% believed that climate change affects human health. Two thirds (68.7%) said that climate change is a serious issue and 65.9% indicated action is needed for prevention. Few learners indicated climate change events had affected them, although many reported difficulties concentrating during hot weather (72.9%). Female learners had lower knowledge levels than male learners, but more frequent heat-related symptoms. Learners scoring high on knowledge questions expressed the most concern about climate change and had the highest heat impacts. Many youth seem unaware that climate change threatens their future. Heat-related symptoms are common, likely undermining educational performance, especially as temperatures escalate. More is needed to mainstream climate change into South African school curricula.
openalex:W4282944628 mag: KerkoCite.ItemAlsoKnownAs: 10.4102/jamba.v14i1.1162 5072953:QMURAEXR
Keywords: C:South Africa; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:secondary school learners; oa:sdg:13 Climate action; oa:topic:T10119 Sustainability Transitions and Resilience in Social-Ecological Systems; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Indoor Thermal Comfort and Adaptive Thermal Behaviors of Students in Primary Schools Located in the Humid Subtropical Climate of India - Lala, Betty; Murtyas, Solli; Hagishima, Aya (Sustainability, 2022)
This study investigated children’s perceptions and adaptive behaviors related to indoor thermal conditions of classrooms in primary schools with no air-conditioning systems during both summer and winter in Dehradun City, Uttarakhand, India. Responses were collected from 5297 school children aged 6–13 years. During the measurement periods, 100% and 94% of the samples were obtained under conditions outside an 80% thermally acceptable comfort range in winter and summer, respectively. The analysis using receiver operating characteristics suggested that the students had the least sensitivity to the temperature variation for all scales of the thermal sensation vote (TSV). Approximately 95.1% of students were “very satisfied”, “satisfied”, or “slightly satisfied” with the thermal conditions under the condition of “extreme caution” or “danger” of heat risk. In contrast, adaptive thermal behaviors, such as adjusting clothing insulation ensembles, opening or closing classroom windows and doors, and utilizing ceiling fans, were found to be the most affordable options for optimizing indoor thermal comfort. Children’s reports of thermal sensations and thermal satisfaction did not correspond to the actual physical environment. This draws attention to the adequacy of applying widely used methods of TSV-based identification of the thermal comfort range in classrooms for children, especially in hot environments. The findings of this study are expected to serve as an evidence-based reference for local governments and authorities to take appropriate measures to mitigate heat risks for schoolchildren in the future.
openalex: W4282836325
Keywords: C:India; _z:class:countries; _z:class:themes; evidence_review_2; oa:keyword:thermal comfort; oa:sdg:13 Climate action; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T12950 Learning Environments in Education; openalex:import; openalex:yes

Indoor heat measurement data from low-income households in rural and urban South Asia - Tasgaonkar, Premsagar; Zade, Dipak; Ehsan, Sana; Gorti, Ganesh; Mamnun, Nabir; Siderius, Christian; Singh, Tanya (Scientific Data, 2022)
Rising temperatures are causing distress across the world, and for those most vulnerable, it is a silent killer. Information about indoor air temperature in residential dwellings is of interest for a range of reasons, such as health, thermal comfort and coping practices. However, there have been only few studies that measure indoor heat exposure, and contrast these to outdoor temperatures in rural-urban areas, of which none are in South Asia. We aim to close this knowledge gap with our indoor and outdoor heat measurement dataset, covering five low-income sites in South Asia. Two sites are in rural areas (Maharashtra, India), while three sites focus on urban areas (Dhaka, Delhi and Faisalabad). Data are based on 206 indoor temperature data loggers and complemented by data from five outdoor automated weather stations. The data-set can be used to examine temperature and humidity variation in low-socioeconomic status households in rural and urban areas and to better understand factors aggravating heat stress. This is important to plan and implement actions for combating heat stress.
openalex: W4281659215 KerkoCite.ItemAlsoKnownAs: 4874017:I54T7UCT 4874017:I54T7UCT 10.1038/s41597-022-01314-5 5072953:A33GK7LY 5072953:TDIH7QC7
Keywords: C:India; Environmental impact; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:indoor heat measurement data; oa:sdg:1 No poverty; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11244 Impact of Climate Change on Human Health; openalex:n:1; openalex:yes

Indoor heat measurement data from low-income households in rural and urban South Asia - Tasgaonkar, Premsagar; Zade, Dipak; Ehsan, Sana; Gorti, Ganesh; Mamnun, Nabir; Siderius, Christian; Singh, Tanya (Scientific Data, 2022)
Rising temperatures are causing distress across the world, and for those most vulnerable, it is a silent killer. Information about indoor air temperature in residential dwellings is of interest for a range of reasons, such as health, thermal comfort and coping practices. However, there have been only few studies that measure indoor heat exposure, and contrast these to outdoor temperatures in rural-urban areas, of which none are in South Asia. We aim to close this knowledge gap with our indoor and outdoor heat measurement dataset, covering five low-income sites in South Asia. Two sites are in rural areas (Maharashtra, India), while three sites focus on urban areas (Dhaka, Delhi and Faisalabad). Data are based on 206 indoor temperature data loggers and complemented by data from five outdoor automated weather stations. The data-set can be used to examine temperature and humidity variation in low-socioeconomic status households in rural and urban areas and to better understand factors aggravating heat stress. This is important to plan and implement actions for combating heat stress.
openalex: W4281659215 KerkoCite.ItemAlsoKnownAs: 10.1038/s41597-022-01314-5 2129771:C3BHQZH3 4874017:I54T7UCT 5072953:A33GK7LY 5072953:TDIH7QC7
Keywords: C:India; Environmental impact; _z:class:countries; _z:class:themes; _z:no_pdf; evidence_review; oa:keyword:indoor heat measurement data; oa:sdg:1 No poverty; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11244 Impact of Climate Change on Human Health; openalex:n:1; openalex:yes

Should we paint all classroom roofs white to improve learning in Tanzania? - EdTech Hub, EdTech Hub (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0122 4874017:BVVHRHAQ 5072953:CSF3JH66
Keywords: C:Tanzania; _z:class:countries; _z:class:themes

Should we paint all classroom roofs white to improve learning in Tanzania? - EdTech Hub, EdTech Hub (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0122 2129771:2DMWFKKH 4874017:BVVHRHAQ
Keywords: evidence_review

Teachers' Perceptions About Climate Change: A Comparative Study of Public and Private Schools and Colleges in Bangladesh - Ahmed, Mahfuzuddin; Ahmed, Khandaker Jafor; Chowdhury, Mohammed Thanvir Ahmed; Haq, Shah Md Atiqul (Frontiers in climate, 2022)
This study examines school and college teachers' perceptions about climate change, taking into account academic backgrounds and experiences with the impacts of climate change. The study included 95 teachers from three schools and colleges (two private and one public) in the city of Sylhet, Bangladesh. The results show that most teachers have heard about climate change and understand what it means. Most also perceive that temperatures in Bangladesh are rising or fluctuating and that rainfall is falling or fluctuating. The chi-squared test shows that teachers' perceptions about climate change depend on whether their educational institution is private or public and whether they believe their home locality is at risk of extreme weather events (EWE). Binary and multinomial logistic regressions were used to specifically examine the impact of teachers' academic backgrounds and their previous experiences with extreme weather events on their perceptions about climate change. The results of the binary logistic regression show that educational institution type and the teaching levels (SSC: Secondary School Certificate or HSC: Higher Secondary School Certificate; or both levels) in which the teacher teaches are two significant predictors of teachers' perceptions about temperature change. The multinomial logistic regression analysis of perceptions about changes in precipitation shows that there is a statistically significant effect for factors including type of educational institution, bachelor-level study area, hometown vulnerable to EWEs, and environmental or climate-change-related courses taken.
openalex: W4281687641
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:yes

Climate change and Australian general practice vocational education: a cross-sectional study - Wild, Katherine; Tapley, Amanda; Fielding, Alison; Holliday, Elizabeth G.; Ball, Jean; Horton, Graeme; Blashki, Grant; Davey, Andrew; Driel, Mieke van; Turner, Alexandria; FitzGerald, Kristen; Spike, Neil; et al. (Family Practice, 2022)
Climate change is a rapidly progressing threat to global health and well-being. For general practitioners (GPs) currently in training, the effects of climate change on public health will shape their future professional practice We aimed to establish the prevalence and associations of Australian GP registrars' (trainees') perceptions of climate change as it relates to public health, education, and workplaces.A cross-sectional questionnaire-based study of GP registrars of three Australian training organizations. The questionnaire assessed attitudes regarding adverse health effects of climate change (over the next 10-20 years), and agreement with statements on (i) integrating health impacts of climate change into GP vocational training, and (ii) GPs' role in making general practices environmentally sustainable.Of 879 registrars who participated (response rate 91%), 50.4% (95% CI 46.8%, 54.0%) perceived a large or very large future health effect of climate change on their patients, and 61.8% (95% CI 58.6%, 65.0%) agreed that climate health impacts should be integrated within their education programme. 77.8% (95% CI 74.9%, 80.4%) agreed that GPs should have a leadership role in their practices' environmental sustainability. Multivariable associations of these attitudes included female gender, training region, and (for the latter two outcomes) perceptions of future impact of climate change on patient health.GP registrars are motivated to receive climate health education and engage in environmentally sustainable practice. This may primarily reflect concern for future practice and patient care.
openalex: W4282924928
Keywords: C:Australia; _z:class:countries; _z:class:themes; oa:keyword:vocational education; oa:topic:T11244 Impact of Climate Change on Human Health; oa:topic:T12947 Salutogenesis and Sense of Coherence in Health; oa:topic:T13555 Strategies to Reduce Low-Value Health Care Services; openalex:import; openalex:yes

Climate change and Australian general practice vocational education: a cross-sectional study - Wild, Katherine; Tapley, Amanda; Fielding, Alison; Holliday, Elizabeth G.; Ball, Jean; Horton, Graeme; Blashki, Grant; Davey, Andrew; Driel, Mieke van; Turner, Alexandria; FitzGerald, Kristen; Spike, Neil; et al. (Family Practice, 2022)
Climate change is a rapidly progressing threat to global health and well-being. For general practitioners (GPs) currently in training, the effects of climate change on public health will shape their future professional practice We aimed to establish the prevalence and associations of Australian GP registrars' (trainees') perceptions of climate change as it relates to public health, education, and workplaces.A cross-sectional questionnaire-based study of GP registrars of three Australian training organizations. The questionnaire assessed attitudes regarding adverse health effects of climate change (over the next 10-20 years), and agreement with statements on (i) integrating health impacts of climate change into GP vocational training, and (ii) GPs' role in making general practices environmentally sustainable.Of 879 registrars who participated (response rate 91%), 50.4% (95% CI 46.8%, 54.0%) perceived a large or very large future health effect of climate change on their patients, and 61.8% (95% CI 58.6%, 65.0%) agreed that climate health impacts should be integrated within their education programme. 77.8% (95% CI 74.9%, 80.4%) agreed that GPs should have a leadership role in their practices' environmental sustainability. Multivariable associations of these attitudes included female gender, training region, and (for the latter two outcomes) perceptions of future impact of climate change on patient health.GP registrars are motivated to receive climate health education and engage in environmentally sustainable practice. This may primarily reflect concern for future practice and patient care.
openalex: W4282924928
Keywords: C:Australia; _z:class:countries; _z:class:themes; oa:keyword:vocational education; oa:topic:T11244 Impact of Climate Change on Human Health; oa:topic:T12947 Salutogenesis and Sense of Coherence in Health; oa:topic:T13555 Strategies to Reduce Low-Value Health Care Services; openalex:import; openalex:yes

Modeling the impact of indoor relative humidity on the airborne transmission of several respiratory viruses risk using a modified Wells-Riley model - Aganovic, Amar; Bi, Yang; Bi, Yang; Cao, Guangyu; Kurnitski, Jarek; Wargocki, Pawel (CLIMA 2022 conference, 2022)
There is good evidence supporting the airborne transmission of many respiratory viruses (measles, influenza A, human rhinovirus and the novel SARS-CoV-2). Relative humidity (RH) is an important factor in understanding airborne transmission as it may impact both airborne survival, inactivation by biological decay, and the gravitational settling of the virusladen droplets. This study aimed to estimate and compare the impact of indoor relative humidity on the airborne infection risk caused by these viruses using a novel modified version of the Wells-Riley model. To gain insights into the mechanisms by which relative humidity might impact airborne transmission infection risk, we modeled the size distribution and dynamics of airborne viruses emitted from a speaking person in a typical residential setting over a relative humidity (RH) range of 20–80% at a temperature of 20-21 °C. Besides the size transformation of virus-containing droplets due to evaporation and then removal by gravitational settling, the modified model also considers the removal mechanism by ventilation. The direction and magnitude of RH impact depended on the respiratory virus. Measles showed a highly significant RH impact that was as strong as the ventilation impact, as the infection risk was roughly the same at RH of 13.5 % and 6 ACH compared to a higher RH of 70 % and 0.5 ACH. For other viruses, ventilation dominated over RH. In the case of SARS-CoV-2, a very high RH of 83.5% was needed to reduce the infection risk. For rhinovirus, however, the high RH of 80% increased the infection risk. Within the acceptable range of RH of 20-50% indoors, our modeling showed that RH had practically no impact for SARS-CoV-2 and rhinovirus, while the upper RH significantly reduced the infection risk of influenza A at the lowest ventilation rate of 0.5 ACH. This relative impact of RH on infection risk became very weak at higher ventilation rates of 2-6 ACH independently of the virus types (except measles). In conclusion, we showed that in wellventilated rooms, RH range of 20-50% did not affect the airborne risk of influenza A, SARSCoV-2, and rhinovirus.
KerkoCite.ItemAlsoKnownAs: 10.34641/CLIMA.2022.363 2129771:9DKJ5XA4 4682641:RY22WFV5 4682641:ZXCG74X9 5072953:8RMRWC4A
Keywords: BE:RELEVANT; _z:class:countries; _z:class:themes

Development of the TAIL rating scheme for indoor environmental quality in schools - Tran, Minh-Tien; Wei, Wenjuan; Dassonville, Claire; Mandin, Corinne; Wargocki, Pawel; Hequet, Valérie (CLIMA 2022 conference, 2022)
The TAIL rating scheme was developed to assess indoor environmental quality (IEQ) in offices and hotels undergoing deep renovation and was recently extended by the PredicTAIL method allowing prediction of IEQ through modeling. TAIL provides the methodology for rating the quality of the thermal, acoustic, and luminous environments, the indoor air quality, and the overall quality of the indoor environment. The present work is an extension of the use of TAIL rating scheme for school classrooms to provide necessary information for effective actions and mitigation measures to improve classroom IEQ. The TAIL was invented by examining the literature and certification schemes to identify the parameters that characterize IEQ in offices and hotels; 12 parameters were selected. A similarly pragmatic approach is followed when developing the TAIL for schools. The literature published after 2010 was surveyed to identify papers presenting measurements of IEQ in classrooms in Europe, the USA, and Australia; 75 papers were identified. Besides the 12 parameters already included in TAIL, the studies also used other parameters to characterize classroom IEQ. These parameters will be evaluated for their importance for the teaching, learning, and well-being of pupils, as well as measuring complexity, among others. Based on this assessment, the relevant parameters will be selected for inclusion in the TAIL rating for schools. The selection will be assisted using the measurements from the extensive campaign organized by the Indoor Air Quality Observatory in 308 schools and 602 classrooms in France; some of these data will be used to assess the efficacy of the TAIL for schools indicator. The relationships between the newly developed TAIL for schools, the teacher’s perceptions of indoor environmental quality, and detailed building characteristics will be studied.
KerkoCite.ItemAlsoKnownAs: 10.34641/CLIMA.2022.244 2129771:KYSDIHAD 4682641:4GVDN4PA 4682641:GBDCAQVS 5072953:R9R7JUKI
Keywords: BE:RELEVANT; C:Australia; C:France; _z:class:countries; _z:class:themes; evidence_review_2

Effects of airing behaviours on bedroom air pollutants during sleep - Liao, Chenxi; Fan, Xiaojun; Petrova Bivolarova, Mariya; Mainka, Anna; Sekhar, Chandra; Laverge, Jelle; Lan, Li; Akimoto, Mizuho; Wargocki, Pawel (CLIMA 2022 conference, 2022)
Higher ventilation rates were verified to have a positive impact on indoor air quality and therefore benefit sleep quality. However, how does ventilation influence bedroom air quality if the outdoor air quality is poor? Whilst ventilation helps to reduce indoor pollution it inadvertently brings outdoor pollution indoors, such as NO2, which is from vehicular emission. In this study, we collected the info of window and door status during sleep and measured carbon dioxide (CO2), nitrogen dioxide (NO2), volatile organic compounds (VOCs) and particulate matter (PM2.5 and PM10) among 38 bedrooms while occupants were sleeping during nights. Meanwhile, the air change rate (ACR) was calculated. The experiments were conducted in the heating season (September to December 2020) in the capital region of Denmark. The median values were 981.8 ppm (mean CO2 level during sleep), 0.6 h-1 (ACR), 3.4 µg·m−3 (NO2), 166.2 µg·m−3 (VOCs), 11.0 µg·m-3 (PM10) and 2.8 µg·m-3 (PM2.5). CO2 levels were positively correlated with VOCs levels, whereas negatively correlated with NO2 levels in bedrooms. ACR was also negatively correlated with VOCs. CO2 levels were significantly higher whereas NO2 levels were lower with both window and door closed compared to them with either window or door open. With higher ventilation rates, while occupants would be less exposed to indoor pollution of VOCs, they would be increasingly exposed to NO2. Future studies of bedroom ventilation and sleep quality should consider outdoor air quality.
KerkoCite.ItemAlsoKnownAs: 10.34641/CLIMA.2022.128 2129771:L2WIZ7XM 4682641:WH92LGZX 5072953:DQ7SI2SX
Keywords: BE:RELEVANT; C:Denmark; _z:class:countries; _z:class:themes

Quality of life and acoustic comfort in educational environments of curitiba, Brazil - Levandoski, Gustavo; Zannin, Paulo Henrique Trombetta (Journal of Voice, 2022)
Background It is believed that poor classroom acoustics leads to lower levels of student learning and exposes teachers vocal folds to greater physical wear and tear. Objective This study sought to compare the quality of life by World Health Organization (whoqol-bref) questionnaire of 61 teachers working at schools with different acoustic conditions. Methods This paper reports on a descriptive exploratory study aimed at ascertaining the following: (1) outdoor sound pressure levels in the immediate surroundings of two primary schools; (2) background noise levels inside classrooms; (3) reverberation times in classrooms; (4) the teacher's perception of noise in the work environment; (5) the teacher's vocal intensity in the classroom; and (6) the teacher's perceived quality of life. Results It was found that the quality of life of teachers, as well as the major causes of acoustic discomfort, do not stem from a source outside the classroom, halls, and physical education classes. Instead, they originate inside the classroom and are caused by students during school hours; the teachers’ vocal intensity exceeds the limits of tolerability both in schools that provide acoustic comfort and in those that do not. Conclusions The basic conditions required to ensure the health of the participants in this study during their workday were found to be unsatisfactory.
KerkoCite.ItemAlsoKnownAs: 2129771:739XQKR4 2129771:739XQKR4 2129771:739XQKR4 2129771:739XQKR4 10.1016/j.jvoice.2020.05.030 4874017:RBVXDIR6 5072953:6IEJPF8B openalex: W3039386481
Keywords: C:Brazil; Quality of life; Reverberation time; Sound pressure levels; Teachers; Vocal intensity; _z:class:countries; _z:class:themes; evidence_review_2; oa:keyword:acoustic comfort; oa:sdg:1 No poverty; oa:topic:T10283 Impact of Hearing Loss on Cognitive Function; oa:topic:T11692 Effects of Noise Pollution on Health and Well-being; oa:topic:T11824 Global Burden of Child Injury Prevention; openalex:n:1; openalex:yes

Building energy prediction using artificial neural networks: A literature survey - Lu, Chujie; Li, Sihui; Lu, Zhengjun (Energy and Buildings, 2022)
Building Energy prediction has emerged as an active research area due to its potential in improving energy efficiency in building energy management systems. Essentially, building energy prediction belongs to the time series forecasting or regression problem, and data-driven methods have drawn more attention recently due to their powerful ability to model complex relationships without expert knowledge. Among those methods, artificial neural networks (ANNs) have proven to be one of the most suitable and potential approaches with the rapid development of deep learning. This survey focuses on the studies using ANNs for building energy prediction and provides a bibliometric analysis by selecting 324 related publications in the recent five years. This survey is the first review article to summarize the details and applications of twelve ANN architectures in building energy prediction. Moreover, we discuss three open issues and main challenges in building energy prediction using ANNs regarding choosing ANN architecture, improving prediction performance, and dealing with the lack of building energy data. This survey aims at giving researchers a comprehensive introduction to ANNs for building energy prediction and investigating the future research directions when they attempt to implement ANNs to predict building energy demand or consumption.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2021.111718 5072953:4TKR444J openalex: W3217470798
Keywords: Artificial neural networks; Building energy prediction; Deep learning; Smart buildings; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:energy prediction; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11052 Electricity Price and Load Forecasting Methods; oa:topic:T11344 Traffic Flow Prediction and Forecasting; openalex:n:1; openalex:yes

Occupancy behaviour and patterns: Impact on energy consumption of high-rise households in southeast China - Zhang, Wuxia; Calautit, John Kaiser (Smart Energy, 2022)
With the rapid urbanization in China, energy consumption and corresponding carbon emissions in residential buildings are growing. Because occupant behaviour plays a significant role in building energy performance and occupant comfort, understanding the crucial links between occupant lifestyles and energy use is the key. Most studies on the relationship between occupancy behaviour and energy usage have been conducted in public or commercial buildings. Because data is difficult to obtain and key information about existing houses is required, research on high rise residential buildings is limited. To acquire information on thermal satisfaction, residential equipment ownership and usage habits and attitude to smart meters, this paper conducted a comprehensive survey of 112 metropolitan families living in a typical booming city. A case study high-rise residential building is modelled in a building energy simulation tool. The result is compared with the actual energy bill acquired from occupants or smart meters to better understand the energy usage in this area. The results showed that a large variation in energy use could exist in different households, which is influenced by several factors such as occupancy patterns and habits, as observed in the survey. At the same time, it shows the challenge of predicting the energy use of such a building with varying internal heat gains, set points and window opening behaviours across the different households.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.segy.2022.100072 5072953:NW2N9ZM9 openalex: W4280534598
Keywords: C:China; _z:class:countries; _z:class:themes; oa:keyword:energy consumption; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11692 Effects of Noise Pollution on Health and Well-being; oa:topic:T11963 Impact of Nighttime Light Data on Various Fields; openalex:n:1; openalex:yes

Integrating Climate Change and Smart Agriculture Contents into Nigerian School Curriculum - Ahmed, Abdullahi Hussein; Ibrahim, Ochapa; Agunbiade, Mahmud Wasilah (Indonesian Journal of Curriculum and Educational Technology Studies, 2022)
The importance of the agricultural sector to the Nigerian economy is highly invaluable, although, it is highly responsive and vulnerable to climate change. Climate change has caused decline and volatility in agricultural production, thereby exacerbating food insecurity and hunger in countries such as Nigeria. Most of the Nigerian farmers are rainfed and conservative towards technological change, this calls for the need to develop curriculum contents on smart agriculture for youth who will steer agricultural activities in the nearest future. This study adopts Stufflebeam’s (Content-Input-Process-Product) curriculum content creation process to develop content on climate change and smart agriculture for incorporation into the senior school agricultural science curriculum in Nigeria. The contents were developed using the Food and Agricultural Organization of the United Nations outlined climate-smart agricultural practices as suggested in themes 1 and 2 of the curriculum
Abstrak
Sektor pertanian sangat penting bagi perekonomian Nigeria, meskipun sangat responsif dan rentan terhadap perubahan iklim. Perubahan iklim telah menyebabkan penurunan dan ketidakstabilan dalam produksi pertanian, sehingga memperburuk kerawanan pangan dan kelaparan di negara-negara seperti Nigeria. Sebagian besar petani Nigeria menggarap pertanian tadah hujan dan konservatif terhadap perubahan teknologi. Kondisi tersebut meniscayakan perlunya mengembangkan konten kurikulum pertanian cerdas (smart agriculture content) untuk pemuda yang akan mengarahkan kegiatan pertanian dalam waktu terdekat. Studi ini mengadopsi model Stufflebeam (Content-Input-Process-Product) dalam proses pembuatan konten kurikulum untuk mengembangkan materi tentang perubahan iklim dan pertanian cerdas untuk dimasukkan dalam kurikulum ilmu pertanian sekolah menengah di Nigeria. Konten dikembangkan mengacu pada Organisasi Pangan dan Pertanian Perserikatan Bangsa-Bangsa yang menguraikan praktik pertanian cerdas iklim sebagai tema 1 dan 2 yang disarankan dari kurikulum
openalex:W4385673538 mag: KerkoCite.ItemAlsoKnownAs: 10.15294/ijcets.v10i1.50938 5072953:VXBQI7PI
Keywords: C:Nigeria; C:Peru; _z:class:countries; _z:class:themes; oa:keyword:nigerian school curriculum; oa:keyword:smart agriculture; oa:keyword:smart agriculture contents; oa:topic:T12904 Agricultural Education and School Gardening Research; oa:topic:T13930 Global Trends in Education and Technology; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Integrating Climate Change and Smart Agriculture Contents into Nigerian School Curriculum - Ahmed, Abdullahi Hussein; Ibrahim, Ochapa; Agunbiade, Mahmud Wasilah (Indonesian Journal of Curriculum and Educational Technology Studies, 2022)
The importance of the agricultural sector to the Nigerian economy is highly invaluable, although, it is highly responsive and vulnerable to climate change. Climate change has caused decline and volatility in agricultural production, thereby exacerbating food insecurity and hunger in countries such as Nigeria. Most of the Nigerian farmers are rainfed and conservative towards technological change, this calls for the need to develop curriculum contents on smart agriculture for youth who will steer agricultural activities in the nearest future. This study adopts Stufflebeam’s (Content-Input-Process-Product) curriculum content creation process to develop content on climate change and smart agriculture for incorporation into the senior school agricultural science curriculum in Nigeria. The contents were developed using the Food and Agricultural Organization of the United Nations outlined climate-smart agricultural practices as suggested in themes 1 and 2 of the curriculum
Abstrak
Sektor pertanian sangat penting bagi perekonomian Nigeria, meskipun sangat responsif dan rentan terhadap perubahan iklim. Perubahan iklim telah menyebabkan penurunan dan ketidakstabilan dalam produksi pertanian, sehingga memperburuk kerawanan pangan dan kelaparan di negara-negara seperti Nigeria. Sebagian besar petani Nigeria menggarap pertanian tadah hujan dan konservatif terhadap perubahan teknologi. Kondisi tersebut meniscayakan perlunya mengembangkan konten kurikulum pertanian cerdas (smart agriculture content) untuk pemuda yang akan mengarahkan kegiatan pertanian dalam waktu terdekat. Studi ini mengadopsi model Stufflebeam (Content-Input-Process-Product) dalam proses pembuatan konten kurikulum untuk mengembangkan materi tentang perubahan iklim dan pertanian cerdas untuk dimasukkan dalam kurikulum ilmu pertanian sekolah menengah di Nigeria. Konten dikembangkan mengacu pada Organisasi Pangan dan Pertanian Perserikatan Bangsa-Bangsa yang menguraikan praktik pertanian cerdas iklim sebagai tema 1 dan 2 yang disarankan dari kurikulum
openalex:W4385673538 mag: KerkoCite.ItemAlsoKnownAs: 10.15294/ijcets.v10i1.50938 5072953:VXBQI7PI
Keywords: _z:class:countries; _z:class:themes; oa:keyword:nigerian school curriculum; oa:keyword:smart agriculture; oa:keyword:smart agriculture contents; oa:topic:T12904 Agricultural Education and School Gardening Research; oa:topic:T13930 Global Trends in Education and Technology; openalex:n:1; openalex:yes; ⛔ No DOI found

Effects of Ceiling Fans on the Thermal Comfort of Students in Learning Environments of Bayero University, Kano, Nigeria - Ali, Sani Muhammad; D. Martinson, Brett; Al-Maiyah, Sura (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2022)
It is well known that thermal comfort is influenced by major physical parameters; air and radiant temperatures, humidity, and air speed in combination with personal attributes; clothing insulation and activity level. Although temperature is conventionally considered in adaptive thermal comfort model, as the most important physical parameter where cooling is involved, moderate air speed can enhance thermal comfort during higher temperatures. Through convective and evaporative cooling, ceiling fans cool people by causing sweat from the occupant’s body to evaporate. The northern part of Nigeria, being in the tropics, is known for higher temperature regimes for most part of the year. The use of air conditioning to achieve thermal comfort is not sustainable, for economic reasons and the lack of stable electrical energy. Therefore, a majority of naturally ventilated spaces could be kept thermally comfortable with the control of ceiling fans and operable windows. As part of a research work on learning environments in a Northern Nigerian university, this study reports on the effects of ceiling fans on the thermal comfort perception of the students in two lecture theatres. Air speed, air and radiant temperatures, relative humidity were measured, concurrently comfort surveys were undertaken in the spaces, from which activity levels and clothing insulations were obtained. Adaptive thermal comfort standards, ASHRAE 55 and EN 15251, state that thermal comfort can be maintained as air temperature rises with the use of ceiling fans operating at moderate speed. The results show that reductions of 31% and 22% in overheating from the two lecture theatres were realised, as a result of ceiling fans usage, measured by the degree hour’s exceedance indicator. These results were further corroborated by the students’ acceptance of thermal conditions of the lecture theatres at temperatures above Tmax.

Towards a critical pedagogy of place for environmental conservation - Ajaps, Sandra; Forh Mbah, Marcellus (Environmental Education Research, 2022)
KerkoCite.ItemAlsoKnownAs: 10.1080/13504622.2022.2050889 5072953:EKR6HMCP openalex: W4220771464
Keywords: _z:class:countries; _z:class:themes; oa:keyword:critical pedagogy; oa:keyword:environmental conservation; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T12997 Experiential Education and Adventure Therapy; oa:topic:T14007 Place-Based Education in Rural Communities; openalex:n:1; openalex:yes

Design and implementation of 3-D printed radiation shields for environmental sensors - Botero-Valencia, J.S.; Mejia-Herrera, M; Pearce, J.M.; Botero-Valencia, J. S.; Mejia-Herrera, M.; Pearce, Joshua M. (HardwareX, 2022)
openalex: W4210462955 KerkoCite.ItemAlsoKnownAs: 10.1016/j.ohx.2022.e00267 2486141:AINUPQFJ 4874017:8U74RIEI 5072953:6AD669D2 5072953:8KEJY5IB 5072953:Y5RHXA8V
Keywords: 3-D printing; Additive manufacturing; Climatic variables; Environmental monitoring; Environmental sensing; Environmental variables; Internet of Things (IoT); Open hardware; Radiation shield; Sensing; Smart agriculture; _z:class:countries; _z:class:themes; low cost; oa:keyword:radiation shields; oa:topic:T10783 Additive Manufacturing and 3D Printing Technologies; openalex:n:1; openalex:yes

Protecting human health in a time of climate change: how Cochrane should respond - Thomson, Denise; Cumpston, Miranda; Delgado-Figueroa, Netzahualpilli; Ebi, Kristie L.; Haddaway, Neal R.; Heijden, Maarten van der; Heyn, Patricia; Lokotola, Christian L.; Meerpohl, Joerg J; Metzendorf, Maria‐Inti; Parker, Eva Rawlings; Phalkey, Revati; et al. (The Cochrane library, 2022)
Image credit: Axel Fassio / CIFOR There is an urgent need to respond to climate change's multiple intersecting impacts on human health. Health journals around the world recently published a joint call for immediate action by governments and health professionals.[1] Researchers and methodologists also have an important contribution to make, by producing and synthesizing evidence relevant to climate‐health impacts. In particular, we argue that Cochrane needs to mobilize its expertise in high‐quality evidence syntheses to prioritize the production of reviews needed by global decision makers. This will involve working closely with stakeholders to ensure that both topics and methods are aligned to the task of strengthening health resilience to oncoming climate shocks. Health‐system decision makers need to be ready to monitor, anticipate, manage and adapt to a wide range of climate‐related health risks.[2] The increasing frequency, intensity and duration of extreme weather events, such as heatwaves, floods, droughts and wildfires, have extensive effects on both physical and mental health.[3, 4, 5] Other impacts include alterations to patterns of food‐, water‐ and vector‐borne diseases; changes to food production that increase risks of malnutrition; emergence of multi‐drug‐resistant infectious diseases and acceleration of drug resistance in existing infectious diseases; breakdown of ecosystem services; and the mental health impacts of climate‐related disasters and disruptions to traditional ways of life.[6, 7, 8, 9, 10, 11, 12] Climate‐health issues are multi‐system problems, with complex outcomes stemming from the interaction of hazards, exposures, pre‐existing vulnerabilities, and capacity.[13, 14] Targeted responses must be focused on improving methods for risk quantification, especially cascading and overlapping exposures, and strengthening climate resilience and environmental sustainability of health systems. This can be accomplished by understanding the magnitude and pattern of climate‐related health risks, at various spatio‐temporal scales; identifying adaptation strategies that will ameliorate impacts;[2, 15] and establishing mitigation strategies that will reduce the environmental impacts of health systems themselves.[16, 17] Although the climate‐health research base is growing rapidly, the current literature is dominated by impact studies, with relatively few studies focusing on human response to climate change, climate adaptation and climate mitigation for human health.[18, 19] Synthesizing this research, to identify what works, why, for whom and in what circumstances, will be vital for guiding policy and practice decisions.[20, 21] Syntheses can also help identify what doesn't work and the associated harms of interventions that may also provide some benefits, thereby attenuating the risks of unintended consequences and locking in effects of maladaptation; increasing efficiency of healthcare spending; and helping to identify gaps in current knowledge.[22] This is no small challenge. The body of relevant evidence – both published research and grey literature – is extensive and multidisciplinary, transcending the traditional boundaries of health research.[20] Cochrane has already identified climate change as a key issue in its strategic plans in the coming years. It is now time to translate that high‐level awareness into action. Internally, it is our responsibility to maintain an understanding of the organization's carbon footprint and to develop a plan to reach net zero.[23] It must also be an organizational priority to contribute research efforts towards understanding the health effects of adaptation and climate mitigation interventions. Specifically, Cochrane can help meet decision makers’ needs in the following ways: supporting the identification and prioritization of important and unaddressed research questions for evidence syntheses; producing, in conjunction with stakeholders, new living reviews that address key questions; evaluating new methods and supporting the development and implementation of these where appropriate; supporting the engagement of diverse and vulnerable communities at all levels; working with other organizations to improve the efficiency of knowledge production and usage, and reducing research waste.[24] To accomplish these goals, some foundational work must occur. In order to produce the actionable, policy‐relevant syntheses that decision makers will need, the health evidence synthesis community must broaden its definition of evidence to include mechanistic understanding, theory, data, projections of how risks could evolve over spatial and temporal scales, and expert judgement.[20] The nature of climate change as a multi‐disciplinary topic with hard‐to‐define system boundaries means that search strategies will yield very large numbers of hits with low precision, making the tasks of screening, data extraction and analysis highly resource‐intensive. Technologies like machine learning and linked evidence ecosystems could be a vital means of dealing with these broader evidence bases.[19, 20, 21, 22, 23, 24, 25] For effective syntheses, we need to improve existing methods, while repurposing some from other fields and sometimes developing new ones. Improving evidence synthesis for public health interventions, such as considering effectiveness from a population perspective and incorporating non‐randomized, economic and qualitative evidence, as well as equity considerations, can be relevant to work on complex climate‐health topics.[26, 27, 28] This includes innovation of methods to incorporate modelling studies into synthesis where direct evidence is not available.[29] As well, review authors should be encouraged to conduct analyses that incorporate not just changing exposures, but also changing contexts, such as demographics, economic growth, urbanization, etc, and consequently author teams will need to encompass the range of disciplines that bring the competency to do this kind of work.[14, 15] Those producing health‐related evidence syntheses have much to learn from other synthesis traditions, such as those in the environmental science community. This will help to avoid duplication and waste; to explore questions that intersect across health, the environment and other sectors of policy; and to learn from their work in novel methods not yet considered in Cochrane Reviews, such as synthesis across multiple lines and types of evidence relevant to the health impacts of environmental risks and exposure.[20, 30] It will be important to establish and strengthen relationships with other climate‐orientated evidence synthesis organizations, such as the Collaboration for Environmental Evidence and the Campbell Collaboration's Climate Solutions Coordinating Group. It is worth noting that synthesis that supports decision making can be facilitated by enhancing the research base of primary studies. Designing and implementing climate‐resilient health policies and programmes will involve evaluation of a range of potential future scenarios in a range of geographic settings.[13, 31] This work would be facilitated by researchers developing consensus guidelines around the design, conduct and reporting of climate health‐impact projections.[28] Such guidelines, particularly if incorporated into editorial standards, should support higher‐quality research, and should facilitate synthesis by leading to less heterogeneity between studies, which can increase possibilities for meta‐analysis.[28, 32] It would also be valuable to have more studies on how climate‐relevant interventions are implemented, as success of an intervention is affected by the strategies for addressing aspects of the context into which it is introduced and (ideally) sustained.[14, 33, 34, 35] Cochrane could also support decision makers by identifying existing Cochrane Reviews that address climate‐sensitive health impacts, but are not necessarily explicitly stated by authors to be relevant to climate change.[36, 37] When the COVID‐19 pandemic hit, Cochrane mobilized to produce syntheses needed for global decision making in an unprecedented and rapidly evolving health emergency. Climate change is also a health crisis, and the evidence synthesis community must respond to decision‐making needs with equivalent vigour. We must optimize, and where appropriate, repurpose methods to synthesize available evidence and speed the generation of relevant new evidence to support decision making. Throughout, ongoing engagement with stakeholders and decision makers will be important to ensure that Cochrane is focusing its resources where they are most needed. As we witness changes to the climate now, we do so knowing that the future will likely look nothing like the present. It is time for Cochrane to bring our expertise to the work of informing the decision making needed to avert or mitigate the ongoing health effects of global climate change.
openalex: W4225271885
Keywords: _z:class:countries; openalex:citedBy; openalex:import; selected_for:effects of climate ch...on learning...LMICs 2024; tagged

Discourses of climate change education: The case of geography textbooks for secondary and higher secondary education in South Africa and Norway - Trædal, Leif Tore; Eidsvik, Erlend; Manik, Sadhana (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 2022)
The purpose of the article, which is a comparative study, is to explore climate change discourses in South African and Norwegian geography textbooks by addressing the following questions: What policy discourses of climate change can be identified in the textbooks? How is the climate change content of geography textbooks influenced by predominant discourses in society? The authors assert that problems and solutions to climate change in textbooks are influenced by dominant discourses of climate change in society. Despite expecting to find a strong emphasis on ecological modernization and a win-win discourse in the Norwegian context, and perhaps a stronger focus on civic environmentalism and global injustice in the South African context, their findings reflected that for both countries, textbooks predominantly leaned towards belief in international agreements and green governmentality. Some emphasis was placed on ecological modernization, particularly in South Africa, while civic environmentalism and global injustice perspectives were marginal and lacked context. The overlapping nature of perspectives identified in the textbooks also demonstrated the complexity of identifying problems and solutions connected to climate change. The authors conclude that political ecology can offer a consistent didactical framework to examine the diversity of interests, perspectives and ‘stories’ about climate change at different scales.
openalex:W4293099274 mag: KerkoCite.ItemAlsoKnownAs: 10.1080/00291951.2022.2062044 5072953:SNI35D5Z
Keywords: C:Norway; C:South Africa; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:climate change; oa:keyword:climate change education; oa:keyword:geography textbooks; oa:sdg:13 Climate action; oa:topic:T10119 Sustainability Transitions and Resilience in Social-Ecological Systems; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T12343 Geography Education and Spatial Thinking; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

‘It is unbelievable’: Francis Kéré becomes first black architect to win the Pritzker prize - Wainwright, Oliver; @ollywainwright (The Guardian, 2022)
Burkinabe architect takes the profession’s highest honour, having made his name with schools and medical facilities in Africa, built by local communities with minimal resources
Keywords: Africa; Architecture; Art and design; Awards and prizes; Burkina Faso; Culture; World news; _z:class:countries

Generative spaces of climate change adaptation: Focus on disability inclusion - Humalisto, Niko (2022)
Climate change increases livelihood vulnerability and exposure to risks around the globe, but these impacts are not equally distributed among different people and places.Among the disadvantaged are persons with disabilities but their inclusion in projects and planning for climate change adaptation is low.Nepal is a challenging but typical context in the global South, where persons with disabilities have limited capacities to demand their basic rights, from secure livelihoods to sanitation, to be respected.Concurrently, (localised) institutions might not have the capacity to protect their constitutional rights.Consequently, while Nepalese policy encourages disability inclusion in adaptation planning, doing so in practice faces manifold political, cultural and social barriers.This chapter examines the conditions for inclusive adaptation based on ethnographic data from development projects run by seven Nepalese NGOs.The results show that democratic governance needs to be enhanced, and that the accountability of state institutions must co-evolve with the resilient livelihood opportunities for persons with disabilities.Inclusive adaptation hinges on creating trade-offs and positive feedback loops by generating opportunities for communal participation, refining evidence for circulation, and enabling scalar linkages between stakeholders and duty-bearers.
openalex: W4280497831
Keywords: _z:class:countries; openalex:import; openalex:yes

A critical review on occupant behaviour modelling for building performance simulation of naturally ventilated school buildings and potential changes due to the COVID-19 pandemic - Franceschini, Paula Brumer; Neves, Leticia Oliveira (2022)
Occupant behaviour (OB) is one of the main causes of the energy performance gap between buildings’ performance prediction versus reality, since, due to its uncertainty and unpredictability, it is often oversimplified in the building performance simulation (BPS). Hence, previous studies developed OB models, mainly in the residential and office contexts, in order to predict and represent human behaviour in BPS. Yet, school buildings are different from other typologies due to contextual factors (e.g., occupants’ age, different daily timetables and group rules) and are in a unique position to promote energy efficiency for tomorrow’s citizens. Assessing OB in schools can lead to an improvement of the indoor environment, especially in naturally ventilated buildings, where window operation behaviour directly impacts on the air change rates and, consequently, on the indoor air quality. This study addresses the knowledge gap on OB modelling for naturally ventilated (NV) and mixed-mode (MM) school buildings. The reviewed papers were organized in three main themes, namely (i) OB models for BPS of NV and MM buildings, (ii) OB research studies in NV and MM school buildings and (iii) potential changes on OB in school buildings due to the COVID-19 pandemic. The analysis focused on three phases of the OB modelling framework: data collection (pre-processing), model development (processing) and model implementation (post-processing). Important research gaps are identified, such as the reduced number of studies that cover the three phases of the modelling framework within the school buildings context and the need to better investigate the teachers’ behaviour and collective actions as important OB drivers in classrooms. Future research topics are also identified, such as which are the potential changes on actions’ drivers due to the COVID-19 pandemic in NV classrooms and to what extent they will be durable or ephemeral.
KerkoCite.ItemAlsoKnownAs: 4874017:YUC279LR 5072953:WUW46PD3
Keywords: Behaviour model; Building performance simulation; COVID-19; Natural ventilation; Occupant behaviour; School buildings; _z:class:countries; _z:class:themes

Buildings’ internal heat gains prediction using artificial intelligence methods - Liang, Rui; Ding, Wangfei; Zandi, Yousef; Rahimi, Abouzar; Pourkhorshidi, Sara; Khadimallah, Mohamed Amine (Energy and Buildings, 2022)
A large part of energy consumption in homes, offices and commercial spaces is related to Heating, Ventilation and Air-conditioning (HVAC) devices. The effective parameter on the consumption of HVAC systems is internal heat gains that arise from occupants, electric equipment and lighting. In order to reduce the energy consumption of these systems, internal heat gains should be predicted accurately. Since there are few investigations performed on the prediction of internal heat gains, in this paper, three predictive models, namely multiple regression model, Levenberg–Marquardt back-propagation (LM-BP) model and similar days method based on combined weights, have been deployed. By assessing the influential factors on internal heat gains, fundamental theories, structures, equations and parameters of these models are thoroughly proposed. To examine the prediction techniques, an office building in China was considered. It was found that all the proposed models have high accuracy; however, the LM-BP neural network showed the most precision among other models with RMSE = 15.59, MAE = 10.16 and MAPE = 6.35. This model had a higher agreement with the actual internal heat gains compared to the predetermined working programs in the ASHRAE standard 90.1. The proposed models used in this study can lead to providing a theoretical base for scholars and engineers to improve the predictive control of HVAC systems, which plays an important role in enhancing thermal comfort, saving energy of residential buildings.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2021.111794 5072953:YZBX9DTI openalex: W4200023968
Keywords: Building; C:China; Internal heat gains; LM-BP neural network model; Office; Similar day model; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:internal heat gains prediction; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:n:1; openalex:yes

A Sanitation Argument for Clean Indoor Air: Meeting a Requisite for Safe Public Spaces - Leonardi, Anthony; Mishra, Asit (Frontiers in Public Health, 2022)
Keywords: _z:class:countries

The effects of ventilation and temperature on sleep quality and next-day work performance: pilot measurements in a climate chamber - Fan, Xiaojun; Shao, Huiqi; Sakamoto, Mitsuharu; Kuga, Kazuki; Lan, Li; Wyon, David P.; Ito, Kazuhide; Bivolarova, Mariya P.; Liao, Chenxi; Wargocki, Pawel (Building and Environment, 2022)
Ten healthy young adults slept one by one in a specially designed and constructed sleep capsule located in a climate chamber at two temperatures (24 °C and 28 °C) and two ventilation rates that ensured that the resulting CO2 concentrations were 800 and 1700 ppm. Subjectively rated sleep quality was reduced at 28 °C and reduced ventilation, while sleep onset latency was longer under these conditions. Sleep efficiency was lower at 28 °C. Subjectively rated fatigue and sleepiness decreased after sleeping under all conditions but less so after sleeping at 28 °C. The subjects indicated that their work performance improved after sleeping at 24 °C but not when ventilation was reduced and the temperature increased. Both objectively measured and subjectively rated work performance was worse after sleeping in the condition with increased temperature. The subjects felt warmer at 28 °C although the thermal environment was still rated as acceptable but the air in the capsule was rated stuffier, the acceptability of the air quality decreased and the rated odour intensity increased at this condition. The wrist skin temperature was always higher at 28 °C with reduced ventilation but only during the sleep onset latency period. The subjects felt slightly warm and rated the air stuffier when ventilation was reduced. The present results, albeit from a small exploratory pilot study, show that increased temperature and reduced ventilation both have negative effects on sleep quality, which may have consequences for next-day work performance. These pilot experiment results require validation due to the low number of subjects.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.buildenv.2021.108666 2129771:BUB5I8PW 4682641:FPDE9BKS 5072953:TI7U7JQ5 openalex: W4200468114
Keywords: BE:RELEVANT; Next-day work performance; Physiological responses; Sleep quality; Temperature; Ventilation; _z:class:countries; _z:class:themes; oa:keyword:sleep quality; oa:sdg:13 Climate action; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11244 Impact of Climate Change on Human Health; oa:topic:T11373 Effects of Sleep Deprivation and Fatigue on Performance; openalex:n:1; openalex:yes

Analysis of various climate change parameters in India using machine learning - Wamanse, Rutvij; Patil, Tushuli (arXiv (Cornell University), 2022)
Climate change in India is one of the most alarming problems faced by our community. Due to adverse and sudden changes in climate in past few years, mankind is at threat. Various impacts of climate change include extreme heat, changing rainfall patterns, droughts, groundwater, glacier melt, sea-level rise, and many more. Machine Learning can be used to analyze and predict the graph of change using previous data and thus design a model which in the future can furthermore be used to catalyze impactful work of climate change and take steps in the direction to help India fight against the upcoming climate changes. In this paper, we have analyzed 17 climate change parameters about India. We have applied linear regression, exponential regression, and polynomial regression to the parameters and evaluated the results. Using the designed model, we will predict these parameters for the years 2025,2030, 2035. These predicted values will thus help our community to prevent and take actions against the adverse and hazardous effects on mankind. We have designed and created this model which provides accurate results regarding all 17 parameters. The predicted values will therefore help India to be well equipped against climate change. This data when made available to the people of India will help create awareness among them and will help us save our country from the haphazard effects of climate change.
openalex: W4221139878
Keywords: C:India; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:various climate change parameters; oa:sdg:13 Climate action; oa:topic:T11052 Electricity Price and Load Forecasting Methods; openalex:import; openalex:yes

Climate Change, Ageing and Disability: Life Experience of Being Old, Disabled and Affected by Climate-Induced Disasters in China (2022)
openalex: W4225102740
Keywords: _z:class:countries; openalex:import; openalex:yes

Covid-19: An urgent call for global "vaccines-plus" action - Greenhalgh, T; Griffin, Stephen; Gurdasani, D; Hamdy, A; Katzourakis, A; McKee, M; Michie, Susan; Pagel, C; Roberts, A; Yates, K; Alwan, Nisreen; Agius, R; et al. (BMJ: British Medical Journal, 2022)
Keywords: _z:class:countries

Using satellite data and deep learning to estimate educational outcomes in data-sparse environments - Runfola, D.; Stefanidis, A.; Baier, H. (Remote Sensing Letters, 2022)
The lack of systematic measurements of socioeconomic factors on a worldwide scale remains a significant challenge to our understanding of human well-being. A growing body of literature suggests that some of these measurement gaps can be filled using remote sensing, imputing human conditions on the ground based on the ways in which social groups have modified – or, not – their physical environment. In this article, we contribute to this growing body of literature by presenting a case study estimating school test scores based solely on publicly available imagery in both the Philippines (2010, 2014) and Brazil (2016). We contrast single image convolutional neural network (CNN) approaches to multisource ensembles and find predictive accuracy for individual schools across years and regions ranging from 76% to 80%. Finally, we discuss broader considerations related to the operational use of CNN-based approaches for measuring socioeconomic factors, and provide open source computer code for community use.

More Than Just Climate Change: The Search for Eco-socially Just Change Education in Canada - Blenkinsop, Sean; Ho, Yi Chien Jade (2022)
openalex: W4294911723
Keywords: C:Canada; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T12997 Experiential Education and Adventure Therapy; oa:topic:T14007 Place-Based Education in Rural Communities; openalex:import; openalex:yes

Chapter 3 - Typical environmental challenges - Emetere, Moses Eterigho (Numerical Methods in Environmental Data Analysis, 2022)
In this chapter, various environmental conditions or parameters that have wide extensive intricacy in environmental science are considered although the parameters are not all of the parameters that exist in environmental science. This chapter is expected to introduce a concept that would lead to selected environmental cases for the suceeding chapters.
KerkoCite.ItemAlsoKnownAs: 10.1016/B978-0-12-818971-9.00004-1 2129771:JHHBE25F 4874017:TBSTBZVW
Keywords: Challenges; Conditions; Environment; Model; evidence_review

Adaptive model for thermal comfort of students in secondary schools in the tropical city of Makassar - Hamzah, Baharuddin; Mulyadi, Rosady; Ishak, Muhammad Taufik (AIP Conference Proceedings, 2022)
This research aimed to examine the thermal comfort performance of students in naturally ventilated secondary schools’ classrooms in Makassar. The analysis compared the thermal balance and the adaptive model. The study analyzed data gathered from surveys conducted at eight secondary schools and local weather stations. The data consists of the measured indoor thermal environment of 48 classrooms. The personal data, users’ perceptions, and adaptive behaviors of 1,594 students were recorded in the questionnaire sheets. The questionnaire also recorded the thermal perception of students about the thermal environments of classrooms. In terms of thermal sensation, the study found that the neutral temperature estimated by PMV was overestimated the neutral temperature developed by actual votes of students. The PMV model estimated the neutral temperature of students at 23.0 °C which was about 7 °C lower than the neutral temperature calculated using the students’ actual thermal sensation votes (30.2 °C). This was a very big discrepancy between the predicted and the actual. The adaptive thermal comfort model produces more appropriate results than the PMV model. The modified Humphrey’s model predicted more close neutral temperature to the actual one which was 29.1 °C. Students adapt to the thermal environment through several activities. This adaptation makes students remain comfortable even in the hot thermal environment.
openalex:W4313047375 mag: KerkoCite.ItemAlsoKnownAs: 2129771:FFKMCPV6 2129771:FFKMCPV6 10.1063/5.0094787 5072953:R95ZVNPF
Keywords: _C:Indonesia; _z:class:countries; _z:class:themes; _z:no_pdf; evidence_review_2; oa:keyword:thermal comfort; oa:sdg:11 Sustainable cities and communities; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T12950 Learning Environments in Education

Including Sustainable Architectural Design in the Teaching Pedagogy: A District Adapted to the Desert Climate of the Oasis of Nafta–Tunisia - Jouini, Nour El Houda; Kharrat, Fakher; Chaabani, Mouldi; Zair, Kaouther (2022)
Nafta is an oasis located in the governorate of Tozeur in the South of Tunisia. The unique natural and built environment it offers has been degrading due to climate change, pollution, and overexploitation. Additionally, the new residential districts are unsuitable for the desert climate of the area. Not only do they fail to provide thermal comfort, especially during the heat waves, but also they contain non-eco-friendly materials such as concrete. However, we notice that the vernacular architecture respects the climate context and can serve as a reference. Teaching second-grade architecture students, we tried to include this in our pedagogy method to raise awareness about the matter. This paper presents the project of a sustainable district in Nafta conducted with the students during a workshop. The study shows that urban morphology and the building design can significantly influence the energy efficiency and the ecological footprint of the district. It also reveals that the vernacular architecture can be a reference to rebuilt contemporary eco-friendly cities.
openalex:W4226193814 mag: KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-030-76081-6_100 5072953:9S834NUJ
Keywords: C:Tunisia; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:sustainable architectural design; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:import; openalex:n:1; openalex:yes

Disaster and Climate Change-Induced Displacement of Persons with Disabilities: A Human Rights Perspective - Kälin, Walter (2022)
Disasters and adverse effects of climate change may significantly exacerbate pre-existing vulnerabilities of persons with disabilities. This is particularly true if such persons are displaced within their country or across borders. The systematic promotion and mainstreaming of disability-inclusive and rights-based approaches to disaster risk management and climate action are crucial to mitigate these challenges. The human rights of persons with disabilities which remain applicable during disasters and the principles of non-discrimination and equality of opportunity, participation and inclusion, accessibility, and reasonable accommodation help in shaping disability-inclusive measures to prevent displacement as well as the provision of protection and assistance during displacement. Finally, including persons with disabilities in programs and projects on durable solutions and ensuring their participation in decisions aimed at ending their displacement are crucial to avoid replicating and rebuilding barriers and ensuring their full and effective participation in society.
openalex: W4297840452
Keywords: _z:class:countries; openalex:import; openalex:yes

Adopting Indigenous Knowledge Systems to Enhance Peace Education Programs for Climate Change and Adaptation in Zimbabwe - Moyo-Nyoni, Ntombizakhe (2022)
In Zimbabwe, like many parts of the world, climate change has triggered the occurrence of conflicts, which exacerbates social, economic and political instabilities. In response to the global climate crisis, United Nations established Sustainable Development Goal 13 (SDG 13) in 2015, which advocates for taking action against climate change. The Zimbabwean government established its climate change policy in 2016, by drawing heavily on the thirteenth Sustainable Development Goal. Enshrined in SDG 13, is a call to incorporate various knowledge systems underpinned by its unique epistemology to tackle climate change. Thus, this chapter seeks to explore the use of Indigenous Knowledge Systems (IKS) in adapting to climate change. The IKS will be tested in the Lusulu ward, Lupane District, Matabeleland North Province, Zimbabwe (“Lusulu”). Primary data was sourced from focus group discussions and individual interviews. Findings revealed that the Lusulu community utilizes indigenous practices to safeguard their environment, such as the conservation of trees and the use of natural strategies such as crop rotation and use of organic matter to replenish the land. Furthermore, with regards to relationships damaged by climate changes, the indigenes apply non-violent techniques such as negotiations, mediations and consultations, which hinge on indigenous systems. The main goal of this chapter is to trigger conversations among policymakers, peace educators and civic society organisations in Sub-Saharan Africa, on the role which IKS can play in the handling of conflicts linked to climate change and, consequently, the proper facilitation of SDG 13.
openalex:W4285144254 mag: KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-030-99411-2_3 5072953:8DBUFBDI
Keywords: C:Zimbabwe; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:indigenous knowledge; oa:keyword:indigenous knowledge systems; oa:keyword:peace education programs; oa:sdg:13 Climate action; oa:topic:T10439 Adaptation to Climate Change in Agriculture; oa:topic:T12467 Rangeland Degradation and Pastoral Livelihoods; oa:topic:T12635 Struggle for National Identity in Zimbabwean History; openalex:import; openalex:n:1; openalex:yes

Towards an Integrated Approach to Climate Change Education in Tanzania: The Role of Indigenous Knowledge Systems - Mugabe, Paschal Arsein; Mbah, Marcellus; Apollo, Abigael; Mbah, Marcellus F. (Indigenous Methodologies, Research and Practices for Sustainable Development, 2022)
There have been many efforts globally toward fighting climate change; including international agreements, conferences, research, policies, forums, etc. In addition to these efforts, climate change education has recently emerged as an essential capacity-building tool to curb the climate crisis. However, development practitioners from the Global South have cited limitations with climate change education due to the dominance of Eurocentric epistemologies over indigenous knowledge (IK) approaches. This study therefore advocates for the integration of indigenous knowledge into climate change education in Tanzania for achieving a sustainable environment. Seventy documents, including peer-reviewed papers, reports from corporate institutions, policy briefs, proceedings and other grey literature were reviewed. We establish that IK systems are not integrated into CCE in Tanzania. However, we find opportunities for integration due to the evidence of the existing CCE efforts and potential complementary indigenous practices. By identifying, documenting, and validating indigenous knowledge and merging this knowledge with scientific insights, the fostering of an integrated approach to combat the enduring effects of climate change can be evidenced.
openalex:W4312587358 mag: KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-031-12326-9_16 5072953:7MNR46WW 5072953:F3ACIBMT
Keywords: C:Tanzania; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change education; oa:keyword:indigenous knowledge systems; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T12656 Impact of Climate Change on Human Migration; oa:topic:T13839 Volunteer Tourism and Global Development Impacts; openalex:import; openalex:n:1; openalex:yes

Climate change and the right to health of people with disabilities - Stein, Penelope J. S.; Stein, Michael Ashley (The Lancet Global Health, 2022)
Climate change is directly and disproportionately threatening the right to health of people with disabilities due to higher ambient temperatures, elevated air pollutants, and increasing exposure to extreme weather events that include heatwaves, floods, hurricanes, and wildfires. Strikingly, the global mortality rate of people with disabilities in natural disasters is up to four times higher than people without disabilities due to a scarcity of inclusive planning, accessible information, early warning systems, transportation, and discriminatory attitudes within institutions and among individuals.1Izutsu T Disability-inclusive disaster risk reduction and humanitarian action: an urgent global imperative.https://www.un.org/development/desa/disabilities/wp-content/uploads/sites/15/2020/03/Final-Disability-inclusive-disaster.pdfDate: Nov 29, 2019Date accessed: November 19, 2021Google Scholar Disasters also disrupt access to health-care services, medications, oxygen, haemodialysis, personal care assistance, and medical devices. Heat extremes are linked with elevated emergency room visits, hospital admittance, and mortality for individuals with mental health, cardiorespiratory, and other disabilities; pre-existing psychosocial disabilities triples the risk of death during heatwaves.2Bouchama A Dehbi M Mohamed G Matthies F Shoukri M Menne B Prognostic factors in heatwave-related deaths: a meta-analysis.Arch Intern Med. 2007; 167: 2170-2176Crossref PubMed Scopus (311) Google Scholar High ambient temperatures also negatively affect the health of individuals whose disabilities are affected by temperature sensitivity or thermoregulation, including multiple sclerosis and spinal cord injuries. Likewise, numerous medications, including diuretics and antidepressants, can affect the thermoregulation of people with mental and physical disabilities.3Ebi KL Capon A Berry P et al.Hot weather and heat extremes: health risks.Lancet. 2021; 398: 698-708Summary Full Text Full Text PDF PubMed Scopus (81) Google Scholar More broadly, climate change increases the risk of undernutrition, water insecurity, stress-related psychiatric disorders, and alters the geographical distribution of infectious diseases.Climate change exacerbates existing inequalities with indirect disproportionate effects on people with disabilities due to their lack of access to health-care services and increased exposure to social determinants of health such as poverty, and lack of access to education, employment, or adequate housing. Often individuals with disabilities experience intersecting forms of multiple discrimination from belonging to specific groups including women, Indigenous people, children, racial minorities, and older people. The COVID-19 pandemic highlights and intensifies these inequalities.4Shakespeare T Ndagire F Seketi QE Triple jeopardy: disabled people and the COVID-19 pandemic.Lancet. 2021; 397: 1331-1333Summary Full Text Full Text PDF PubMed Scopus (44) Google Scholar Ironically, those with disabilities most at risk from climate change have contributed the least to greenhouse gases, including the 800 million people with disabilities living in low-income countries.5UN Department of Economic and Social AffairsFactsheet on persons with disabilities.https://www.un.org/development/desa/disabilities/resources/factsheet-on-persons-with-disabilities.htmlDate accessed: November 25, 2021Google Scholar Accordingly, climate vulnerability and the right to health of people with disabilities is being increasingly acknowledged, including within the Paris Agreement.The threat of climate change to people with disabilities' right to health urgently necessitates that governments reduce greenhouse gas emissions. States failing to comply with the Paris Agreement obligations or excluding disability from climate change mitigation and adaption efforts, are violating human rights obligations, including the UN Convention on the Rights of Persons with Disabilities.6Stein MA Stein PJ Weiss D Lang R Health care and the UN Disability Rights Convention.Lancet. 2009; 374: 1796-1798Summary Full Text Full Text PDF PubMed Scopus (34) Google Scholar In 2021, an individual with temperature-dependent multiple sclerosis, Uhthoff's syndrome, filed a law suit against the Austrian government alleging that a failure to set effective climate protection measures violated his human rights.7Mex M v Austria. European Court on Human Rights; Strasbourg, France; March 25, 2021.Google ScholarClimate change adaptation provides a global opportunity to increase health equality for people with disabilities as required by the UN Sustainable Development Goals, using the human rights principles of participation, inclusion, empowerment, non-discrimination, and accessibility. Attaining climate resilient health equality will require empowering people with disabilities and their organisations to represent their needs and identify solutions in equitable participatory planning and implementation processes, verified by disability indicators and intersectional analyses. Governments should include disability organisations as stakeholders to ensure disability-inclusive health adaption planning. Disability indicators and disaggregated data are crucial for the development of disability-inclusive policies.8The Lancet Global HealthDisability: measurement matters.Lancet Glob Health. 2021; 9e1028Summary Full Text Full Text PDF Scopus (3) Google Scholar Health-care facilities must be accessible, including post-disaster; laudably, the World Bank has committed to inclusive post-disaster reconstruction. A UN Framework Convention on Climate Change disability constituency and disability action plan, both absent from COP26, would facilitate disability leadership in climate change action.Health-care professionals, throughout their education, should receive training on the effects of climate change on the health of individuals with disabilities and disability cultural competency. Clinical trials inclusive of people with disabilities are required to determine how medications affect body temperature regulation at high temperatures. Enabling people with disabilities to enter health-care professions and collaborate in development and disaster risk reduction can provide untapped knowledge on disability discrimination and adaptation. Future research is crucially needed on the effect of climate change mitigation and adaption measures, and targeted disability-inclusive approaches, on the health of people with disabilities—particularly in low-income and middle-income countries—to foster best practices for enhancing climate resilience. Climate change is directly and disproportionately threatening the right to health of people with disabilities due to higher ambient temperatures, elevated air pollutants, and increasing exposure to extreme weather events that include heatwaves, floods, hurricanes, and wildfires. Strikingly, the global mortality rate of people with disabilities in natural disasters is up to four times higher than people without disabilities due to a scarcity of inclusive planning, accessible information, early warning systems, transportation, and discriminatory attitudes within institutions and among individuals.1Izutsu T Disability-inclusive disaster risk reduction and humanitarian action: an urgent global imperative.https://www.un.org/development/desa/disabilities/wp-content/uploads/sites/15/2020/03/Final-Disability-inclusive-disaster.pdfDate: Nov 29, 2019Date accessed: November 19, 2021Google Scholar Disasters also disrupt access to health-care services, medications, oxygen, haemodialysis, personal care assistance, and medical devices. Heat extremes are linked with elevated emergency room visits, hospital admittance, and mortality for individuals with mental health, cardiorespiratory, and other disabilities; pre-existing psychosocial disabilities triples the risk of death during heatwaves.2Bouchama A Dehbi M Mohamed G Matthies F Shoukri M Menne B Prognostic factors in heatwave-related deaths: a meta-analysis.Arch Intern Med. 2007; 167: 2170-2176Crossref PubMed Scopus (311) Google Scholar High ambient temperatures also negatively affect the health of individuals whose disabilities are affected by temperature sensitivity or thermoregulation, including multiple sclerosis and spinal cord injuries. Likewise, numerous medications, including diuretics and antidepressants, can affect the thermoregulation of people with mental and physical disabilities.3Ebi KL Capon A Berry P et al.Hot weather and heat extremes: health risks.Lancet. 2021; 398: 698-708Summary Full Text Full Text PDF PubMed Scopus (81) Google Scholar More broadly, climate change increases the risk of undernutrition, water insecurity, stress-related psychiatric disorders, and alters the geographical distribution of infectious diseases. Climate change exacerbates existing inequalities with indirect disproportionate effects on people with disabilities due to their lack of access to health-care services and increased exposure to social determinants of health such as poverty, and lack of access to education, employment, or adequate housing. Often individuals with disabilities experience intersecting forms of multiple discrimination from belonging to specific groups including women, Indigenous people, children, racial minorities, and older people. The COVID-19 pandemic highlights and intensifies these inequalities.4Shakespeare T Ndagire F Seketi QE Triple jeopardy: disabled people and the COVID-19 pandemic.Lancet. 2021; 397: 1331-1333Summary Full Text Full Text PDF PubMed Scopus (44) Google Scholar Ironically, those with disabilities most at risk from climate change have contributed the least to greenhouse gases, including the 800 million people with disabilities living in low-income countries.5UN Department of Economic and Social AffairsFactsheet on persons with disabilities.https://www.un.org/development/desa/disabilities/resources/factsheet-on-persons-with-disabilities.htmlDate accessed: November 25, 2021Google Scholar Accordingly, climate vulnerability and the right to health of people with disabilities is being increasingly acknowledged, including within the Paris Agreement. The threat of climate change to people with disabilities' right to health urgently necessitates that governments reduce greenhouse gas emissions. States failing to comply with the Paris Agreement obligations or excluding disability from climate change mitigation and adaption efforts, are violating human rights obligations, including the UN Convention on the Rights of Persons with Disabilities.6Stein MA Stein PJ Weiss D Lang R Health care and the UN Disability Rights Convention.Lancet. 2009; 374: 1796-1798Summary Full Text Full Text PDF PubMed Scopus (34) Google Scholar In 2021, an individual with temperature-dependent multiple sclerosis, Uhthoff's syndrome, filed a law suit against the Austrian government alleging that a failure to set effective climate protection measures violated his human rights.7Mex M v Austria. European Court on Human Rights; Strasbourg, France; March 25, 2021.Google Scholar Climate change adaptation provides a global opportunity to increase health equality for people with disabilities as required by the UN Sustainable Development Goals, using the human rights principles of participation, inclusion, empowerment, non-discrimination, and accessibility. Attaining climate resilient health equality will require empowering people with disabilities and their organisations to represent their needs and identify solutions in equitable participatory planning and implementation processes, verified by disability indicators and intersectional analyses. Governments should include disability organisations as stakeholders to ensure disability-inclusive health adaption planning. Disability indicators and disaggregated data are crucial for the development of disability-inclusive policies.8The Lancet Global HealthDisability: measurement matters.Lancet Glob Health. 2021; 9e1028Summary Full Text Full Text PDF Scopus (3) Google Scholar Health-care facilities must be accessible, including post-disaster; laudably, the World Bank has committed to inclusive post-disaster reconstruction. A UN Framework Convention on Climate Change disability constituency and disability action plan, both absent from COP26, would facilitate disability leadership in climate change action. Health-care professionals, throughout their education, should receive training on the effects of climate change on the health of individuals with disabilities and disability cultural competency. Clinical trials inclusive of people with disabilities are required to determine how medications affect body temperature regulation at high temperatures. Enabling people with disabilities to enter health-care professions and collaborate in development and disaster risk reduction can provide untapped knowledge on disability discrimination and adaptation. Future research is crucially needed on the effect of climate change mitigation and adaption measures, and targeted disability-inclusive approaches, on the health of people with disabilities—particularly in low-income and middle-income countries—to foster best practices for enhancing climate resilience. We declare no competing interests.
openalex: W4200083773
Keywords: _z:class:countries; openalex:import; openalex:yes

An Occupant-Centric Control Strategy for Indoor Thermal Comfort, Air Quality and Energy Management - WANG, ZU; Calautit, John Kaiser; Tien, Paige; Wei, Shuangyu; Zhang, Wuxia; Wu, Yupeng; Xia, Liang (SSRN Electronic Journal, 2022)
KerkoCite.ItemAlsoKnownAs: 10.2139/ssrn.4293660 5072953:9MHRD9Z2 openalex: W4318815365
Keywords: _z:class:countries; _z:class:themes; _z:no_pdf; _z:not_duplicate; oa:keyword:indoor thermal comfort; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; openalex:n:1; openalex:yes

The significance of disadvantaged crop species to improve food systems and security in the changing climate: Learning from Motheo District, South Africa - Zuma-Netshiukhwi, G. (International Journal of Agriculture and Nutrition, 2022)
Emerging evidence indorse shifts in food production, reduction in yield due to climate variability and change. An increase in food production is a requirement to respond to the demands of the growing population worldwide. As many studies focus on underutilised and/or neglected crops. The questions are, underutilised by who? Or neglected by who? These are the indigenous ancient crop species utilised from generations to generations, which are used by most in rural areas mostly across all African countries. These crop species are utilised for consumption and medicinal purposes within localities, needs to be acknowledged, supported and not grouped as food for the “poor” or “weeds”. Besides, its promotion as a food of choice is the best climate change adaptation strategy. A huge variety of crops avails rather than relying on few crop species. Utilisation of selected few crops leaves the abundance of genetic resources for food security and nutrition. Focusing on the promotion of disadvantaged crops would provide a diversified agricultural system and food resources. Such crop species play an integral role for income generation and nutritional balance. The crop species have a great prospective to enhance crop diversity, food variety and nutrition. Field management systems plays a significant role on when to introduce weeding control mechanisms, when to harvest and which types of these crops to expect per season. With the use of transdisciplinary research approach, we provide a list of disadvantaged crop species and evidence to improve food and nutrition security, increase agricultural diversification, minimise environmental and its physiological response show resilience in the changing climate.
openalex:W4379043718 mag: KerkoCite.ItemAlsoKnownAs: 10.33545/26646064.2022.v4.i1a.53 5072953:TQU6MS5S
Keywords: C:South Africa; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:disadvantaged crop species; oa:topic:T10367 Agricultural Innovation and Livelihood Diversification; oa:topic:T12403 Nutritional and Functional Potential of Ancient Grains; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Performance optimization of natural ventilation in classrooms to minimize the probability of viral infection and reduce draught risk - Fageha, Mohammed K.; Alaidroos, Alaa (Sustainability, 2022)
This paper presents a detailed analysis to optimize natural ventilation performance in educational buildings to minimize the probability of viral infection (POI) and avoid draught discomfort. A whole building energy simulation tool has been coupled with the Wells–Riley equation to predict the probability of infection and Fanger’s draught equation to estimate the draught risk for classroom environments. Several parameters have been investigated, including window opening fraction (WOF), volume-to-student ratio, number of source patients, and exposure time. The analysis confirmed a dual effect of space volume on the POI where the POI can be increased or decreased simultaneously when the space volume is increased. Therefore, the WOF/(Volume/Student) ratio is introduced, and an optimization analysis is performed to determine the optimum ratio that delivers the lowest POI. The results showed that a WOF/(Volume/Student) ratio between 0.1 and 0.17 is recommended to guarantee low values of POI for a standard Volume/Student ratio of 6 m3. Even though high ventilation rates are required to prevent viral infection, it will certainly increase the draught risk. Therefore, optimal ventilation rates are required to maintain low POI and minimum draught risk, which can be achieved by optimum design of windows and implementing control systems for window operations to minimize turbulence effects and reduce the possibility of draught discomfort.
Number: 22 Publisher: Multidisciplinary Digital Publishing Institute KerkoCite.ItemAlsoKnownAs: 10.3390/su142214966 4874017:Z7KC6JMM 5072953:F9ZHY8PD openalex: W4309008685
Keywords: _z:class:countries; _z:class:themes; airborne viral infection; draught risk; educational buildings; indoor air quality; natural ventilation; openalex:n:1; openalex:yes

Performance optimization of natural ventilation in classrooms to minimize the probability of viral infection and reduce draught risk - Fageha, Mohammed K.; Alaidroos, Alaa (Sustainability, 2022)
This paper presents a detailed analysis to optimize natural ventilation performance in educational buildings to minimize the probability of viral infection (POI) and avoid draught discomfort. A whole building energy simulation tool has been coupled with the Wells–Riley equation to predict the probability of infection and Fanger’s draught equation to estimate the draught risk for classroom environments. Several parameters have been investigated, including window opening fraction (WOF), volume-to-student ratio, number of source patients, and exposure time. The analysis confirmed a dual effect of space volume on the POI where the POI can be increased or decreased simultaneously when the space volume is increased. Therefore, the WOF/(Volume/Student) ratio is introduced, and an optimization analysis is performed to determine the optimum ratio that delivers the lowest POI. The results showed that a WOF/(Volume/Student) ratio between 0.1 and 0.17 is recommended to guarantee low values of POI for a standard Volume/Student ratio of 6 m3. Even though high ventilation rates are required to prevent viral infection, it will certainly increase the draught risk. Therefore, optimal ventilation rates are required to maintain low POI and minimum draught risk, which can be achieved by optimum design of windows and implementing control systems for window operations to minimize turbulence effects and reduce the possibility of draught discomfort.
Number: 22 KerkoCite.ItemAlsoKnownAs: 10.3390/su142214966 4874017:Z7KC6JMM 5072953:F9ZHY8PD openalex: W4309008685
Keywords: _z:class:countries; _z:class:themes; airborne viral infection; draught risk; educational buildings; indoor air quality; natural ventilation; oa:keyword:natural ventilation; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10990 Airborne Transmission of Respiratory Viruses; oa:topic:T11692 Effects of Noise Pollution on Health and Well-being; openalex:n:1; openalex:yes

Validation of Designbuilder Simulation Accuracy Using Field Measured Data of Indoor Air Temperature in a Classroom Building - Abba, Habu Yusuf; Majid, Roshida Abdul; Ahmed, Muhammad Hamdan; Gbenga, Olutobi (Management, 2022)
KerkoCite.ItemAlsoKnownAs: 2129771:4UHQEB9X 4682641:55AFYSVG 5072953:WM5Q6W8Y
Keywords: BE:RELEVANT; _z:class:countries; _z:class:themes; ⛔ No DOI found

Combined effects of ventilation rates and indoor temperatures on cognitive performance of female higher education students in a hot climate - Ahmed, Riham; Mumovic, Dejan; Bagkeris, Emmanouil; Ucci, Marcella (Indoor air, 2022)
Impairment in mental functions attributed to the effects of indoor air quality and thermal conditions has received considerable attention in the past decade, particularly for educational buildings where students’ cognitive performance is essential to foster learning. This study explores the combined effects of indoor temperatures and CO2 levels as markers for ventilation rates on cognitive performance among female students (16–23 years old) in Saudi Arabia. The longitudinal experiments involved nine conditions combining three CO2 concentration levels (achieved via changes in ventilation) and three temperature levels involving 499 participants, all exposed to the nine conditions. The study implemented a computer-based cognitive performance battery with “9Button” keyboards. Univariable and multivariable multilevel regression models explored the association of indoor temperature and CO2 levels (as markers for ventilation rates) with cognitive performance after adjusting for potential confounders. Potential benefits were found on speed and accuracy of tasks of cognitive perfor- mance when indoor temperature was set between 20 and 23ºC and at CO2 levels of 600 ppm compared to higher temperatures and poorer ventilation rates and that both ventilation and thermal environmental control are important and need to be improved for achieving optimum learning conditions. Nevertheless, the results are relevant for short-term exposures lasting no more than 2 h.
openalex: W4211195236 KerkoCite.ItemAlsoKnownAs: 10.1111/ina.13004 2129771:7WXPHPA2 4682641:MM48GLCP 5072953:ANVRVIK3 5072953:NQLCUEPF
Keywords: BE:RELEVANT; C:Saudi Arabia; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11002 Indoor Air Quality and Health Effects; oa:topic:T11244 Impact of Climate Change on Human Health; openalex:n:1; openalex:yes

Effects of thermal sensation and acclimatization on cognitive performance of adult female students in Saudi Arabia using multivariable-multilevel statistical modeling - Ahmed, Riham; Ucci, Marcella; Mumovic, Dejan; Bagkeris, Emmanouil (Indoor air, 2022)
In the hot climate of Saudi Arabia, people living year-round in air-conditioned spaces are likely to develop high expectations for homogeneity and cool temperatures, becoming potentially more sensitive if thermal conditions deviate from the comfort zone they expect. This paper presents the results from a field intervention investigating the association between participants’ thermal sensations with cognitive performance in a female university in Saudi Arabia. The climatic context plays a key role in choosing Saudi Arabia, whereas the total reliance on air-conditioners (AC) for cooling is believed to have significant effects on occupants’ perceptions of the comfort temperature. Results reveal discrepancies in the actual thermal sensations between the Saudi and non-Saudi participants which affected their performances. “Cool” and “Slightly Cool” sensations versus neutral were associated with significant lower percentage of errors and significant higher speed for all participants independently of any association with ethnicity and acclimatization. The estimates remained significant even after adjusting for ethnicity and the number of years spent in the country and the set temperature of AC at home. Implications of the study suggest a preference for staying cool when working independently of acclimatization status. Practical Implications. This study confirms that there is a strong association between indoor temperature, thermal sensations, and cognitive performance in young adult female students. The practical implications of this research highlight that findings from previous studies may not be applicable to climates such as Saudi Arabia, where the pervasive presence of air-conditioning is not only affecting occupants’ preferences for cooler temperatures, but may also impact on their cognitive performance at lower temperatures, compared with other climatic regions.
KerkoCite.ItemAlsoKnownAs: 10.1111/ina.13005 2129771:UE8PMH8F 4682641:XU7Y5YK5 5072953:MU9EYDVY openalex: W4212818674
Keywords: BE:RELEVANT; C:Saudi Arabia; _z:class:countries; _z:class:themes; evidence_review; oa:keyword:thermal sensation; oa:sdg:13 Climate action; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11692 Effects of Noise Pollution on Health and Well-being; oa:topic:T12950 Learning Environments in Education; openalex:n:1; openalex:yes

Deconstructing Community-Based Research for Sustainable Development: The Role of Indigenous Knowledge Holders - Ajaps, Sandra; Mbah, Marcellus F. (Indigenous Methodologies, Research and Practices for Sustainable Development, 2022)
Series Title: World Sustainability Series KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-031-12326-9_4 5072953:Y2Y5Q6AF
Keywords: _z:class:countries; _z:class:themes

Cooking Aerosol - Amouei Torkmahalleh, Mehdi (Handbook of Indoor Air Quality, 2022)
Keywords: _z:class:countries

Engaging local youths in humanitarian response is not a matter of if but how - Apollo, Abigael; Mbah, Marcellus Forh (Journal of International Humanitarian Action, 2022)
Abstract Despite being critical responders in humanitarian crises, local youths are continually left out of the humanitarian action agenda. This paper used a qualitative methodology to investigate local youths’ role in humanitarian response and their impacts and assessed how humanitarian actors influence the effectiveness of youth engagement. The data was collected through semi-structured interviews with local youths who participated in the Ebola response in Sierra Leone. Findings showed that young people are significantly contributing to crises response. However, they lack an enabling environment and support system to convert their skills into valuable humanitarian resources efficiently. Therefore, despite the rhetoric that many reports and policies reflect, this study establishes that the realities of youth engagement in humanitarian activities are often misunderstood and controlled for the self-interest of different actors other than youths themselves. It advocates for a renewed focus and support for young people’s skills as paramount for effective humanitarian response and building back resilient communities after emergencies. Besides, engaging local youths in tackling crises empowers them with transferable skills and stimulates their passion for participating in development issues within their communities.
KerkoCite.ItemAlsoKnownAs: 10.1186/s41018-022-00118-x 5072953:G7EVXRD4 openalex: W4226148211
Keywords: C:Sierra Leone; _z:class:countries; _z:class:themes; oa:keyword:humanitarian response; oa:keyword:local youths; oa:topic:T10747 Community Resilience to Natural Disasters; oa:topic:T11556 Impact of Child Labor Interventions; oa:topic:T11581 Ebola Virus Research and Outbreaks; openalex:n:1; openalex:yes

Engaging local youths in humanitarian response is not a matter of if but how - Apollo, Abigael; Mbah, Marcellus Forh (Journal of International Humanitarian Action, 2022)
Abstract Despite being critical responders in humanitarian crises, local youths are continually left out of the humanitarian action agenda. This paper used a qualitative methodology to investigate local youths’ role in humanitarian response and their impacts and assessed how humanitarian actors influence the effectiveness of youth engagement. The data was collected through semi-structured interviews with local youths who participated in the Ebola response in Sierra Leone. Findings showed that young people are significantly contributing to crises response. However, they lack an enabling environment and support system to convert their skills into valuable humanitarian resources efficiently. Therefore, despite the rhetoric that many reports and policies reflect, this study establishes that the realities of youth engagement in humanitarian activities are often misunderstood and controlled for the self-interest of different actors other than youths themselves. It advocates for a renewed focus and support for young people’s skills as paramount for effective humanitarian response and building back resilient communities after emergencies. Besides, engaging local youths in tackling crises empowers them with transferable skills and stimulates their passion for participating in development issues within their communities.
KerkoCite.ItemAlsoKnownAs: 10.1186/s41018-022-00118-x 5072953:G7EVXRD4 openalex: W4226148211
Keywords: _z:class:countries; _z:class:themes; oa:keyword:humanitarian response; oa:keyword:local youths; oa:topic:T10747 Community Resilience to Natural Disasters; oa:topic:T11556 Impact of Child Labor Interventions; oa:topic:T11581 Ebola Virus Research and Outbreaks; openalex:n:1; openalex:yes

Education, anthropogenic environmental change and sustainable development: A rudimentary framework and reflections on proposed causal pathways for positive change in low and lower middle-income countries - Bangay, Colin (Development Policy Review, 2022)
The article seeks to support policy-makers in considering the role of education in response to the climate–environment emergency. It argues for a holistic framing of education's response, incorporating both climate and environment. While recognizing the imperative of global action, it emphasizes the need for national/local education systems approaches that reflect the distinct and localized challenges and responsibilities pertinent to high-income countries (HICs) and low- and lower-middle income counties (L&LMICs). Purpose After presenting an overview of climate–environmental issues and education the article offers a rudimentary framework categorizing education responses to anthropogenic environmental change (AEC). Methods and approach The article brings together findings from education, demography, disaster risk reduction (DRR), and environmental studies. Findings The key findings are: (1) that education provision in L&LMICs is already being affected by environmental change; (2) the causal links between education and positive environmental impacts are weakly evidenced; (3) the bulk of literature is preoccupied with global climate change and CO2 emissions to the detriment of localized environmental considerations; and (4) that education should be viewed more as a “force multiplier”—alongside areas such as health, reproductive rights, social justice, and livelihoods. Policy implications The article argues that to achieve Sustainable Development Goal (SDG) 4.7—whereby education systems of all nations equip students for sustainable development—there is a need for a more geographically specific understanding of the drivers of both climate change and environmental degradation. Differentiated education reform responses are required which reflect both responsibility for carbon emissions and vulnerability to climate and environmental impacts. In HICs this would suggest a greater focus on mitigation (reduction of carbon emissions) and in L&LMICs on adaptation (responding to AEC).
openalex: W4200081357 KerkoCite.ItemAlsoKnownAs: 10.1111/dpr.12615 2129771:KSD4L4BL 4682641:92NLNTIW 4874017:ABPQD88F 5072953:6SJI8BK4 5072953:9HV3AQA6 5072953:DWQMPBJN 5072953:MMNZDMRC 5072953:SRP5U6HW 5072953:UTCADFVL 5440726:DU2FMVU3
Keywords: BE:RELEVANT; _z:class:countries; _z:class:themes; _z:no_pdf; climate; demography; education; environment; oa:keyword:anthropogenic environmental change; oa:keyword:sustainable development; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11336 Indoor Air Pollution in Developing Countries; oa:topic:T12656 Impact of Climate Change on Human Migration; openalex:n:1; openalex:yes; system; ⛔ No DOI found

Agriculture, climate change and technical efficiency: The case of sub-Saharan Africa - Bannor, Frank (University of Johannesburg, 2022)
Keywords: _z:class:countries

Occupant Emissions and Chemistry - Bekö, Gabriel; Wargocki, Pawel; Duffy, Emer (Handbook of Indoor Air Quality, 2022)
Keywords: _z:class:countries

The Effects of Air Temperature to the Cognitive Performance of Grade Five Pupils - Bigueja, Myrna C.; Tabardillo, Rosemarie A.; Amoroso, Sheila E.; Tabardillo, Joselito D. (2022)
High temperature makes the children uneasy during classroom activities. This study examines the effect of air temperature to children‟s cognitive performance. The school profile was determined such as: the total number of teachers, number of enrollees, land area (sq.m.), number of buildings and number of trees was determined to support the analysis of the data collected. The respondents were the Top thirty (30) Grade V pupils from public city elementary school in the Bicol Region. The pen-and-paper test was administered using the standardized test question in Science V of forty (40) items. The examination was done in the room without ventilation at 9:00 O‟clock to 11 O‟clock in the morning. Outdoor and indoor air temperature was recorded. The temperature recorded in the seven Public Central City Elementary Schools ranged from 240C to 310C. The recorded temperature indicates that the air contains particulates or pollutants like CO2 resulting in high temperature. Future work is required to establish evidence based guidelines for average temperatures and CO2 levels in classrooms. Findings suggest that high ventilation rates and low temperatures are required to provide optimum health outcomes and learning conditions. Natural Ventilation is also recommended through planting more trees in school vicinity to provide fresher air.
KerkoCite.ItemAlsoKnownAs: 4874017:95QJB2CK 4874017:95QJB2CK 2129771:FU6YMJ8Z 4682641:84YTA4AD 5072953:XSX7GKLA
Keywords: BE:RELEVANT; C:Philippines; _z:class:countries; _z:class:themes; evidence_review_2; ⛔ No DOI found

Indoor Air Quality in Offices - Cattaneo, Andrea; Spinazzè, Andrea; Cavallo, Domenico M. (Handbook of Indoor Air Quality, 2022)
Keywords: _z:class:countries

Localising knowledge systems - Chipindi, Ferdinand Mwaka; Johnson, Ane Turner; Mbah, Marcellus Forh (Decolonising African Higher Education, 2022)
KerkoCite.ItemAlsoKnownAs: 5072953:3AJZEPR5
Keywords: _z:class:countries; _z:class:themes

Integrated artificial neural network prediction model of indoor environmental quality in a school building - Cho, Ji Hyeon; Moon, Jin Woo (Journal of Cleaner Production, 2022)
KerkoCite.ItemAlsoKnownAs: 10.1016/j.jclepro.2022.131083 5072953:JXB63T88 openalex: W4214705633
Keywords: _important; _z:class:countries; _z:class:themes; oa:keyword:indoor environmental quality; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T12120 Low-Cost Air Quality Monitoring Systems; openalex:n:1; openalex:yes; selected_for:Predictive models for classroom conditions 2024

Integrated Phase Change Material windcatcher system for hybrid cooling and ventilation in tropical building - Eso, Olamide; Darkwa, Jo; Calautit, John (2022)
This study presents a novel solar fan-assisted multi-directional windcatcher (MDW) with encapsulated phase change material tubes (E-PCMT) for tropical buildings. The ventilation, cooling, and thermal storage performance of the integrated ventilative cooling system is investigated using Computational Fluid Dynamics (CFD) Ansys Fluent software under tropical climate conditions. A parametric geometric analysis of three different E-PCMT configurations with melting temperatures at 28oC was conducted to assess the thermal storage performance at different air velocities. The impact of the optimised EPCMT when incorporated inside the air stream of the MDW was further studied. To overcome air flow resistance caused by the obstruction by EPCM-T inside the air streams, the windcatcher airflow is assisted by a wall-mounted axial solar fan that is activated when outdoor air velocity is less than 2m/s. The results based on a typical tropical location showed that the system was able to achieve a consistent and stable air temperature drop of up to 2.64oC over a 4-6-hour. Even at an outdoor air velocity of 1.88m/s, the novel integrated system, in addition to its cooling performance was still able to achieve a supply air velocity rate of 0.16 - 0.57 m/s, meeting the ventilation rates required for indoor comfort.
KerkoCite.ItemAlsoKnownAs: 4874017:GA76HUTU 5072953:NEMABBUB
Keywords: _z:class:countries; _z:class:themes; ⛔ No DOI found

Integrated Phase Change Material windcatcher system for hybrid cooling and ventilation in tropical building - Eso, Olamide; Darkwa, Jo; Calautit, John (2022)
This study presents a novel solar fan-assisted multi-directional windcatcher (MDW) with encapsulated phase change material tubes (E-PCMT) for tropical buildings. The ventilation, cooling, and thermal storage performance of the integrated ventilative cooling system is investigated using Computational Fluid Dynamics (CFD) Ansys Fluent software under tropical climate conditions. A parametric geometric analysis of three different E-PCMT configurations with melting temperatures at 28oC was conducted to assess the thermal storage performance at different air velocities. The impact of the optimised EPCMT when incorporated inside the air stream of the MDW was further studied. To overcome air flow resistance caused by the obstruction by EPCM-T inside the air streams, the windcatcher airflow is assisted by a wall-mounted axial solar fan that is activated when outdoor air velocity is less than 2m/s. The results based on a typical tropical location showed that the system was able to achieve a consistent and stable air temperature drop of up to 2.64oC over a 4-6-hour. Even at an outdoor air velocity of 1.88m/s, the novel integrated system, in addition to its cooling performance was still able to achieve a supply air velocity rate of 0.16 - 0.57 m/s, meeting the ventilation rates required for indoor comfort.
KerkoCite.ItemAlsoKnownAs: 2129771:EXW7YRGB 4874017:GA76HUTU
Keywords: evidence_review; ⛔ No DOI found

Secondary education provision and impacts of low secondary uptake on wider societal outcomes - Fitzpatrick, R. (Institute of Development Studies, 2022)
KerkoCite.ItemAlsoKnownAs: 5440726:GPNKTFNK 5440726:U89MPHPE
Keywords: _z:class:countries

Improving Resilience, Adaptation and Mitigation to Climate Change Through Education in Low- and Lower-middle Income Countries - Fitzpatrick, Rachael; West, Helen (Institute of Development Studies, 2022)
Climate resilience is the ability to anticipate, prepare for, and respond to hazardous events, trends, or disturbances related to climate (C2ES, 2022). Mitigation focuses on reducing the human impacts contributing to climate change (Burton, 2007, cited in Rousell & Cutter-Mackenzie-Knowles, 2020). Adaptation is about increasing people’s adaptive capacity, reducing the vulnerability of communities and managing risks (Anderson, 2012). Anderson further defines adaptation as not just being able to adapt from one stable climate to another but having the skills to adapt to uncertainty and make informed decisions in a changing environment. While ‘climate change’ is the term used throughout these briefs, it should be read as a shorthand for a more inclusive approach, which also captures associated environmental degradation. The Intergovernmental Panel on Climate Change (IPCC) warned, in their latest report, that global surface temperatures will continue to increase until 2050 (IPCC, 2021, p. 17). This will take place regardless of human intervention to reduce greenhouse gas emissions. The report also warns that the traditional technocratic approaches are insufficient to tackle the challenge of climate change, and that greater focus on the structural causes is needed. High- and upper-middle-income countries have been persistently shown to be the biggest contributors to the global carbon dioxide emissions, with lower income countries facing the most disruptive climate hazards, with Africa countries particularly vulnerable (CDP, 2020; IPCC, 2021). The vulnerability of low-income contexts exacerbates this risk, as there is often insufficient infrastructure and resources to ensure resilience to climate hazards (IPCC, 2021). For decades, advocates of climate change education have been highlighting the potential of education to help mitigate against climate change, and support adaptation efforts. However, implementation has been patchy, with inconsistent approaches and a lack of evidence to help determine the most effective way forward.This paper is divided into three sections, drawing together evidence on the key aspects of system reform,green and resilient infrastructure and Curriculum, pedagogy, assessment and teacher development.
Accepted: 2022-08-22T10:47:53Z KerkoCite.ItemAlsoKnownAs: 5072953:82L5RABA 5072953:Y825QEQ2 5440726:4NQRZ633
Keywords: _z:class:countries

Forging a university-aided indigenous community education: Village elders and social development in a secondary city of Cameroon - Fonchingong, Charles Che; Mbah, Marcellus (Universities, Society and Development: African Perspectives of University Community Engagement in Secondary Cities, 2022)
KerkoCite.ItemAlsoKnownAs: 5072953:EC3RN7GH 5072953:WT8CFGA3 5072953:YRZRYRMA
Keywords: C:Cameroon; _z:class:countries; _z:class:themes; ⛔ No DOI found

Carbon-smart schools mitigate climate change and improve learning - Forbes, Catriona (2022)
Recent studies confirm the extent to which improvements in classroom condition can positively impact children’s ability to learn. With so many classrooms needed, there is an opportunity to both improve the design of schools and instigate a change in attitude towards carbon-smart construction.
KerkoCite.ItemAlsoKnownAs: 4874017:AVWACYLY 5072953:5HWD6RCE
Keywords: _z:class:countries; _z:class:themes

Carbon-smart schools mitigate climate change and improve learning - Forbes, Catriona (2022)
Recent studies confirm the extent to which improvements in classroom condition can positively impact children’s ability to learn. With so many classrooms needed, there is an opportunity to both improve the design of schools and instigate a change in attitude towards carbon-smart construction.
KerkoCite.ItemAlsoKnownAs: 2129771:NNPI22TM 2486141:P9GPFW24
Keywords: evidence_review

Addressing the climate, environment, and biodiversity crises in and through girls’ education - Foreign, Commonwealth & Development Office (2022)
Keywords: _z:class:countries; selected_for:effects of climate ch...on learning...LMICs 2024

Comprehensive School Safety Framework 2022-2030: for Child Rights and Resilience in the Education Sector - GADRRRES (2022)
KerkoCite.ItemAlsoKnownAs: 2129771:MM6ZRHSX 2129771:MM6ZRHSX 2129771:MM6ZRHSX 2129771:MM6ZRHSX 4874017:W7XZGYJM 5072953:H7JESU5A
Keywords: _z:class:countries; _z:class:themes; evidence_review_2

Fragranced Consumer Products as Sources - Goodman, Nigel; Nematollahi, Neda (Handbook of Indoor Air Quality, 2022)
Keywords: _z:class:countries

The role of education in addressing climate change - GPE Secretariat (2022)
In this blog series, experts and thought leaders present their views on how essential education is to addressing climate change.
KerkoCite.ItemAlsoKnownAs: 4874017:8IMBA755 5072953:2Q4FKL4Y
Keywords: _z:class:countries; _z:class:themes

Disease Burden of Indoor Air Pollution - Hänninen, Otto; Mandin, Corinne; Liu, Wei; Liu, Ningrui; Zhao, Zhuohui; Zhang, Yinping (Handbook of Indoor Air Quality, 2022)
KerkoCite.ItemAlsoKnownAs: 5072953:8TLP4ZKT 5072953:DFN83GY6
Keywords: _z:class:countries

Introduction to Particles in Indoor Air - Hopke, Philip K.; Liu, Cong (Handbook of Indoor Air Quality, 2022)
Keywords: _z:class:countries

Africa - I.P.C.C. (Climate Change 2022: Impacts, Adaptation and Vulnerability. Contribution of Working Group II to the Sixth Assessment Report of the Intergovernmental Panel on Climate Change, 2022)
Keywords: _z:class:countries

Optimization of building envelopes using indigenous materials to achieve thermal comfort and affordable housing in Abuja, Nigeria - Jegede, O.E.; Taki, A. (International Journal of Building Pathology and Adaptation, 2022)
Keywords: _z:class:countries

Evaluation of thermal comfort and air quality of low-income housing in Kampala City, Uganda - Kajjoba, D.; Kasedde, H.; Olupot, P.W.; Lwanyaga, J.D. (Energy and Built Environment, 2022)
Keywords: _z:class:countries

Indoor Air Quality in the Context of Climate Change - Kinney, Patrick L. (Handbook of Indoor Air Quality, 2022)
Keywords: _z:class:countries

An explorative study on the potential of green roofs providing thermal comfort conditions for indoor spaces in Kumasi - Koranteng, C.; Nyame-Tawiah, D.; Gyimah, K.A.; Simons, B. (Ghana. Open House International, 2022)
Keywords: _z:class:countries

Cognitive performance was reduced by higher air temperature even when thermal comfort was maintained over the 24–28°C range - Lan, Li; Tang, Jieyu; Wargocki, Pawel; Wyon, David P; Lian, Zhiwei (Indoor Air, 2022)
This study managed to create thermal comfort conditions at three temperatures (24°C-T24, 26°C-T26, and 28°C-T28) by adjusting clothing and air velocity. Thirty- six subjects (18 males and 18 females) were exposed to each of the three conditions for 4.5 h in a design balanced for order of presentation of conditions. During each exposure, they rated the physical environment, their comfort, the intensity of acute subclinical health symptoms, and their mental load, and they performed a number of cognitive tasks. Their physiological reactions were monitored. The subjects rated T24 to be comfortably cool, T26 to be comfortably neutral, and T28 to be comfortably warm. Their self-estimated performance did not differ between conditions but 12 of 14 objective metrics of cognitive performance decreased significantly at the elevated temperatures: compared with T24, their average cognitive performance decreased by 10% at T26 and by 6% at T28. At the elevated temperatures, their parasympathetic nervous system activity (as indicated by PNN50) and their arterial blood oxygen saturation level (SpO2) were both lower, which would be expected to result in reduced cognitive performance. The subjects also rated their acute subclinical health symptoms as more intense and their workload as higher at the elevated temperatures. These results suggest that where cognitive performance is the priority, it is wise to ensure a comfortably cool environment. The present study also supports the use of fans or natural ventilation to reduce the need for mechanical cooling.
KerkoCite.ItemAlsoKnownAs: 10.1111/ina.12916 2129771:IZDK8FG8 4682641:CIQ8XNFD 4682641:M2MHIUAK 5072953:JG79T4UC openalex: W3184331866
Keywords: BE:RELEVANT; C:China; _z:class:countries; _z:class:themes; evidence_review; oa:keyword:cognitive performance; oa:keyword:higher air temperature; oa:keyword:thermal comfort; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11109 Physiological Responses to Heat Stress in Humans; oa:topic:T11244 Impact of Climate Change on Human Health; openalex:n:1; openalex:yes

Investigating the relation between electroencephalogram, thermal comfort, and cognitive performance in neutral to hot indoor environment - Lang, Xiaoyue; Wargocki, Pawel; Liu, Weiwei (Indoor Air, 2022)
The relation between electroencephalogram signals, thermal comfort, and cognitive performance in neutral to hot indoor environment was investigated. The experiments were carried out at four temperatures: 26ºC, 30ºC, 33ºC, and 37ºC, and two relative humidity levels: 50% and 70%. Thirty-two subjects were exposed for 175 min. The electroencephalogram signals were measured for 30 min 25 min after the onset of exposure while the recruited subjects performed neurobehavioral tests and rated their thermal comfort. The relative power of electroencephalogram signals has a significant correlation with thermal comfort and performance of neurobehavioral tests. The ratings of acceptability of thermal environment and thermal comfort, the speed, accuracy, and PI of completing the tests are negatively correlated with the relative power of δ-band, but positively correlated with θ-band, α-band, and β-band. The ratings of thermal sensation have a better correlation with the above four bands, but the correlation trend is opposite. A linear relation was found between electroencephalogram signals and the speed. The results showed that the relative power of P7 channel located in the occipital lobe is the most suitable as a single electroencephalogram channel to reflect joint thermal comfort and cognitive performance at high temperatures, especially its α-band.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/ina.12941 KerkoCite.ItemAlsoKnownAs: 10.1111/ina.12941 2129771:9F3VADMF 4682641:4NSJKT5N 5072953:97RP6PQB openalex: W3203651962
Keywords: BE:RELEVANT; C:China; _z:class:countries; _z:class:themes; acceptability of thermal environment; cognitive performance; electroencephalogram; oa:keyword:electroencephalogram; oa:keyword:thermal comfort; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10977 Biomedical Optical Imaging and Spectroscopy; oa:topic:T11109 Physiological Responses to Heat Stress in Humans; occipital lobe; openalex:n:1; openalex:yes; thermal comfort; thermal sensation

Household Air Pollution in Rural Area - Luo, Zhihan; Shen, Guofeng (Handbook of Indoor Air Quality, 2022)
KerkoCite.ItemAlsoKnownAs: 5072953:H6MM4XI8 5072953:RTCANXJX 5072953:YCI5CLW8
Keywords: _z:class:countries

Influence of Ventilation on Indoor Air Quality - Lv, Mengqiang; Liu, Sumei; Cao, Qing; Zhang, Tengfei; Liu, Junjie (Handbook of Indoor Air Quality, 2022)
Keywords: _z:class:countries

IAQ in Commercial Air Transportation - Mayer, Florian; Fox, Richard; Space, David; Bezold, Andreas; Wargocki, Pawel (Handbook of Indoor Air Quality, 2022)
Keywords: _z:class:countries

Forging a university-aided indigenous community education - Mbah, M.; Fonchingong, C. C. (Sun Press, 2022)
KerkoCite.ItemAlsoKnownAs: 5072953:4LNTUT6Y
Keywords: _z:class:countries; _z:class:themes; _z:no_pdf; ⛔ No DOI found

Decolonisation of Research Methodologies for Sustainable Development in Indigenous Settings - Mbah, Marcellus F.; Bailey, Megan (Indigenous Methodologies, Research and Practices for Sustainable Development, 2022)
Series Title: World Sustainability Series KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-031-12326-9_2 5072953:VTA2GCYA
Keywords: _z:class:countries; _z:class:themes

Indigenous Methodologies, Research and Practices for Sustainable Development - Mbah, Marcellus F.; Leal Filho, Walter; Ajaps, Sandra (Springer Nature, 2022)
KerkoCite.ItemAlsoKnownAs: 5072953:G2X2SHFW
Keywords: _z:class:countries; _z:class:themes

Policies and practices of climate change education in South Asia: towards a support framework for an impactful climate change adaptation - Mbah, Marcellus F.; Shingruf, Ayesha; Molthan-Hill, Petra (Climate Action, 2022)
Publisher: Nature Publishing Group KerkoCite.ItemAlsoKnownAs: 10.1007/s44168-022-00028-z 5072953:XUP5XFP7 openalex: W4313403736
Keywords: _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change education; oa:keyword:impactful climate change adaptation; oa:sdg:13 Climate action; oa:topic:T10119 Sustainability Transitions and Resilience in Social-Ecological Systems; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T12656 Impact of Climate Change on Human Migration; openalex:n:1; openalex:yes

Policies and practices of climate change education in South Asia: towards a support framework for an impactful climate change adaptation - Mbah, Marcellus F.; Shingruf, Ayesha; Molthan-Hill, Petra (Climate Action, 2022)
KerkoCite.ItemAlsoKnownAs: 10.1007/s44168-022-00028-z 5072953:XUP5XFP7 openalex: W4313403736
Keywords: _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change education; oa:keyword:impactful climate change adaptation; oa:sdg:13 Climate action; oa:topic:T10119 Sustainability Transitions and Resilience in Social-Ecological Systems; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T12656 Impact of Climate Change on Human Migration; openalex:n:1; openalex:yes

Envisioning the Indigenised university for sustainable development - Mbah, Marcellus Forh; Ajaps, Sandra; Johnson, Ane Turner; Yaffa, Sidat (International Journal of Sustainability in Higher Education, 2022)
Publisher: Emerald Publishing Limited KerkoCite.ItemAlsoKnownAs: 10.1108/IJSHE-09-2021-0413 5072953:CCFEHKYQ openalex: W4229372231
Keywords: _z:class:countries; _z:class:themes; oa:keyword:indigenised university; oa:keyword:sustainable development; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11806 Impact of Service-Learning in Higher Education; oa:topic:T11835 Sustainability Education in Higher Education Institutions; openalex:n:1; openalex:yes

Envisioning the Indigenised university for sustainable development - Mbah, Marcellus Forh; Ajaps, Sandra; Johnson, Ane Turner; Yaffa, Sidat (International Journal of Sustainability in Higher Education, 2022)
KerkoCite.ItemAlsoKnownAs: 10.1108/IJSHE-09-2021-0413 5072953:CCFEHKYQ openalex: W4229372231
Keywords: _z:class:countries; _z:class:themes; oa:keyword:indigenised university; oa:keyword:sustainable development; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11806 Impact of Service-Learning in Higher Education; oa:topic:T11835 Sustainability Education in Higher Education Institutions; openalex:n:1; openalex:yes

How can “community voices” from qualitative research illuminate our understanding of the implementation of the SDGs? A scoping review - Mbah, Marcellus Forh; East, Linda A. (Sustainability, 2022)
In 2015, the United Nations committed to 17 Sustainable Development Goals (SDGs) to drive global development policy and practice. Six years into the implementation of the 15-year agenda, the SDGs are subject to extensive monitoring and research at the national, regional, and global levels using quantitative data sets. In contrast, this scoping review considered the contribution of qualitative research studies published in 2021, utilizing data collected from local, place-based community participants. Qualitative research with community participants connects global policy with place-based experience, thus potentially offering a valuable perspective on SDG implementation. Searches were carried out using the Scopus database to identify studies that explicitly linked their aims and objectives to the SDGs. Fifty-four papers met the criteria for inclusion in the review and were charted, mapped, and analysed. For the majority of studies, data collection was carried out in lower-middle income and low-income countries. The “voices” of community participants highlight tensions and challenges affecting the implementation of the SDGs. Reviewing this body of research as a whole identified opportunities to strengthen future qualitative research that will further illuminate progress towards the SDGs.
Publisher: MDPI KerkoCite.ItemAlsoKnownAs: 10.3390/su14042136 5072953:J8XNG3YF openalex: W4213067626
Keywords: _z:class:countries; _z:class:themes; oa:keyword:community voices”; oa:keyword:qualitative research illuminate; oa:sdg:10 Reduced inequalities; oa:topic:T10596 Maternal and Child Nutrition in Developing Countries; oa:topic:T12227 Sustainability Assessment and Impact Evaluation; oa:topic:T14464 Analysis of Impact Investing in Finance and Social Policy; openalex:n:1; openalex:yes

How can “community voices” from qualitative research illuminate our understanding of the implementation of the SDGs? A scoping review - Mbah, Marcellus Forh; East, Linda A. (Sustainability, 2022)
In 2015, the United Nations committed to 17 Sustainable Development Goals (SDGs) to drive global development policy and practice. Six years into the implementation of the 15-year agenda, the SDGs are subject to extensive monitoring and research at the national, regional, and global levels using quantitative data sets. In contrast, this scoping review considered the contribution of qualitative research studies published in 2021, utilizing data collected from local, place-based community participants. Qualitative research with community participants connects global policy with place-based experience, thus potentially offering a valuable perspective on SDG implementation. Searches were carried out using the Scopus database to identify studies that explicitly linked their aims and objectives to the SDGs. Fifty-four papers met the criteria for inclusion in the review and were charted, mapped, and analysed. For the majority of studies, data collection was carried out in lower-middle income and low-income countries. The “voices” of community participants highlight tensions and challenges affecting the implementation of the SDGs. Reviewing this body of research as a whole identified opportunities to strengthen future qualitative research that will further illuminate progress towards the SDGs.
KerkoCite.ItemAlsoKnownAs: 10.3390/su14042136 5072953:J8XNG3YF openalex: W4213067626
Keywords: _z:class:countries; _z:class:themes; oa:keyword:community voices”; oa:keyword:qualitative research illuminate; oa:sdg:10 Reduced inequalities; oa:topic:T10596 Maternal and Child Nutrition in Developing Countries; oa:topic:T12227 Sustainability Assessment and Impact Evaluation; oa:topic:T14464 Analysis of Impact Investing in Finance and Social Policy; openalex:n:1; openalex:yes

Government budget for 2022-2023 - MOF (2022)
KerkoCite.ItemAlsoKnownAs: 2129771:IILGFTTZ 4874017:PPV2V7XI
Keywords: evidence_review

Climate Change Education at Universities: Relevance and Strategies for Every Discipline - Molthan-Hill, Petra; Blaj-Ward, Lia; Mbah, Marcellus Forh; Ledley, Tamara Shapiro (Handbook of Climate Change Mitigation and Adaptation, 2022)
KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-030-72579-2_153 5072953:TYWGK7RL
Keywords: _z:class:countries; _z:class:themes

Encouraging natural ventilation to improve indoor environmental conditions at schools. Case studies in the north of Spain before and during COVID - Monge-Barrio, Aurora; Bes-Rastrollo, Maira; Dorregaray-Oyaregui, Sara; González-Martínez, Purificación; Martin-Calvo, Nerea; López-Hernández, Dolores; Arriazu-Ramos, Ainhoa; Sánchez-Ostiz, Ana (Energy and Buildings, 2022)
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2021.111567 2129771:VV68XHRE 4682641:HVQK4BR6 4874017:CZNE7Y2M 5072953:CCWTB68H 5072953:WXU6VAXA openalex: W3206694443
Keywords: BE:RELEVANT; C:Spain; _z:class:countries; _z:class:themes; evidence_review_2; oa:keyword:indoor environmental conditions; oa:keyword:natural ventilation; oa:sdg:1 No poverty; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10990 Airborne Transmission of Respiratory Viruses; oa:topic:T11244 Impact of Climate Change on Human Health; openalex:n:1; openalex:yes

WHO Health Guidelines for Indoor Air Quality and National Recommendations/Standards - Morawska, Lidia; Huang, Wei (Handbook of Indoor Air Quality, 2022)
KerkoCite.ItemAlsoKnownAs: 5072953:G5FECQ7X 5072953:VFX3H77A
Keywords: _z:class:countries

Tanzania Weather & Climate - Natural habitat adventures (2022)
Tanzania has a generally comfortable climate year-round. Browse this month by month break down of weather and climate in Tanzania.
KerkoCite.ItemAlsoKnownAs: 2129771:6NSGMVM4 4682641:SN6WXZXP 5072953:7A53B4AH
Keywords: C:Tanzania; _z:class:countries; _z:class:themes

Comparative cost advantages of Interlocking Stabilised Soil Blocks and Sandcrete Blocks for building construction in South-West Nigeria - Obafemi, A. Ibitoye; Oluwole, Alagbe; Oladipupo, Dare-Abel (2022)
Interlocking stabilized soil blocks (ISSBS) is undoubtedly one of the contemporary buildingmaterials used for building construction works in developing countries. The ISSBs is gaining fast recognition as frontline alternative to Sandcrete blocks for affordable housing development in Nigeria. However, despite the positive reports of United Nations upholding ISSB as an affordable building material for low cost housing in developing African nations, the patronage of ISSBs is low-slung when compared to the conventional Sandcrete blocks (SBs). This study explored the comparative cost advantages of Interlocking stabilized soil blocks and Sandcreteblocks for building construction in Southwestern Nigeria with the view of promoting it’s usage for affordable housing development. The objectives were; to identify the most common types of Interlocking stabilised soil blocks and Sandcrete blocks used for building construction works in southwestern Nigeria; to analyze the cost of ISSBS for building walling system; to compare the cost of building walling systems with Interlocking stabilized soil blocks and Sandcrete blocks in Southwestern Nigeria. Existing literature on the use of Interlocking stabilised soil blocks (ISSBs) were reviewed. Using qualitative research approaches where Interviews and documentaries was phenomenal; the cost comparativeness of ISSBs and SBs in this study was analyzed using Empirical data’s obtained from local construction markets and ISSBs promoters. Findings revealed the cost of ISSBs is relatively cheaper than Sandcrete blocks due to the mortar-less walling systems; the eradication of wall rendering and drastic reduction in the use of cement, concrete, reinforcement and industrial materials. The study recommended that more agencies should be established. Promoters of ISSBs should invests heavily on awareness and sensitization of the populace on the significance of adoption ISSBs for building construction.
KerkoCite.ItemAlsoKnownAs: 2129771:CZGTRU9J 4874017:TRPZE9KH
Keywords: evidence_review

Comparative cost advantages of Interlocking Stabilised Soil Blocks and Sandcrete Blocks for building construction in South-West Nigeria - Obafemi, A. Ibitoye; Oluwole, Alagbe; Oladipupo, Dare-Abel (2022)
Interlocking stabilized soil blocks (ISSBS) is undoubtedly one of the contemporary buildingmaterials used for building construction works in developing countries. The ISSBs is gaining fast recognition as frontline alternative to Sandcrete blocks for affordable housing development in Nigeria. However, despite the positive reports of United Nations upholding ISSB as an affordable building material for low cost housing in developing African nations, the patronage of ISSBs is low-slung when compared to the conventional Sandcrete blocks (SBs). This study explored the comparative cost advantages of Interlocking stabilized soil blocks and Sandcreteblocks for building construction in Southwestern Nigeria with the view of promoting it’s usage for affordable housing development. The objectives were; to identify the most common types of Interlocking stabilised soil blocks and Sandcrete blocks used for building construction works in southwestern Nigeria; to analyze the cost of ISSBS for building walling system; to compare the cost of building walling systems with Interlocking stabilized soil blocks and Sandcrete blocks in Southwestern Nigeria. Existing literature on the use of Interlocking stabilised soil blocks (ISSBs) were reviewed. Using qualitative research approaches where Interviews and documentaries was phenomenal; the cost comparativeness of ISSBs and SBs in this study was analyzed using Empirical data’s obtained from local construction markets and ISSBs promoters. Findings revealed the cost of ISSBs is relatively cheaper than Sandcrete blocks due to the mortar-less walling systems; the eradication of wall rendering and drastic reduction in the use of cement, concrete, reinforcement and industrial materials. The study recommended that more agencies should be established. Promoters of ISSBs should invests heavily on awareness and sensitization of the populace on the significance of adoption ISSBs for building construction.
KerkoCite.ItemAlsoKnownAs: 4874017:TRPZE9KH 5072953:ET7JN9CU
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; openalex:n:0

Evaluation of indoor thermal comfort conditions of residential traditional and modern buildings in a warm-humid climate - Okafor, M.U.; Awuzie, B.O.; Otasowie, K.; Marcel-Okafor, U.; Aigbavboa, C. (Sustainability, 2022)
Keywords: _z:class:countries

Public Health Education in Africa: The Case of Epistemic (in) Justice and Indigenous Health Systems - Orjinta, Amarachi Jane-Frances; Mbah, Marcellus F. (Indigenous Methodologies, Research and Practices for Sustainable Development, 2022)
Series Title: World Sustainability Series KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-031-12326-9_13 5072953:BMP34WX6
Keywords: _z:class:countries; _z:class:themes

A model for thermal comfort assessment of naturally ventilated housing in the hot and dry tropical climate - Ouedraogo, A.L.S.-N.; Messan, A.; Yamegueu, D.; Coulibaly, Y. (International Journal of Building Pathology and Adaptation, 2022)
Keywords: _z:class:countries

Prioritizing learning during COVID-19: The most effective ways to keep children learning during and postpandemic - Panel, Global Education Evidence Advisory (The World Bank, FCDO, and UNICEF Office of Research - Innocenti, 2022)
Keywords: _z:class:countries

Girls’ education and climate change: A critical review of the literature - Pankhurst, Camilla (Centre for Education and International Development, UCL, 2022)
Girls’ education is often positioned as a panacea for a host of the world’s problems. As the UK Prime Minister put it at the Global Education Summit: ‘This is the silver bullet, this is the magic potion, this is the panacea. This is the universal cure, this is the Swiss Army knife, complete with allen key and screwdriver and everything else that can solve virtually every problem that afflicts humanity’ (Prime Minister's Office, 10 Downing Street, 2021). One such problem is climate change. Girls’ education is heralded for its ability to improve individuals’ and countries’ resilience, to instil environmental concern and behaviours, and to produce tomorrow’s green workers and leaders. Perhaps the most pervasive claimed benefit of girls’ education is of a relationship with slowed population growth and reduced emissions, which has led some to position educating girls as one of the most cost-effective climate mitigation strategies (Project Drawdown, n.d.). But are these claims true? If we educated every girl, would we slow, halt and eventually reverse climate change and literally save the world? And what does the narrative of girls’ education as climate change inoculation mean in the context of the learning, climate, and COVID-19 crises? This paper outlines the findings of a rigorous review into the research question: ‘what evidence is there in low and lower-middle income countries (LLMICs) of the pathways between girls’ education and climate change?’. The review includes 98 studies published from 2012 to January 2022. I offer a new conceptual framework which sets out multiple, layered pathways between girls’ education and climate change, and map included studies against this framework. An assessment of the quality of studies enables identification of areas of relative strength and weakness in the evidence base. The review highlights that while there is evidence of a relationship between girls’ education and climate change in LLMICs, the evidence base is limited and inconsistent. It exposes important gaps for widely assumed causal links of girls’ education on climate change and highlights the need for further, high quality research in diverse contexts.
KerkoCite.ItemAlsoKnownAs: 5072953:H8GVVHIV 5072953:VWU2Y4MG 5440726:DE4SG2EI
Keywords: _z:class:countries; selected_for:effects of climate ch...on learning...LMICs 2024

Evaluating Ventilation Performance - Persily, Andrew (Handbook of Indoor Air Quality, 2022)
KerkoCite.ItemAlsoKnownAs: 5072953:2HTUW6W4 5072953:NAJK72TU
Keywords: _z:class:countries

Poor indoor climate: Its impact on health and life satisfaction, as well as its wider socio-economic costs - Phillips, William; Janta, Barbara; Gehrt, Daniel; Flemons, Lillian; Gkousis, Evangelos; Cole, Sam; Smith, Pamina; Hafner, Marco (2022)
KerkoCite.ItemAlsoKnownAs: 2129771:GLCGM6ZP 4682641:NHR73DX9 5072953:ZUAR2YZU
Keywords: BE:Annotated; BE:RELEVANT; _z:class:countries; _z:class:themes

Effects of IAQ on Office Work Performance - Porras-Salazar, Jose Ali; Schiavon, Stefano; Tham, Kwok Wai (Handbook of Indoor Air Quality, 2022)
Keywords: _z:class:countries

Should we paint all classroom roofs white to improve learning in Tanzania? - Proctor, J. (2022)
Type: [Working Paper].
Keywords: _z:class:countries

Should we paint all classroom roofs white to improve learning in Tanzania? - Proctor, Jamie (2022)
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0122 2129771:M6H5RYYN 2486141:4MVMCRNC
Keywords: evidence_review

Year long monitoring of indoor air quality and ventilation in school classrooms in Victoria, Australia - Rajagopalan, Priyadarsini; Andamon, Mary Myla; Woo, Jin (Architectural Science Review, 2022)
KerkoCite.ItemAlsoKnownAs: 10.1080/00038628.2021.1988892 2129771:JYKTZFVU 4682641:7VMXIBCD 5072953:EQQLSN8D openalex: W3207991211
Keywords: BE:RELEVANT; C:Australia; _z:class:countries; _z:class:themes; _z:no_pdf; evidence_review_2; oa:keyword:indoor air; oa:keyword:indoor air quality; oa:keyword:ventilation; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10190 Health Effects of Air Pollution; oa:topic:T11002 Indoor Air Quality and Health Effects; openalex:n:1; openalex:yes

Urban Heat in Johannesburg and Ekurhuleni: Impacts and Mitigation Options, Technical Annex. Study conducted under the authority of the World Bank - Ridder, K.; Kusambiza-Kiingi, F.; Lefebre, F.; Makwela, M.; Memela, W.; Ndlovu, C.; Segodi, S.; Souverijns, N.; Tshabalala, B.; Veldeman, N. (2022)
Issue: 2022/RMA/R/2738 Pages: 116
Keywords: _z:class:countries

Indoor air quality and health in schools: A critical review for developing the roadmap for the future school environment - Sadrizadeh, Sasan; Yao, Runming; Yuan, Feng; Awbi, Hazim; Bahnfleth, William; Bi, Yang; Cao, Guangyu; Croitoru, Cristiana; De Dear, Richard; Haghighat, Fariborz; Kumar, Prashant; Malayeri, Mojtaba; et al. (Journal of Building Engineering, 2022)
Several research studies have ranked indoor pollution among the top environmental risks to public health in recent years. Good indoor air quality is an essential component of a healthy indoor environment and significantly affects human health and well-being. Poor air quality in such environments may cause respiratory disease for millions of pupils around the globe and, in the current pandemic-dominated era, require ever more urgent actions to tackle the burden of its impacts. The poor indoor quality in such environments could result from poor management, operation, maintenance, and cleaning. Pupils are a different segment of the population from adults in many ways, and they are more exposed to the poor indoor environment: They breathe in more air per unit weight and are more sensitive to heat/cold and moisture. Thus, their vulnerability is higher than adults, and poor conditions may affect proper development. However, a healthy learning environment can reduce the absence rate, improves test scores, and enhances pupil/teacher learning/teaching productivity. In this article, we analyzed recent literature on indoor air quality and health in schools, with the primary focus on ventilation, thermal comfort, productivity, and exposure risk. This study conducts a comprehensive review to summarizes the existing knowledge to highlight the latest research and solutions and proposes a roadmap for the future school environment. In conclusion, we summarize the critical limitations of the existing studies, reveal insights for future research directions, and propose a roadmap for further improvements in school air quality. More parameters and specific data should be obtained from in-site measurements to get a more in-depth understanding at contaminant characteristics. Meanwhile, site-specific strategies for different school locations, such as proximity to trans portation routes and industrial areas, should be developed to suit the characteristics of schools in different regions. The socio-economic consequences of health and performance effects on children in classrooms should be considered. There is a great need for more comprehensive studies with larger sample sizes to study on environmental health exposure, student performance, and indoor satisfaction. More complex mitigation measures should be evaluated by considering energy efficiency, IAQ and health effects.
KerkoCite.ItemAlsoKnownAs: 2129771:NTBFI4GF 2129771:NTBFI4GF 2129771:NTBFI4GF 2129771:NTBFI4GF 10.1016/j.jobe.2022.104908 5072953:SMX87LLQ
Keywords: _z:class:countries; evidence_review

The Health Effects of Indoor Air Pollution - Samet, Jonathan; Holguin, Fernando; Buran, Meghan (Handbook of Indoor Air Quality, 2022)
Keywords: _z:class:countries

Global Tracking of Climate Change Adaptation Policy Using Machine Learning: a Systematic Map Protocol - Sietsma, Anne J.; Callaghan, Max; Biesbroek, Robbert; Theokritoff, Emily; Thomas, Adelle; Canosa, Iván Villaverde; Schleussner, Carl-Friedrich; Ford, James D.; Minx, Jan C. (2022)
Keywords: _z:class:countries

Control of Airborne Particles: Filtration - Stephens, Brent; Maynard, Andrew; Hopke, Philip K. (Handbook of Indoor Air Quality, 2022)
KerkoCite.ItemAlsoKnownAs: 5072953:HLW6WDI4 5072953:PHTZHG74 5072953:UA33VNUC 5072953:YXLA6H7V
Keywords: _z:class:countries

A Low-Cost Sensor Network for Real-Time Thermal Stress Monitoring and Communication in Occupational Contexts - Sulzer, Markus; Christen, Andreas; Matzarakis, Andreas (Sensors, 2022)
openalex: W4214759886 KerkoCite.ItemAlsoKnownAs: 10.3390/s22051828 2486141:X7TIZVKQ 4874017:HVITRDWE 5072953:Q7DK3EPR 5072953:YWCGMQPB
Keywords: _important; _z:class:countries; _z:class:themes; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11244 Impact of Climate Change on Human Health; openalex:n:1; openalex:yes

Climate change impacts and mitigation strategies of South African manufacturing companies - Thabisile Vilakazi (2022)
KerkoCite.ItemAlsoKnownAs: 5072953:9R85USYA 5072953:TX8HWLEG
Keywords: _z:class:countries

Modelling indoor environment indicators using artificial neural network in the stratified environments - Tian, Xue; Cheng, Yong; Lin, Zhang (Building and Environment, 2022)
Publisher: Elsevier KerkoCite.ItemAlsoKnownAs: 10.1016/j.buildenv.2021.108581 5072953:Z9DCL2VR openalex: W3213888880
Keywords: _important; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:indoor environment indicators; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:n:1; openalex:yes; selected_for:Predictive models for classroom conditions 2024

Modelling indoor environment indicators using artificial neural network in the stratified environments - Tian, Xue; Cheng, Yong; Lin, Zhang (Building and Environment, 2022)
KerkoCite.ItemAlsoKnownAs: 10.1016/j.buildenv.2021.108581 5072953:Z9DCL2VR openalex: W3213888880
Keywords: _important; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:indoor environment indicators; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:n:1; openalex:yes; selected_for:Predictive models for classroom conditions 2024

Tanzania Climate Statetement 2022 - TMA (2022)
KerkoCite.ItemAlsoKnownAs: 2129771:M5YMHSFS 4874017:82HWHTG9
Keywords: evidence_review

Open database for international and national indoor environmental quality guidelines - Toyinbo, Oluyemi; Hägerhed, Linda; Dimitroulopoulou, Sani; Dudzinska, Marzenna; Emmerich, Steven; Hemming, David; Park, Ju-Hyeong; Haverinen-Shaughnessy, Ulla; the Scientific Technical Committee 34 of the International Society of Indoor Air Quality, Climate (Indoor Air, 2022)
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/ina.13028 KerkoCite.ItemAlsoKnownAs: 10.1111/ina.13028 4874017:CWB75DCJ 5072953:3G245LS4 openalex: W4224278549
Keywords: _z:class:countries; _z:class:themes; guidelines; indoor; oa:topic:T10190 Health Effects of Air Pollution; oa:topic:T11244 Impact of Climate Change on Human Health; oa:topic:T11692 Effects of Noise Pollution on Health and Well-being; openalex:n:1; openalex:yes; pollutants; regulations

Occupants’ responses to window views, daylighting and lighting in buildings: A critical review - Vasquez, Natalia Giraldo; Rupp, Ricardo Forgiarini; Andersen, Rune Korsholm; Toftum, Jørn (Building and Environment, 2022)
This paper presents a critical review of studies addressing the effects of window views, daylighting, and lighting on occupant behavior, perception, performance, and well-being. A systematic search in the Scopus database was performed in November 2021 and yielded 515 hits. Seventy-six studies were selected according to the following criteria: i) papers presenting research results with participants’ responses and ii) accounting for daylighting, lighting, or window view assessments. The study and setting features, participants, predictors and outcomes, the statistical approach, the reported significance level, and study limitations were extracted from each paper. The analysis then identified differences in the effect of the predictor on the outcome. The number of records obtained through the structured analysis was 240. A wide range of predictors have been used in indoor daylighting, lighting, and window view research to assess people’s responses. The most commonly used predictors were artificial lighting features and window features -qualitative predictors - followed by some properties of the light sources, such as correlated color temperature, spectral distribution and horizontal illuminance. Differences in the methods for data collection, the used predictors, the outcomes, and the ways to measure the outcomes generated inconclusive results or results that were limited to the specific study. We extracted data from selected studies to suggest a simple model for the prediction of occupant performance from illuminance and correlated color temperature. The data points were few and scattered and the model, therefore, suffers from considerable uncertainties. Yet, it quantifies performance effects in ranges that are comparable with similar models from other indoor environment domains.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.buildenv.2022.109172 2129771:ACWLIE85 4682641:BBG374H3 5072953:IA5HXXA5 openalex: W4280562794
Keywords: BE:RELEVANT; _z:class:countries; _z:class:themes; oa:sdg:11 Sustainable cities and communities; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10692 Impact of Urban Green Space on Public Health; oa:topic:T11963 Impact of Nighttime Light Data on Various Fields; openalex:n:1; openalex:yes

Effects of Classroom Air Quality on Learning in Schools - Wargocki, Pawel (Handbook of Indoor Air Quality, 2022)
This chapter describes the evidence of the effects of indoor air quality (IAQ) on learning of children and gives an overview of the size of the effects expected. The results from the published experiments on the effects of classroom air quality on the performance of schoolwork do confirm that these effects are systematic and show that improving classroom air quality will have a significant positive effect on some aspects of learning, both on cognitive skills and academic attainment, as well as academic achievements and absence rates. Present studies show that to ensure classroom IAQ conducive to learning, CO2 levels (indicating the adequacy of ventilation) should be kept below 900 ppm at all times. It should be ensured that windows can be opened when needed, to improve classroom IAQ, and CO2 sensors should be installed to indicate when windows must be open (or any other measure to improve IAQ must be executed) if the CO2 concentration is too high and when they should be closed to conserve energy.
KerkoCite.ItemAlsoKnownAs: 10.1007/978-981-16-7680-2_65 2129771:99ZNKGFB 4874017:UEPIKD9J
Keywords: evidence_review

Experimental study of the negative effects of raised bedroom temperature and reduced ventilation on the sleep quality of elderly subjects - Yan, Yan; Zhang, Haodong; Kang, Mengyuan; Lan, Li; Wang, Zhentao; Lin, Yanbin (Indoor Air, 2022)
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/ina.13159 KerkoCite.ItemAlsoKnownAs: 5072953:8RRXHKYL 5072953:ZDSHHN3Y
Keywords: _z:class:countries; _z:no_pdf; elderly; raised temperature; sleep quality; sleeping conditions; ventilation

Testing and Reducing VOC Emissions from Building Materials and Furniture - Zhang, Jianshun Jensen; Chen, Wenhao; Liu, Ningrui; Guo, Bing Beverly; Zhang, Yinping (Handbook of Indoor Air Quality, 2022)
Keywords: _z:class:countries

History and Perspective on Indoor Air Quality Research - Zhang, Yinping; Hopke, Philip K.; Mandin, Corinne (Handbook of Indoor Air Quality, 2022)
KerkoCite.ItemAlsoKnownAs: 5072953:5488R58J 5072953:JZYW6XDP
Keywords: _z:class:countries

The Agricultural Water-Energy Nexus of Rural India under Climate Change: How Learning Coordination Becomes Key to Technology Adoption - Kimmich, Christian (2021)
Surprisingly or not, agriculture can be a crucial sector that either enables or impedes the transition towards sustainable development of urban areas. This is also the case for the emerging megacity of Hyderabad. Several rural-urban linkages support this perspective: (a) migration patterns, dependent on agricultural and rural income, and development paths; (b) the food security and provisioning dimension, especially relevant in the case of perishable agricultural commodities that cannot be traded over long distances; (c) water allocation for agricultural production versus drinking water supply in the city; and (d) electricity allocation for agricultural production versus urban consumption. This research focuses especially on the latter linkage (d), as electricity provision is one of the most crucial factors of sustainable development for Hyderabad, becoming either a driver or inhibitor. In India, electricity supply for agricultural irrigation is highly subsidised, increasing the scarcity for urban, industrial, and commercial uses. With a share of 36% of all electricity consumption in the state of Andhra Pradesh, agriculture has a very high potential for energy efficiency and mitigation measures. Based on background studies and stakeholder analyses, the thesis analyses two levels: (I) the macro level on the political economy of infrastructure regulation, and (II) the micro level of electricity distribution and utilisation in irrigation. Through this twofold approach, the level and measures enabling a transition towards sustainable resource use can be identified. At the macro level, a model of regulation and party competition is applied. This model is tested against the empirical background generated through an analysis of the law, the discourse in newspapers and semi-structured interviews with experts and practitioners. The micro level, which is the focus of this article, sets up an analysis of the agricultural production economy based on interviews and a farm-level survey. The analysis at the level of electricity distribution and agricultural production systems indicates that, although farmers do not have to pay per unit of electric energy utilised, the costs of poor infrastructure impose heavy burdens on agricultural enterprises. Adding the current kWh unit generation costs of electricity would by far exceed those for each of the other input factors of production. The absence of unit costs has led to highly inefficient groundwater irrigation and the high costs of pump-set burnouts to severe voltage fluctuations. These problems work as indirect incentivesor striking reasons for farmers to improve the electricity quality by adopting new technologies through coordinated social learning practices or concerted, joint action. These solutions can be combined with energy efficiency measures. Effective measures and new technologies are most feasible at the level of the electricity sub-station, isolating an agricultural electricity feeder and the connected distribution transformers for the installation of capacitors.
openalex: W3173516129 mag: 3173516129
Keywords: C:India; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T11336 Indoor Air Pollution in Developing Countries; oa:topic:T12724 Integrated Management of Water; Energy; and Food Resources; openalex:import; openalex:yes

Climate Change and Counselling Education: The Incontrovertible Role of Counselling in Psycho-Social Human Adjustment in Nigeria - Francisca, Chigbu Eberechukwu; Chisara, Obi Joy Sylvia; Uzoekwe, H. E.; Nnadi, Grace Chinyere (Asian Journal of Education and Social Studies, 2021)
Climate change threatens to aggravate problem of mental health and social inequality in Nigeria. The causes and danger associate with it has continuously intensified its effect thereby causing some psychological and social problems in the life of people, communities and society at large. Therefore, it becomes pertinent for counselling professionals to come together to address the issues both at local and international levels.
In this article, the focal point is on ways Counsellors can respond to climate change through counselling, advocacy, learning, sensitization and psycho-social human adjustment.
openalex:W4210718910 mag: KerkoCite.ItemAlsoKnownAs: 10.9734/ajess/2021/v25i130591 5072953:W2FMDH7D
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; oa:keyword:counselling education; oa:topic:T11761 Psychological Resilience and Well-being; oa:topic:T12485 The Role of Optimism in Psychological Well-being; oa:topic:T13536 Conceptualization and Measurement of Time Perspective; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Disability and climate change: A critical realist model of climate justice - King, Molly M.; Gregg, Maria A. (Sociology Compass, 2021)
Abstract Existing literature on climate change as an issue of environmental justice documents the heightened vulnerability of people with disabilities to the effects of climate change. Additionally, there are numerous studies showing that access to information is a prerequisite for perceiving risk and taking action. Building on this work, our review seeks to understand how physical disability relates to perceptions of climate‐related risk and adaptations to climate‐related events. We introduce a critical realist model of climate justice to understand the relationships between the environmental features that disable, risk perception and information seeking, and adaptive capacity and resilience to climate change. In understanding the vulnerability and adaptive capacity of people with disabilities to climate change, this review synthesizes research on one of the U.S.’s largest minority communities with the goals of better understanding how vulnerable populations cope with climate change and integrating them into climate action and policy.
openalex: W4200061506
Keywords: _z:class:countries; openalex:import; openalex:yes

A short review on passive strategies applied to minimise the building cooling loads in hot locations - Al-Yasiri, Qudama; Szabó, Márta (Analecta Technica Szegedinensia, 2021)
Cooling and air-conditioning systems are responsible for the highest energy consumption in buildings located in hot areas. This high share does not only increase the building energy demand cost but also increases the environmental impact, the topmost awareness of the modern era. The development of traditional systems and reliance on renewable technologies have increased drastically in the last century but still lacks economic concerns. Passive cooling strategies have been introduced as a successful option to mitigate the energy demand and improve energy conservation in buildings. This paper shed light on some passive strategies that could be applied to minimise building cooling loads to encourage the movement towards healthier and more energy-efficient buildings. For this purpose, seven popular passive technologies have been discussed shortly: multi-panned windows, shading devices, insulations, green roofing, phase change materials, reflective coatings, and natural ventilation using the windcatcher technique. The analysis of each strategy has shown that the building energy could be improved remarkably. Furthermore, adopting more passive strategies can significantly enhance the building thermal comfort even under severe weather conditions.
Number: 2 KerkoCite.ItemAlsoKnownAs: 10.14232/analecta.2021.2.20-30 2129771:7KL78HVL 4874017:26QC7JLD
Keywords: Passive strategies; cooling load reduction; energy saving; evidence_review; insulations; thermal mass

Effects of Classroom Noise on Learning: Perceptions of Grade 10–12 Girl Learners - Goldschagg, Paul; Bekker, Tanya (Africa Education Review, 2021)
Noise disturbance has been recognised as a problem in schools, affecting the intelligibility of speech, and consequently, educational outcomes. Whilst research has explained various effects of noise on learning, less is known about specific learner populations’ perceptions of the effects of noise on their learning. This article reports on a study that compared the noise perceptions of learners at two all-girls high schools (one comprising mostly English home-language speakers; the other English second-language speakers) in Johannesburg, South Africa. The findings of the purposive questionnaire survey that was administered to girls aged 15–18 are presented. Sound measurements are considered alongside questionnaire data and published standards for acceptable classroom noise. Higher levels of noise interference were reported by second-language speakers, which suggest that increased language processing demands make these learners more susceptible to the negative effects of noise. Thus, the implications point to the need for schools to recognise and minimise the negative effects of noise particularly when learners are engaged in tasks of higher order cognitive demand or when teachers are verbally presenting new or complex concepts. This is particularly true for girls for whom English is their second language.
KerkoCite.ItemAlsoKnownAs: 10.1080/18146627.2021.2004551 2129771:ZY4EVACA 4874017:24BAPDSK
Keywords: evidence_review

Effect of Climate Change on Acquisition of Quality Education: A Case Study of Maasai Pastoralists in Narok County, Kenya - Korir, Jacqueline (Advances in Social Sciences Research Journal, 2021)
Climate change is a global phenomenon with far reaching impacts. Arid and semi-arid communities in Kenya, among them the Maasai community from Narok County, are dependent on the natural resources for their livelihood thus are greatly hit by the adverse impacts of climate change. This paper sought to establish the indirect effects of climate change on the quality of education among the Maasai community. Desktop literature review approach and key informant phone interviews were adopted for data collection. The review of literature indicated that increased poverty levels arising from climate change has largely affected the affordability of quality education. Therefore, people in Maasai community resort to coping mechanisms on labour demands that accelerate school dropout as well as early marriages. The Maasai herders are forced to increase their migration trends to long distances, a practice that has increased child labour disrupting learning for most school going children. In addition, the girl child has become more vulnerable to sexual abuse and early marriages with a consequent denial of education opportunities. The effect of the climate change on wildlife habitat has led to human- wildlife conflict that poses a threat to the security of the community members and therefore interferes with the smooth running of schools. Consequently, interventions to mitigate climate change effects should not only concentrate on the direct but also the indirect impacts that have got multiplier effects on sectors like education. These interventions should include, provision of adequate water infrastructure, investment in education policy and boarding school Infrastructural development.
openalex:W4200255919 mag: KerkoCite.ItemAlsoKnownAs: 2129771:5WUG6XTM 2129771:5WUG6XTM 2129771:5WUG6XTM 2129771:5WUG6XTM 10.14738/assrj.812.11314 5072953:5CMQ9PNQ
Keywords: C:Kenya; _z:class:countries; _z:class:themes; _z:no_pdf; evidence_review_2; oa:topic:T11755 Influence of Climate on Human Conflict; oa:topic:T12467 Rangeland Degradation and Pastoral Livelihoods; oa:topic:T13839 Volunteer Tourism and Global Development Impacts; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Assessment of climate change training needs of agricultural extension agents in Abia state, Nigeria - Ifeanyi-obi; Ekere (South African Journal of Agricultural Extension (SAJAE), 2021)
The study assessed the agricultural extension agents' climate change training needs in Abia state. Eighty-three extension agents were chosen for the study using a simple random sampling procedure. Questionnaire was used to collect data, which was then summarized using percentages, frequency counts, and the mean. The findings indicated that male agricultural extension agents comprised a majority (53%) of the state's agricultural extension agents. The average household contained between one and five members (60%). Only 10% have a master's degree, while the majority (69%) have a bachelor's degree. The average length of employment was 15 years. The study's findings indicated that there are still extension agents who are unaware of climate change (1%). Agricultural extension agents in the study area have a limited understanding of all six climate change statements. Extension agents provide significant climate change services to farmers, including technical advice on climate change ( =2.0), the establishment of Small Plot Adaptation Techniques (SPAT) to monitor the impact of climate change (=2.1), and educating farmers on appropriate agrochemicals for climate change adaptation (weed and pest control) ( =2.2). Additionally, the results indicated that understanding fundamental climate change concepts ( =3.7), utilising cultural practises to mitigate and adapt to climate impacts ( =3.4), and environmentally friendly management practises to mitigate and adapt to climate change ( =3.4) were the primary areas of need for climate change training among extension agents. Inadequate funding for training (=3.4), a lack of financial support from organizations ( =3.3), and an inability to access financial support from funders (=3.3) were the major barriers to attending climate change training for extension agents. Regular climate change seminars and training workshops for agricultural extension agents at the federal and state levels will help to improve their overall knowledge of climate change issues. The Agricultural Development Program should utilize Forth nightly training (FNT) meetings to educate extension agents about climate change issues.
openalex:W4200426133 mag: KerkoCite.ItemAlsoKnownAs: 10.17159/2413-3221/2021/v49n3a12854 5072953:28QPEBRE
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; oa:keyword:agricultural extension agents; oa:keyword:climate change training needs; oa:sdg:13 Climate action; oa:topic:T10439 Adaptation to Climate Change in Agriculture; oa:topic:T13530 Climate Change and Environmental Impact; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

What Can We Learn from Rural Youth in British Columbia, Canada? Environment and Climate Change—Issues and Solutions - Udas, Pranita Bhushan; Fournier, Bonnie; Christianson, Tracy M.; Desbiens, Shannon (Sustainability, 2021)
“What can we learn from rural youth?” was a youth-led arts-based participatory action research project carried out to understand and facilitate positive youth development in two rural communities in the province of British Columbia, Canada. Data was collected using photovoice, visual art, journal reflections, and group discussions. During the study, youth expressed a strong connection with nature for their development or wellbeing. Issues such as environmental degradation and climate change were identified as causes for concern. They discussed human responsibility for environmental stewardship both in their local communities and globally. Climate change hazards such as flood and fire, human action leading to environmental pollution, and human responsibility for environmental stewardship surfaced as issues for their development. Youth expressed a felt responsibility to act on climate change and to reduce the anthropogenic impact on the Earth. Based on youth voices, we conclude that attempts to engage youth in climate action without considering their psychosocial wellbeing, may overburden them.
openalex: W4200453673
Keywords: C:United States; _z:class:countries; _z:class:themes; oa:keyword:rural youth; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11998 Positive Youth Development in the United States; oa:topic:T12997 Experiential Education and Adventure Therapy; openalex:import; openalex:yes

What Can We Learn from Rural Youth in British Columbia, Canada? Environment and Climate Change—Issues and Solutions - Udas, Pranita Bhushan; Fournier, Bonnie; Christianson, Tracy M.; Desbiens, Shannon (Sustainability, 2021)
“What can we learn from rural youth?” was a youth-led arts-based participatory action research project carried out to understand and facilitate positive youth development in two rural communities in the province of British Columbia, Canada. Data was collected using photovoice, visual art, journal reflections, and group discussions. During the study, youth expressed a strong connection with nature for their development or wellbeing. Issues such as environmental degradation and climate change were identified as causes for concern. They discussed human responsibility for environmental stewardship both in their local communities and globally. Climate change hazards such as flood and fire, human action leading to environmental pollution, and human responsibility for environmental stewardship surfaced as issues for their development. Youth expressed a felt responsibility to act on climate change and to reduce the anthropogenic impact on the Earth. Based on youth voices, we conclude that attempts to engage youth in climate action without considering their psychosocial wellbeing, may overburden them.
openalex: W4200453673
Keywords: C:Canada; C:United States; _z:class:countries; _z:class:themes; oa:keyword:rural youth; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11998 Positive Youth Development in the United States; oa:topic:T12997 Experiential Education and Adventure Therapy; openalex:import; openalex:yes

Burkina Faso: Why some West African architects are choosing mud over concrete (National Geographic) - Barza Wire (Barza Wire, 2021)
A group of architects in West Africa are pushing to use mud over concrete to build houses. In countries such as Burkina Faso, as people have become wealthier, they have transitioned to using …
KerkoCite.ItemAlsoKnownAs: 2129771:I2X77XHN 5072953:FNYRA99M
Keywords: C:Burkina Faso; _z:class:countries; _z:class:themes

Climate change resilience of school premises in Cyprus: An examination of retrofit approaches and their implications on thermal and energy performance - Heracleous, C.; Michael, Aimilios; Savvides, Andreas; Hayles, Carolyn (Journal of Building Engineering, 2021)
Educational buildings form a significant part of non-residential buildings that are of public use, and, in the case of Cyprus, this building stock tends to be less energy-efficient compared to a number of other public building typologies. Moreover, it is the purpose, frequency of use and user density of these buildings that make them a special case for study. These buildings are no longer fit for their assigned purpose as they require significant energy for heating in the winter and cooling in the summer, to avoid overheating. These conditions cause significant concerns in school buildings in Cyprus and the effects of climate change exacerbates these parameters. This research aims to evaluate the effectiveness of different retrofitting measures and their impact on the thermal comfort and the energy performance of educational premises under different climatic scenarios. For the purposes of this study, a secondary school building was selected as a representative case study of educational buildings in Cyprus and was modelled using IES-VE. Retrofit measures optimizing geometry, construction and operation were examined using a calibrated dynamic thermal simulation model in current and future climatic scenarios, to determine both their effectiveness in minimizing heating demand in the winter and overheating conditions in the summer period. Comfort conditions were assessed with reference to international standards based on adaptive thermal comfort. The study demonstrates that most educational buildings in Cyprus cannot ensure thermal comfort conditions, without the support of technical systems, neither in the present nor in anticipated future climatic conditions, thereby indicating the urgent need to take action. According to the research results, natural ventilation and insulation of the roof are considered very important in achieving this goal, as they have the potential to minimize the cooling degree hours by 96.8% and the heating degree hours by 4.3%. A combination of all passive measures and heat recovery ventilation can reduce degree hours for both heating and cooling by 51% in the current climatic conditions, and by 60% and 66.4% according to climatic projections for 2050 and 2090, respectively. The methodology for the evaluation of the thermal and energy behaviour of the educational building stock applied in this study could be a trustworthy tool for decision-making in energy retrofitting projects in Cyprus, as well as in other areas with similar climatic conditions.
openalex: W3202364395 mag: 3202364395
Keywords: C:Cyprus; _z:class:countries; _z:class:themes; evidence_review_2; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:import; openalex:yes

A survey of bedroom ventilation types and the subjective sleep quality associated with them in Danish housing - Liao, Chenxi; Akimoto, Mizuho; Bivolarova, Mariya Petrova; Sekhar, Chandra; Laverge, Jelle; Fan, Xiaojun; Lan, Li; Wargocki, Pawel (Science of The Total Environment, 2021)
We performed a survey of the types of bedroom ventilation in Danish dwellings (January–February 2020) and the associated subjective sleep quality. Five hundred and seventeen people responded. Their median age was 33 years old and 55.4% of them were males. We used an online questionnaire and collected information on the type of bedroom ventilation, bedroom airing behaviour by the respondents, the bedroom environment, building surroundings and location, and sleep disturbance caused by stuffy air, noise, and the thermal environment. Subjective sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI); its median among respondents was >5 indicating reduced sleep quality. 35.4% of the bedrooms had mechanical, 24.6% exhaust, and 40.0% natural ventilation. Sleeping in a bedroom with mechanical ventilation tended to reduce sleep disturbance. The absence of mechanical ventilation and the presence of carpet in the bedroom were all associated with stuffy air causing sleep disturbance, which was the second most sleep disturbing factor. PSQI increased significantly with increased sleep disturbance. People who reported that their sleep was disturbed by stuffy air or “too warm” conditions opened windows frequently during the day or night, but no association was found between PSQI and bedroom airing behaviours. Our results are valid for the heating season and the survey would have to be repeated in the non-heating season to permit generalization of the findings. The results present associations and are qualitative, so field measurements are necessary to validate the present observations and provide further explanations.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.scitotenv.2021.149209 2129771:5DU85DEJ 4682641:W4ZVX6EJ 5072953:S9TX6GQB openalex: W3186482159
Keywords: BE:RELEVANT; Noise; Occupant behaviour; PSQI; Sleep disturbance; Stuffy air; Thermal comfort; _z:class:countries; _z:class:themes; oa:keyword:bedroom ventilation types; oa:keyword:subjective sleep quality; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10316 Sleep and Insomnia; oa:topic:T11692 Effects of Noise Pollution on Health and Well-being; openalex:n:1; openalex:yes

Pathologies of the hearing aid under the influence of global climate change and ecology - Ryzhkin, Nikolay; Ivanova, Anna; Savchenko, Yulia; Polin, R; Korobov, I. A. (IOP Conference Series: Earth and Environmental Science, 2021)
Abstract This article discusses the pathological changes of the hearing aid in connection with the deterioration of the environmental situation around the world, presents the psychophysical features that deal with the struggle of children with hearing impairment (hard of hearing and deaf). The method of physical education in the course of classes in the wrestling section for the adaptation and harmonious physical development of hard-of-hearing children is proposed and investigated. In our opinion, exercises in wrestling contribute to the development of a number of many valuable physical and psychological qualities that are necessary for a child with hearing impairment. The hypothesis of the study is based on the assumption that the inclusion of special developed methods for wrestling will allow to achieve significant results in a short time in children with hearing impairment. The use of wrestling exercises allows you to maximize the development of the functions of these analyzers for deaf children to more effectively participate in the compensation of lost qualities as a result of impaired hearing aid.
openalex: W4200431447
Keywords: _z:class:countries; openalex:import; openalex:yes

Climate for changing lenses : Reconciliation through site-specific, media arts-based environmental education on the water and climate change nexus in South Africa and Canada - Borek, Sarah Van (2021)
This study took place in the context of a growing racialised global water crisis and increasing demands worldwide for transforming higher education at institutions of ongoing settler colonialism. It presents a conceptualisation of what education, research and activism can look like and unfolded inside a doctoral research project that expands what doctoral education can look like. Using a media arts-based praxis process, I developed a relational model of university curriculum – site-specific, media arts-based, environmental education – with potential to cultivate relations (human and nonhuman) towards reconciliation while contributing to justice at the water-climate change nexus. My aim as a settler-ally was to expand my teaching and curriculum practices, thereby also offering curriculum transformation inspiration to others. My research was rooted in my concept of reconciliation as a practice towards thriving together, where the ‘together’ was inclusive of both humans and nonhumans. The curriculum engaged students in de/re/constructing water narratives through making site-specific videos focused on local water bodies. Decolonising artistic approaches known as slow media and soundscape recording were strategically incorporated into audio/video mapping assignments where students observed water aesthetics in ways that shifted their perceptions about water and entities entangled with it. Students met with Knowledge Keepers (Indigenous and non-Indigenous people from outside the academy with existing relationships to water bodies). A photovoice methodology was used in these meetings with Knowledge Keepers to reconfigure traditional film director-subject power relations. Guest lecturers from non-traditional backgrounds contributed diverse perspectives. Ecomotricity was incorporated, whereby students were in deliberate movement in/with water bodies through canoeing together. The curriculum culminated in a public screening/education event where resulting videos, interspersed with educational games facilitated by students, surfaced emotions, knowledge co-production and new synergies amongst the event’s temporary community. Through two iterations of the curriculum, where I co-designed and taught a course called Making Waveforms, one in Vancouver, Canada and one in Cape Town, South Africa, I explored the primary research question: How can a relational site specific, media arts-based university environmental education curriculum cultivate students’ relational sensibilities and abilities oriented towards reconciliation of diverse peoples and ecosystems in South Africa and Canada? Iterating the curriculum across these two contexts allowed me to assess which aspect(s) of the curriculum may have been applicable across these and other contexts. By using mixed methods of data collection and sharing throughout the research journey, I explored the sub-questions: a) How is reconciliation understood currently by university students in South Africa and Canada? and b) How can a relational site-specific, media arts-based university environmental education curriculum and my PhD methodologies (PhD-by-publication, website, and participatory approaches to podcasting, video making, and song creation), contribute to decolonising higher education, and thereby further contribute to reconciliation of diverse peoples and ecosystems in South Africa and Canada? Integral to my praxis process, I undertook a PhD-by-publication that involved writing four academic journal articles, with each paper presenting a key stage in the process. The papers, all of which have been submitted to peer-reviewed academic journals, form part of this thesis and can be found in the Appendices. The course was originally developed around Donati’s (2011) relational sociology and Gergen’s (2009) relational education theory. Throughout my praxis process, I expanded my theoretical influences as called for by the research and teaching practice. The journey behind my first PhD paper, (Towards) Sound research practice: Podcast- building as modeling relational sensibilities at the water-climate change nexus in Cape Town, began when I officially started my doctoral studies in early 2018. The paper was co- authored with a fellow PhD scholar from Rhodes University’s Environmental Learning Research Centre (ELRC), Anna James. It presents an experimental arts-based methodology we co-developed for doing contextual profiling by building a socially-engaged podcast series, called DayOne, to explore the lived experiences of the Cape Town water crisis of 2018. It includes my initial tool of analysis for exploring how the curriculum might cultivate relational sensibilities and abilities towards reconciliation. The podcast pedagogy offered opportunities to develop some relational learning processes. The analytical tool was developed from cross-referencing reconciliation and relational educational theories. This paper also incorporated theories in relational solidarity and social movement learning. The podcast episodes included personal narratives that, in turn, revealed diverse ideologies and polarisations in the water situation. Working with the audio medium highlighted possibilities for creating and shifting affective relations. Recording and editing soundscapes of water bodies began explorations of the agential qualities of water. These were foundational dynamics to explore in building the reconciliation curriculum. The paper is published in the International Journal of New Media, Technology, and the Arts (2019, Volume 14, Issue 1). My second PhD paper, A media arts-based praxis process of building towards a relational model of curriculum oriented towards reconciliation through water justice, presents my methodology for and analysis of a pilot course I co-designed and taught at the Emily Carr University of Art + Design (ECUAD) in Vancouver, Canada in 2018. This course served as contextual profiling around the water situation in Vancouver. The course was offered in partnership with a science-based environmental non-profit called the David Suzuki Foundation and an Indigenous-led post-secondary school called the Native Education College. The course’s public event was hosted at the Beaty Biodiversity Museum. At this stage, I was introduced to Cree/Métis filmmaker, Gregory Coyes, and his Indigenous cinematic narrative approach known as Slow Media. Integrating slow media into video mapping assignments presented exciting possibilities for shifting views and valuing of water. This was the stage at which my concept of reconciliation expanded to explicitly include nonhumans. I applied my initial analytical tool to the curriculum here, which revealed the three most prominent relational sensibilities and abilities towards reconciliation cultivated by students through the course: (1) knowledge ecologies; (2) a hopeful social imaginary; and (3) embodied ways of knowing. I began to make connections between the curriculum and Mi’kmaq elder Albert Marshall’s concept of ‘Two-Eyed-Seeing’, and expanded the notion to ‘Three-Eyed-Seeing’ to include artistic approaches. Deeply inspired by Bekerman and Zembylas’s (2012) Teaching Contested Narratives, I began to see the growing importance of the narrative aspects of reconciliation education. The paper is published in the University of Pretoria’s Journal of Decolonising Disciplines (2021, Volume 1, Issue 2). My third PhD paper, Water as artist-collaborator: Posthumanism and reconciliation in relational media arts-based education, presents a 2019 iteration of the curriculum at ECUAD in Vancouver, and illustrates my shift to include posthuman theories in my analysis. This course was offered in affiliation with the David Suzuki Foundation, and in collaboration with the Native Education College. The culminating public event was hosted by the Beaty Biodiversity Museum. Decentring the human in this data analysis better supported my research and curricular aims. The strong technoculture of the media arts-based curriculum fits well with many posthuman concepts. This posthuman reading of the course and data enabled me to see what changes were emerging through student-water-technology intra-actions, and how these supported relations towards reconciliation as well as water justice. Most notable of these changes was the emergence of water’s agential qualities, specifically of water as becoming collaborator in artistic/knowledge co-production, where students think with water. I argued this contributes to reconciliation by decentring the human, enabling relations in which power is more equal, and where there are greater possibilities for mutual responsibility between related entities. This is where I developed the concept of audio/video as relational texts, supporting the creating and shifting of affective relations more than the monumentalised verbal/written knowledge of traditional universities. This is also where I realised that relational work towards reconciliation would require engaging with the hidden curriculum of institutions. The paper is published in the journal Reconceptualizing Educational Research Methodology (2021, Volume 12, Issue 1), as part of a special issue on Posthuman Conceptions of Change in Empirical Educational Research. My fourth PhD paper, originally entitled Making waveforms: Implicit knowledge representation through video water narratives as decolonising practice towards reconciliation in South Africa’s higher education, presents an analysis of the 2019 iteration of the curriculum in South Africa. I co-designed and led a course called Making Waveforms at the University of Cape Town’s Future Water Institute (FWI) in collaboration with Rhodes University. The course was co-designed/facilitated with FWI’s Research Fellow Amber Abrams, who also co-authored this paper. The course’s public event was hosted by a non- profit organisation called the Tshisimani Centre for Activist Education. This paper explored the ways that non-verbalisable, implicit learning – understood as part of many non- Euro/Western ways of knowing – takes place in the Making Waveforms course and how this influenced water-specific climate behaviours while contributing to decolonised reconciliation practice for higher education institutions. Drawing on theories of implicit and explicit knowledge, we first showed how implicit learning primarily took place through: 1) site- specific audio/video mapping of water bodies; 2) meetings with Knowledge Keepers; and 3) an interactive public screening event. We highlighted how this non-verbalisable learning produced feelings of empathy for diverse peoples and waterways, as well as aesthetic appreciation of water, and how this can contribute to more response-able water behaviours. This, we argued, supported the valuing of implicit knowledge within a traditional educational setting, thereby pluralising knowledge, and was key to reconciliation/decolonisation in higher education. Iterating the curriculum for the South African context emphasised the importance of context-specificity of the course overall, and also of the relational work embedded in the curriculum. This paper is under review by the University of Toronto’s journal Curriculum Inquiry (CI). Following receipt of CI's internal review process, the title of the paper has since been updated to Non-verbalisable, implicit knowledge through cellphilms as decolonised reconciliation practice towards response-able water behaviours in South Africa. Through reflective analysis of my four papers, I developed a concept for an Anatomy of Decoloniz/sed Curriculum consisting of five key parts: 1) relationality; 2) multimodality; 3) narratives/counter-narratives; 4) context-specificity; and 5) unhidden curriculum. Four metareflections have been included in this thesis, each corresponding with one of the four papers, and presented chronologically according to the stage of the praxis process with which they correspond. In these metareflections, I applied Kolb’s (1984) Experiential Learning Cycle model for reflective writing, based on the premise that through experiences we can expand our understanding, and included four key stages: 1) concrete experience; 2) reflective observation; 3) abstract conceptualisation; and 4) active experimentation. For the concrete experience, I provided a thick description of my process in writing the paper, as well as aspects of the phase in my praxis process that was the focus of the paper, not included in but relevant to the paper. For the reflective observation, I identified any aspects of the experience that were new to me and which therefore presented opportunities for me to learn. For the abstract conceptualisation, I critically analysed my concrete experience and reflective observation to determine which, if any, of the five key parts of the Anatomy of Decoloniz/sed Curriculum that I outline in my introduction relate to this phase of my PhD praxis process. For the active experimentation, I made conclusions about the extent to which this phase of my PhD embraced decoloniality in practice, and built on this new understanding to make recommendations for myself and others committed to the decolonial project as part of my contribution to knowledge. These metareflections also invite readers to follow my personal narrative of becoming-with water, meaning my transformation from being water illiterate to embracing a ‘watershed mind’ (Wong, 2011). Multimodality, which I propose as a key part of an Anatomy of Decoloniz/sed Curriculum, is embedded in the representational aspects of this thesis. The courses I co-designed and taught as part of this project resulted in the creation of 20 short student films. My contextual profiling involved a podcast methodology that was ongoing throughout my study, as a model of decolonised research-communication-education-action at the water-climate change nexus. This methodology resulted in the creation of four DayOne podcast episodes, co-produced with a PhD colleague, Anna James. Some of these episodes are available in all three main languages of Cape Town (Xhosa, Afrikaans, and English). I evolved the podcast methodology in a later stage of my praxis process as a form of member checking with contributors involved in various stages and aspects of the research. Once the four papers were written, I created a series of four short videos called In the Flow, with each video representing a translation of one of the four papers. I invited various contributors of the research project to either watch one or more of the In the Flow videos and/or read one or more of the academic papers, and then to respond in a Zoom call with me. The responses were then shared publicly in a series of seven Climate for Changing Lenses podcast episodes. Parts of these are included in a final song/music video called Please Don’t Blow It. A Climate for Changing Lenses website was created to host all of this multimedia content that forms part of this thesis. A link to this website is provided in the Introduction section of this thesis. My research contributes to the advancement of knowledge in the areas of relational and reconciliation pedagogy, decolonising higher education, arts-based teaching, learning and research methodologies and the water-climate change nexus. My praxis process provided a relational model of reconciliation curriculum that has been tried and tested in two international contexts: Canada and South Africa.
openalex:W4226398406 mag: KerkoCite.ItemAlsoKnownAs: 10.21504/10962/192754 5072953:5SBH6I5A 5072953:WRNMPK2E
Keywords: C:Canada; C:South Africa; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:climate change; oa:keyword:environmental education; oa:topic:T12997 Experiential Education and Adventure Therapy; openalex:import; openalex:n:1; openalex:yes

The Impact of Occupancy Energy Use Behaviour of High-Rise Dwellings In Southeast China - Wuxia, Wuxia; Zhang, Wuxia; Calautit, John Kaiser; Hamaza, Neveen (2021)
KerkoCite.ItemAlsoKnownAs: 10.46855/energy-proceedings-8316 5072953:JM4D5PC9
Keywords: C:China; _z:class:countries; _z:class:themes

Building Occupancy Prediction Through Machine Learning for Enhancing Energy Efficiency, Air Quality and Thermal Comfort: Review and Case Study - Wuxia, Wuxia; Zhang, Wuxia; Tien, Paige; Calautit, John Kaiser; Wu, Yupeng (2021)
KerkoCite.ItemAlsoKnownAs: 10.46855/energy-proceedings-8314 5072953:Q3BMJFGC
Keywords: _z:class:countries; _z:class:themes

Building capacity for climate-change education in Aotearoa New Zealand schools - Everth, Thomas; Bright, Ria; Morey, Chris; DePetris, Thea; Gaze, Sarah; Barker, Anne; Soanes, Andrea; Gurney, Laura; Eames, Chris (2021)
The government of Aotearoa New Zealand has recognised the gravity of climate change by adopting a Climate Emergency declaration, passing the Zero Carbon Act (2019), and asking the Climate Change Commission to chart a pathway towards a carbon-zero future. The climate emergency necessitates transformation of the practices and visions of individuals and society towards a sustainable future. We argue that education must be recognised as a key enabler for this transformational process. In this article, we draw on our recommendations to the Climate Change Commission (2021a) for structural changes in our education system to build capacity for the implementation of climate-change education for a sustainable future. Our focus is on building capacity in school leaders and teachers through development of knowledge and skills, provision of time and space, and cultural embedding of education on sustainable living and climate change into the ways we all teach and learn. Our intention is to provide a “think piece” to be considered and discussed by school educators and leaders across Aotearoa New Zealand.
openalex: W3210193220 mag: 3210193220
Keywords: C:New Zealand; _z:class:countries; _z:class:themes; oa:keyword:climate-change climate-change; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; openalex:import; openalex:yes

Building capacity for climate-change education in Aotearoa New Zealand schools - Everth, Thomas; Bright, Ria; Morey, Chris; DePetris, Thea; Gaze, Sarah; Barker, Anne; Soanes, Andrea; Gurney, Laura; Eames, Chris (2021)
The government of Aotearoa New Zealand has recognised the gravity of climate change by adopting a Climate Emergency declaration, passing the Zero Carbon Act (2019), and asking the Climate Change Commission to chart a pathway towards a carbon-zero future. The climate emergency necessitates transformation of the practices and visions of individuals and society towards a sustainable future. We argue that education must be recognised as a key enabler for this transformational process. In this article, we draw on our recommendations to the Climate Change Commission (2021a) for structural changes in our education system to build capacity for the implementation of climate-change education for a sustainable future. Our focus is on building capacity in school leaders and teachers through development of knowledge and skills, provision of time and space, and cultural embedding of education on sustainable living and climate change into the ways we all teach and learn. Our intention is to provide a “think piece” to be considered and discussed by school educators and leaders across Aotearoa New Zealand.
openalex: W3210193220 mag: 3210193220
Keywords: C:New Zealand; _z:class:countries; _z:class:themes; oa:keyword:climate-change climate-change; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; openalex:import; openalex:yes

Combination of lighting retrofit and life cycle cost analysis for energy efficiency improvement in buildings - Belany, Pavol; Hrabovsky, Peter; Kolkova, Zuzana (Energy Reports, 2021)
This article deals with the possibilities the lighting retrofit and the life cycle cost analysis economic analysis in the process of increasing the energy efficiency of buildings. It contains basic information about lighting retrofit and the life cycle cost analysis and its implementation for cost estimation for a building lighting system. The accuracy of the life cycle cost analysis was verified on three lighting systems. The first system consisted of an old (original) lighting system that was commonly used in office buildings. The other two lighting systems are based on the concept of retrofit lighting. One system is based on switching according to the movement of people and the other system is based on sensing daylight and maintaining the intensity of lighting at the prescribed level. By measuring the power consumption of these systems, data of power consumption were obtained. The data from life cycle cost analysis were obtained by calculation. Finally, the results between each measurement and data from life cycle cost analysis were evaluated and compared. After compared the data, the resulting accuracy of life cycle cost analysis was determined. The last aim was to determine its suitability for other use in modernization, retrofit, design of new lighting systems, and in the process of increasing energy efficiency of buildings.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.egyr.2021.04.044 4874017:K9BL92GL 5072953:4VIRDKXP openalex: W3158473716
Keywords: Consumption of electricity; Economic; Life cycle cost analysis; Lighting retrofit; Lighting systems; Measurement; _z:class:countries; _z:class:themes; oa:keyword:energy efficiency improvement; oa:keyword:life cycle cost analysis; oa:keyword:lighting retrofit; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11954 Energy Efficiency in Manufacturing and Industry Sector; oa:topic:T14138 Life Cycle Costing in Construction and Infrastructure Projects; openalex:n:1; openalex:yes

Climate Disaster Risk, Disability, and Resilience - Calgaro, Emma (Current history, 2021)
This essay examines the everyday inequalities, stigmas, and injustices that leave people with disabilities highly vulnerable to escalating climate change risks. It argues that including people with disabilities in disaster risk reduction processes is essential to shaping inclusive, effective policies and practices. Examples of several programs that have done so are discussed. Focusing on the strengths of people with disabilities as resilient change-makers and as the experts in their own lives—instead of viewing them as dependent on others—can lead to the changes necessary to recognize their personal sovereignty and deliver disaster justice. Third in a series on disability rights around the world.
openalex: W3210488461 mag: 3210488461
Keywords: _z:class:countries; openalex:import; openalex:yes

Perception of gender in children's voices - Barreda, Santiago; Assmann, Peter F. (The Journal of the Acoustical Society of America, 2021)
KerkoCite.ItemAlsoKnownAs: 10.1121/10.0006785 2129771:HI6VSIF4 5072953:XVM2MZXK openalex: W3216504255
Keywords: _z:class:countries; _z:class:themes; oa:keyword:gender; oa:topic:T10201 Speech Recognition Technology; oa:topic:T10403 Speech Perception and Phonetics; oa:topic:T10863 Diagnosis and Treatment of Voice Disorders; openalex:n:1; openalex:yes

Expressed Willingness and Awareness of Students towards Climate Change in Lahore, Pakistan - Gulraiz, Khadija; Ali, Aabgeen (Indonesian Journal of Innovation and Applied Sciences, 2021)
Global climate change is one of the most significant threats to our generation, the fundamentals of the issue lie in the fact that the anthropogenic contribution of greenhouse gases is changing the global climate at a rapid rate causing immense warming trends and displaced cold weather. This study examined the awareness levels of college/university students on climate change and their willingness to mitigate the effects of climate change. 69 students from Lahore’s different public and private sector universities were asked to fill out a survey questionnaire form online and were questioned on their attitudes about climate change and their willingness to take action to mitigate its effects.
openalex: W3209827689 mag: 3209827689
Keywords: C:Pakistan; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:yes

A hybrid deep transfer learning strategy for thermal comfort prediction in buildings - Somu, Nivethitha; Sriram, Anirudh; Kowli, Anupama; Ramamritham, Krithi (Building and Environment, 2021)
Since the thermal condition of living spaces affects the occupants' productivity and their quality of life, it is important to design effective heating, ventilation and air conditioning (HVAC) control strategies for better energy efficiency and thermal comfort. An essential step in HVAC control and energy optimization is thermal comfort modeling. Recently, data-driven thermal comfort models have been preferred over the Fanger's Predicted Mean Vote (PMV) model due to higher accuracy and ease of use. However, the unavailability of comprehensive labelled thermal comfort data from the occupants poses a significant modeling challenge. This paper addresses data inadequacy issues by adopting ‘transfer learning’ to leverage well learned knowledge from source domain (same climate zones) to target domain (different climate zone) where modeling data is sparse. Specifically, a Transfer Learning based Convolutional Neural Networks-Long Short Term Memory neural networks (TL CNN-LSTM) is designed for effective thermal comfort modeling that exploits the spatio-temporal relations in the thermal comfort data. The significant modeling parameters for TL CNN-LSTM are identified using the Chi-squared test. Further, the lack of sufficient samples across all thermal conditions in the available thermal comfort datasets was handled by Synthetic Minority Oversampling Technique (SMOTE). Experiments with two source (ASHRAE RP-884 and Scales Project) and one target (Medium US office) datasets demonstrate the ability of TL CNN-LSTM in achieving an accuracy of >55% with limited data in target buildings. The limitation of TL CNN-LSTM is its continued dependence on intrusive parameters and the challenges in assessing its adaptability to different climate zones.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.buildenv.2021.108133 5072953:FVAW22VY 5072953:SNMR652J openalex: W3181530645
Keywords: Buildings; Deep learning; Energy efficiency; HVACs; Thermal comfort; Transfer learning; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:thermal comfort prediction; oa:sdg:13 Climate action; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:n:1; openalex:yes

Classroom Temperature and Learner Absenteeism in Public Primary Schools in the Eastern Cape, South Africa - Pule, Vicky; Mathee, Angela; Melariri, Paula; Kapwata, Thandi; Abdelatif, Nada; Balakrishna, Yusentha; Kunene, Zama; Mogotsi, Mirriam; Wernecke, Bianca; Wright, Caradee (International Journal of Environmental Research and Public Health, 2021)
Children spend a significant proportion of their time at school and in school buildings. A healthy learning environment that supports children should be thermally conducive for learning and working. Here, we aimed to study the relations between indoor classroom temperatures and learner absenteeism as a proxy for children’s health and well-being. This one-year prospective study that spanned two calendar years (from June 2017 to May 2018) entailed measurement of indoor classroom temperature and relative humidity, calculated as apparent temperature (Tapp) and collection of daily absenteeism records for each classroom in schools in and around King Williams Town, Eastern Cape province, South Africa. Classroom characteristics were collected using a standardized observation checklist. Mean indoor classroom temperature ranged from 11 to 30 °C, while mean outdoor temperature ranged from 6 °C to 31 °C during the sample period. Indoor classroom temperatures typically exceeded outdoor temperatures by 5 °C for 90% of the study period. While multiple factors may influence absenteeism, we found absenteeism was highest at low indoor classroom Tapp (i.e., below 15 °C). Absenteeism decreased as indoor Tapp increased to about 25 °C before showing another increase in absenteeism. Classroom characteristics differed among schools. Analyses of indoor classroom temperature and absenteeism in relation to classroom characteristics showed few statistically significant relations—although not exceptionally strong ones—likely because of the multiple factors that influence absenteeism. However, given the possible relationship between indoor temperature and absenteeism, there is a learning imperative to consider thermal comfort as a fundamental element of school planning and design. Furthermore, additional research on factors besides temperature that affect learner absenteeism is needed, especially in rural areas.
KerkoCite.ItemAlsoKnownAs: 10.3390/ijerph182010700 2129771:NVDRMIPP 4874017:UQYUZZ8N
Keywords: evidence_review

An IoT-based deep learning approach to analyse indoor thermal comfort of disabled people - Brik, Bouziane; Esseghir, Moez; Merghem-Boulahia, Leila; Snoussi, Hichem (Building and Environment, 2021)
Monitoring the thermal comfort of building occupants is crucial for ensuring sustainable and efficient energy consumption in residential buildings. Existing studies have addressed the monitoring of thermal comfort through questionnaires and activities involving occupants. However, few studies have considered disabled people in the monitoring of thermal comfort, despite the potential for impairments to present thermal requirements that are significantly different from those of an occupant without a disability. Additionally, people with disabilities can experience difficulties in expressing their thermal comfort, which further complicates assessment and monitoring. To overcome this, we propose the development of a new learning model using a deep neural network. Our model can predict the indoor thermal comfort of differently abled people in real time to facilitate remote monitoring. We generated our real dataset using a new Internet of Things (IoT) architecture. Our architecture also includes a data collection scheme to ensure an efficient collection process, enabling the collection of targeted data before transferring them to cloud servers for further data analysis. Experimental results illustrate the reliability of our data collection scheme in gathering useful and targeted data, as well as the efficiency of our deep learning-based model, which achieved an accuracy of 94% and a precision and recall of 98% and 97%, respectively.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.buildenv.2021.108056 2129771:ZRVWRNN9 5072953:KCFYCHC9 openalex: W3176869133
Keywords: Building sustainability; Deep learning; Disabled people; Indoor thermal comfort prediction and monitoring; Internet of Things (IoT); _z:class:countries; _z:class:themes; oa:keyword:indoor thermal comfort; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T10990 Airborne Transmission of Respiratory Viruses; openalex:n:1; openalex:yes

Mitigating the impacts of climate change on education for persons with disabilities - Duc, Minh Nguyen (Tạp chí Khoa học Giáo dục, 2021)
Climate change has a negative effect on health and enrollment in activities, especially for education for people with disabilities. People with disabilities mostly come from impoverished families where public services are underdeveloped. Thus, they face disadvantages when participating in online and face-to-face education because the quality of infrastructure and learning materials is inadequate. The difficulties for education for people with disabilities are also exacerbated by climate change which also affects people without disabilities. In detail, the support for people with disabilities are significantly reduced in terms of special learning materials and facilities, which are consistently more expensive than the common ones. Since the life quality declines because of climate change, people without disabilities will contest for jobs and thus leading to difficulties in the output of education for people with disabilities and affecting their learning motivation adversely. To tackle these restrictions, a comprehensive and synchronous solution is required.
openalex: W4212935190
Keywords: _z:class:countries; openalex:import; openalex:yes

Climate Change and Disability Issues in Vietnam - Hải, Nguyễn Xuân (Tạp chí Khoa học Giáo dục, 2021)
Despite of the fact that, disability issue as well as person with disability has been investigated and applied these research results in practice to support them to cover their basic human rights, be fully developed and included into the communities. However, researches on climate change with its impacts on the disabilty and how person with disability overcomes and adapts to climate change are considered as a limitation in the country. The contents of paper focuses on a very first step of research’s results on theoretical issues on climate change and disability in order to have an overall picture and some orientations towards this issue in current practice and the coming development phase in Vietnam.
openalex: W4213278123
Keywords: _z:class:countries; openalex:import; openalex:yes

Early education on environmental protection and skills to respond to natural disaster and climate change for children disabilities at early intervention center - Hoang, Yen (Tạp chí Khoa học Giáo dục, 2021)
The article poses an idea to ensure children's right to access to information, education on environmental protection (EPE) and skills to respond to natural disasters and climate change (CC) for children with disabilities from an early age through educational and therapeutic programs, rehabilitation at Early Intervention Centers. The program will include 2 main components: Component 1 provides information about the surrounding environment and environmental protection education. Component 2 will be activities to practice some skills to respond to natural disasters and climate change. This program will be built according to the suggested framework and developed in ways that are suitable for different types of disabilities to be highly applicable. These are pictures, videos, braille, sign language for component 1 and game activities, plays or situations integrated with intervention and therapy activities for component 2
openalex: W4212928891
Keywords: _z:class:countries; openalex:import; openalex:yes

Model predictive control strategy using encoder-decoder recurrent neural networks for smart control of thermal environment - Li, Yue; Tong, Zheming (Journal of Building Engineering, 2021)
The development of deep learning (DL) technology provides an opportunity for accurate prediction and effective control of complex building systems. However, despite the high prediction performance of DL models, few studies integrate DL with the model predictive control (MPC) algorithm for improving building management. In this study, a DL-based MPC framework using encoder-decoder recurrent neural network is developed for real-time control of building thermal environment to exploit the advantage of both DL and MPC algorithms. In addition, to simulate the dynamic interaction between indoor airflow and HVAC systems, a co-simulation platform by integrating HVAC simulator and CFD model is developed to evaluate the proposed building control strategy. Two case studies including a confined space with mixing ventilation and an office room subjected to solar radiation are used for validation of the proposed method. The performance of the DL-based MPC algorithm for building thermal environment control is compared with the traditional proportion-integration-differentiation (PID) controller and the adaptive PID controller. Approximately 4% and 7% energy savings are achieved on average through DL-based MPC compared with adaptive and conventional PID control, respectively. The proposed DL-based MPC framework shows a promising application prospect for building automationby taking the advantage of both deep learning and MPC algorithms.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.jobe.2021.103017 5072953:9D2T6MFM openalex: W3184051402
Keywords: Computational fluid dynamics; Model predictive control; Recurrent neural networks; Smart control; Thermal environment; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:model predictive control strategy; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; oa:topic:T11529 Refrigeration Systems and Technologies; openalex:n:1; openalex:yes

Model predictive control strategy using encoder-decoder recurrent neural networks for smart control of thermal environment - Li, Yue; Tong, Zheming (Journal of Building Engineering, 2021)
The development of deep learning (DL) technology provides an opportunity for accurate prediction and effective control of complex building systems. However, despite the high prediction performance of DL models, few studies integrate DL with the model predictive control (MPC) algorithm for improving building management. In this study, a DL-based MPC framework using encoder-decoder recurrent neural network is developed for real-time control of building thermal environment to exploit the advantage of both DL and MPC algorithms. In addition, to simulate the dynamic interaction between indoor airflow and HVAC systems, a co-simulation platform by integrating HVAC simulator and CFD model is developed to evaluate the proposed building control strategy. Two case studies including a confined space with mixing ventilation and an office room subjected to solar radiation are used for validation of the proposed method. The performance of the DL-based MPC algorithm for building thermal environment control is compared with the traditional proportion-integration-differentiation (PID) controller and the adaptive PID controller. Approximately 4% and 7% energy savings are achieved on average through DL-based MPC compared with adaptive and conventional PID control, respectively. The proposed DL-based MPC framework shows a promising application prospect for building automationby taking the advantage of both deep learning and MPC algorithms.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.jobe.2021.103017 5072953:9D2T6MFM openalex: W3184051402
Keywords: Computational fluid dynamics; Model predictive control; Recurrent neural networks; Smart control; Thermal environment; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:model predictive control strategy; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; oa:topic:T11529 Refrigeration Systems and Technologies; openalex:n:1; openalex:yes

Meta-analysis of 35 studies examining the effect of indoor temperature on office work performance - Porras-Salazar, Jose Ali; Schiavon, Stefano; Wargocki, Pawel; Cheung, Toby; Tham, Kwok Wai (Building and Environment, 2021)
Several relationships between air temperature and work performance have been published. We reanalysed the one developed in 2006 by Seppänen et al.; which is probably the best known. We found that even when significant, its prediction accuracy is very low (R2 = 0.05, MAE = 1.9%, RMSE = 3.1%). We consequently reviewed the literature and found 35 studies on the effects of temperature on office work performance. We used Seppänen et al.’s approach to normalise the data reported in these studies and explored the feasibility to develop a new relationship using regression models, models based on the Maximal Adaptability framework, and machine learning. We could not find a relationship between temperature and office work performance neither for the range of temperatures measured in most of the office buildings (20 °C–30 °C) or a wider range (18 °C–34 °C). Plausible reasons are discussed including the variety of methods used to assess performance, the multiple uncontrolled confounders, and the fact that temperature alone may not fully describe how the thermal environment affects building occupants. We do not recommend the use in practice of any of the models relating temperature to office work performance examined in the present study. The lack of relationships does not necessarily refute that temperature affects the performance of office work. Coordinated research predicated on a shared protocol enabling integrated analysis in the modelling of the relationships between the indoor thermal environment and office work performance is proposed to be carried out before using them in practice. We made the database open-source and developed an application for data exploring.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.buildenv.2021.108037 2129771:3WB6E2E4 4682641:B4RYFHC6 4682641:PEAZCXFI 5072953:XHSSELJ3 openalex: W3171272084
Keywords: BE:RELEVANT; C:Mali; Cognitive performance; Indoor air temperature; Offices; Productivity; Thermal environment; _z:class:countries; _z:class:themes; oa:keyword:indoor temperature; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11002 Indoor Air Quality and Health Effects; oa:topic:T12256 Impact of Workspace Environment on Work Performance; openalex:n:1; openalex:yes; type:meta-analysis

Optimizing thermal comfort and energy use for learning environments - Taylor, Mary; Brown, Nathan C.; Rim, Donghyun (Energy and Buildings, 2021)
Thermal comfort is a critical component of indoor environments, especially in schools where learning is the main objective. However, thermal comfort comes at a price that many schools are unable to afford. Therefore, it is critical to determine a method to lower the energy costs of a building while still maintaining occupant thermal comfort. The objective of this study is to investigate how three indoor environmental parameters of air speed, humidity, and air temperature influence energy and thermal comfort in classroom environments. We employed a multi-objective optimization method that considers all three thermal parameters in the design and operation of a classroom. This method is demonstrated for three distinct climate locations (very hot and humid, cold and humid, warm and marine). Overall, our findings demonstrate significant energy savings from 1.3 to 9.1 kWh/year/m2 for cases where energy reduction is achieved. These values are for cases where the total annual number of hours that more than 10% of people are dissatisfied in a space are 0 to 42 in Miami and San Francisco and 26 to 49 in Boston. This translates to a cost savings of $3,000 to $12,800 per year for the entire building at current market rates. Note that for all locations, there were also cases where the number of hours that more than 10% of people were dissatisfied were reduced from the baseline value while still reducing energy use. This optimization framework shows promise for building mechanical designers seeking to maintain increased levels of thermal comfort throughout the year while lowering energy use.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2021.111181 2129771:JGWBQ9ZN 4682641:MNJ28P67 4682641:VRCRT79Y 5072953:2T8LM26W openalex: W3170652612
Keywords: Air speed; BE:RELEVANT; Building energy; Classroom; Humidity; Multi-objective optimization; Thermal comfort; _z:class:countries; _z:class:themes; evidence_review_2; oa:keyword:thermal comfort; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T10990 Airborne Transmission of Respiratory Viruses; openalex:n:1; openalex:yes

Awareness and responses to the impacts of climate change and air pollution: voices from parents of children with disabilities - The, Hop Bui; Cong, Khanh Nguyen; Cam, Huong Nguyen Thi; Trang, Thu Dinh Nguyen; Tuyet, Anh Tran (Tạp chí Khoa học Giáo dục, 2021)
This paper shows the findings of an in-depth interviewing study on the awareness and responses of parents of children with disabilities to climate change and air pollution. The study was conducted in a sample of 87 parents. It found that: 1) The parents have had common awareness and concern about the problems; 2) Their children have been being more vulnerable to climate change and air pollution, particularly more school days off and less learning performance; & 3) The parents showed their common actions towards protection to the child and environment; but rarely knew about IT innovation supporting their child’s learning. Several of them showed their expectation of providing the online learning and IT
openalex: W4212972128
Keywords: _z:class:countries; evidence_review_2; openalex:import; openalex:yes

Education of children with disabilities response to climate change and air pollution - Thị, Huế Nguyễn; Thu, Huyen Le Thi (Tạp chí Khoa học Giáo dục, 2021)
This article presents the most basic issues about climate change, air pollution and its negative impacts on human life, including children with disabilities. Climate change is a change of climate and of related components including oceans, land, Earth's surface, and the glacial atmosphere, such as increasing temperature, melting ice, and rising sea levels... Air pollution is a negative change of components in the air mainly due to smoke, dust, foreign gases, causing odors, reducing visibility, causing climate change and diseases for humans and animals. life and the natural environment. Climate change and air pollution are both the causes of disability, exacerbating disability levels and hindering society from supporting and helping people with disabilities in general and children with disabilities in particular. On the basis of research results, we propose educational measures to help children with disabilities cope with the impacts of climate change and air pollution. That is: - Educating children to practice to improve their health and maintain personal hygiene; - Educating children on environmental protection; - Educating children to recognize the risk signs of climate change and air pollution to prevent them; - Educating children how to ask for help when needed; - Educating children to know how to protect themselves against the impacts of climate change and air pollution.
openalex: W4213141683
Keywords: _z:class:countries; openalex:import; openalex:yes

Climate change education for children with disabilities toward sustainable develoment - Thi, Nga hoang (Tạp chí Khoa học Giáo dục, 2021)
The article presents the interrelationship between climate change and sustainable development, thereby showing the importance of climate change education for children including children with disabilities to the sustainable development of each country in particular and globally. At the same time, through studying the orientation of climate change education for children in general and the characteristics, abilities and special needs of children with disabilities, the article proposes basic adjustment orientations in climate change education for children with disabilities.
openalex: W4212786489
Keywords: _z:class:countries; openalex:import; openalex:yes

Climate Change and Teacher’s Performance in Secondary School in Benue State Nigeria - Ortsa, Mhenmbee Gabriel; Ndidiamaka, Akwam Jane (International Journal of Educational Management and Innovation, 2021)
The study investigated climate change and Teachers performance in secondary schools in Benue State, Nigeria. Two research questions and two hypotheses guided the study. Survey research design was adopted for the study. The population compromised 5,225 teachers from 512 secondary schools. A total of 528 (10%) teachers from 51 (10%) secondary schools was sampled using proportionate stratified sampling technique: A 10-items self structured questionnaire titled “climate change and teachers performance questionnaire (CCTPQ) was used for data collection. The data were analyzed using mean and standard deviation to answer the research questions while chi-square (x2) test of goodness of fit was used to test the hypotheses at 0.05 level of significance. The finding of the study revealed that rainfall has a significant impact on teachers’ performance in secondary school in Benue State, Nigeria. The study also found that excessive heat has a significant impact on teachers’ performance in secondary schools. it was concluded that climate change significantly impact on teachers performances in secondary school in Benue State, Nigeria. Based on the findings, it was recommended among others that secondary, principals should provide rain-cut to teacher during raining season to enable them perform effectively and the government should provide Air-conditions or sling fans during excessive heat in the classrooms for efficient teahers performance.
openalex:W3203806973 mag:3203806973 KerkoCite.ItemAlsoKnownAs: 2129771:7WU9NW6V 2129771:7WU9NW6V 2129771:7WU9NW6V 2129771:7WU9NW6V 10.12928/ijemi.v2i3.4106 5072953:J8GQMNQP
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; evidence_review_2; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T12013 Measurement and Evaluation of Sustainable Development; oa:topic:T14228 Multidisciplinary Research in Science and Society; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Integrating Climate Change Adaptation Strategies into the Secondary School English Language Curriculum in Nigeria for Sustainable Development - Egbe, Cajetan Ikechukwu; Nnamani, Amaka Obiageli; Uzoegwu, Patricia N.; Ukoha, Evelyn (2021)
The paper sought the opinions of English language teachers on the integration of climate change adaptation strategies into the secondary school English language curriculum in Nigeria for sustainable development. Three research questions guided the study. The design of the study was the survey research design. The study was carried out in Nsukka Education Zone of Enugu State with 137 English language teachers constituting the sample for the study. The Climate Change Adaptation Questionnaire was developed and validated. The data got were analyzed using means and standard deviation to answer the research questions. The results revealed that respondents agreed that climate change themes such as meaning, causes, vulnerability and impact as well as climate change adaptation strategies should be integrated into the secondary school English language curriculum. They also agreed that debates, stories, drama and speeches are some of the strategies through which climate change adaptation can be integrated into the English language curriculum. They were also of the opinion that integration of climate change adaptation strategies into the English language curriculum would require the training and retraining of teachers and production of relevant textbooks. On the basis of the findings it was recommended that the English language curriculum should be expanded to include climate change themes, while workshops should be organized at the school, community, state and federal levels to sensitize all stakeholders, including teachers, students and parents on the reality of climate change and appropriate adaptation strategies.
openalex:W3200935789 mag:3200935789 KerkoCite.ItemAlsoKnownAs: 5072953:4EAZNMDX
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change adaptation; oa:keyword:climate change adaptation strategies; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

University students’ perceptions of climate change: the case study of the University of the South Pacific-Fiji Islands - Prasad, Ravinesh Rohit; Mkumbachi, Ramadhani Lausi (International Journal of Climate Change Strategies and Management, 2021)
Purpose Higher education plays a vital role in educating citizens about climate change and promoting pro-environment behavior. Based on this statement, this study aims to analyze and evaluate students’ perception of climate change at the University of the South Pacific in Fiji. The study aims to understand the main ideas and concepts of climate change by analyzing information habits and individual opinions on the causes of climate change as perceived by the students of two student organizations aimed at environmental protection. Design/methodology/approach A qualitative approach was used to gather data on students’ perceptions and information habits toward climate change. The data were collected through a questionnaire to characterize students from the socio-demography and their perceptions, information habits and knowledge relating to climate change. This paper uses the case study method to examine students’ climate change perceptions at two different student organizations at the same university. The research study involved a focus group technique. Two focus groups at the University of the South Pacific were administered. The focus groups’ selection in this study took into account the aims and objectives of the students’ organization toward climate change awareness, adaptation, mitigation and environment protection. Findings The focus groups participants believe that climate change is a serious problem in the South Pacific region. Results suggest significant differences in climate change perception at the two students’ organizations chosen for this study. Students at the Econesian society nicknamed climate change as a nuclear weapon for the South Pacific responsible for changes in the habitat, coral bleaching, lifestyle changes, mother of all other environmental problems and the introduction of invasive species into Fiji. Students at Wantok Moana-related climate change to drastic weather changes, lack of fish feed and additional toxins in the sea. The results also showed that students at the Econesian society have a better understanding of climate change than the students of Wantok Moana. Practical implications This paper provides an insight into how students of Small Islands Developing States view climate change and the factors affecting their opinions. It also shows how climate change perception varies within the same university. This implies the need to integrate climate change into the higher education curriculum and more research on this topic. Originality/value This paper is the first to compare and contrast university students’ climate change perception in Fiji. The results make an essential contribution to the extant climate change literature by identifying and categorizing climate change perception and the factors that shape students’ perception of climate change from the university students’ perspective in Fiji.
openalex: W3197893784 mag: 3197893784
Keywords: C:Fiji; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; oa:topic:T12503 Social Acceptance of Renewable Energy Innovation; openalex:import; openalex:yes

Integrating Total Disability Management in a Climate of Change: A Case Study - EdD, Jesko; Mary, E (2021)
Integrated disability management (IDM) is a cost-containment strategy increasingly being employed by human resources and risk management departments to address occupational and non-occupational illness and injury in a consistent manner. The goal is to both reduce on-the-job injury and minimize the loss of work time due to injury or illness. Although a large number of organizations have embraced the IDM concept, implementing IDM often is difficult because of the complex array of contracts, policies, procedures, corporate cultures and structures. Although extensive research has examined leaders' influence on change in various types of businesses, to date, research has not specifically explored major change strategies utilized by leaders to help organizations adapt their programs in ways that facilitate IDM implementation. This study began to explore this topic. It was a qualitative case study of one organization's efforts to implement IDM. The study employed observations and document reviews, along with interviews with a variety of stakeholders, to investigate the IDM change process, in general, and leaders' actions, in particular. The research questions of the study were: (a) Does evidence support the existence of an IDM program in this site? (b) If so, what did leaders do to contribute to implementing IDM? The study utilized two conceptual frameworks. One framework, developed from the IDM literature, consisted of four indicators signaling IDM program achievement (e.g., common reporting, injury prevention/management, a clear return-to-work policy and employing data management systems). The second framework, taken from the change literature, articulated eight indicators of leader behavior associated with successful change initiatives. These indicators were: instilling urgency, utilizing teamwork, creating/communicating vision, empowering subordinates, insuring short-term wins, consolidating gains, and transforming organizational culture. The findings of the study reveal that the site exhibited all four of the characteristics of IDM. Injury prevention strategies, however, were incorporated into the program design only after a change in risk management leadership occurred; significant cost containment also did not occur until this change occurred. The evidence also reveals that program leaders employed most of the strategies associated with successful change initiatives, though there was limited evidence to support claims about fundamental cultural change.
openalex: W3195235367 mag: 3195235367
Keywords: _z:class:countries; openalex:import; openalex:yes

Climate Change and Higher Education in Pakistan - Malik, Abdul; Ghafur, Tiyba; Majeed, Azra Abdul; Arshad, Arooj; Khatoon, Majida; Khan, Wajahat (Turkish Online Journal of Qualitative Inquiry, 2021)
This study was aimed at climate change and higher education in Pakistan. To know climate change and higher education. Educational sector to tackle climate change. Core subject values of climate change. Is it for knowledge enrichment or information acquisition climate change and higher education? This study was based on qualitative research methods. Purposive sampling techniques were used in this study. Most teachers were described the, for more than a decade technology has altered the whole education system. We concluded by this research that a few people are aware of the increasing issues of the environment and think about climate change's impact on the community.
openalex: W3198655396 mag: 3198655396
Keywords: C:Pakistan; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; openalex:import; openalex:yes; ⛔ No DOI found

Integrating Climate Change into the Pre-Vocational Agriculture Curriculum for Sustainable Food Security: Views from Teachers: Inspectorate and Curriculum Designers in Eswatini - Mathenjwa, Mpendulo; Asogwa, Vincent C.; Gule, Zanele M. (2021)
Increasing impacts of Climate Change in Eswatini compelled Government to inform her citizens about its causes, impacts and mitigating measures. Such changes in climate affects mainly farmers and threatens sustainable future food security and the comfort of the younger generation. Hence, this study sought to explore how climate change can be integrated into Pre-Vocational Agriculture Curriculum in secondary schools in Eswatini. Five research questions were answered through a mixed method research design. The population was N=22 and 2 instruments were used and validated by experts. Internal consistency of questionnaire was determined using Cronbach Alpha co-efficient formula, which yielded 0.76. The findings revealed that the major objectives of Pre-Vocational Agriculture curriculum were to enable students acquire and apply basic knowledge and principles of climate change mitigation strategies and to provide students with knowledge on the causes of climate change. The main content of climate change are human activities that facilitate climate change, impact of climate change and meaning of both climate change and global warming. The problem-solving method and field trip were the leading instructional methods. Finally, the objective-type questions and assignments formed primary evaluation techniques of climate change for integration into the curriculum. Recommendations were that the Ministry of Education and Training should integrate the identified objectives and content areas into Pre-Vocational Agriculture curriculum in secondary schools; Schools Agriculture Inspectorate should also organise workshops for Pre-Vocational Agriculture teachers to improve their knowledge on climate change for effective teaching and evaluation of concepts in secondary schools.
openalex:W3199469450 mag:3199469450 KerkoCite.ItemAlsoKnownAs: 5072953:NJ5V9J6P
Keywords: C:eSwatini; _z:class:countries; _z:class:themes; oa:keyword:sustainable food security; oa:sdg:2 Zero hunger; oa:topic:T10367 Agricultural Innovation and Livelihood Diversification; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T12904 Agricultural Education and School Gardening Research; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Integrating Climate Change into the Pre-Vocational Agriculture Curriculum for Sustainable Food Security: Views from Teachers: Inspectorate and Curriculum Designers in Eswatini - Mathenjwa, Mpendulo; Asogwa, Vincent C.; Gule, Zanele M. (2021)
Increasing impacts of Climate Change in Eswatini compelled Government to inform her citizens about its causes, impacts and mitigating measures. Such changes in climate affects mainly farmers and threatens sustainable future food security and the comfort of the younger generation. Hence, this study sought to explore how climate change can be integrated into Pre-Vocational Agriculture Curriculum in secondary schools in Eswatini. Five research questions were answered through a mixed method research design. The population was N=22 and 2 instruments were used and validated by experts. Internal consistency of questionnaire was determined using Cronbach Alpha co-efficient formula, which yielded 0.76. The findings revealed that the major objectives of Pre-Vocational Agriculture curriculum were to enable students acquire and apply basic knowledge and principles of climate change mitigation strategies and to provide students with knowledge on the causes of climate change. The main content of climate change are human activities that facilitate climate change, impact of climate change and meaning of both climate change and global warming. The problem-solving method and field trip were the leading instructional methods. Finally, the objective-type questions and assignments formed primary evaluation techniques of climate change for integration into the curriculum. Recommendations were that the Ministry of Education and Training should integrate the identified objectives and content areas into Pre-Vocational Agriculture curriculum in secondary schools; Schools Agriculture Inspectorate should also organise workshops for Pre-Vocational Agriculture teachers to improve their knowledge on climate change for effective teaching and evaluation of concepts in secondary schools.
openalex:W3199469450 mag:3199469450 KerkoCite.ItemAlsoKnownAs: 5072953:NJ5V9J6P
Keywords: _z:class:countries; _z:class:themes; oa:keyword:sustainable food security; oa:sdg:2 Zero hunger; oa:topic:T10367 Agricultural Innovation and Livelihood Diversification; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T12904 Agricultural Education and School Gardening Research; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Health impact assessment and climate change: A scoping review - Ammann, Priska; Dietler, Dominik; Winkler, Mirko S. (The Journal of Climate Change and Health, 2021)
Climate change has various adverse impacts on public health, ranging from heat-related illness to an increased risk of undernutrition in low-income countries. Health impact assessment (HIA) has been advocated as a valuable tool to systematically identify and quantify the effects of climate change on public health and to inform and evaluate the impact of disease-specific adaptation measures as well as health co-benefits of mitigation measures. We conducted a scoping review to map out peer-reviewed literature on HIA in the context of climate change. Web of Science, Scopus and PubMed were searched without language or time restriction. Publications were included in the full text screening that presented or discussed the application of HIA for investigating health impacts of climate change, or associated adaptation and mitigation measures. In total, 76 peer-reviewed publications from 26 countries were included and characterized. There was a paucity of studies on HIA in the context of climate change from low- and middle-income countries. The most investigated climate change effects were related to temperature and air-pollution. Consequently, associated health impacts, such as respiratory or cardiovascular morbidity and mortality, were examined most frequently. Research-driven HIAs with a quantitative methodological approach were the predominant choice to assess health impacts of climate change. Only one in five publications applied a classical step-by-step HIA approach. While quantitative assessment of health impacts associated with climate change seems to be a well established field of research, the few publications applying a step-by-step HIA approach to systematically anticipate potential health impacts of climate change in a given context point at a missed opportunity for strengthening intersectoral collaboration to maximize health (co-) benefits of climate mitigation and adaptation measures. To promote the use of step-by-step HIA in regions that are most affected by climate change, HIA teaching and training efforts are urgently needed.
openalex: W3197500705 mag: 3197500705
Keywords: evidence_review; openalex:citedBy; openalex:import; selected_for:effects of climate ch...on learning...LMICs 2024; tagged

Promoting climate change issues in medical education: Lessons from a student-driven advocacy project in a Canadian Medical school - Hansen, Micah; Rohn, Stephanie; Moglan, Elisabeta; Sutton, Wesley; Olagunju, Andrew T (The Journal of Climate Change and Health, 2021)
Health advocacy is an essential competency prescribed by many professional medical bodies tasked with fostering the development of medical trainees into well-rounded physicians. With increasing recognition of the ramifications of the negative impacts of climate change on population health, mitigation intervention is gaining traction as an important area in public health and physician's advocacy work. However, several lines of evidence show that Canadian medical training provides limited curricular activities to understand the impacts of climate change on health. This report highlights an advocacy effort by a group of medical students at McMaster University, Canada to promote better awareness and formal educational activities on climate change and health among medical learners. The project involves educational activities, didactic lectures, and an engagement with the medical school administration to promote curricular activities and resources on climate change and health. The lessons from this advocacy work include the need for better integration of climate change issues and health education into medical training, celebrating climate advocacy work, and creating a formalized portfolio within medical school administration to support climate change and health issues.
openalex: W3174537593 mag: 3174537593
Keywords: C:Canada; C:Mali; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T11244 Impact of Climate Change on Human Health; oa:topic:T12947 Salutogenesis and Sense of Coherence in Health; oa:topic:T13555 Strategies to Reduce Low-Value Health Care Services; openalex:import; openalex:yes

Disability-adjusted life years due to chronic and hidden hunger under food system evolution with climate change and adaptation to 2050 - Sulser, Timothy B.; Beach, Robert; Wiebe, Keith; Dunston, Shahnila; Fukagawa, Naomi K. (The American Journal of Clinical Nutrition, 2021)
Climate change presents an increasing challenge for food-nutrition security. Nutrition metrics calculated from quantitative food system projections can help focus policy actions.To estimate future chronic and hidden hunger disability-adjusted life years (DALYs)-due to protein-energy undernutrition and micronutrient deficiencies, respectively-using food systems projections to evaluate the potential impact of climate change and agricultural sector investment for adaptation.We use a novel combination of a chronic and hidden hunger DALY estimation procedure and food system projections from quantitative foresight modeling to assess DALYs under alternative agricultural sector scenarios to midcentury.Total chronic and hidden hunger DALYs are projected to increase globally out to 2050-by over 30 million compared with 2010-even without climate change. Climate change increases total DALY change between 2010 and 2050 by nearly 10% compared with no climate change. Agricultural sector investments show promise for offsetting these impacts. With investments, DALY incidence due to chronic and hidden hunger is projected to decrease globally in 2050 by 0.24 and 0.56 per 1000 capita, respectively. Total global DALYs will still rise because projected population growth will outpace the rate reduction, especially in Africa south of the Sahara. However, projections also show important regional reductions in total DALYs due to chronic (13.9 million in South Asia, 4.3 million in East Asia and the Pacific) and hidden hunger (7.5 million in East Asia and the Pacific) with investments.Food system projections to 2050 show a decreasing DALY incidence from both chronic and hidden hunger. Population growth is projected to outpace these improvements and lead to increasing total chronic and hidden hunger DALYs globally, concentrated in Africa south of the Sahara. Climate change increases per-capita chronic and hidden hunger DALY incidence compared with no climate change. Agricultural sector investments show the potential to offset the climate impact on DALYs.
openalex: W3162922423 mag: 3162922423
Keywords: _z:class:countries; openalex:import; openalex:yes

The Place of Climate Change in the New Senior Secondary School Curriculum for Sustainable Development in Nigeria - Evey, Cyril K. (2021)
Climate change has become very topical because of the crisis it has caused in every part of the world. Natural disasters are fast becoming global phenomena. There are now such familiar expressions as hurricane Katrina, sunnami, and others which past generations did not know of. These words simply emphasize the dimensions wind, flood, and rains have taken in recent times. In Nigeria particularly, flooding is taking an embarrassing dimension. It now sacks communities and destroys lives and property. Farms are being washed off daily and houses are being pulled down by wind in various areas of the country. The concept of secondary school education, reasons for climate change in the senior secondary school curriculum and sustainable development are reflected. Some suggestions are reflected that people should develop habit of being environmentally friendly about the way they live to manage the climate change pandemic.
openalex:W3187450839 mag:3187450839 KerkoCite.ItemAlsoKnownAs: 5072953:T286IQVJ
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:sustainable development; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

How do teachers’ perceptions of climate change vary in terms of importance, causes, impacts and mitigation? A comparative study in Bangladesh - Chowdhury, Mohammed Thanvir Ahmed; Ahmed, Khandaker Jafor; Ahmed, Mahfuzuddin; Haq, Shah Md Atiqul (SN Social Sciences, 2021)
Since climate change education is an integral element in the increasingly urgent global approach to solving the problem of climate change, understanding perceptions of climate change among teachers in different academic institutions could play a significant role in how and to what extent institutions address the need to educate learners on this subject, specifically, and participate in other climate change mitigation strategies, in general. This study, therefore, examines teachers' perceptions of climate change regarding its significance, causes, consequences, and mitigation, through analysis of a self-administered structured questionnaire completed by 95 teachers from public and private educational institutions in the city of Sylhet in Bangladesh. Results from descriptive and inferential statistical analysis show that public and private school teachers have an understanding of climate change regarding its significance, causes, consequences, and mitigation. The results also reveal that the sociodemographic characteristics of teachers, as well as academic-related factors, influence their perceptions of climate change. This research concludes that teachers in public institutions have a greater awareness and understanding of climate change than those working in private schools. The research findings have broader implications for further research and policy recommendations and, in particular, draw the attention of the Departments of Education and Disaster Management in Bangladesh or in countries with similar contexts to introduce environmental and disaster education and training opportunities for teachers.
openalex: W3185025178 mag: 3185025178
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; oa:topic:T11835 Sustainability Education in Higher Education Institutions; openalex:import; openalex:yes

How do teachers’ perceptions of climate change vary in terms of importance, causes, impacts and mitigation? A comparative study in Bangladesh - Chowdhury, Mohammed Thanvir Ahmed; Ahmed, Khandaker Jafor; Ahmed, Mahfuzuddin; Haq, Shah Md Atiqul (SN Social Sciences, 2021)
Since climate change education is an integral element in the increasingly urgent global approach to solving the problem of climate change, understanding perceptions of climate change among teachers in different academic institutions could play a significant role in how and to what extent institutions address the need to educate learners on this subject, specifically, and participate in other climate change mitigation strategies, in general. This study, therefore, examines teachers' perceptions of climate change regarding its significance, causes, consequences, and mitigation, through analysis of a self-administered structured questionnaire completed by 95 teachers from public and private educational institutions in the city of Sylhet in Bangladesh. Results from descriptive and inferential statistical analysis show that public and private school teachers have an understanding of climate change regarding its significance, causes, consequences, and mitigation. The results also reveal that the sociodemographic characteristics of teachers, as well as academic-related factors, influence their perceptions of climate change. This research concludes that teachers in public institutions have a greater awareness and understanding of climate change than those working in private schools. The research findings have broader implications for further research and policy recommendations and, in particular, draw the attention of the Departments of Education and Disaster Management in Bangladesh or in countries with similar contexts to introduce environmental and disaster education and training opportunities for teachers.
openalex: W3185025178 mag: 3185025178
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; oa:topic:T11835 Sustainability Education in Higher Education Institutions; openalex:import; openalex:yes

Assessment of the Perception and Awareness of Climate Change and the Influence of Information Amongst Tertiary Education Students in North-East Nigeria - Malgwi, Philip Gana; Joshua, Williams K. (2021)
Climate change is one of the greatest environmental problems confronting the 21st century. It has impacted several systems of the economy in areas such as food availability and supply, access to basic education, natural energy, healthcare, environment, security and many other socio-economic and political arms of governance. Accurate information and awareness especially among the youths are critical to mitigating the impact of climate change. This paper assesses the perception of climate change amongst students studying in higher institutions of learning in Northern Nigeria. It further investigates the available and accessible medium of information relating to climate change in universities, polytechnics and colleges of education. The results were analysed descriptively and showed that most of the students are aware of the changes in weather patterns, with flood and heatwaves contributing the most changes affecting the environment at 20.5% and 46.6% respectively. In addition, the results showed that although information relating to climate change is readily available, it is however not easily accessible due to the cost of the internet bundle (39.75%) and the cost of journal and textbook subscriptions (26.25%). Therefore, information must be made accessible especially in tertiary institutions to raise an informed set of graduates who will tackle societal issues proactively and sustainably.
openalex:W3211651715 mag:3211651715 KerkoCite.ItemAlsoKnownAs: 5072953:5K536WQA
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:topic:T14224 Global Impact of Gas Flaring; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Climate change education in public health and medical curricula in Australian and New Zealand Universities: a mixed methods study of barriers and areas for further action - Lal, Avantika; Walsh, Erin; Weatherell, A; Slimings, Claudia (medRxiv (Cold Spring Harbor Laboratory), 2021)
Abstract Background The World Health Organization deemed climate change and air pollution as the top threat to global health in 2019. The importance of climate for health is recognised by healthcare professionals, who need to be equipped to deliver environmentally sustainable healthcare and promote planetary health. There is some evidence that climate change and health is not strongly embedded in accredited master-level public health training programs and medical programs globally, however, the immersion of climate-health in Australian and New Zealand programs is unclear. Objectives To explore the extent to which climate-health education is currently embedded into public health and medical curricula in Australia and New Zealand. Methods Educators identified by their coordination, convenorship, or delivery into programs of public health and medicine at universities in Australia and New Zealand were invited to participate in a cross-sectional, exploratory mixed methods study. Participants completed an online quantitative survey and qualitative interviews regarding their experience in program and course delivery, and the prominence of climate-health content within program and course delivery. Quantitative surveys were analysed using descriptive statistics and qualitative interview content was analysed via a modified ground theory approach. Results The response rate of the quantitative survey was 43.7% (21/48). Ten survey respondents also completed qualitative interviews. Quantitative results showed that epidemiologists were the most common experts involved in design and delivery of this curriculum, with a reliance on guest lecturers to provide updated content. Qualitative interviews highlighted the ad-hoc role of Indigenous-led content in this field, the barriers of time and resources to develop a coherent curriculum and the important role of high-level champions to drive the inclusion of climate change and planetary health. Conclusion There is an urgent need to strengthen current support available for pedagogical leadership in the area of climate and broader environmental change teaching at universities.
openalex: W3169456940 mag: 3169456940
Keywords: C:Australia; C:New Zealand; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T11244 Impact of Climate Change on Human Health; oa:topic:T12041 Public Health and Health Promotion Framework; oa:topic:T12947 Salutogenesis and Sense of Coherence in Health; openalex:import; openalex:yes

Climate change education in public health and medical curricula in Australian and New Zealand Universities: a mixed methods study of barriers and areas for further action - Lal, Avantika; Walsh, Erin; Weatherell, A; Slimings, Claudia (medRxiv (Cold Spring Harbor Laboratory), 2021)
Abstract Background The World Health Organization deemed climate change and air pollution as the top threat to global health in 2019. The importance of climate for health is recognised by healthcare professionals, who need to be equipped to deliver environmentally sustainable healthcare and promote planetary health. There is some evidence that climate change and health is not strongly embedded in accredited master-level public health training programs and medical programs globally, however, the immersion of climate-health in Australian and New Zealand programs is unclear. Objectives To explore the extent to which climate-health education is currently embedded into public health and medical curricula in Australia and New Zealand. Methods Educators identified by their coordination, convenorship, or delivery into programs of public health and medicine at universities in Australia and New Zealand were invited to participate in a cross-sectional, exploratory mixed methods study. Participants completed an online quantitative survey and qualitative interviews regarding their experience in program and course delivery, and the prominence of climate-health content within program and course delivery. Quantitative surveys were analysed using descriptive statistics and qualitative interview content was analysed via a modified ground theory approach. Results The response rate of the quantitative survey was 43.7% (21/48). Ten survey respondents also completed qualitative interviews. Quantitative results showed that epidemiologists were the most common experts involved in design and delivery of this curriculum, with a reliance on guest lecturers to provide updated content. Qualitative interviews highlighted the ad-hoc role of Indigenous-led content in this field, the barriers of time and resources to develop a coherent curriculum and the important role of high-level champions to drive the inclusion of climate change and planetary health. Conclusion There is an urgent need to strengthen current support available for pedagogical leadership in the area of climate and broader environmental change teaching at universities.
openalex: W3169456940 mag: 3169456940
Keywords: C:Australia; C:New Zealand; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T11244 Impact of Climate Change on Human Health; oa:topic:T12041 Public Health and Health Promotion Framework; oa:topic:T12947 Salutogenesis and Sense of Coherence in Health; openalex:import; openalex:yes

An adaptive thermal comfort model for naturally ventilated classrooms of technical institutions in Madurai - Subhashini, S.; Kesavaperumal, Thirumaran; Noguchi, Masa (Open House International, 2021)
Purpose Occupants dwelling in hot climatic regions of India for a longer term are tolerable to high temperature levels than predicted by American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE) standards. The purpose of this study is to evaluate the thermal sensations (TS) and neutral temperature of the occupants in naturally ventilated (NV) and air-conditioned (AC) classrooms of two technical institutions located in the same premises in the suburbs of Madurai. The main focus of this study is to understand the occupants’ behaviour in response to the thermal conditions of the educational buildings particularly in the warm and humid climatic zone of Madurai. Design/methodology/approach This research collected data through field studies. The data included 383 survey questionnaires from NV classrooms and 285 from AC classrooms, as well as on-site measurements of interior and exterior weather conditions. The TS results show that the students preferred well-designed NV classrooms than AC classrooms. A new adaptive comfort equation derived from this study can be applied to NV classrooms in warm and humid climates where mean outdoor temperature exceeds 40°C. Findings The neutral temperature derived for NV classrooms in Madurai ranged from 29°C to 34°C. Thus, the occupants in the NV classrooms of the higher learning educational institutions in the warm and humid climatic region of Madurai can adapt well to higher indoor temperature levels than predicted by ASHRAE comfort levels with minimum adjustments. Research limitations/implications The study was limited to only occupants in two premier higher learning technical educational institutions located in Madurai region within 5–10 km within the city limits to understand the implications of microclimate with respect to the urban context. Thus, further research is required to examine the tendency under local conditions in other regions beyond those applied to this study. Social implications The findings of this study showed that occupants in higher learning educational intuitions in Madurai prefer NV classrooms than AC classrooms. Therefore, with rising demands of energy use for mechanical ventilation and the associated high cost for running AC buildings, architects should prioritize the design of energy efficient buildings through the optimal use of passive design strategies for ventilation and thermal comfort. This study gives a base data for architects to understand the adaptive limitations of occupants and design NV buildings that can promote natural ventilation and provide better thermal environments that can help increase the productivity of students. Originality/value This paper was an attempt to develop the adaptive comfort model for NV classrooms in Madurai regions. There has been no attempt to identify the adaptive comfort levels of occupants in higher learning technical educational institutions located in warm and humid climatic region of India.
openalex:W3171886172 mag:3171886172 KerkoCite.ItemAlsoKnownAs: 10.1108/ohi-03-2021-0075 5072953:KBDT86P2
Keywords: C:India; _z:class:countries; _z:class:themes; oa:keyword:adaptive thermal comfort model; oa:keyword:thermal comfort; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T10990 Airborne Transmission of Respiratory Viruses

Climate Change and Human Security in Sub-Saharan Africa - Chilunjika, A.; Gumede, N. (African Renaissance, 2021)
Climate change has been referred to as a security threat that has weakened the ability of states to deal with severe weather patterns, droughts, land degradation, flooding, and other climate-related changes. Climate change has significantly affected poor communities in developing countries, particularly those in sub-Saharan Africa. The proneness of these sub-Saharan African communities to the scourge of climate change is exacerbated by low precipitation, high temperatures, and high poverty levels. If climate change issues are not addressed at the local level, sub-Saharan Africa is likely to become the epicentre of a global food crisis. This study focuses on the effects of climate change on human security in sub-Saharan Africa. The study extensively relied on secondary written sources such as reports, conference papers, books, journal articles, government publications, magazines, and bulletins to gather data. Data was analysed using thematic and content analysis. The study established that climate change affects human security through extreme weather elements, injuries and deaths due to flooding, water scarcity, and climate-induced migration. It also affects human health, food production and development, and food security, as well as triggering conflict. It is therefore imperative that strategies be adopted to address the adverse effects of climate change on human security in sub-Saharan Africa.
KerkoCite.ItemAlsoKnownAs: 5072953:9YPP8XSW 5072953:J3C32S2V

Cooling buildings by nearly 5ºC possible thanks to new whiter-than-white paint - Parnell, Andrew (The Conversation, 2021)
New barium sulphate-based paint could help reduce effects of climate change.
KerkoCite.ItemAlsoKnownAs: 2129771:FJSAYLEL 4874017:S2MB2ZMK
Keywords: evidence_review

Gendered Perceptions of Climate Change and Climate Action - A Comparative Study among Bangladeshi and Norwegian University Students Studying and Living in Norway - Karim, Tasnina (2021)
openalex: W3182528404 mag: 3182528404
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:keyword:climate action; oa:keyword:climate change; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11244 Impact of Climate Change on Human Health; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:yes

Gendered Perceptions of Climate Change and Climate Action - A Comparative Study among Bangladeshi and Norwegian University Students Studying and Living in Norway - Karim, Tasnina (2021)
openalex: W3182528404 mag: 3182528404
Keywords: C:Bangladesh; C:Norway; _z:class:countries; _z:class:themes; oa:keyword:climate action; oa:keyword:climate change; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11244 Impact of Climate Change on Human Health; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:yes

Gamification for climate change engagement: review of corpus and future agenda - Fernández Galeote, Daniel; Rajanen, Mikko; Rajanen, Dorina; Legaki, Nikoletta-Zampeta; Langley, David J; Hamari, Juho (Environmental Research Letters, 2021)
Both bottom-up and top-down initiatives are essential for addressing climate change effectively. These include initiatives aiming to achieve widespread behavioral change towards reduction of greenhouse gas emissions as well as pursuing education regarding adaptation measures. While awareness of the issue of climate change is now pervasive, and actions are being taken at all levels of society, there is still much to do if international goals are to be met. Games and gamification offer one approach to foster both behavioral change and education. In this paper, we investigate the state-of-the-art of game-based climate change engagement through a systematic literature review of 64 research outputs comprising 56 different gamified approaches. Our analysis of the literature reveals a trend of promising findings in this nascent and growing area of research, suggesting the potential to impact multiple engagement dimensions simultaneously, as well as create an engaging gameful experience. Overall, the corpus appears to offer a fruitful balance in foci between climate science, mitigation, and adaptation, as well as a variety of formats in game-based approaches (i.e. digital, analog, and hybrid). However, shortcomings were also observed, such as geographic and demographic imbalances and the short duration of interventions. The reviewed studies yield a large number of results indicating climate change engagement through gamification, especially in the form of cognitive engagement, affect towards climate change-related topics, and in-game behavioral engagement with others. Nevertheless, heterogeneity in terms of contexts, designs, outcomes, and methods, as well as limited rigor in research designs and reporting, hinders drawing overall conclusions. Based on our review, we provide guidelines regarding contexts, interventions, results, and research quality and internal validity for advancing the space of game-based interventions for climate change engagement.
KerkoCite.ItemAlsoKnownAs: 10.1088/1748-9326/abec05 2129771:CRHY4NSC 5072953:4IPSS56P openalex: W3134086441
Keywords: _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change engagement; oa:sdg:13 Climate action; oa:topic:T10731 Gamification in Education and Learning; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T12214 The Role of Narrative in Persuasive Communication; openalex:n:1; openalex:yes

Increased climate variability and sedentarization in Tanzania: Health and nutrition implications on pastoral communities of Mvomero and Handeni districts, Tanzania - Ripkey, Carrie E; Little, Peter D.; Domínguez-Salas, Paula; Kinabo, Joyce; Mwanri, Akwilina Wendelin; Girard, Amy Webb (Global Food Security, 2021)
African pastoralists are undergoing significant changes in livelihood strategies, from predominantly mobile pastoralism to agro-pastoralism in which both livestock raising and cultivation of crops are practiced, to agro-pastoralism combined with wage labor and petty trade. These changes often result in fixed settlements or a process known as sedentarization. Previous research indicates that sedentarization and increased climate variability are prominent forces shaping livelihood opportunities and constraints in East Africa, but the effects of these co-occurring processes have yet to be investigated. This paper develops theory, using qualitative data collected in Morogoro and Tanga Regions of Tanzania, explaining the relationships between climate variability, pastoral sedentarization, livelihood outcomes, and resulting nutritional status. We observed that the co-occurring processes of increased climate variability and sedentarization among pastoralists in these regions have dramatic impacts on communities’ economic prosperity, health status, and nutritional outcomes. Due to risks associated with climate and sedentarization, land tenure policies that allow continued practice of highly mobile livelihood strategies, namely, legal recognition of collective land rights, should be adopted.
openalex: W3134390762 mag: 3134390762
Keywords: _z:class:countries; openalex:cites; openalex:import

Poorly designed acoustics in schools affect learning efficiency and well-being - Souza, Eduardo (ArchDaily, 2021)
Acoustic discomfort can harm the process of knowledge acquisition, interfering with attention and worsening student-teacher communication.
KerkoCite.ItemAlsoKnownAs: 2129771:2F762SK3 2129771:2F762SK3 2129771:2F762SK3 2129771:2F762SK3 4874017:ZHT8VQ5S 5072953:RQAT9QZS
Keywords: _z:class:countries; _z:class:themes; evidence_review_2

Respiratory Performance of Humans Exposed to Moderate Levels of Carbon Dioxide - Mishra, Asit; Wargocki, Pawel; Tham, K. (Indoor Air, 2021)
In a business as usual scenario, atmospheric carbon dioxide concentration (CO2) could reach 950 parts per million (ppm) by 2100. Indoor CO2 concentrations will rise consequently, given its dependence on atmospheric CO2 levels. If buildings are ventilated following current standards in 2100, indoor CO2 concentration could be over 1300 ppm, depending on specific ventilation codes. Such exposure to CO2 could have physiological and psychological effects on building occupants. We conducted a randomized, within‐subject study, examining the physiological effects on the respiratory functions of 15 persons. We examined three exposures, each 150 min long, with CO2 of: 900 ppm (reference), 1450 ppm (decreased ventilation), and 1450 ppm (reference condition with added pure CO2). We measured respiratory parameters with capnometry and forced vital capacity (FVC) tests. End‐tidal CO2 and respiration rates did not significantly differ across the three exposures. Parameters measured using FVC decreased significantly from the start to the end of exposure only at the reduced ventilation condition (p < 0.04, large effect size). Hence, poor ventilation likely affects respiratory parameters. This effect is probably not caused by increased CO2 alone and rather by other pollutants—predominantly human bioeffluents in this work—whose concentrations increased as a result.

Progress in climate change adaptation research - Sietsma, Anne J.; Ford, James D.; Callaghan, Max; Minx, Jan C. (Environmental Research Letters, 2021)
Abstract The scientific literature on climate change adaptation has become too large to assess manually. Beyond standard scientometrics, questions about if and how the field is progressing thus remain largely unanswered. Here we provide a novel, inquisitive, computer-assisted evidence mapping methodology that combines expert interviews ( n = 26) and structural topic modelling to evaluate open-ended research questions on progress in the field. We apply this to 62 191 adaptation-relevant scientific publications (1988–2020), selected through supervised machine learning from a comprehensive climate change query. Comparing the literature to key benchmarks of mature adaptation research, our findings align with trends in the adaptation literature observed by most experts: the field is maturing, growing rapidly, and diversifying, with social science and implementation topics arising next to the still-dominant natural sciences and impacts-focused research. Formally assessing the representativeness of IPCC citations, we find evidence of a delay effect for fast-growing areas of research like adaptation strategies and governance. Similarly, we show significant topic biases by geographic location: especially disaster and development-related topics are often studied in Southern countries by authors from the North, while Northern countries dominate governance topics. Moreover, there is a general paucity of research in some highly vulnerable countries. Experts lastly signal a need for meaningful stakeholder involvement. Expanding on the methods presented here would aid the comprehensive and transparent monitoring of adaptation research. For the evidence synthesis community, our methodology provides an example of how to move beyond the descriptive towards the inquisitive and formally evaluating research questions.
openalex: W3156756966 mag: 3156756966 KerkoCite.ItemAlsoKnownAs: 5072953:3SHSBCF3 5072953:5NZEBIZN 5440726:R3KI822U
Keywords: _z:class:countries; openalex:cites; openalex:import; selected_for:effects of climate ch...on learning...LMICs 2024; tagged

Using recurrent neural networks for localized weather prediction with combined use of public airport data and on-site measurements - Han, Jung Min; Ang, Yu Qian; Malkawi, Ali; Samuelson, Holly W. (Building and Environment, 2021)
Weather data is a crucial input for myriad applications in the built environment, including building energy modeling and daylight analysis. Building science practitioners and researchers have been able to select from a variety of weather files, such as Weather Year for Energy Calculation 2 (WYEC2) and the Typical Meteorological Year (TMY). However, commonly used weather files are typically synthesized to represent trends over a relatively longer periods of time, and are often unable to accurately depict climatic conditions that result from local contexts, such as the heat island effect, wind flow, even local temperature and relative humidity. This results in discrepancies in building performance simulations. This study proposes a methodology using recurrent neural networks to generate synthetic localized weather data that are significantly more accurate and representative of local conditions than standard weather files. The predictions were validated against actual on-site measurements, and achieved a low mean square error of 2.96 and over 185% improvement in validation accuracy. Overall, the performance of selected models has shown over 100% improvements in test accuracy compared with standard weather files and weather station data at the nearest airport. The proposed methodology can be used to morph generic weather files to accurately represent localized conditions, or generate localized data for a longer time span with only a subset of data available/collected. This is useful for downstream built environment applications, especially building energy modeling, since representative weather data capturing trends of temperature and other variables will result in enhanced accuracies of the building energy models. The method can also be used in urban analysis pipelines to enhance resilience against climate change.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.buildenv.2021.107601 5072953:Y3I5DSHL openalex: W3120887079
Keywords: Building energy modeling; Climate change; Deep learning; Gated recurrent unit; Recurrent neural network; Weather file; _z:class:countries; _z:class:themes; oa:keyword:recurrent neural networks; oa:keyword:weather prediction; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:n:1; openalex:yes; selected_for:Predictive models for classroom conditions 2024

LED there be light: The impact of replacing lights at schools in South Africa - Booysen, M. J.; Samuels, J. A.; Grobbelaar, S. S. (Energy and Buildings, 2021)
South Africa’s private sector – under significant pressure to become energy efficient and employ sustainability principles – has long been implementing energy-saving mechanisms. Unfortunately, there seems to exist many misplaced incentives in South Africa’s public sector that prevent it from embracing energy-efficient technology. With the falling cost of LED lighting and the rising cost of electricity, however, conversions are increasingly cost-efficient. Effecting these changes are increasingly urgent given the national utility-imposed rolling blackouts and climate change concerns. The primary education sector is a particularly attractive test case, since money saved on utilities can be allocated to desperately needed value-adding services in schools. From a technical perspective, however, the cost-benefit of replacements and the range of options facing decision-makers could be overwhelming. To assess the impact of replacing fluorescent lights with LED lights at schools in South Africa, we propose a model that draws on smart metering data, a bench-test assessment of available LED lights and tariff rates. The model was validated with field tests at three schools and used to assess the impact at seven local schools. The results show that the setup cost differs substantially from the life-cycle cost, and that buying the cheapest lights could prove to be the costliest decision over the light’s life cycle. The results also show that lights contribute from 31% to 57% of electricity expenditure, and that monetary savings of 21% to 39% are achievable by replacing fluorescent tubes with the most efficient LED lighting option available.
KerkoCite.ItemAlsoKnownAs: 2129771:7395NDET 2129771:7395NDET 10.1016/j.enbuild.2021.110736 4874017:B6B6SWRQ 5072953:8Y9338LZ openalex: W3120223305
Keywords: C:South Africa; Efficiency improvement; Energy saving; Energy usage; LED lights; School electricity; School energy profiles; School lights; Smart meter; _z:class:countries; _z:class:themes; evidence_review_2; oa:keyword:lights; oa:topic:T10298 Influence of Built Environment on Active Travel; oa:topic:T11336 Indoor Air Pollution in Developing Countries; oa:topic:T11963 Impact of Nighttime Light Data on Various Fields; openalex:n:1; openalex:yes

Proposed Model of Neutral Temperature Equation for Adaptive Thermal Comfort in Student Flats Units in the Tropics - Samsuddin; Rahim, Ramli; Hamzah, Baharuddin; Mulyadi, Rosady (Civil engineering and architecture, 2021)
Thermal comfort of residential rental flats is one of the problems from the ventilation aspect considering that the planning of flats is based on natural ventilation. This article is intended to formulate an alternative to the neutral temperature equation from the equation proposed by Humphrey, Auliciem, de Dear, Nicol, and Roaf with day and night measurement times. Measurements were carried out for three weeks in a student rental apartment building, Hasanuddin University Faculty of Engineering in Bontomarannu, Gowa Regency, which has 5 floors with 104 rooms. Measurements were made with 2,577 respondents during the day, and 2,043 at night. During the day, with an operating temperature between 29.2℃ to 31.0℃, the neutral temperature (Tn) obtained from the PMV model is 27.6℃ (To). This figure is lower than the actual choice of the TSV scale and the TCV scale, which were 30.3℃ (To) and 29.7℃ (To), respectively. At night, with an operating temperature between 27.7℃ to 29.5℃, the neutral temperature (Tn) obtained from the PMV model is 26.2℃ (To). Meanwhile, the neutral temperature obtained from the respondents' actual choices (TSV and TCV) were 28.8℃ (To) and 28.2℃ (To), respectively. The neutral temperature equations presented in the Humphrey, Auliciem, de Dear, Nicol, and Roaf equations show a lower thermal coefficient than the corrected thermal coefficient and the elaboration of the equations carried out in this study, both from daytime measurements and from night measurements.
openalex:W3165232330 mag:3165232330 KerkoCite.ItemAlsoKnownAs: 10.13189/cea.2021.090220 5072953:IQHW2NIP
Keywords: _z:class:countries; _z:class:themes; oa:keyword:adaptive thermal comfort; oa:sdg:11 Sustainable cities and communities; oa:topic:T13520 Urban Design and Cultural Heritage Conservation

Informed-Decision Regarding Global Warming and Climate Change Among High School Students in the United Kingdom - Kurup, Premnadh M.; Levinson, Ralph; Li, Xia (Canadian Journal of Science, Mathematics and Technology Education, 2021)
Abstract Global warming and climate change are serious issues facing humanity at present and education needs to focus on including informed-decision in classroom practices. The conceptual framework used in this study has provided interconnections that influence beliefs and understandings in providing a knowledge base for making “informed-decision” among high school students. This study was conducted in three year 9 classes in two high schools in the UK and among 65 students. An inquiry intervention model was developed using the 5E instructional model (Engage, Explore, Explain, Elaborate, and Evaluate) to identify beliefs and understanding and to strengthen students’ knowledge base. This study used a design-based research setting and utilised a mixed methodology. The Wilcoxon signed-rank tests were computed to examine the pre-post-difference among questionnaire items, and structural equation modelling (SEM) was utilised to explore the relationship between belief, understanding, and intention. Data analysis of the intervention revealed that students developed a strong understanding of the causes and effects of global warming. There is evidence that students used that knowledge to “inform-decision” in relation to global warming and climate change. Promoting informed decision-making through science teaching can encourage responsible action in the future. The real gap identified in this study is that the regular school curriculum does not engage socio-scientific issues in the real world and has no opportunity to organise an inquiry-based instructional sequence for informed decision-making.
openalex: W3130706422 mag: 3130706422
Keywords: C:United Kingdom; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:global warming; oa:sdg:13 Climate action; oa:topic:T10072 Enhancing Science Education through Inquiry and Argumentation; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11715 Impact of Instructional Interventions on Critical Thinking Skills; openalex:import; openalex:yes

“It is not something that has been discussed”: Climate change in teacher education in Greenland and Canada - Demant-Poort, Lars; Berger, Paul D. (Journal of Geoscience Education, 2021)
We describe findings from an exploratory study on Greenlandic and Canadian preservice teachers’ (PSTs’) views on climate change teaching and teacher education programs. Greenland and Canada are experiencing more rapid warming than the global average. Climate resilience is thus of great importance and climate change needs to be taught to foster innovations and adaptation and to prepare young citizens to be engaged participants in policy debates about mitigation. Forty-five PSTs at the University of Greenland and Lakehead University answered a survey comprised mainly Likert Scale and open-ended questions. We found that PSTs need more knowledge about climate change, while, across disciplines, almost all would like to teach climate change and believe that preparing to do so should be a part of initial teacher education.
openalex: W3128848735 mag: 3128848735
Keywords: C:Canada; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:teacher education; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; oa:topic:T12503 Social Acceptance of Renewable Energy Innovation; openalex:import; openalex:yes

Methods and Trends for Water-Energy-Carbon Emissions Nexus Assessment - Wang, Xuechao; Klemeš, Jiří Jaromír; Varbanov, Petar Sabev (Chemical engineering transactions, 2021)
The Water-Energy-Carbon Emissions (WEC) nexus has been drawing increasing attention. However, very few studies, to date, were conducted to comprehensively review the assessment approaches, challenges and trends of future works for regional and sectoral CWC nexus. This paper aims to analyse and review the WEC nexus assessment methods, challenges of WEC network management and ways to go in the future. Eight different kinds of WEC nexus assessment methods are introduced, as well as their advantages and drawback. Five future work directions of WEC nexus assessment are proposed. This study provides a better understanding of the WEC nexus and more approaches to assess the WEC nexus.
openalex: W3126909309 mag: 3126909309
Keywords: _z:class:countries; openalex:import; openalex:related

Monitoring and moderating extreme indoor temperatures in low-income urban communities - Wilby, R L; Kasei, R; Gough, K V; Amankwaa, E F; Abarike, M; Anderson, N J; Codjoe, S N A; Griffiths, P; Kaba, C; Abdullah, K; Kayaga, S; Matthews, T; et al. (Environmental Research Letters, 2021)
Abstract Climate change presents significant threats to human health, especially for low-income urban communities in the Global South. Despite numerous studies of heat stress, surprisingly little is known about the temperatures actually encountered by people in their homes, or the benefits of affordable adaptations. This paper examines indoor air temperature measurements gathered from 47 living rooms within eight low-income communities of Accra and Tamale, Ghana. Using multiple temperature indices and a tiered analysis, we evaluate indoor temperature variations linked to roof type, ceiling insulation, presence of fans, and tree shade, for different housing types and locations. Our data reveal indoor temperatures in the range 22.4 °C to 45.9 °C for Accra, and 22.2 °C to 43.0 °C in Tamale. Using dummy regression analysis, we find that tree shade reduces the number of very hot days (>40 °C) and nights (>30 °C) by about 12 and 15 d per year, respectively. Building materials also strongly moderate indoor temperatures but in opposing ways: rooms with traditional mud walls and thatch roofs are on average 4.5 °C cooler than rooms in concrete block houses with uninsulated metal roofs during the day but are 1.5 °C warmer at night; rooms with ceiling insulation are on average 6.9 °C cooler in the day but 1.4 °C warmer at night. We conclude that sub-daily data are necessary for reporting extreme indoor temperatures, and that trade-offs between minimum and maximum temperatures require interventions to be assessed carefully before attempting to counter extreme heat inside homes.
openalex: W3120706877 KerkoCite.ItemAlsoKnownAs: 5072953:8X6VEF4H 5072953:HVBQDPYY 5072953:TNZ33ZBF
Keywords: C:Ghana; _z:class:countries; _z:class:themes; oa:keyword:extreme indoor temperatures; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11244 Impact of Climate Change on Human Health; openalex:n:1; openalex:yes

School renovations in rural Tanzania with C-re-aid - C-re-aid (Field Study of the World, 2021)
In 2019-2020 I managed two school renovations in Shimbwe village in Northern Tanzania while working for architectural NGO Cr-e-aid.
KerkoCite.ItemAlsoKnownAs: 2129771:55FLC488 4874017:9D7BFRPF
Keywords: evidence_review

Mapping global research on climate and health using machine learning (a systematic evidence map) - Berrang‐Ford, Lea; Sietsma, Anne J.; Callaghan, Max; Minx, Jan C.; Scheelbeek, Pauline; Haddaway, Neal R.; Haines, Andy; Belesova, Kristine; Dangour, Alan D. (Wellcome open research, 2021)
Climate change is already affecting health in populations around the world, threatening to undermine the past 50 years of global gains in public health. Health is not only affected by climate change via many causal pathways, but also by the emissions that drive climate change and their co-pollutants. Yet there has been relatively limited synthesis of key insights and trends at a global scale across fragmented disciplines. Compounding this, an exponentially increasing literature means that conventional evidence synthesis methods are no longer sufficient or feasible. Here, we outline a protocol using machine learning approaches to systematically synthesize global evidence on the relationship between climate change, climate variability, and weather (CCVW) and human health. We will use supervised machine learning to screen over 300,000 scientific articles, combining terms related to CCVW and human health. Our inclusion criteria comprise articles published between 2013 and 2020 that focus on empirical assessment of: CCVW impacts on human health or health-related outcomes or health systems; relate to the health impacts of mitigation strategies; or focus on adaptation strategies to the health impacts of climate change. We will use supervised machine learning (topic modeling) to categorize included articles as relevant to impacts, mitigation, and/or adaptation, and extract geographical location of studies. Unsupervised machine learning using topic modeling will be used to identify and map key topics in the literature on climate and health, with outputs including evidence heat maps, geographic maps, and narrative synthesis of trends in climate-health publishing. To our knowledge, this will represent the first comprehensive, semi-automated, systematic evidence synthesis of the scientific literature on climate and health.
openalex: W3123565732 mag: 3123565732 KerkoCite.ItemAlsoKnownAs: 5072953:GFL5SIHV 5072953:JM6Z48XW 5440726:CIWDU4DU
Keywords: openalex:cites; openalex:import; selected_for:effects of climate ch...on learning...LMICs 2024; tagged

Estimation of the Carbon Footprint, Its Contributory Factors, and Knowledge and Attitudes about Climate Change among Medical Students in Sri Lanka - Wijesinghe, P.S.; Mathurahan, S; Wijesundere, DS; Ranawaka, S; Arambepola, C; Chang, Tsangyao (Journal of environment pollution and human health, 2021)
The threat to human health from climate change through malnutrition, disease and extreme weather conditions is substantial. Instead of being advocates for a greener planet, doctors are known to possess a large carbon footprint (CFP). Whether a trend towards a higher CFP is initiated during the formative medical student years is not known. This study aimed to estimate the CFP among medical students and to assess their knowledge and attitudes towards climate change. A descriptive, cross-sectional study was conducted among 256 randomly selected medical students in Sri Lanka. The mean CFP of a medical student was 5.64 (SD=2.72) mtCO2/year. The highest contribution to the CFP was from lifestyle factors (68.97%) followed by travel (26.41%). The CFP increased with increasing household income (p=0.001). 82% of students knew the meaning of âgreenhouse effectâ, but only 33% knew the meaning of âcarbon footprintâ; 58.3% were aware of the adverse effects of climate change while only 42.3% could name 3 or more gases that contribute to it. About a third considered their CFP to be negligible. However, 86.3% elected to change their mode of transport to minimize their CFP. Over 90% considered issues of climate change the responsibility of the government while only 7% felt that it was the responsibility of the individual. The CFP of medical students was higher than the per capita national average while knowledge about it was inadequate. Educating medical students on climate change and emphasizing the importance of individual responsibility is likely to change behavior towards a greener lifestyle.
openalex: W3120741477 mag: 3120741477
Keywords: C:Sri Lanka; _z:class:countries; _z:class:themes; oa:keyword:carbon footprint; oa:keyword:climate change; oa:sdg:2 Zero hunger; oa:topic:T11244 Impact of Climate Change on Human Health; oa:topic:T11488 Perceptions and Communication of Climate Change; oa:topic:T11731 Global Surgery and Health Development; openalex:import; openalex:yes

Estimation of the Carbon Footprint, Its Contributory Factors, and Knowledge and Attitudes about Climate Change among Medical Students in Sri Lanka - Wijesinghe, P.S.; Mathurahan, S; Wijesundere, DS; Ranawaka, S; Arambepola, C; Chang, Tsangyao (Journal of environment pollution and human health, 2021)
The threat to human health from climate change through malnutrition, disease and extreme weather conditions is substantial. Instead of being advocates for a greener planet, doctors are known to possess a large carbon footprint (CFP). Whether a trend towards a higher CFP is initiated during the formative medical student years is not known. This study aimed to estimate the CFP among medical students and to assess their knowledge and attitudes towards climate change. A descriptive, cross-sectional study was conducted among 256 randomly selected medical students in Sri Lanka. The mean CFP of a medical student was 5.64 (SD=2.72) mtCO2/year. The highest contribution to the CFP was from lifestyle factors (68.97%) followed by travel (26.41%). The CFP increased with increasing household income (p=0.001). 82% of students knew the meaning of âgreenhouse effectâ, but only 33% knew the meaning of âcarbon footprintâ; 58.3% were aware of the adverse effects of climate change while only 42.3% could name 3 or more gases that contribute to it. About a third considered their CFP to be negligible. However, 86.3% elected to change their mode of transport to minimize their CFP. Over 90% considered issues of climate change the responsibility of the government while only 7% felt that it was the responsibility of the individual. The CFP of medical students was higher than the per capita national average while knowledge about it was inadequate. Educating medical students on climate change and emphasizing the importance of individual responsibility is likely to change behavior towards a greener lifestyle.
openalex: W3120741477 mag: 3120741477
Keywords: C:Sri Lanka; _z:class:countries; _z:class:themes; oa:keyword:carbon footprint; oa:keyword:climate change; oa:sdg:2 Zero hunger; oa:topic:T11244 Impact of Climate Change on Human Health; oa:topic:T11488 Perceptions and Communication of Climate Change; oa:topic:T11731 Global Surgery and Health Development; openalex:import; openalex:yes

Gross Domestic Product Modeling Using “Panel-Data” Concept - Ghosh, Sarada; Samanta, G. P. (2021)
In this work, we want to predict gross domestic product (GDP) using ‘panel-data’ models. Gross domestic product for fifteen individual countries of Europe in different four years (1995, 2000, 2005 and 2010) under various components of GDP are used here. The panel-data models have been developed using the investment, labour force growth and budget surplus as inputs in order to predict the GDP of the countries which help us to perceive the economic condition of Europe from the statistical point of view. The results indicate that the random effects model is more appropriate than fixed effects model. In addition, this chapter also contains a panel data regression model with cross-sectional dependence, heteroscedasticity and also considers serially correlated disturbances for random effects.
openalex: W3168928502 mag: 3168928502
Keywords: openalex:import; openalex:related

Mainstreaming of Climate Change Adaptation in Moroccan Companies: Tools, Teachings, and Perspectives - Jaouhari, Youssef; Stour, Laila; Agoumi, Ali (2021)
openalex:W3174591388 mag:3174591388 KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-030-22759-3_308-1 5072953:W7WAS9CN
Keywords: _z:class:countries; _z:class:themes; _z:no_pdf; _z:not_duplicate; oa:keyword:climate change; oa:keyword:climate change adaptation; oa:keyword:moroccan companies; oa:topic:T10119 Sustainability Transitions and Resilience in Social-Ecological Systems; oa:topic:T12656 Impact of Climate Change on Human Migration; oa:topic:T14296 Climate Change and Sustainable Development; openalex:import; openalex:n:1; openalex:yes

Mainstreaming of Climate Change Adaptation in Moroccan Companies: Tools, Teachings, and Perspectives - Jaouhari, Youssef; Stour, Laila; Agoumi, Ali (2021)
openalex:W4243527633 mag: KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-030-57281-5_308 5072953:2VXESVIQ
Keywords: _z:class:countries; _z:class:themes; _z:no_pdf; _z:not_duplicate; oa:keyword:climate change; oa:keyword:climate change adaptation; oa:keyword:moroccan companies; oa:topic:T10119 Sustainability Transitions and Resilience in Social-Ecological Systems; oa:topic:T12656 Impact of Climate Change on Human Migration; oa:topic:T14296 Climate Change and Sustainable Development; openalex:import; openalex:n:1; openalex:yes

Where are persons with disabilities? A reflexive thematic analysis of Federal Government climate change documents - MacDonald, Sarah Ellen (2021)
openalex: W3200006596 mag: 3200006596
Keywords: _z:class:countries; openalex:import; openalex:yes

Assessment of the Perceived Impact of Climate Change on Student-Teachers in Nigerian Tertiary Institutions - Marcel, Ezemoyih Chuks; Ekeh; Onyemaechi, David; Elom; Chinyere; Chijioke, Uwaleke Chidebe; Chika, Uzosike Peter; Eze; Nnenna, Claris; Mbana, Okpara Catherine; Obodo; Chikaodinaka, Abigail (2021)
The study assesses the perceived impact of climate change on student teachers in Nigerian tertiary institutions. The study adopted descriptive survey research design. Two research questions guided the study while two hypotheses were formulated and tested at 0.05 level of significance. The population of the study comprised of all the students of 2020/2021 final year Degree students of Alex Ekwueme Federal University and NCE students of Enugu State College of Education (Technical). Purposive sampling technique was used to select one hundred and eighty (180) students from both institutions. The instrument for data collection was a structured questionnaire titled Questionnaire on Perceived Impact of Climate Change Teacher (QPICC). The questionnaire was structured by the researchers and validated by two experts in Science Education and Measurement and Evaluation respectively. Data collected were analyzed using mean and standard deviation to answer the research questions while t-test statistics was used to test the null hypotheses. The findings revealed that student-teachers have adequate knowledge of cause, impacts and solution of climate change respectively. The researchers recommended that climate change education be introduced into the teacher training institutions and regular training and workshops be organized to update teachers knowledge on the causes, impacts and mitigation strategies on climate change.
openalex:W3169165837 mag:3169165837 KerkoCite.ItemAlsoKnownAs: 5072953:KF2SIXPF
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Assessment of the Perceived Impact of Climate Change on Student-Teachers in Nigerian Tertiary Institutions - Marcel, Ezemoyih Chuks; Ekeh; Onyemaechi, David; Elom; Chinyere; Chijioke, Uwaleke Chidebe; Chika, Uzosike Peter; Eze; Nnenna, Claris; Mbana, Okpara Catherine; Obodo; Chikaodinaka, Abigail (2021)
The study assesses the perceived impact of climate change on student teachers in Nigerian tertiary institutions. The study adopted descriptive survey research design. Two research questions guided the study while two hypotheses were formulated and tested at 0.05 level of significance. The population of the study comprised of all the students of 2020/2021 final year Degree students of Alex Ekwueme Federal University and NCE students of Enugu State College of Education (Technical). Purposive sampling technique was used to select one hundred and eighty (180) students from both institutions. The instrument for data collection was a structured questionnaire titled Questionnaire on Perceived Impact of Climate Change Teacher (QPICC). The questionnaire was structured by the researchers and validated by two experts in Science Education and Measurement and Evaluation respectively. Data collected were analyzed using mean and standard deviation to answer the research questions while t-test statistics was used to test the null hypotheses. The findings revealed that student-teachers have adequate knowledge of cause, impacts and solution of climate change respectively. The researchers recommended that climate change education be introduced into the teacher training institutions and regular training and workshops be organized to update teachers knowledge on the causes, impacts and mitigation strategies on climate change.
openalex:W3169165837 mag:3169165837 KerkoCite.ItemAlsoKnownAs: 5072953:KF2SIXPF
Keywords: _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Climate Change Adaptation and Sustainability in the Bangladeshi School Curriculum - Shohel, M. Mahruf C.; Roy, Goutam; Chowdhury, Tanjeeba; Alam, Atm S.; Shams, Shahriar (2021)
Bangladesh is one of the most affected countries by climate change and extremely vulnerable to environmental degradation. Young people, as the new generation, need to understand the consequences of climate change and its impact on their lives and the lives of their fellow citizens. This chapter presents the findings from a systematic evaluation of Bangladeshi school curriculum, and how it prepares the future generation for climate change adaptation and ensures a sustainable future for them. This chapter highlights the recommendations from the findings and suggests how the national curriculum could address climate change mitigation and adaptation for sustainability by providing contents to offer grounding for the young people as global citizens to act in the local context. Although there is some content included in the school textbooks related to climate change and sustainable development issues, there is a need for inclusion of more relevant contents in the national school curriculum so that school textbooks provide enough contents on climate change, its mitigation and adaptation.
openalex: W3128544837 mag: 3128544837
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:sustainability; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; oa:topic:T11835 Sustainability Education in Higher Education Institutions; openalex:import; openalex:yes

Climate Change Adaptation and Sustainability in the Bangladeshi School Curriculum - Shohel, M. Mahruf C.; Roy, Goutam; Chowdhury, Tanjeeba; Alam, Atm S.; Shams, Shahriar (2021)
Bangladesh is one of the most affected countries by climate change and extremely vulnerable to environmental degradation. Young people, as the new generation, need to understand the consequences of climate change and its impact on their lives and the lives of their fellow citizens. This chapter presents the findings from a systematic evaluation of Bangladeshi school curriculum, and how it prepares the future generation for climate change adaptation and ensures a sustainable future for them. This chapter highlights the recommendations from the findings and suggests how the national curriculum could address climate change mitigation and adaptation for sustainability by providing contents to offer grounding for the young people as global citizens to act in the local context. Although there is some content included in the school textbooks related to climate change and sustainable development issues, there is a need for inclusion of more relevant contents in the national school curriculum so that school textbooks provide enough contents on climate change, its mitigation and adaptation.
openalex: W3128544837 mag: 3128544837
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:sustainability; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; oa:topic:T11835 Sustainability Education in Higher Education Institutions; openalex:import; openalex:yes

How Do Endogenous Cultural Institutions (not) Shape Peasant Farmers’ Climate Adaptation Practices? Learning from Rural Cameroon - Silberberger, Magdalene; Kimengsi, Jude Ndzifon (SSRN Electronic Journal, 2021)
The inter-linked issues of climate change and sustainable development remain high on the science and policy agenda, especially in sub-Saharan Africa (SSA) where context-specific local adaptation practices are required in her agricultural system. However, the dearth of scientific (quantitative) evidence on how endogenous cultural institutions (ECIs) shape the local adaptation practices of rural farmers in SSA, stalls, in part, the advancement of climate adaptation practice in the agricultural sector. Based on a representative sample of 158 farming households in rural Cameroon, we contribute to bridge this knowledge gap, by: (1) exploring the household socio-economic attributes and general social and political factors that determine peasant farmer’s compliance with agro-based ECIs, and (2) estimating the effect of ECI compliance on farmers’ adaptation practices. Our estimation revealed the following: Increasing compliance with ECIs is a function of increasing age of peasant farmers. While political factors do not sufficiently explain compliance with ECIs, state influence, mirrored through the application of formal rules significantly contributes to a decline in compliance. Differential levels of compliance with ECIs produce differential climate adaptation outcomes; while some ECIs (e.g. traditional rain forecast) significantly explain several climate adaptation practices, others (e.g. pouring of libation) do not. While we conclude that the differentiated effects of ECI compliance manifest throughout the climate adaptation practices of peasant farmers, we also call for further empirical evidence to ground this claim.
openalex:W3170877388 mag:3170877388 KerkoCite.ItemAlsoKnownAs: 10.2139/ssrn.3822319 5072953:FNSKVT2R
Keywords: C:Cameroon; _z:class:countries; _z:class:themes; oa:keyword:climate adaptation practices; oa:keyword:endogenous cultural institutions; oa:keyword:rural cameroon; oa:sdg:13 Climate action; oa:topic:T10367 Agricultural Innovation and Livelihood Diversification; oa:topic:T10439 Adaptation to Climate Change in Agriculture; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

The Challenges and Opportunities for Climate Change Education at Makerere University in Kampala Uganda - Ssekamatte, David; Speck, Karsten; Siebenhüner, Bernd (2021)
Societies across the globe are battling with the effects of climate change as seen in the scientific evidence produced periodically by the Intergovernmental Panel on Climate Change (IPCC). Africa has been identified as more vulnerable to climate change given its weak governance systems, low technology, dependency on ecological resources for livelihood as well as conflict and high poverty levels. Educational responses to climate change though recognized, are yet to be explored by various countries on the continent. The researchers conducted a qualitative study to examine the perspectives and views of university lecturers, administrators and students on climate change related courses and programmes regarding opportunities and challenges for climate change education at Makerere University as part of a larger multiple comparative study in East Africa. A case study design was adopted. Semi-structured in-depth interviews and focus group discussions were conducted to collect data from a total of 25 participants at the case university. Data was analysed using thematic analysis based on Braun and Clarke (2006) with the help of MAXQDA software. Findings revealed a wide range of perspectives and views regarding the challenges and opportunities for climate change education at this university. It is expected that the findings of this study may contribute to empirical scientific knowledge on climate change education at universities in the African context.
openalex:W3181083211 mag:3181083211 KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-030-74693-3_12 5072953:X3G9264B
Keywords: C:Uganda; _z:class:countries; _z:class:themes; oa:keyword:climate change education; oa:topic:T10119 Sustainability Transitions and Resilience in Social-Ecological Systems; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:n:1; openalex:yes

Long-Term Effects of Climate Change on Housing Market analytics in Amaravati, Capital of Andhra Pradesh in India, Using Machine Learning - Usharani, Bhimavarapu (2021)
Housing markets are known to be affected by adverse environments (i.e., environmental air pollution incidents affect Indian urban residents). Urban atmosphere quality has changed extensively with PM2.5 and O3 becoming the primary atmosphere indicators of concern because of dense cities in recent years. There is a correlation between the air pollution of Amaravati with the housing market model. When estimating the housing market, the chapter makes use of the extended regression model together with several constant results in conformity with higher rule. However, there is an insignificant affinity including the concentration regarding SO2 and the concentration of O3 appears according to positively increase the housing values. This chapter therefore examines the influence of actual real estate investment over atmosphere characteristics through the use of a sample on 26 prefecture-level cities in India from 2010–2019 through countless econometric models.
openalex: W3166439007 mag: 3166439007
Keywords: C:India; _z:class:countries; _z:class:themes; oa:keyword:housing market analytics; oa:sdg:11 Sustainable cities and communities; oa:topic:T10632 Consequences of Mortgage Credit Expansion and Housing Market Dynamics; openalex:import; openalex:yes

Analysis of traditional windcatchers and the effects produced by changing the size, shape, and position of the outlet opening - Varela-Boydo, C. A.; Moya, S. L.; Watkins, R. (Journal of Building Engineering, 2021)
Increased thermal comfort in buildings is consuming large amounts of energy around the world, especially in hot arid and semi-arid regions. Finding and adapting ways to naturally cool buildings should be a priority for researchers in the subject. For centuries the Middle East cultures have used wind towers to cool their buildings and they have proved to be a cost-effective, easy to implement and reliable solution for passive cooling that requires almost negligible energy to operate. The present work tests one traditional windcatcher and 33 modifications of the design of the outlet opening. It seeks to act as a guide to how both to enhance and also avoid reducing performance when designing windcatchers with traditional designs. Using CFD modelling, the volumetric airflow that was captured by the catcher was computed for the different outlet modifications, and this revealed which designs restrain the flow and which boost the airflow, making the wind towers more effective.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.jobe.2020.101828 4874017:BLJKASWR 5072953:3HQSCDNQ openalex: W3087560224
Keywords: Badgir; Natural ventilation; Passive cooling; Wind towers; Windcatchers; _z:class:countries; _z:class:themes; oa:keyword:traditional windcatchers; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10466 Numerical Weather Prediction Models; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:n:1; openalex:yes

Factors shaping students' perception of climate change in the western Himalayas, Jammu & Kashmir, India - Zeeshan, Mohd; Sha, Liqing; Tomlinson, Kyle W.; Azeez, P. A. (Current Research in Environmental Sustainability, 2021)
The Himalayas are considered highly vulnerable to climate change, and hence making adaptation strategies for the area to cope with the effects of climate change is crucial. These strategies should be developed and implemented with grassroots participation at local to regional levels. For informed participation, the local inhabitants need to be conscious of climate change and its implications. Hence, we explored the level of awareness among school students and their participation in actions and advocacy concerning climate change. We assumed that in Rajouri, being a small city with traditional values and worldview, the students' responses would largely reflect that of their immediate surroundings. We examined the variations in the responses of the students with respect to the type of schools (private versus public), location (urban versus rural), education level (secondary versus higher secondary), and gender. A questionnaire survey on awareness, advocacy, and action received 717 responses, of which 27% showed high awareness of climate change, 60% were highly proactive to advocacy and 88% were willing to be involved in actions concerning their environment. However, students who were found to be aware of climate change through the formal education system were not involved in adaptation and mitigation actions. We assume that no direct or indirect involvement possibly indicates a need of motivation in the curricular system. Hence suggest more attention be given to climate change in formal education with appropriate changes in curricula and pedagogy, with opportunity for hands-on exposure, to inspire the students to be more proactive in adaptation and mitigation efforts. That would facilitate the future generation to take active participation in developing appropriate adaptation strategies towards climate change.
openalex: W3149647225 mag: 3149647225
Keywords: C:India; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10119 Sustainability Transitions and Resilience in Social-Ecological Systems; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:yes

Efficiency of Solar Shading Devices to Improve Thermal Comfort in a Sports Hall - Dudzińska, Anna (Energies, 2021)
Thermal environment in sports facilities is probably one of the most important parameters, determining the safety and performance of athletes. Such facilities, due to the required operating temperature and physical activity of users, are a serious challenge for both investors and administrators, especially in summer. The additional criterion of low energy consumption in extremely airtight and well-insulated passive buildings often results in overheating of the interior, creating considerable economic and operational problems. The significant need to reduce solar gain during periods of high outdoor temperatures for low-energy buildings prompts a variety of design solutions. Sun shading systems, as an indispensable element of glazed surfaces, are designed to control the amount of solar radiation reaching the building interior, at the same time creating a favorable microclimate inside. This article analyzes the effects of sun shading, which have actually been applied and modified on the southern façade of a passive sports hall in Słomniki. Measurements of the thermal conditions in the hall were the starting point, on the basis of which a model of the object was created in the DesignBuilder program. Using simulation analyses, thermal conditions arising with the use of different variants of internal and external shading devices were studied in the program. The results presented in the article show that in a well-insulated hall of large volume, appropriately selected external shading devices are only able to reduce the access of sunlight to the rooms. External brise-soleils are able to limit the access of solar radiation to the rooms by up to 30%, but this is not enough to guarantee internal thermal comfort. Internal blinds do not affect the interior microclimate significantly and do not protect protection from overheating. Momentary differences in PMV values for different patterns of closing the blinds do not exceed 0.2.
Number: 12 KerkoCite.ItemAlsoKnownAs: 10.3390/en14123535 2129771:LLN65HUW 4874017:X39357V8
Keywords: evidence_review; overhangs; overheating; passive building; solar protection; sports hall; thermal comfort

Research on the effect of different position on classroom ventilation in a “L” type teaching building - Liu, Xiaodong; Yang, Li; Niu, Shengnan (Journal of Building Engineering, 2021)
The ventilation effect in different places in the teaching building is different. The aim of this paper is to study the relative ventilation relationship of the rooms in “L” type middle school teaching building. Taking Xiamen in the subtropical ...
KerkoCite.ItemAlsoKnownAs: 2129771:357M2ALK 2129771:357M2ALK 10.1016/j.jobe.2020.101852 4874017:AJRWLQ5Q 5072953:7774EGBB openalex: W3090363571
Keywords: _z:class:countries; _z:class:themes; evidence_review_2; oa:keyword:classroom ventilation; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10990 Airborne Transmission of Respiratory Viruses; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:n:1; openalex:yes

ANSI/ASHRAE Standard 55-2020. Thermal environmental conditions for human occupancy - A.S.H.R.A.E. (American Society of Heating, Refrigerating and Air-Conditioning Engineers, 2021)
Pages: 80 ,

Monitoring and Assessment of Indoor Environmental Conditions after the Implementation of COVID-19-Based Ventilation Strategies in an Educational Building in Southern Spain - Aguilar, Antonio J.; de la Hoz-Torres, María L.; Martínez-Aires, Mª; Ruiz, Diego P. (Sensors, 2021)
KerkoCite.ItemAlsoKnownAs: 10.3390/s21217223 2129771:XZFHV8UQ 4682641:DWETE6D8 4682641:SP2AIEN2 5072953:NZFL2RLX openalex: W3208226162
Keywords: BE:RELEVANT; C:Spain; _z:class:countries; _z:class:themes; oa:keyword:indoor environmental conditions; oa:keyword:ventilation strategies; oa:sdg:3 Good health and well-being; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10990 Airborne Transmission of Respiratory Viruses; oa:topic:T11692 Effects of Noise Pollution on Health and Well-being; openalex:n:1; openalex:yes

Natural ventilation in warm climates: The challenges of thermal comfort, heatwave resilience and indoor air quality - Ahmed, Tariq; Kumar, Prashant; Mottet, Laetitia (Renewable and Sustainable Energy Reviews, 2021)
In buildings, energy is primarily consumed by mechanical air conditioning systems. Low energy alternatives, such as natural ventilation, are needed. However, they need to be able to cope with increasing heatwaves and pollution, particularly in warm climates. This review paper looked at the ability of natural ventilation to provide adequate thermal comfort, resilience against heatwaves, and good Indoor Air Quality in warm climates. Single-sided ventilation demonstrates the poorest ability to provide thermal comfort, while cross ventilation highlights better performance in terms of reducing indoor air temperatures compared to outdoor. However, windcatchers and solar chimneys displayed even better performance by producing relatively high ventilation rates. During heatwaves and future climatic scenarios, natural ventilation, by cross-ventilation, was not able to meet internal thermal comfort standards. A potential low energy solution could be combining solar chimneys or windcatchers with water evaporation cooling. A critical synthesis of the literature suggests that these systems can generate high ventilation rates and keep indoor temperatures around 8 °C cooler than outdoor temperatures in warm weather (>35 °C). However, no studies were found testing these systems against future climate scenarios, and further studies are recommended. The literature supported natural ventilation being effective in removing pollution generated indoors due to adequate ventilation rates. However, using unfiltered natural ventilation for areas with high outdoor pollution can increase the indoor deposition of harmful particulate matter. With increasing air pollution, further studies are urgently required to investigate filter enabled natural ventilation, particularly with solar chimney/windcatcher incorporated.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.rser.2020.110669 4874017:WV39KJ7P 5072953:GMN9959T 5072953:VPTBEGCL
Keywords: _z:class:countries; _z:class:themes

Natural ventilation in warm climates: the challenges of thermal comfort, heatwave resilience and indoor air quality - Ahmed, Tariq; Kumar, Prashant; Mottet, Laetitia (2021)
In buildings, energy is primarily consumed by mechanical air conditioning systems. Low energy alternatives, such as natural ventilation, are needed. However, they need to be able to cope with increasing heatwaves and pollution, particularly in warm climates. This review paper looked at the ability of natural ventilation to provide adequate thermal comfort, resilience against heatwaves, and good Indoor Air Quality in warm climates. Single-sided ventilation demonstrates the poorest ability to provide thermal comfort, while cross ventilation highlights better performance in terms of reducing indoor air temperatures compared to outdoor. However, windcatchers and solar chimneys displayed even better performance by producing relatively high ventilation rates. During heatwaves and future climatic scenarios, natural ventilation, by cross-ventilation, was not able to meet internal thermal comfort standards. A potential low energy solution could be combining solar chimneys or windcatchers with water evaporation cooling. A critical synthesis of the literature suggests that these systems can generate high ventilation rates and keep indoor temperatures around 8 °C cooler than outdoor temperatures in warm weather (>35 °C). However, no studies were found testing these systems against future climate scenarios, and further studies are recommended. The literature supported natural ventilation being effective in removing pollution generated indoors due to adequate ventilation rates. However, using unfiltered natural ventilation for areas with high outdoor pollution can increase the indoor deposition of harmful particulate matter. With increasing air pollution, further studies are urgently required to investigate filter enabled natural ventilation, particularly with solar chimney/windcatcher incorporated.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.rser.2020.110669 2129771:KP6F7NQ8 4874017:WV39KJ7P
Keywords: evidence_review

Farmers’ adaptation strategies to combat climate change in drought prone areas in Bangladesh - Anik, A.R. (International Journal of Disaster Risk Reduction, 2021)
KerkoCite.ItemAlsoKnownAs: 5072953:HKNW8MEY 5072953:SBSCAHWC

Challenges and opportunities for climate change education (CCE) in East Africa: A critical review - Apollo, Abigael; Mbah, Marcellus Forh (Climate, 2021)
It is undoubtedly clear that climate change is happening, and its adverse impacts could reverse the progress made toward meeting sustainable development goals. The global crisis poses one of the most severe challenges to reducing poverty and existing inequalities, especially in developing countries that are projected to be highly vulnerable to climate variability. However, the education sector provides an untapped opportunity for successful climate change adaptation and mitigation through knowledge and skill acquisitions, and consequently, positive behavioral change. Specifically, education can capacitate individuals and communities to make informed decisions and take practical actions for climate-resilient sustainable development. This study is focused on East Africa, a region whose economy heavily relies on climate-dependent activities. At present, East African governments are already embedding climate change in their school curriculum. However, they lack coherent approaches to leverage climate change education as a tool in their adaptation and mitigation strategies. Therefore, this review explores some of the critical barriers to climate change education and possible opportunities for leveraging learning to promote sustainable development in East Africa.
KerkoCite.ItemAlsoKnownAs: 10.3390/cli9060093 5072953:4DQCFNDM openalex: W3166039787
Keywords: _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change education; oa:topic:T10439 Adaptation to Climate Change in Agriculture; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11336 Indoor Air Pollution in Developing Countries; openalex:n:1; openalex:yes

COP26: Glasgow will 'welcome' climate protests says council leader’ - B.B.C. (BBC News, 2021)

COP26: The World Is Watching’, Feature Story - Bank, World (2021)

Country classification’ - Bank, World (World Bank Data, 2021)

What is learning poverty?’ - Bank, World (World Bank Brief, 2021)

Systematic mapping of global research on climate and health: a machine learning review - Berrang-Ford, Lea; Sietsma, Anne J.; Callaghan, Max; Minx, Jan C.; Scheelbeek, Pauline FD; Haddaway, Neal R.; Haines, Andy; Dangour, Alan D. (The Lancet Planetary Health, 2021)
Background The global literature on the links between climate change and human health is large, increasing exponentially, and it is no longer feasible to collate and synthesise using traditional systematic evidence mapping approaches. We aimed to use machine learning methods to systematically synthesise an evidence base on climate change and human health. Methods We used supervised machine learning and other natural language processing methods (topic modelling and geoparsing) to systematically identify and map the scientific literature on climate change and health published between Jan 1, 2013, and April 9, 2020. Only literature indexed in English were included. We searched Web of Science Core Collection, Scopus, and PubMed using title, abstract, and keywords only. We searched for papers including both a health component and an explicit mention of either climate change, climate variability, or climate change-relevant weather phenomena. We classified relevant publications according to the fields of climate research, climate drivers, health impact, date, and geography. We used supervised and unsupervised machine learning to identify and classify relevant articles in the field of climate and health, with outputs including evidence heat maps, geographical maps, and narrative synthesis of trends in climate health-related publications. We included empirical literature of any study design that reported on health pathways associated with climate impacts, mitigation, or adaptation. Findings We predict that there are 15 963 studies in the field of climate and health published between 2013 and 2019. Climate health literature is dominated by impact studies, with mitigation and adaptation responses and their cobenefits and co-risks remaining niche topics. Air quality and heat stress are the most frequently studied exposures, with all-cause mortality and infectious disease incidence being the most frequently studied health outcomes. Seasonality, extreme weather events, heat, and weather variability are the most frequently studied climate-related hazards. We found major gaps in evidence on climate health research for mental health, undernutrition, and maternal and child health. Geographically, the evidence base is dominated by studies from high-income countries and China, with scant evidence from low-income counties, which often suffer most from the health consequences of climate change. Interpretation Our findings show the importance and feasibility of using automated machine learning to comprehensively map the science on climate change and human health in the age of big literature. These can provide key inputs into global climate and health assessments. The scant evidence on climate change response options is concerning and could significantly hamper the design of evidence-based pathways to reduce the effects on health of climate change. In the post-2015 Paris Agreement era of climate solutions, we believe much more attention should be given to climate adaptation and mitigation options and their effects on human health. FundingForeign, Commonwealth & Development Office.
KerkoCite.ItemAlsoKnownAs: 2129771:QUG9TZFB 2129771:QUG9TZFB 2129771:QUG9TZFB 2129771:QUG9TZFB 2129771:QUG9TZFB 10.1016/S2542-5196(21)00179-0 2129771:IDJZNM3S 2129771:SXRZDSH6 2486141:TY6XRCLY 5072953:T5HTLW4W
Keywords: evidence_review; selected_for:effects of climate ch...on learning...LMICs 2024

Influence of Air Temperature on School Teachers’ Mood and the Perception of Students’ Behavior - Boix-Vilella, Salvador; Saiz-Clar, Elena; León-Zarceño, Eva; Serrano, Miguel Angel (Sustainability, 2021)
KerkoCite.ItemAlsoKnownAs: 10.3390/su13179707 2129771:4PNX97S6 4682641:95GTJTGG 5072953:WSUVFQIH openalex: W3197930002
Keywords: BE:RELEVANT; _z:class:countries; _z:class:themes; evidence_review; oa:keyword:air temperature; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T12950 Learning Environments in Education; openalex:n:1; openalex:yes

Effect of roof colour on indoor temperature and human comfort levels, with implications for malaria control: a pilot study using experimental houses in rural Gambia - Carrasco-Tenezaca, M.; Jatta, E.; Jawara, M.; Bradley, J.; Pinder, M.; D'Alessandro, U.; Knudsen, J.; Lindsay, S.W. (Malar J, 2021)

Social Solidarity Economy and Village-centric Development in North-West Cameroon - Che, Charles Fonchingong; Mbah, Marcellus (The International Journal of Community and Social Development, 2021)
Amidst shrinking budgets for community development in most of sub-Saharan Africa, the social solidarity economy is touted as a model in local development. This article situates solidarity initiatives and capability-focused outcomes that deliver enhanced livelihoods, social security and community development. The conceptual framing of social theory, social capital and social economy informs this case study with focus on the Ndong Awing Cultural and Development Association, North-West region, Cameroon. The analysis of semi-structured interviews and secondary sources suggests that solidarity networks such as njangis, cooperatives, quarter development unions and diaspora networks promote village-centric development. These overlapping networks generate scarce financial and human resources–essential packages for livelihoods and welfare. Emerging state policy is yet to calibrate these mechanisms of ground-up, mutual development drives. Galvanising these solidarity assets require meaningful co-productionand revamped state−community relations. This article offers a paradigm shift in how village groups mobilise income, capital and financing of village projects, nurtured through human development and agency.
KerkoCite.ItemAlsoKnownAs: 10.1177/25166026211015474 5072953:NA9P9KZU openalex: W3168107988
Keywords: C:Cameroon; _z:class:countries; _z:class:themes; oa:keyword:cameroon; oa:topic:T10987 Microfinance; Gender Empowerment; and Economic Development; oa:topic:T13839 Volunteer Tourism and Global Development Impacts; oa:topic:T14464 Analysis of Impact Investing in Finance and Social Policy; openalex:n:1; openalex:yes

Impact of Outdoor Particles on Indoor Air - Chen, Chen; Zhao, Bin (Handbook of Indoor Air Quality, 2021)

Born into the Climate Crisis: Why we must act now to secure children’s rights - Children, Save (2021)
KerkoCite.ItemAlsoKnownAs: 5072953:DHM47BGR 5072953:WLGYB9JV

Climate and Environmental Literacy - Day, Earth (2021)

Autoregressive neural networks with exogenous variables for indoor temperature prediction in buildings - Delcroix, Benoit; Ny, Jérôme Le; Bernier, Michel; Azam, Muhammad; Qu, Bingrui; Venne, Jean-Simon (Building Simulation, 2021)
KerkoCite.ItemAlsoKnownAs: 5072953:EGDEINDB
Keywords: _important; _z:class:countries; _z:class:themes; selected_for:Predictive models for classroom conditions 2024; ⛔ No DOI found

Five Ways That Education Systems Can Support Girls in the Face of Climate Change, Today’ - Devonald, M. (Center for Global Development Commentary and Analysis, 2021)

Fund Girls’ Education. Don’t Greenwash It’ - Devonald, M. (Center for Global Development Commentary and Analysis, 2021)

Urban planning for transitions - Douay, Nicolas; Minja, Michael (ISTE, 2021)
Keywords: _z:class:countries

Urban planning for transitions - Douay, Nicolas; Minja, Michael (ISTE, 2021)
KerkoCite.ItemAlsoKnownAs: 5072953:2IQKAJS4
Keywords: _z:class:countries; _z:class:themes

Indoor Conditions in Educational Buildings: the Case of Bolzano Schools - Dugaria, S.; Pernigotto, G.; Gasparella, A. (2021)
KerkoCite.ItemAlsoKnownAs: 2129771:ATN2CWVY 4682641:EVVGIVLW 4682641:VNW4QECN 5072953:Q7L9Z454
Keywords: BE:RELEVANT; _z:class:countries; _z:class:themes; evidence_review_2; ⛔ No DOI found

Natural Disasters Cost $210 Billion Worldwide in 2020’ - Dure (Investopedia News Trends, 2021)

Does Gender Climate Influence Climate Change? The Multidimensionality of Gender Equality and Its Countervailing Effects on the Carbon Intensity of Well-Being - Ergas, Christina; Greiner, Patrick Trent; McGee, Julius Alexander; Clement, Matthew Thomas (Sustainability, 2021)
The carbon intensity of well-being (CIWB) (a ratio measuring the amount of CO2 emitted per unit of life expectancy at birth) is an increasingly popular way to measure the ecological efficiency of nations. Although research demonstrates that economic development typically reduces this efficiency, little research has explored the extent to which social equality improves it. This study uses panel data for 70 nations between 1995 and 2013 to assess how various aspects of gender equality affect the ecological efficiency of nations. We estimate a series of Prais-Winsten regression models with panel-corrected standard errors (PCSE) to assess how increases in the percentage of women in parliament, expected years of education for women, and the percentage of women in the labor force independently affect CIWB. Our findings indicate that across all nations, increases in the percentage of women in parliament and expected years of schooling reduce CIWB; however, increases in the percentage of women in the labor force increase CIWB. Our results further show that the relationship between different dimensions of gender equality and CIWB differs between more developed and less developed nations. Finally, we find that increases in the number of women in parliament and women’s education attenuate the relationship between women’s labor force participation and CIWB. We discuss the variation in our results by reviewing relevant eco-gender literatures and feminist economics.
KerkoCite.ItemAlsoKnownAs: 5072953:4ECALPD5 5072953:JYUI3HGS 5072953:RG4EXAJY
Keywords: _z:class:countries; carbon intensity of well-being; climate change; gender and environment; social inequality; sustainable development

Declaration on girls’ education: recovering from COVID-19 and unlocking agenda 2030 - Foreign, U.K.; Commonwealth; Office, Development (2021)
Pages: – – –2021– – – – – – – –19– – – –2030

A greener, fairer future: Why leaders need to invest in climate and girls’ education - Fund, Malala (2021)
KerkoCite.ItemAlsoKnownAs: 5072953:QNGW6RDC 5072953:RQ9CNF7K

Change the subject: How leaders can take action for climate education at COP26 - Fund, Malala (2021)
KerkoCite.ItemAlsoKnownAs: 5072953:VKZASDYX 5072953:YJGRA84A

Girls’ Education and COVID-19. What past shocks can teach us about mitigating the impact of pandemics - Fund, Malala (2021)

Maternal Undernutrition in Adolescence and Child Human Capital Development Over the Life Course: Evidence from an International Cohort Study - Georgiadis, A.; Benny, L.; Dornan, P.; Behrman, J. (Maternal Undernutrition in Adolescence and Child Human Capital Development Over the Life Course: Evidence from an International Cohort Study—Georgiadis—2021—Economica—Wiley Online Library, 2021)

Analysis and Documentation of Experiments on Cool Roofs and Walls in KwaZulu-Natal - GIZ (Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ) GmbH, 2021)
KerkoCite.ItemAlsoKnownAs: 4874017:T6Y47YER 5072953:BWI4JM3D
Keywords: _z:class:countries; _z:class:themes

Reparations for Climate Change in Africa as a Driver of State Responsibility, Human Rights Protection and Global Development - Gorimbo, Sarudzai (University of Johannesburg, 2021)

PM speech at the Global Education Summit - Great Britain, Prime Minister’s Office, 10 Downing Street (2021)

Haileybury Youth Trust Uganda - HYT Uganda (2021)
KerkoCite.ItemAlsoKnownAs: 4874017:NKESLX8R 5072953:JV9HIVHH
Keywords: C:Uganda; _z:class:countries; _z:class:themes

Gendered Dimensions of Unpaid Activities: An Empirical Insight into Rural Bangladesh Households - Islam, F.B.; Sharma, M. (Sustainability, 2021)
KerkoCite.ItemAlsoKnownAs: 5072953:5XS3USV8 5072953:AETS79BI

Nigerian cultural beliefs about mental health conditions and traditional healing: a qualitative study - Jidong, Dung Ezekiel; Bailey, Di; Sodi, Tholene; Gibson, Linda; Sawadogo, Natéwindé; Ikhile, Deborah; Musoke, David; Madhombiro, Munyaradzi; Mbah, Marcellus (The Journal of Mental Health Training, Education and Practice, 2021)
KerkoCite.ItemAlsoKnownAs: 10.1108/JMHTEP-08-2020-0057 5072953:MXKP887W openalex: W3162989923
Keywords: C:Niger; C:Nigeria; _z:class:countries; _z:class:themes; openalex:n:0; openalex:n:1; openalex:yes

(Un) subjugating indigenous knowledge for sustainable development: considerations for community-based research in African higher education - Johnson, Ane Turner; Mbah, Marcellus Forh (Journal of Comparative and International Higher Education, 2021)
KerkoCite.ItemAlsoKnownAs: 10.32674/jcihe.v13iSummer.3707 5072953:JWMXZ78C openalex: W3173299148
Keywords: _z:class:countries; _z:class:themes; oa:keyword:indigenous knowledge; oa:keyword:sustainable development; oa:topic:T12160 Decolonizing Education in African Context; oa:topic:T12345 Transformative Learning Theory and Practice; oa:topic:T14464 Analysis of Impact Investing in Finance and Social Policy; openalex:n:1; openalex:yes

A guidance note on climate-smart school construction planning - Kazemi, Maha; Mackintosh, Alasdair; Ramirez, Ana; Sullivan, Ian (2021)
Ahead of COP-26 we published a self-funded guidance note on climate-smart school construction planning.
KerkoCite.ItemAlsoKnownAs: 2129771:Y3VB6CGA 2129771:Y3VB6CGA 4874017:GIB5KTEI 5072953:UUQEFJ5D
Keywords: _z:class:countries; _z:class:themes; evidence_review_2; ⛔ No DOI found

Effect of design and operational strategies on thermal comfort and productivity in a multipurpose school building - Kükrer, Ergin; Eskin, Nurdil (Journal of Building Engineering, 2021)
KerkoCite.ItemAlsoKnownAs: 4874017:UPZGWBDC 4874017:UPZGWBDC 10.1016/j.jobe.2021.102697 2129771:JDR4V5F8 4682641:XZHUTQW6 5072953:GNJP2WA2 openalex: W3161791932
Keywords: BE:RELEVANT; _z:class:countries; _z:class:themes; evidence_review_2; oa:keyword:multipurpose school building; oa:keyword:thermal comfort; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11529 Refrigeration Systems and Technologies; openalex:n:1; openalex:yes

The Climate Change Education Ambition Report Card - Kwauk, C. (2021)

A New Green Learning Agenda: Approaches to Quality Education for Climate Action - Kwauk, C.; Casey, O. (Center for Universal Education at The Brookings Institution, 2021)
KerkoCite.ItemAlsoKnownAs: 5072953:34KCWTG5 5072953:AW44M437 5072953:Q469R8TI 5440726:LXT8UU99
Keywords: _z:class:countries

Unleashing the creativity of teachers and students to combat climate change: An opportunity for global leadership - Kwauk, C.; Winthrop, R. (2021)
KerkoCite.ItemAlsoKnownAs: 2129771:EE7GBPVX 2129771:EE7GBPVX 5072953:D5T9WJGL 5072953:EVIE92VS
Keywords: _z:class:countries; evidence_review_2

Unleashing the creativity of teachers and students to combat climate change: An opportunity for global leadership - Kwauk, C.; Winthrop, R. (2021)
KerkoCite.ItemAlsoKnownAs: 2129771:EE7GBPVX 5072953:D5T9WJGL 5072953:EVIE92VS
Keywords: _z:class:countries; evidence_review_2

Changing climate change: The carbon budget and the modifying-work of the IPCC - Lahn, Bard; Lahn, Bård (Social Studies of Science, 2021)
Over the last 10 years, the concept of a global ‘carbon budget’ of allowable CO 2 emissions has become ubiquitous in climate science and policy. Since it was brought to prominence by the Fifth Assessment Report of the IPCC, the carbon budget has changed how climate change is enacted as an issue of public concern, from determining the optimal rate of future emissions to establishing a fixed limit for how much emissions should be allowed before they must be stopped altogether. Exploring the emergence of the carbon budget concept, this article shows how the assessment process of the IPCC has offered scientific experts the means to modify how the climate issue is problematized, and discusses the implications of this ‘modifying-work’ for the politics of climate change. It finds that the ‘modified climate issue’ must be seen as an outcome of the ordinary work within established scientific and political institutions, and the agency these institutions afford scientists to enact the issue differently. On this basis, it argues that the case of the carbon budget holds important insights not only for the relationship between climate science and policy, but also for the pragmatist literature on ‘issue formation’ in STS.
KerkoCite.ItemAlsoKnownAs: 10.1177/0306312720941933 2129771:DCRUJGCN 2129771:UVCUJV8U 4874017:DFI9G5HK 4874017:ZGXHX4VS
Keywords: evidence_review

Sleep and Indoor Air Quality - Lan, Li; Lian, Zhiwei (Handbook of Indoor Air Quality, 2021)
KerkoCite.ItemAlsoKnownAs: 5072953:AF3IQJRJ 5072953:UNXXBFHX
Keywords: _important

Environmental degradation and female economic inclusion in sub-Saharan Africa: Effort towards Sustainable Development Goal 5 - Langnel, Z. (Development Southern Africa, 2021)
KerkoCite.ItemAlsoKnownAs: 5072953:EYQ2MPHA 5072953:SL7SLYK9

Gender equality in climate policy and practice hindered by assumptions - Lau, J.D. (Nature Climate Change, 2021)

Overall effects of temperature steps in hot summer on students' subjective perception, physiological response and learning performance - Liu, Jiajing; Kang, Jian; Li, Zeyu; Luo, Hanbin (Energy and Buildings, 2021)
University students are very likely to experience temperature steps before class in hot summer. This study aims to investigate the overall effects of step changes on students’ subjective perception, physiological response and learning performance, so as to explore an optimal thermal condition for classrooms in hot summer. Four typical temperature step conditions (S6: 34 °C-28 °C, S8: 34 °C-26 °C, S10: 34 °C24 °C, S12: 34 °C–22 °C) were developed to conduct experiments on sixteen participants. It has been found that after temperature steps, no more than 62.5% of students consistently found thermally acceptable at 22 °C; students felt the most acceptable and comfortable at 26 °C; the effect of thermal environment on workload was not significant in most cases, especially for memory-related tasks; students’ negative mood was less at 26 °C than at 28 °C and 22 °C. When the temperature step was less than S12, blood pressure and blood oxygen saturation were insensitive to temperature steps; core temperature continued to rise during the first 5 min and then decreased significantly when the temperature step exceeded S8. No significant difference in learning performance was found among the four conditions; the differences in relative performance between thermal conditions were <2%, and are not likely to have practical meaning in building management practice. Overall, the optimal thermal condition is 26 °C, and it is recommended to set the indoor temperature between 24 and 28 °C.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2021.111124 2129771:SUQEEL9Z 4682641:7BF3Z8EW 5072953:CMQGZDBV openalex: W3164401217
Keywords: BE:RELEVANT; _z:class:countries; _z:class:themes; oa:keyword:hot summer; oa:sdg:4 Quality education; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11109 Physiological Responses to Heat Stress in Humans; oa:topic:T11244 Impact of Climate Change on Human Health; openalex:n:1; openalex:yes

ASTM and ASHRAE Standards for the Assessment of Indoor Air Quality - Liu, Xiaoyu (Handbook of Indoor Air Quality, 2021)

Ecofeminism and Natural Resource Management: Justice Delayed, Justice Denied - Liu, Y. (Sustainability, 2021)
KerkoCite.ItemAlsoKnownAs: 5072953:DUD8HIT7 5072953:INMVAITH

Comfort temperature prediction according to an adaptive approach for educational buildings in tropical climate using artificial neural networks - López-Pérez, L. A.; Flores-Prieto, J. J.; Ríos-Rojas, C. (Energy and Buildings, 2021)
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2021.111328 5072953:7XWJIK4N openalex: W3191355140
Keywords: _important; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T10990 Airborne Transmission of Respiratory Viruses; openalex:n:1; openalex:yes; selected_for:Predictive models for classroom conditions 2024

Fostering University Contribution Towards Sustainable Development: The Instrumentality of Indigenous Knowledge System - Mbah, Marcellus Forh; Johnson, Ane Turner (Sustainable Development in Africa, 2021)
Series Title: World Sustainability Series KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-030-74693-3_2 5072953:KS2D6ZWF
Keywords: _z:class:countries; _z:class:themes

A systematic review of the deployment of indigenous knowledge systems towards climate change adaptation in developing world contexts: implications for climate change education - Mbah, Marcellus; Ajaps, Sandra; Molthan-Hill, Petra (Sustainability, 2021)
Countries in the developing world are increasingly vulnerable to climate change effects and have a lesser capacity to adapt. Consideration can be given to their indigenous knowledge systems for an integrated approach to education, one which is more holistic and applicable to their context. This paper presents a systematic review of the indigenous knowledge systems (IKSs) deployed for climate change adaptation in the developing world and advances implications for climate change education. A set of inclusion criteria was used to screen publications derived from two databases and grey literature searches, and a total of 39 articles constituted the final selection. Postcolonial theory’s lens was applied to the review of the selected publications to highlight indigenous people’s agency, despite IKSs’ marginalization through colonial encounters and the ensuing epistemic violence. The categories of social adaptation, structural adaptation, and institutional adaptation emerged from the IKS-based climate change adaptation strategies described in the articles, with social adaptation being the most recurrent. We discussed how these strategies can be employed to decolonise climate change education through critical, place-based, participatory, and holistic methodologies. The potential outcome of this is a more relatable and effective climate change education in a developing world context.
KerkoCite.ItemAlsoKnownAs: 10.3390/su13094811 5072953:NSRVHAFX openalex: W3158575593
Keywords: C:Bangladesh; C:Benin; C:Bolivia; C:Brazil; C:Colombia; C:Ethiopia; C:Fiji; C:Ghana; C:India; C:Indonesia; C:Iran; C:Malawi; C:Malaysia; C:Namibia; C:Nepal; C:Nigeria; C:Peru; C:Philippines; C:South Africa; C:Tanzania; C:Uganda; C:Vietnam; C:Zimbabwe; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change adaptation; oa:keyword:indigenous knowledge systems; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T12656 Impact of Climate Change on Human Migration; oa:topic:T14007 Place-Based Education in Rural Communities; openalex:n:1; openalex:yes

Fostering University Contribution Towards Sustainable Development Within an African Context: The Instrumentality of Indigenous Knowledge System - Mbah, Marcellus; Johnson, Ane Turner (2021)
KerkoCite.ItemAlsoKnownAs: 5072953:MLNVAGE8
Keywords: _z:class:countries; _z:class:themes; ⛔ No DOI found

Institutionalizing the intangible through research and engagement: Indigenous knowledge and higher education for sustainable development in Zambia - Mbah, Marcellus; Johnson, Ane Turner; Chipindi, Ferdinand M. (International Journal of Educational Development, 2021)
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2021.102355 5072953:7BN57V53 openalex: W3126269799
Keywords: C:Zambia; _z:class:countries; _z:class:themes; oa:keyword:indigenous knowledge; oa:sdg:4 Quality education; oa:topic:T11300 Global Governance in Education Policy Research; oa:topic:T12160 Decolonizing Education in African Context; oa:topic:T14207 Students and Staff as Partners in Higher Education; openalex:n:1; openalex:yes

The Car-free Livability Programme, Oslo - Minja, Michael (Urban planning for transitions, 2021)
More than half of the global population lives in cities, thus forcing cities to expand in order to accommodate the huge populations. Unfortunately, this urban growth has been suggested as a major cause for the majority of harmful emissions that pose a big threat to resources and the environment. With this in mind, it is important for cities to “grow” smartly, ensuring that city growth does not come in the way of the livelihood and well-being of the future generations. The city of Oslo, Norway, realized this and came up with a number of transformative urban projects that ended up being quite successful. The European Green Capital of 2019 started by effectuating the climate and energy strategy in 2016 (European Union et al. 2018).
KerkoCite.ItemAlsoKnownAs: 5072953:VG5S6G52
Keywords: C:Norway; _z:class:countries; _z:class:themes

The Car-free Livability Programme, Oslo - Minja, Michael (Urban planning for transitions, 2021)
More than half of the global population lives in cities, thus forcing cities to expand in order to accommodate the huge populations. Unfortunately, this urban growth has been suggested as a major cause for the majority of harmful emissions that pose a big threat to resources and the environment. With this in mind, it is important for cities to “grow” smartly, ensuring that city growth does not come in the way of the livelihood and well-being of the future generations. The city of Oslo, Norway, realized this and came up with a number of transformative urban projects that ended up being quite successful. The European Green Capital of 2019 started by effectuating the climate and energy strategy in 2016 (European Union et al. 2018).
KerkoCite.ItemAlsoKnownAs: 5072953:VG5S6G52
Keywords: _z:class:countries; _z:class:themes

Evaluating the perception of thermal environment in naturally ventilated schools in a warm and humid climate in Nigeria - Munonye, C.; Ji, Y. (Building Services Engineering Research and Technology, 2021)
Keywords: evidence_review_2

A comprehensive assessment of climate change threats and adaptation of nature based tourism in Zimbabwe - Mushawemhuka, William J (University of Johannesburg, 2021)
KerkoCite.ItemAlsoKnownAs: 5072953:DWJYZZ42 5072953:W8DLFUGV

Modeling the Heat Flow Dynamics of a Houses Using Stochastic Differential Equations - Nardone, Pablo Sabino Mayo (2021)
KerkoCite.ItemAlsoKnownAs: 5072953:UIXBQB6E
Keywords: _z:class:countries; _z:class:themes; ⛔ No DOI found

Global Issues: Climate Change - Nations, United (2021)

A Literature Review of the Impacts of Heat Stress on Human Health across Africa - Ncongwane, Katlego P.; Botai, Joel O.; Sivakumar, Venkataraman; Botai, Christina M. (Sustainability, 2021)
Heat stress-related illness attributed to the changing climate, particularly the more frequent extreme high temperatures, is becoming a theme of public concern, especially in the most vulnerable regions, such as the African continent. Knowledge of the existing research directions and gaps on heat stress and human health is vital for informing future strategic research foci capable of influencing policy development, planning, adaptation, and mitigation efforts. In this regard, a bibliometric analysis was conducted, with an emphasis on Africa, to assess regional research contributions to heat stress impacts on human health. The goals of the study were to review publication growth and patterns of the scientific publications and to identify key players (especially collaborating institutions and countries) and the evolution of research themes on the African continent, while paying attention to global trends and emergent hot topics and methodology of heat stress research. Using the Web of Science (WoS) and Scopus core collection databases, a structured keyword search was undertaken, which yielded 463 and 58 research publications from around the world and Africa, respectively. The retrieved scientific documents, published between 1968 and 2020, were analyzed and visualized using a bibliometric analysis technique and the VOSviewer software tool. The results indicate low statistics and slow scientific growth in publication output, with the highest peak having been reached in 2018, resulting in 13 scientific publications. While global research collaborations are successfully reflected in the literature, there is a considerable gap in understanding heat stress and related collaborations between African countries and international institutions. The review study has identified key opportunities that can benefit Africa through the expansion of the scope of heat stress and human health research on the continent. These opportunities can be achieved by closing the following research gaps: (1) vulnerability assessments within demographic classes, such as the elderly, (2) personal exposure and associated risks, (3) Urban Heat Island (UHI) evaluation for urban environments, and (4) heat adaptation research, which will enable informed and targeted preventive actions that will limit future heat health impacts. The authors opine that the pursuit of such studies will be most impactful if the current knowledge gaps are bridged through transdisciplinary research supported by local, regional, and international collaborators.
KerkoCite.ItemAlsoKnownAs: 10.3390/su13095312 2129771:CPYLA39E 4682641:B7NBEQHK 5072953:3LDA7CRE openalex: W3162290498
Keywords: BE:LMIC; BE:RELEVANT; _z:class:countries; _z:class:themes; evidence_review; oa:keyword:heat stress; oa:topic:T10190 Health Effects of Air Pollution; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11244 Impact of Climate Change on Human Health; openalex:n:1; openalex:yes; type:literature review

Urban Household Energy Use: Analyzing Correlates of Charcoal and Firewood Consumption in Kampala City, Uganda - Nzabona, A. (Journal of Environmental and Public Health, 2021)
KerkoCite.ItemAlsoKnownAs: 5072953:36D6ATT6 5072953:A23NES8L

Reducing cooling demands in Sub-Saharan Africa: A study on the thermal performance of passive cooling methods in enclosed spaces - Olawale-Johnson, O.P.; Ajwang, P.; Ondimu, S.N. (Journal of Sustainable Development of Energy, Water and Environment Systems, 2021)

State of the Global Climate 2020 - Organization, World Meteorological (2021)

Effect of the orientation on the comfort of a building made with compressed earth block - Oumarou, F.; Ouedraogo, A.; Ky, S.; Bhandari, R.; Konfe, A.; Konate, R.; Adamou, R.; Bathiebo, D.; Kam, S. (Smart Grid and Renewable Energy, 2021)
Keywords: _z:class:countries

Gender and participation in community based adaptation: Evidence from the decentralized climate funds project in Senegal - Patnaik, Hannah (Akanksha) (World Development, 2021)
Efforts to promote inclusive participation in community-based adaptation projects highlight the importance of giving those most vulnerable to climate change a voice. This paper explores the involvement and inclusion of women in participatory spaces in the Decentralized Climate Funds pilot project in Senegal to evaluate whether only the voices and demands of the powerful and vocal few were raised and heard. Using semi-structured interviews and focus group discussions, the paper explores and analyzes the factors motivating and constraining women’s active and empowered meaningful participation. The findings reveal that women in the Kaffrine region of Senegal experienced different levels of participation in community decision-making, ranging from nominal and passive participation to active and substantive participation. Results highlight that women’s social capital and networks, community-level recognition of women’s role in income generation, and favorable intrahousehold power dynamics were instrumental in encouraging active and empowered participation. The paper finds that the community-based adaptation approach of devolving decision-making to the community level is by itself not sufficient to ensure that women can meaningfully access the participatory process. Future community-based adaptation initiatives can improve their approach and ensure that women are able to voice their needs by understanding the local gender dynamics and designing projects to acknowledge and work within those dynamics.
KerkoCite.ItemAlsoKnownAs: 5072953:D9EMDV2F 5072953:QTPMNRWX 5072953:RZPSD962
Keywords: Africa; Climate change; Community based adaptation; Gender; Participation; Senegal; _z:class:countries

Elementary Classroom Teachers’ Perceptions of Redesigned Classroom Space: A Qualitative Case Study - Pender, Kristin Lee (Old Dominion University, 2021)
KerkoCite.ItemAlsoKnownAs: 2129771:I3X8WJ6T 4682641:6ZUFWNZP 5072953:USBZMH77
Keywords: BE:RELEVANT; _z:class:countries; _z:class:themes

Determinação de zonas de conforto térmico por meio da análise comparativa entre diferentes métodos de caraterização de pessoas termicamente insatisfeitas - Pereira, Pedro Filipe da Conceição (Universidade Tecnológica Federal do Paraná, 2021)
KerkoCite.ItemAlsoKnownAs: 2129771:3MZIVCVE 4682641:UH5YGU22 5072953:ZE3KYXDF
Keywords: BE:LMIC; BE:RELEVANT; _z:class:countries; _z:class:themes

Indoor temperature variability in the Sahel: a pilot study in Ouagadougou, Burkina Faso - Pohl, Benjamin; Dos Santos, Stéphanie; Bai, Guy Martial; Compaoré, Yacouba; Dianou, Kassoum; Diallo-Dudek, Julita; Soura, Abdramane; Janicot, Serge (Theoretical and Applied Climatology, 2021)
Very little research has documented the exposure of populations in Africa to extreme heat. We measured indoor air temperature and humidity hourly for 13 months in seven houses of contrasted architecture and construction materials all in the northern neighbourhoods of Ouagadougou, Burkina Faso. These measurements are compared to air temperatures recorded at the synoptic weather station of Ouagadougou airport and to land surface temperature estimates from Landsat satellite images at seven dates with clear-sky conditions. The results reveal huge temperature differences (exceeding 10 °C) between houses, especially in the afternoon hours of the warmest season. Indoor temperature is also much more variable than land surface (outdoor) temperature in the same locations, as estimated by satellite imagery. Houses with greater thermal inertia smooth the afternoon temperature peak, reducing heat exposure. Heat stress bioindicators reveal that danger thresholds, while rarely reached in some houses, are frequently exceeded in others year round except for the core of the cold winter season (December and January). In spring, the hottest season, the danger threshold is almost permanently exceeded in these dwellings, exposing their inhabitants to significant heat stress. This pilot study shows the primary role of housing in modulating indoor temperature, raising questions of public health and habitability of Sahelian regions in a warming world. This issue will be of increasing importance with ongoing climate change, hence the need for further, more detailed instrumented campaigns in African settlements. Highlights. 1. Indoor temperatures vary tremendously between houses. 2. Contrasts between houses are greatest in the hottest hours of the warm season. 3. Thermal danger or extreme danger levels are often exceeded in some houses. 4. In some houses, heat stress may occur in all seasons except winter. 5. More instrumented campaigns for heat stress in African housing are needed.
openalex: W3202114744 KerkoCite.ItemAlsoKnownAs: 5072953:6KBZIG5K 5072953:EVZQ7HRI 5072953:V549NETZ
Keywords: C:Burkina Faso; _z:class:countries; _z:class:themes; oa:keyword:indoor temperature variability; oa:topic:T10190 Health Effects of Air Pollution; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11244 Impact of Climate Change on Human Health; openalex:n:1; openalex:yes

PM speech at the Global Education Summit - Prime Minister's Office, 10 Downing Street (2021)
Keywords: _z:class:countries

Adaptation Gap Report 2021: The gathering storm – Adapting to climate change in a post-pandemic world - Programme, United Nations Environment (2021)
Place: Nairobi
Keywords: _z:class:countries

Classroom Temperature and Learner Absenteeism in Public Primary Schools in the Eastern Cape, South Africa - Pule, Vicky; Mathee, Angela; Melariri, Paula; Kapwata, Thandi; Abdelatif, Nada; Balakrishna, Yusentha; Kunene, Zamantimande; Mogotsi, Mirriam; Wernecke, Bianca; Wright, Caradee Yael (International Journal of Environmental Research and Public Health, 2021)
Children spend a significant proportion of their time at school and in school buildings. A healthy learning environment that supports children should be thermally conducive for learning and working. Here, we aimed to study the relations between indoor classroom temperatures and learner absenteeism as a proxy for children’s health and well-being. This one-year prospective study that spanned two calendar years (from June 2017 to May 2018) entailed measurement of indoor classroom temperature and relative humidity, calculated as apparent temperature (Tapp) and collection of daily absenteeism records for each classroom in schools in and around King Williams Town, Eastern Cape province, South Africa. Classroom characteristics were collected using a standardized observation checklist. Mean indoor classroom temperature ranged from 11 to 30 °C, while mean outdoor temperature ranged from 6 °C to 31 °C during the sample period. Indoor classroom temperatures typically exceeded outdoor temperatures by 5 °C for 90% of the study period. While multiple factors may influence absenteeism, we found absenteeism was highest at low indoor classroom Tapp (i.e., below 15 °C). Absenteeism decreased as indoor Tapp increased to about 25 °C before showing another increase in absenteeism. Classroom characteristics differed among schools. Analyses of indoor classroom temperature and absenteeism in relation to classroom characteristics showed few statistically significant relations—although not exceptionally strong ones—likely because of the multiple factors that influence absenteeism. However, given the possible relationship between indoor temperature and absenteeism, there is a learning imperative to consider thermal comfort as a fundamental element of school planning and design. Furthermore, additional research on factors besides temperature that affect learner absenteeism is needed, especially in rural areas.
Number: 20 openalex: W3207347323 KerkoCite.ItemAlsoKnownAs: 10.3390/ijerph182010700 2129771:5X34U8BJ 4682641:BHIB2K49 4682641:DIRGNF86 4682641:FCN58JLB 4682641:H9CT2TIJ 4682641:K5QU8QEA 4874017:WFPCZWL8 5072953:IC9R6Y43 5072953:KPVDHIJ7 5072953:UPD3ISR5 5072953:WIW44WHA
Keywords: BE:LMIC; BE:RELEVANT; C:South Africa; _z:class:countries; _z:class:themes; climate change; cold; environmental health; evidence_review; heat; humidity; oa:keyword:learner absenteeism; oa:sdg:11 Sustainable cities and communities; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10692 Impact of Urban Green Space on Public Health; oa:topic:T11244 Impact of Climate Change on Human Health; openalex:n:1; openalex:yes; public health; schoolchildren; selected_for:effects of climate ch...on learning...LMICs 2024

Environmental Factors that Affect the Academic Performance of Senior High School Students during COVID-19 Pandemic - Ragpala, Eric (International Journal of Social Sciences: Current and Future Research Trends, 2021)
The COVID-19 pandemic affected several countries' educational systems, particularly on platforms for teaching and learning. One of the countries that have shifted its educational environment to an online and modular learning modality is the Philippines. As a result, several researchers conducted a study into the various factors that have been linked to student academic performance. This study focused on the environmental factors that affected senior high school student's academic performance during the COVID-19 pandemic. Thematization was employed in this study that highlighted the qualitative approaches in the determination of the environmental factors faced by the senior high school students in their online classes and their coping mechanisms. In this study, online learning experience during the COVID-19 pandemic, quality of education amidst pandemic, environmental factors, academic performance, and coping mechanisms are the themes that were developed based on the respondent's answers. This study used purposive sampling in selecting the respondents that helped the researcher focus on the students' specific traits that are of interest. The environmental factors that were found out are noise, temperature, light, and air quality in respondents’ study area. The researcher also found out other factors that affect the academic performance of the respondents aside from the environmental factors mentioned, such as family, peers, teachers, online games, social media, time, internet connection, health condition, and attitude towards learning.
KerkoCite.ItemAlsoKnownAs: 2129771:RMIDK8QY 4682641:MQQMTVXV 5072953:YJS8ZA77
Keywords: BE:RELEVANT; _z:class:countries; _z:class:themes; evidence_review_2; ⛔ No DOI found

Use of machine learning methods for indoor temperature forecasting - Ramadan, Lara; Shahrour, Isam; Mroueh, Hussein; Chehade, Fadi Hage (Future Internet, 2021)
KerkoCite.ItemAlsoKnownAs: 10.3390/fi13100242 5072953:EY94UDFB openalex: W3199674863
Keywords: _z:class:countries; _z:class:themes; oa:keyword:machine learning; oa:keyword:machine learning methods; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; oa:topic:T12981 Impact of Climate Change on Cultural Heritage Conservation; openalex:n:1; openalex:yes

Does inequality-adjusted human development reduce the impact of natural disasters? A gendered perspective - Roy Chowdhury, Joyita; Parida, Yashobanta; Agarwal Goel, Prarthna (World Development, 2021)
This paper examines how inequality-adjusted human development (IHD) helps minimize male and female flood fatalities across 19 Indian states between 1983 and 2013. We investigate if a higher achievement in the IHD index has affected male and female flood deaths differently while controlling for direct spending on disaster adaptation measures and socio-political factors. The empirical results suggest that Indian states with better IHDI score experience lower flood fatalities in aggregate. A 10% increase in IHDI at the sample mean results in the probability of 38 fewer total deaths from floods. Furthermore, we find a gender-differentiated impact of disasters as males suffer fewer flood fatalities than females with a rise in IHDI. The findings suggest that an additional 10% increase in IHDI at the sample mean results in the probability of 26 fewer male deaths from floods, and the same 10% rise in IHDI shows the probability of 12 fewer female deaths due to floods. Women’s involvement in social, political, and economic decision-making measured through women’s participation in voting in elections, grant them access to flood mitigation and aversion measures, which can reduce the impact of a disaster. However, the current participation rate is not adequate to reduce female flood mortality substantially. Women’s socially constructed responsibilities impose constraints on their participation in activities outside the household, including their mobility to the non-agricultural sector, and therefore, reduce access to warning information, which can increase vulnerability to disasters.
KerkoCite.ItemAlsoKnownAs: 5072953:6L5CVRB6 5072953:DAHZ8DBA 5072953:YFILV8HP
Keywords: Gender budgeting; Gender-wise flood fatalities; Human development; Negative binomial estimate; Women’s participation in electoral process; _z:class:countries

Girl child marriage in Malda district of West Bengal: analysis of prevalence and socio-economic factors - Roy, A.; Chouhan, P. (Vulnerable Children and Youth Studies, 2021)
KerkoCite.ItemAlsoKnownAs: 5072953:22DV6C74 5072953:5HEKACJA
Keywords: _z:class:countries

Socio-economic-and Gender-based Differentials in Choice of Sustainable Mode of Transport: Evidence from Jaipur, India - Saigal, T. (Millennial Asia, 2021)
KerkoCite.ItemAlsoKnownAs: 5072953:LAYR6HQ6 5072953:Q4E6EIBW
Keywords: _z:class:countries

The effects on public health of climate change adaptation responses: a systematic review of evidence from low-and middle-income countries - Scheelbeek, Pauline FD; Dangour, Alan D.; Jarmul, Stephanie; Turner, Grace; Sietsma, Anne J.; Minx, Jan C.; Callaghan, Max; Ajibade, Idowu; Austin, Stephanie E.; Biesbroek, Robbert (Environmental Research Letters, 2021)
Keywords: _z:class:countries

Indoor Air Quality and Overheating in UK Classrooms–an Archetype Stock Modelling Approach - Schwartz, Y.; Korolija, I.; Symonds, P.; Godoy-Shimizu, D.; Dong, J.; Hong, S. M.; Mavrogianni, A.; Grassie, D.; Mumovic, D. (Journal of Physics: Conference Series, 2021)
Abstract. Children spend a large part of their waking lives in school buildings. There is substantial evidence that poor indoor air quality (IAQ) and thermal discomfort can have detrimental impacts on the performance, wellbeing and health of schoolchildren and staff. Maintaining good IAQ while avoiding overheating in classrooms is challenging due to the unique occupancy patterns and heat properties of schools. Building stock modelling has been extensively used in recent years to quantify and evaluate performance of large numbers of buildings at various scales. This paper builds on an archetype stock modelling approach which represents the diversity of the school stock in England through an analysis of The Property Data Survey Programme (PDSP) and the Display Energy Certificates (DEC) databases. The model was used for simulating Indoor-to-Outdoor pollution ratios to estimate indoor air pollution levels (NO2, PM2.5 and CO2) and thermal comfort (overheating) in two climate areas in England: London and the West Pennines. analysis highlighted variations in classrooms’ indoor CO2 levels in different seasons and explored the risk of overheating in relation to a classroom’s orientation.
KerkoCite.ItemAlsoKnownAs: 10.1088/1742-6596/2069/1/012175 2129771:MKP2LJW2 4682641:MIIGV4GG 5072953:MSWX3I9R openalex: W4200047592
Keywords: BE:RELEVANT; _z:class:countries; _z:class:themes; evidence_review_2; oa:sdg:13 Climate action; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10190 Health Effects of Air Pollution; oa:topic:T11002 Indoor Air Quality and Health Effects; openalex:n:1; openalex:yes

The whitest paint is here – and it’s the coolest. Literally. - Service, Purdue News (2021)
In an effort to curb global warming, Purdue University engineers have created the whitest paint yet. Coating buildings with this paint may one day cool them off enough to reduce the need for air conditioning, the researchers say.
KerkoCite.ItemAlsoKnownAs: 4874017:YXG8TZ8M 5072953:BVC42IJX
Keywords: _z:class:countries; _z:class:themes

Education, Girls’ Education and Climate Change - Sims, K. (Institute of Development Studies, 2021)
This Emerging Issue Report (EIR) explores research and evidence on the relationship between education, girls’ education and climate change. There is scientific consensus that climate change is real, manifested through increasing temperatures, changing rainfall patterns and increasing frequency and severity of extreme weather events, including drought, flooding and cyclones (IPCC, 2012, 2014). Climate change, environmental degradation and climate vulnerability are closely linked (IPCC, 2019). Climate change exacerbates environmental and land degradation, especially in areas with drylands and permafrost, river deltas and low-lying coastal areas. There is high confidence that people living in areas affected by environmental degradation are experiencing an increase in the negative effects of climate change (IPCC, 2019). Gender, alongside other drivers of vulnerability and exclusion, is a key determinant of an individual’s vulnerability to the effects of climate change and environmental degradation, and influences how climate change is experienced (Kwauk et al., 2019; Vincent et al., 2014; Muttarak & Lutz, 2014). It is estimated that at least 200 million adolescent girls living in the poorest communities face heightened risk from the effects of climate change (Atkinson & Bruce, 2015). Although this report refers to women and girls throughout, it is important that they are not seen as a homogenous group due to a range of factors that influence identity, including poverty, age, ethnicity, disability, socioeconomic status, geographic location and HIV status, among others (Plan International, 2011; Djoudi et al., 2016). In addition, as this report highlights, women and girls should not be seen as passive victims of climate change, as this can obscure their role as powerful agents of change and may cause misinterpretation of the causes of vulnerability (Ravera et al., 2016). Extreme weather events, such as floods and tropical cyclones, can disrupt learning in a variety of ways. The direct and immediate impacts of extreme weather include damage and/or destruction to education infrastructure; however, indirect and secondary impacts can last much longer (Kousky, 2016; Anderson, 2019). These include, but are not limited to: damage to road and transport links, obstructing access to school and learning; adolescent girls’ unwillingness to attend school if water, sanitation and hygiene (WASH) facilities are not quickly rehabilitated; inability to pay for school fees and/or learning materials; displacement of families; and reduced capacity for learning because of malnutrition or trauma (Kousky, 2016; Anderson, 2019; Nordstrom & Cotton, 2020; Chuang et al., 2018; Siriwardhana et al., 2013). Evidence and commentary on the role of education, and girls’ education, to address climate change through adaptation, resilience and mitigation is limited, albeit growing. This EIR identifies and summarises evidence and key commentary around the following themes: 1. Links between education, particularly girls’ education, and climate change. 2. How climate and environment matter for achieving gender equality. 3. Why securing girls’ education is an important strategy in addressing climate change. The EIR draws on academic research and literature from low- and middle-income countries (LMICs), as well as policy frameworks and grey literature, media articles and blogs from the climate, education and gender fields.
KerkoCite.ItemAlsoKnownAs: 2129771:AU3XTA3Z 2129771:AU3XTA3Z 2129771:AU3XTA3Z 2129771:AU3XTA3Z 10.19088/K4D.2021.044 5072953:45CF3YPF 5072953:LM8B7YHS 5072953:X9VHZB7F 5440726:NJMR8MNX 5440726:VNV4WHGJ
Keywords: _z:class:countries; evidence_review_2

What are the Characteristics of Effective Teacher Professional Development? A Systematic Review and Meta-analysis - Sims, Sam; Fletcher-Wood, Harry; O’Mara, Alison; Cottingham, Sarah; Stansfield, Claire; Herwegen, Jo Van; Anders, Jake (2021)
KerkoCite.ItemAlsoKnownAs: 2129771:AYEFPSZ4 2486141:MD6F4TDU
Keywords: evidence_review; ⛔ No DOI found

The impact of Traffic-Related air pollution on child and adolescent academic Performance: A systematic review - Stenson, Chloe; Wheeler, Amanda J.; Carver, Alison; Donaire-Gonzalez, David; Alvarado-Molina, Miguel; Nieuwenhuijsen, Mark; Tham, Rachel (Environment International, 2021)
Background: The negative health impacts of traffic-related air pollution (TRAP) have been investigated for many decades, however, less attention has been paid to the effect of TRAP on children’s academic performance. Understanding the TRAP-academic performance relationship will assist in identifying mechanisms for improving students’ learning and aid policy makers in developing guidance for protecting children in school environments. Methods: This systematic review assessed the relationship between TRAP and academic performance. Web of Science, PubMed, CINAHL, Medline, PsycINFO, SPORTDiscus, Scopus and ERIC databases were searched for relevant, peer reviewed, articles published in English. Articles assessing exposure to TRAP pollutants (through direct measurement, local air quality monitoring, modelling, or road proximity/density proxy measures) and academic performance (using standardised tests) in children and adolescents were included. Risk of bias was assessed within and between studies. Results: Of 3519 search results, 10 relevant articles were included. Nine studies reported that increased exposure to some TRAP was associated with poorer student academic performance. Study methodologies were highly heterogeneous and no consistent patterns of association between specific pollutants, age groups, learning domains, exposure windows, and exposure locations were established. There was a serious risk of bias within individual studies and confidence in the body of evidence was low. Conclusions: This review found evidence suggestive of a negative association between TRAP and academic performance. However, the quality of this evidence was low. The existing body of literature is small, lacks the inclusion of high-quality exposure measures, and presents limitations in reporting. Future research should focus on using valid and reliable exposure measures, individual-level data, consistent controlling for confounders and longitudinal study designs.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.envint.2021.106696 2129771:GL638AF5 4682641:45BNHEVW 5072953:W52PT62V openalex: W3171995484
Keywords: BE:RELEVANT; _z:class:countries; _z:class:themes; evidence_review; oa:keyword:air pollution; oa:topic:T10190 Health Effects of Air Pollution; oa:topic:T10298 Influence of Built Environment on Active Travel; oa:topic:T11692 Effects of Noise Pollution on Health and Well-being; openalex:n:1; openalex:yes

Development of a tool to predict the socio-economic consequences of better air quality and temperature control in classrooms - Toftum, Jørn; Andersen, Rune; Prado, Jose Joaquin Aguilera; Kolstrup, Kristian; Hauberg, Daniel Sloth; Clausen, Geo (Energy and Buildings, 2021)
A simplified modelling framework for the prediction of the indoor environment, energy use and socioeconomic consequences of improving air quality and temperature in school buildings is suggested. The framework combines established models for infiltration and different modes of ventilation to estimate yearly distributions of the classroom temperature and CO2 concentration. These distributions are used as input to a prediction of pupil performance of schoolwork, their attendance at school, and teacher absence before and after refurbishment of their school building. Eventually, the framework estimates the socio-economic consequences of an improved classroom environment for a school and may be used to evaluate the feasibility of a range of different refurbishment scenarios and support decisions on building upgrades.
KerkoCite.ItemAlsoKnownAs: 4874017:ISJ2C8JL 4874017:ISJ2C8JL 10.1016/j.enbuild.2021.111274 2129771:FFN373CD 4682641:ISVXWBRE 5072953:4TCCGC4P openalex: W3177784809
Keywords: BE:RELEVANT; _z:class:countries; _z:class:themes; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11002 Indoor Air Quality and Health Effects; oa:topic:T11692 Effects of Noise Pollution on Health and Well-being; openalex:n:1; openalex:yes

How physical and built environments impact learning and inclusivity in educational settings: supporting evidence-based practice - Twiss, Trisha Ann (Electronic version published by Vancouver Island University, 2021)
KerkoCite.ItemAlsoKnownAs: 2129771:TRUKBTF6 4682641:FKZDRNG7 5072953:58EPSPUK
Keywords: BE:RELEVANT; _z:class:countries; _z:class:themes

Climate education in the spotlight at COP26: Ministers of Education and Environment meet for historic event - U.N.E.S.C.O. (2021)
Keywords: _z:class:countries

Co-Chairs Conclusions of Education and Environment Minister Summit at COP 26 - UKCOP26 (2021)
Keywords: _z:class:countries

Measuring Particle Concentration and Compositions in Indoor Air - Wallace, Lance; Hopke, Philip (Handbook of Indoor Air Quality, 2021)
Keywords: _z:class:countries

Effects of Classroom Air Quality on Learning in Schools - Wargocki, Pawel (Handbook of Indoor Air Quality, 2021)
This chapter describes the evidence of the effects of indoor air quality (IAQ) on learning of children and gives an overview of the size of the effects expected. The results from the published experiments on the effects of classroom air quality on the performance of schoolwork do confirm that these effects are systematic and show that improving classroom air quality will have a significant positive effect on some aspects of learning, both on cognitive skills and academic attainment, as well as academic achievements and absence rates. Present studies show that to ensure classroom IAQ conducive to learning, CO2 levels (indicating the adequacy of ventilation) should be kept below 900 ppm at all times. It should be ensured that windows can be opened when needed, to improve classroom IAQ, and CO2 sensors should be installed to indicate when windows must be open (or any other measure to improve IAQ must be executed) if the CO2 concentration is too high and when they should be closed to conserve energy.
openalex: W4200277480 openalex: W4312958035 KerkoCite.ItemAlsoKnownAs: 10.1007/978-981-10-5155-5_65-1 2129771:AVPCAPN4 4682641:8UQUYEVQ 4682641:A8NCT2AH 5072953:6A8CWS5D 5072953:9CRAFA2J
Keywords: Absence rate; BE:RELEVANT; Carbon dioxide; Learning; Schools; Sleep; Ventilation; _important; _z:class:countries; _z:class:themes; _z:no_pdf; evidence_review; openalex:n:2; openalex:yes

TAIL, a new scheme for rating indoor environmental quality in offices and hotels undergoing deep energy renovation (EU ALDREN project) - Wargocki, Pawel; Wei, Wenjuan; Bendžalová, Jana; Espigares-Correa, Carlos; Gerard, Christophe; Greslou, Olivier; Rivallain, Mathieu; Sesana, Marta Maria; Olesen, Bjarne W.; Zirngibl, Johann (Energy and Buildings, 2021)
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2021.111029 2129771:RVZSGIX6 4682641:38G9B7P7 4682641:BQSLQ2B9 5072953:ZZYGKPJ6 openalex: W3154483935
Keywords: BE:RELEVANT; _z:class:countries; _z:class:themes; oa:keyword:indoor environmental quality; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11002 Indoor Air Quality and Health Effects; oa:topic:T11692 Effects of Noise Pollution on Health and Well-being; openalex:n:1; openalex:yes

Comparative analysis of user comfort and thermal performance of six types of vernacular dwellings as the first step towards climate resilient, sustainable and bioclimatic architecture in western sub-Saharan Africa - Widera, B. (Renewable and Sustainable Energy Reviews, 2021)
Keywords: _z:class:countries

Major climate change-induced risks to human health in South Africa - Wright, Caradee Y.; Kapwata, Thandi; Du Preez, David Jean; Wernecke, Bianca; Garland, Rebecca M.; Nkosi, Vusumuzi; Landman, Willem A.; Dyson, Liesl; Norval, Mary (Environmental Research, 2021)
KerkoCite.ItemAlsoKnownAs: 10.1016/j.envres.2021.110973 2129771:7N28Q6TR 4682641:GYSLWDGI 5072953:HQAX6KR7 openalex: W3135830796
Keywords: BE:LMIC; BE:RELEVANT; C:South Africa; _z:class:countries; _z:class:themes; oa:topic:T10190 Health Effects of Air Pollution; oa:topic:T11244 Impact of Climate Change on Human Health; openalex:n:1; openalex:yes

Optimising thermostat settings in school and office buildings for thermal comfort, cognitive performance and energy efficiency - Wyon, David P.; Wargocki, Pawel (2021)
KerkoCite.ItemAlsoKnownAs: 2129771:SP7WSIUB 4682641:RUCTJFP3 5072953:7YB3LXT5
Keywords: BE:RELEVANT; _z:class:countries; _z:class:themes; evidence_review_2; ⛔ No DOI found

Temperature-dependent ventilation rates might improve perceived air quality in a demand-controlled ventilation strategy - Yang, Aileen; Holøs, Sverre B.; Resvoll, Marie Opsahl; Mysen, Mads; Fjellheim, Øystein (Building and Environment, 2021)
KerkoCite.ItemAlsoKnownAs: 10.1016/j.buildenv.2021.108180 2129771:F32ZPKJT 4682641:5Y534ZQZ 5072953:TZAIQZVQ openalex: W3183877988
Keywords: BE:RELEVANT; _z:class:countries; _z:class:themes; oa:keyword:air quality; oa:keyword:ventilation; oa:sdg:13 Climate action; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11002 Indoor Air Quality and Health Effects; oa:topic:T11244 Impact of Climate Change on Human Health; openalex:n:1; openalex:yes

Handbook of Indoor Air Quality - Zhang, Yinping; Hopke, Philip K.; Mandin, Corinne (Springer Singapore, 2021)
openalex: W4312443761 openalex: W4236256155
Keywords: _z:class:countries; _z:no_pdf; openalex:n:2; openalex:yes

A study on the prediction of thermal comfort for residuals using LSTM deep learning model - Ho, Jongnam; Cho, Jaeyoun; Shin, Hyunkyu; Lee, Joosung; Kim, Woojae; Ahn, Yonghan (International Journal of Sustainable Building Technology and Urban Development, 2020)
KerkoCite.ItemAlsoKnownAs: 10.22712/susb.20200017 5072953:8XEFB4TS openalex: W3131632464
Keywords: _important; _z:class:countries; _z:class:themes; oa:keyword:thermal comfort; oa:topic:T14156 Structural Analysis and Design Optimization in Engineering; openalex:n:1; openalex:yes; selected_for:Predictive models for classroom conditions 2024

Knowledge of Health Impact of Climate Change and Practice of Preventive Measures among Students of a Nigerian Tertiary Institution - Nzeobi, J. R.; Chineke, H. N.; Ubajaka, Chika Florence; Adogu, Prosper O. U. (Asian Journal of Environment & Ecology, 2020)
Background: Every century has its own public health challenge. Climate change is the present century's challenge. There are various health risks arising from climate change which without mitigation actions, will tend to worsen with each passing day.
Study Aim and Objective: To study the knowledge of health impact of climate change and practice of appropriate preventive measures among students of a Nigerian Tertiary Institution
Methodology: A descriptive cross-sectional survey was carried out using structured questionnaires. These questionnaires were shared randomly among students from five selected departments in the college of health science and data was analyzed using SPSS Version 20.0
Results: It was found that all the students were aware of climate change and 91.7% knew about the effect of climate change on health. Significantly 78.7% believed that climate change was from man-made causes but surprisingly only 34.3% were taking actions in mitigating the effect of climate change.
Conclusion: Despite the high knowledge about climate change, majority of actions taken by the students were just for convenience and to save money, not necessarily because they wanted to prevent the effects of climate change on health.
Recommendation: Government and Non-governmental organizations should form advocacy clubs for young students as a platform to sensitize them on climate change and its effects. There is need to introduce rewards and sponsorships for individuals who successfully learn about climate change and ways to mitigate its effect on health.
openalex:W3114132889 mag:3114132889 KerkoCite.ItemAlsoKnownAs: 10.9734/ajee/2020/v13i430193 5072953:SIHWT9FR
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T11244 Impact of Climate Change on Human Health; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

The Rights of Persons with Disabilities in the Context of the Un Framework Convention on Climate Change (Human Rights Documents Online, 2020)
openalex: W4237993431
Keywords: _z:class:countries; openalex:import; openalex:yes

How can New Zealand schools respond to climate change? - Bolstad, Rachel (2020)
International climate agreements say education can play a key role in responding to the global challenge of climate change. My team and I are currently carrying out research to help build a national picture of educational responses to climate change. Our research suggests that New Zealand’s educational policies and strategies currently provide a diffuse framework for responding to climate change, and there is a lack of coherent messaging “from the top” about what could or should be expected of schools. Yet some innovative practices and approaches are visible across the school network. This article describes what we currently know about climate and sustainability thinking and practice across English-medium schools, and what further actions and supports may be needed across the system.
openalex: W3114429793 mag: 3114429793
Keywords: C:New Zealand; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:new zealand schools; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11806 Impact of Service-Learning in Higher Education; openalex:import; openalex:yes

How can New Zealand schools respond to climate change? - Bolstad, Rachel (2020)
International climate agreements say education can play a key role in responding to the global challenge of climate change. My team and I are currently carrying out research to help build a national picture of educational responses to climate change. Our research suggests that New Zealand’s educational policies and strategies currently provide a diffuse framework for responding to climate change, and there is a lack of coherent messaging “from the top” about what could or should be expected of schools. Yet some innovative practices and approaches are visible across the school network. This article describes what we currently know about climate and sustainability thinking and practice across English-medium schools, and what further actions and supports may be needed across the system.
openalex: W3114429793 mag: 3114429793
Keywords: C:New Zealand; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:new zealand schools; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11806 Impact of Service-Learning in Higher Education; openalex:import; openalex:yes

Perception and Level of Awareness of Climate Change among Adult Learners on Attendance and Performance in Literacy Centres, Ondo State, Nigeria - Olaniyi, Francis O. (Randwick International of Education and Linguistics Science Journal, 2020)
This study investigated theperception and awareness of climate change among adult learners on attendance and performance in literacy centres in Ondo State, Nigeria. Five research questions were generated for the study. The descriptive research design of the survey type was used for the study involving a population of adult learners in literacy centres in Ondo State, Nigeria. Purposive random sampling technique was used to select a sample size of 100 participants drawn from the entire population of adult learners in literacy centres of Ondo State, Nigeria. A self-constructed questionnaire was used as an instrument for the study. Data collected were analysed using descriptive statistics of frequency counts,percentage and mean deviation were used to answer the research questions raised for the study. Findings revealed that the level of awareness on climate change among adult learners on attendance and performance is very high because they were already aware of climate change and its effects on human existence. Also, adult learners do not perceive climate change as the work of nature alone but as well as the effects of activities of man on the environment. Findings also revealed that that several factors like deforestation, bush burning, air pollution and other man’s activities on the environment such as mining, science and technology among others are the causes of climate change. It is therefore recommended that, information should be disseminated to the people on proper management of the environment. Government should not relent in conducting house to house orientation on how to conserve the environment from the effects of climate change.
openalex:W3115427961 mag:3115427961 KerkoCite.ItemAlsoKnownAs: 10.47175/rielsj.v1i3.136 5072953:G3U2A2AP
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:topic:T13530 Climate Change and Environmental Impact; oa:topic:T14296 Climate Change and Sustainable Development; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Perception and Level of Awareness of Climate Change among Adult Learners on Attendance and Performance in Literacy Centres, Ondo State, Nigeria - Olaniyi, Francis O. (Randwick International of Education and Linguistics Science Journal, 2020)
This study investigated theperception and awareness of climate change among adult learners on attendance and performance in literacy centres in Ondo State, Nigeria. Five research questions were generated for the study. The descriptive research design of the survey type was used for the study involving a population of adult learners in literacy centres in Ondo State, Nigeria. Purposive random sampling technique was used to select a sample size of 100 participants drawn from the entire population of adult learners in literacy centres of Ondo State, Nigeria. A self-constructed questionnaire was used as an instrument for the study. Data collected were analysed using descriptive statistics of frequency counts,percentage and mean deviation were used to answer the research questions raised for the study. Findings revealed that the level of awareness on climate change among adult learners on attendance and performance is very high because they were already aware of climate change and its effects on human existence. Also, adult learners do not perceive climate change as the work of nature alone but as well as the effects of activities of man on the environment. Findings also revealed that that several factors like deforestation, bush burning, air pollution and other man’s activities on the environment such as mining, science and technology among others are the causes of climate change. It is therefore recommended that, information should be disseminated to the people on proper management of the environment. Government should not relent in conducting house to house orientation on how to conserve the environment from the effects of climate change.
openalex:W3115427961 mag:3115427961 KerkoCite.ItemAlsoKnownAs: 10.47175/rielsj.v1i3.136 5072953:G3U2A2AP
Keywords: _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:topic:T13530 Climate Change and Environmental Impact; oa:topic:T14296 Climate Change and Sustainable Development; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Impact of Cognitive Tasks on CO2 and Isoprene Emissions from Humans - Gall, Elliott; Mishra, Asit; Li, Jiayu; Laguerre, Aurélie (Environmental Science & Technology, 2020)
The human body emits a wide range of chemicals, including CO2 and isoprene. To examine the impact of cognitive tasks on human emission rates of CO2 and isoprene, we conducted an across-subject, counterbalanced study in a controlled chamber involving 16 adults. The chamber replicated an office environment. In groups of four, participants engaged in 30 min each of cognitive tasks (stressed activity) and watching nature documentaries (relaxed activity). Measured biomarkers indicated higher stress levels were achieved during the stressed activity. Per-person CO2 emission rates were greater for stressed than relaxed activity (30.3 ± 2.1 vs 27.0 ± 1.7 g/h/p, p = 0.0044, mean ± standard deviation). Isoprene emission rates were also elevated under stressed versus relaxed activity (154 ± 25 μg/h/p vs 116 ± 20 μg/h/p, p = 0.041). The chamber temperature was held constant at 26.2 ± 0.49°C; incidental variation in temperature did not explain the variance in emission rates. Isoprene emission rates increased linearly with salivary α-amylase levels (r 2 = 0.6, p = 0.02). These results imply the possibility of considering cognitive tasks when determining building ventilation rates. They also present the possibility of monitoring indicators of cognitive tasks of occupants through measurement of air quality.

LSTM-based indoor air temperature prediction framework for HVAC systems in smart buildings - Mtibaa, Fatma; Nguyen, Kim-Khoa; Azam, Muhammad; Papachristou, Anastasios; Venne, Jean-Simon; Cheriet, Mohamed (Neural Computing and Applications, 2020)
Accurate indoor air temperature (IAT) predictions for heating, ventilation, and air conditioning (HVAC) systems are challenging, especially for multi-zone building and for different HVAC system types. Moreover, the nonlinearity of the buildings thermal dynamics makes the IAT prediction more difficult since it is affected by complex factors such as controlled and uncontrolled points, outside weather conditions and occupancy schedule. This paper presents a long short-term memory (LSTM) model to predict IAT for multi-zone building based on direct multi-step prediction with sequence-to-sequence approach. Two strategies, LSTM-MISO and LSTM-MIMO, are built for multi-input single-output and multi-input multi-output, respectively. The performance of these two strategies has been evaluated based on two case studies on real smart buildings using variable air volume (VAV) and constant air volume (CAV) systems. For both buildings, experimental results showed that the LSTM models outperform multilayer perceptron models by reducing the prediction error by 50%.
KerkoCite.ItemAlsoKnownAs: 10.1007/s00521-020-04926-3 5072953:SHT4N4QB 5072953:WQTUHTQI openalex: W3021449555
Keywords: CAV; HVAC; LSTM; Multi-step ahead predictions; Sequence-to-sequence; VAV; _important; _z:class:countries; _z:class:themes; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:n:1; openalex:yes; selected_for:Predictive models for classroom conditions 2024

LSTM-based indoor air temperature prediction framework for HVAC systems in smart buildings - Mtibaa, Fatma; Nguyen, Kim-Khoa; Azam, Muhammad; Papachristou, Anastasios; Venne, Jean-Simon; Cheriet, Mohamed (Neural Computing and Applications, 2020)
Accurate indoor air temperature (IAT) predictions for heating, ventilation, and air conditioning (HVAC) systems are challenging, especially for multi-zone building and for different HVAC system types. Moreover, the nonlinearity of the buildings thermal dynamics makes the IAT prediction more difficult since it is affected by complex factors such as controlled and uncontrolled points, outside weather conditions and occupancy schedule. This paper presents a long short-term memory (LSTM) model to predict IAT for multi-zone building based on direct multi-step prediction with sequence-to-sequence approach. Two strategies, LSTM-MISO and LSTM-MIMO, are built for multi-input single-output and multi-input multi-output, respectively. The performance of these two strategies has been evaluated based on two case studies on real smart buildings using variable air volume (VAV) and constant air volume (CAV) systems. For both buildings, experimental results showed that the LSTM models outperform multilayer perceptron models by reducing the prediction error by 50%.
KerkoCite.ItemAlsoKnownAs: 10.1007/s00521-020-04926-3 5072953:SHT4N4QB 5072953:WQTUHTQI openalex: W3021449555
Keywords: CAV; HVAC; LSTM; Multi-step ahead predictions; Sequence-to-sequence; VAV; _important; _z:class:countries; _z:class:themes; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:n:1; openalex:yes; selected_for:Predictive models for classroom conditions 2024

Disability Inclusion in Climate Adaptation and Sustainable Development: A North African good practice - Maaninou, Nouha (2020)
openalex: W3107496812 mag: 3107496812
Keywords: _z:class:countries; openalex:import; openalex:yes

The use of recycled plastics for the design of a thermal resilient emergency shelter prototype - Moreno-Sierra, Andres; Pieschacón, Mauricio; Khan, Ahmed (International Journal of Disaster Risk Reduction, 2020)
Context — More than 200 million people suffer every year natural hazards consequences around the world, sensibly affecting vulnerable populations and resulting on building's partial or total damage. In post-disaster scenarios, it is required to provide the construction of temporary facilities that can be used as shelters or educational spaces, and it is suitable to deliver low cost, fast construction, and site adapted solutions. However, many of these units are built with prefabricated elements brought ‘in situ’, but they cannot be produced locally, and they are frequently not adapted to their environment. Purpose The objective of this research is to increase the understanding of recycled plastics materials in order to develop a resilient prototype using modular elements made of plastic waste, and to measure the thermal comfort efficiency of the construction proposal to evaluate its capacity to adapt to the environment. Design/methodology/approach Based on the preliminary examination of natural hazards impacts on buildings, the study has focused on the recycled plastics materials' literature concerning methods and properties, in order to design a plastic-made emergency shelter module prototype. Dy- namic simulations have been conducted in order to evaluate the module's thermal behavior and its resilience to climatic conditions. Research limitations This research suggests the possibility of implementing a community-based plastic recycling process, depending on a production system that can be established at the emergency site, according to technical specifications summarized in the study. Findings The findings suggest that recycled plastic materials have a high-resilient capacity to face different weather conditions and that they are suitable for the construction of shelter modules. Originality/value The result is an efficient, resilient and thermal comfort adapted module assembly system that can be used as an emergency shelter for housing spaces, schools or health centers’ in a post-disaster reconstruction scenario.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijdrr.2020.101885 4874017:QMI8ADFS 5072953:ERQ74FBZ openalex: W3089232016
Keywords: Emergency shelter; Modular structures; Recycled plastics; Resilient architecture; Sustainability; _z:class:countries; _z:class:themes; oa:keyword:recycled plastics; oa:topic:T10753 Microplastic Pollution in Marine and Terrestrial Environments; openalex:n:1; openalex:yes

Indigenous knowledge on climate change adaptation: a global evidence map of academic literature - Petzold, Jan; Andrews, Nadine; Ford, James D.; Hedemann, Christopher; Postigo, Julio C. (Environmental Research Letters, 2020)
There is emerging evidence of the important role of indigenous knowledge for climate change adaptation. The necessity to consider different knowledge systems in climate change research has been established in the fifth assessment report (AR5) of the Intergovernmental Panel on Climate Change (IPCC). However, gaps in author expertise and inconsistent assessment by the IPCC lead to a regionally heterogeneous and thematically generic coverage of the topic. We conducted a scoping review of peer-reviewed academic literature to support better integration of the existing and emerging research on indigenous knowledge in IPCC assessments. The research question underpinning this scoping review is: How is evidence of indigenous knowledge on climate change adaptation geographically and thematically distributed in the peer-reviewed academic literature? As the first systematic global evidence map of indigenous knowledge in the climate adaptation literature, the study provides an overview of the evidence of indigenous knowledge for adaptation across regions and categorises relevant concepts related to indigenous knowledge and their contexts in the climate change literature across disciplines. The results show knowledge clusters around tropical rural areas, subtropics, drylands, and adaptation through planning and practice and behavioural measures. Knowledge gaps include research in northern and central Africa, northern Asia, South America, Australia, urban areas, and adaptation through capacity building, as well as institutional and psychological adaptation. This review supports the assessment of indigenous knowledge in the IPCC AR6 and also provides a basis for follow-up research, e.g. bibliometric analysis, primary research of underrepresented regions, and review of grey literature.
KerkoCite.ItemAlsoKnownAs: 10.1088/1748-9326/abb330 5072953:SVIGHMEM
Keywords: _z:class:countries

Student-Faculty Research Explores Impacts of Climate Change on Agriculture in Bangladesh - Kohr, Kandace (2020)
A summer student-faculty research project has uncovered an incredible relationship between climate change, agricultural sustainability and the human condition.
openalex: W3106596684 mag: 3106596684
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:2 Zero hunger; oa:topic:T10439 Adaptation to Climate Change in Agriculture; openalex:import; openalex:yes; ⛔ No DOI found

Student-Faculty Research Explores Impacts of Climate Change on Agriculture in Bangladesh - Kohr, Kandace (2020)
A summer student-faculty research project has uncovered an incredible relationship between climate change, agricultural sustainability and the human condition.
openalex: W3106596684 mag: 3106596684
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:2 Zero hunger; oa:topic:T10439 Adaptation to Climate Change in Agriculture; openalex:import; openalex:yes; ⛔ No DOI found

Climate change awareness, environmental education and gender role burdens among rural farmers of Northern Cross River State, Nigeria - Eneji, Chris-Valentine Ogar; Onnoghen, Nkanu Usang; Odama, Joseph; Diwa, Juliana Bebuo (International Journal of Climate Change Strategies and Management, 2020)
Purpose The purpose of this study is to examine the extent of climate change awareness among the rural farmers of Northern Cross River state, investigate the gender role analyzes of some daily routine activities carried out by these rural farmers, ascertain the difference in workload burden of the impacts of climate change between men and women, identify the strategies adopted by these rural farmers to mitigate the effects of climate change in their agricultural activities and investigate the roles Environmental Education (EE) can play in helping the rural farmers to design and adopt sustainable adaptation and mitigation strategies to reduce or completely eradicate their vulnerability to climate change effects. Design/methodology/approach The research design adopted for this study is the cross-sectional survey method. Five research questions guided the study. Two sets of instruments were used for data collection, a sample of 1,258 respondents (0.1%) were selected for the study. The researchers personally administered the instruments and collected the same back, two instruments were not properly filled, so they were rejected. Findings The finding of the study revealed that rural farmers have some level of climate change awareness, which they got from radio, newspapers, awareness campaigns, flyers, billboards, among others. Six out of the nine strategies listed were adopted by the rural farmers to mitigate climate change effects among these rural farmers. There is a significant difference in gender workload burden between women and male in the area, the result is positively skewed toward women, implying that the burden of workload for women increased over those of men. The result also shows that EE can influence their attitude toward climate change through awareness creation, knowledge provisions and also encourage members participation in climate change effect mitigation, prevention and adaptation. Research limitations/implications With this result, EE can be used as a tool for the creation of knowledge, awareness, attitude and encourage the participation of these rural farmers toward mitigating and prevention climate change effects among these rural farmers. It was recommended among others that deliberate policies should be designed to make EE help create the needed awareness on climate change, beginning from the causes, effects and mitigation strategies among rural farmers in their community. Practical implications Already, most Environmental Educators have been trained, the government should design and formulate practical policies to use them as extension agent on climate change effort to go to these rural communities and create the needed awareness, knowledge, skills and attitude to help them combat climate change effects including trees and cover crops planting and also re-introducing the use of irrigation agriculture in these farming communities. Social implications With the creation of awareness, social groups and individuals can also make a social investment from these activities and also improve their social capitals, thereby reducing social burdens and improving their living conditions within the rural settings. Originality/value This research is an original research paper from the effort. the purpose is to assess the extent of climate change awareness level and how the effects of climate change increase or reduces the burden of gender workload among rural farmers and the strategies which can be used by these rural farmers to prevent, mitigate and adapt to climate change effects and the roles EE can play. This study has an original value in the sense that in the course of the study, the study hardly saw articles on these specific variables in whole research, hence the resolve to assess these variables.
openalex:W3192544460 mag:3192544460 KerkoCite.ItemAlsoKnownAs: 10.1108/ijccsm-06-2020-0070 5072953:WBFDINZS
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; oa:keyword:environmental education; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T12503 Social Acceptance of Renewable Energy Innovation; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Application of Machine Learning Techniques to Delineate Homogeneous Climate Zones in River Basins of Pakistan for Hydro-Climatic Change Impact Studies - Nusrat, Ammara; Gabriel, Hamza Farooq; Haider, Sajjad; Ahmad, Shakil; Shahid, Muhammad; Jamal, Saad Ahmed (Applied sciences, 2020)
Climatic data archives, including grid-based remote-sensing and general circulation model (GCM) data, are used to identify future climate change trends. The performances of climate models vary in regions with spatio-temporal climatic heterogeneities because of uncertainties in model equations, anthropogenic forcing or climate variability. Hence, GCMs should be selected from climatically homogeneous zones. This study presents a framework for selecting GCMs and detecting future climate change trends after regionalizing the Indus river sub-basins in three basic steps: (1) regionalization of large river basins, based on spatial climate homogeneities, for four seasons using different machine learning algorithms and daily gridded precipitation data for 1975–2004; (2) selection of GCMs in each homogeneous climate region based on performance to simulate past climate and its temporal distribution pattern; (3) detecting future precipitation change trends using projected data (2006–2099) from the selected model for two future scenarios. The comprehensive framework, subject to some limitations and assumptions, provides divisional boundaries for the climatic zones in the study area, suitable GCMs for climate change impact projections for adaptation studies and spatially mapped precipitation change trend projections for four seasons. Thus, the importance of machine learning techniques for different types of analyses and managing long-term data is highlighted.
openalex: W3090569372 mag: 3090569372
Keywords: C:Pakistan; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10029 Climate Change and Variability Research; oa:topic:T10330 Hydrological Modeling and Water Resource Management; oa:topic:T10466 Numerical Weather Prediction Models; openalex:import; openalex:yes

Deep learning-based estimation of PV power plant potential under climate change: a case study of El Akarit, Tunisia - Othman, Afef Ben; Ouni, Ayoub El; Besbes, Mongi (Energy, Sustainability and Society, 2020)
Abstract Background Several climatologists and experts in the renewable energy field agree that GHI and DNI calculation models must be revised because of the increasingly unpredictable and powerful climatic disturbances. The construction of analytical mathematical models for the prediction of these disturbances is almost impossible because the physical phenomena relating to the climate are often complex. We raise the question over the current and future PV system’s sustainable energy production and whether climate disturbances will be affecting this sustainability and resulting in supply decline. Methods In this paper, we tried to use deep learning as a tool to predict the evolution of the future production of any geographic site. This approach can allow for improvements in decision-making concerning the implantation of solar PV or CSP plants. To reach this aim, we have deployed the databases of NASA and the Tunisian National Institute of Meteorology relating to the climatic parameters of the case study region of El Akarit, Gabes, Tunisia. In spite of the colossal amount of processed data that dates back to 1985, the use of deep learning algorithms allowed for the validation of the previously made estimates of the energy potential in the studied region. Results The calculation results suggested an increase in production as it was confirmed by the 2019 measures. The findings obtained from the case study region were reliable and seemed to be very promising. The results obtained using deep learning algorithms were similar to those produced by conventional calculation methods. However, while conventional approaches based on measurements obtained using hardware solutions (ground sensors) are expensive and very difficult to implement, the suggested new approach is cheaper and more convenient. Conclusions In the existence of a protracted controversy over the hypothetical effects of climate change, making advances in artificial intelligence and using new deep learning algorithms are critical procedures to strengthening conventional assessment tools of the production sites of photovoltaic energy and CSP plants.
openalex:W3091557683 mag:3091557683 KerkoCite.ItemAlsoKnownAs: 10.1186/s13705-020-00266-1 5072953:E8H7PHCF
Keywords: C:Tunisia; _z:class:countries; _z:class:themes; oa:keyword:pv power plant potential; oa:topic:T10468 Photovoltaic Maximum Power Point Tracking Techniques; oa:topic:T11052 Electricity Price and Load Forecasting Methods; oa:topic:T11276 Machine Learning Methods for Solar Radiation Forecasting; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Estimation of Thermal Comfort Parameters of Building Occupants Based on Comfort Index, Predicted Mean Vote and Predicted Percent of Dissatisfied People in the North- West Zone of Nigeria - Adekunle, Adebayo; Arowolo T.A; Adeyemi O.A; Kolawole O.A (2020)
Thermal comfort varies significantly between individuals and regions depending on factors such as activity level, clothing, space temperature and relative humidity. This study considers the estimation of thermal comfort parameters such as air temperature, mean radiant temperature, air velocity, emissivity of space, metabolic rates, and heat transfer coefficients to determine comfort index, predicted mean vote, and predicted percent of dissatisfied people. Several equipment were employed to measure thermal comfort parameters indoor of the buildings considered. Results show that Katsina state recorded the least overall comfort index when compared to the remaining states which was attributed to reduced air temperature and relative humidity recorded. Majority of the buildings considered have high mean radiant temperatures and high space diameters which suggests that occupants in this environment are most likely to experience some sort of discomfort especially during summer. Comparing all the thermal comfort of occupants based on Fanger theory, 33.3% felt hot, 26.7% felt warm, 20% felt slightly warm, 13.33% felt slightly cool, 6.7% felt cool, and 0% felt cold which indicates that occupants in this region and Geopolitical zone contend with more of heat than coldness.
KerkoCite.ItemAlsoKnownAs: 10.35629/5252-0205809826 2129771:N6CMPR75 4682641:3YVZT7MI 4682641:7BM443SB 5072953:Y77K8R95
Keywords: BE:LMIC; BE:RELEVANT; C:Nigeria; _z:class:countries; _z:class:themes; openalex:n:0; ⚠️ Invalid DOI; ⛔ No DOI found

Evaluating neutral, preferred and comfort range temperatures and computing adaptive equation for Kano region - Ali, Sani; Martinson, David; Al-Maiyah, Sura (2020)
As the international comfort standards may not be appropriate for all climates, it is imperative to evaluate the comfort requirements of indoor occupants in all regions of the world, particularly in the tropical regions where comprehensive standards are lacking. It is usual to find learning spaces in Nigerian higher institutions in which the thermal qualities do not meet the occupants’ requirements. Despite being in the tropics, where solar radiation is in abundance, Nigerian building industry professionals pay little attention to passive energy utilization. As part of an ongoing study on comfort in higher education facilities involving lecture theatres and laboratories in Bayero University, Kano, an IEQ field study was conducted in 6 learning environments by collecting a total of 1382 questionnaires in addition to physical measurements, covering a period of 10 months and cutting across all the three seasons. This paper examines only the thermal conditions of the university’s learning environments from which an adaptive thermal comfort equation, comfort temperature range, neutral and preferred temperatures are developed for the region. In addition to the measurements of air speed, air and radiant temperatures, relative humidity, a comfort survey was undertaken in the spaces from which activity levels and clothing insulations were obtained. Two different neutral temperatures were obtained for Kano based on operative and indoor running mean temperatures 27.4 °C and 28.1 °C respectively. Similarly a comfort zone of 22 °C to 32 °C was realised and found to be narrower than as recommended by one of the Nigerian standards. The method of calculation suggested by the ASHRAE 55-2013 and ISO-7730 were followed in determining the various comfort indices, while Griffiths’ method was used in obtaining the adaptive comfort equation. The results revealed that the adaptive equation using the weighted running mean outdoor air temperature had the highest coefficient of determination for the region, with approximate regression coefficient of 0.6, which is nearly twice those of ASHRAE 55 and EN15251, however the one based on the daily mean temperature is much closer. Results from the study indicate that subjects in naturally ventilated buildings in the region are comfortable at temperatures different from those suggested by ASHRAE 55 and ISO-7730 standards. The evaluated neutral and preferred temperatures as well as the comfort zone show that subjects are comfortable at up to 32 °C in naturally ventilated buildings in Kano region.
openalex: W3140381866
Keywords: C:Nigeria; openalex:n:0

DeepComfort: Energy-Efficient Thermal Comfort Control in Buildings Via Reinforcement Learning - Gao, Guanyu; Li, Jie; Wen, Yonggang (IEEE Internet of Things Journal, 2020)
Heating, ventilation, and air conditioning (HVAC) are extremely energy consuming, accounting for 40% of total building energy consumption. It is crucial to design some energy-efficient building thermal comfort control strategy which can reduce the energy consumption of the HVAC while maintaining the comfort of the occupants. However, implementing such a strategy is challenging, because the changes of the thermal states in a building environment are influenced by various factors. The relationships among these influencing factors are hard to model and are always different in different building environments. To address this challenge, we propose a deep-reinforcement-learning-based framework, DeepComfort, for thermal comfort control in buildings. We formulate the thermal comfort control as a cost-minimization problem by jointly considering the energy consumption of the HVAC and the occupants' thermal comfort. We first design a deep feedforward neural network (FNN)-based approach for predicting the occupants' thermal comfort and then propose a deep deterministic policy gradients (DDPGs)-based approach for learning the optimal thermal comfort control policy. We implement a building thermal comfort control simulation environment and evaluate the performance under various settings. The experimental results show that our approaches can improve the performance of thermal comfort prediction by 14.5% and reduce the energy consumption of HVAC by 4.31% while improving the occupants' thermal comfort by 13.6%.
Conference Name: IEEE Internet of Things Journal KerkoCite.ItemAlsoKnownAs: 10.1109/JIOT.2020.2992117 5072953:7GFMLRZ4 5072953:8YQPVQVX 5072953:B6TMXZDJ 5072953:CL9VGKT7 openalex: W3023669592
Keywords: Buildings; Deep-reinforcement learning (DRL); Energy consumption; HVAC; Reinforcement learning; Thermal factors; Thermal sensors; _z:class:countries; _z:class:themes; heating; oa:keyword:buildings via reinforcement learning; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11373 Effects of Sleep Deprivation and Fatigue on Performance; oa:topic:T11529 Refrigeration Systems and Technologies; openalex:n:1; openalex:yes; smart building; thermal comfort control; thermal comfort prediction; ventilation and air conditioning (HVAC)

STCMS: A Smart Thermal Comfort Monitor For Senior People - Katsarou, Katerina; Ounoughi, Chahinez; Mouakher, Amira; Nicolle, Christophe (2020 IEEE 29th International Conference on Enabling Technologies: Infrastructure for Collaborative Enterprises (WETICE), 2020)
Undoubtedly, the steady increase in the number of elderly people is not to be underestimated. These demographic changes call attention to new challenges regarding adequate aging-in-place strategies. Since the majority of the senior population spend up to 90% of their time indoors, appropriate and comfortable housing represents an important foundation for such strategies. In this respect, different types of data gathered from sensors, connected devices, and Internet of Things (IoT) technologies come to play an important role to support services for the elderly population in indoor environments. One of the aspects of concern is thermal comfort. In this paper, we introduce a new deep learning-based model framework named STCMS, that uses both Long-Short Term Memory (LSTM) and Deep Neural Networks (DNN) architectures, dedicated to predicting thermal comfort for elderly people. Experiments based on the publicly available dataset, show that our proposed models outperform the pioneering approaches of the literature on the agreed assessment metrics, particularly with an accuracy that varies between 80.29% to 88.16% using only internal and external temperatures data. The proposed approach can be used as a smart thermostat solution integrated into smart home ecosystems dedicated to elderly people. Thus, it would contribute simultaneously to improve their well-being and to reduce energy consumption and health costs.
KerkoCite.ItemAlsoKnownAs: 10.1109/WETICE49692.2020.00044 5072953:IG356NHM openalex: W3127167952
Keywords: DNN-based architecture; Monitoring; Senior citizens; Sensors; Sociology; Statistics; Temperature sensors; Thermal comfort; Through-silicon vias; _z:class:countries; _z:class:themes; bi-directional LSTM; classification; elderly people; oa:keyword:smart thermal comfort monitor; oa:keyword:thermal comfort; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11963 Impact of Nighttime Light Data on Various Fields; openalex:n:1; openalex:yes; prediction framework; sensor data; smart building; time-series

Dwelling Characteristics Influence Indoor Temperature and May Pose Health Threats in LMICs - Teare, June; Mathee, Angela; Naicker, Nisha; Swanepoel, Cheryl; Kapwata, Thandi; Balakrishna, Yusentha; Du Preez, David Jean; Millar, Danielle A.; Wright, Caradee Y. (Annals of Global Health, 2020)
Background: Shelter and safe housing is a basic human need that brings about a sense of ownership, selfsufficiency, and citizenship. Millions of people around the world live in inadequate dwellings in unhealthy areas, such as urban slums. These dwellings may experience indoor temperatures that impact inhabitants’ health. Indoor dwelling temperatures vary depending on many factors including geographic location, such as inland versus coastal. In an era of climate change, understanding how dwelling characteristics influence indoor temperature is important, especially in low- and middle-income countries, to protect health. Objective: To assess indoor temperature in low-cost dwellings located in a coastal setting in relation to dwelling characteristics. Methods: Indoor temperature and relative humidity loggers were installed from 1 June 2017 to 15 May 2018 in 50 dwellings in two settlements in a coastal town on the east coast of South Africa. Ambient outdoor temperature data were obtained from the national weather service, indoor temperature data were converted into apparent temperature, and heat index calculations were made to consider possible heat-health risks. A household questionnaire and dwelling observation assessment were administered. A mixed-effects linear regression model was constructed to consider the impact of dwelling characteristics on indoor apparent temperature. Findings: Among 17 dwellings with all data sets, indoor temperatures were consistently higher than, and well correlated (r = 0.92) with outdoor temperatures. Average differences in indoor and outdoor temperatures were about 4°C, with statistically significant differences in percentage difference of indoor/outdoor between seasons (p < 0.001). Heat indices for indoor temperatures were exceeded mostly in summer, thereby posing possible health risks. Dwellings with cement floors were statistically significantly cooler than any other floor type across all seasons. Conclusions: Low-cost dwellings experienced temperatures indoors higher than outdoor temperatures in part due to floor type. These results help inform interventions that consider housing and human health (n = 289).
openalex: W3047150173 KerkoCite.ItemAlsoKnownAs: 5072953:CK7XBXP8 5072953:D87MZF68 5072953:US4ZR6NG
Keywords: C:South Africa; _z:class:countries; _z:class:themes; oa:keyword:characteristics influence indoor temperature; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10190 Health Effects of Air Pollution; oa:topic:T11244 Impact of Climate Change on Human Health; openalex:n:1; openalex:yes

Noise Levels in Malaysia Primary Schools: Are We Meeting the International Standards? - Ismail, Noraidah; Karim, Khairani; Ismail, Noraidah Binti; Othman, Nur Ain (INTERNATIONAL JOURNAL OF ALLIED HEALTH SCIENCES, 2020)
Noise is increasingly becoming a problem in schools and affects the audibility of speech. The effects of noise hamper learning opportunities for students. Noisy classrooms affect students’ academic performance and wellbeing. Studies have shown that children perform more poorly in noisy situations compared to adults. The current study was done to measure noise levels in classrooms in primary schools in Kuantan. A total of 31 classrooms from eight residential primary schools were selected as the place of study. The noise levels were measured using a sound level meter (SLM) in occupied and unoccupied conditions. On-site observations and checking were done and documented in each school and classroom. The results showed that the noise levels of occupied and unoccupied classrooms were higher than the values recommended by the World Health Organization (WHO) which are 35 dB(A) and 55 dB(A) respectively. The findings showed that the measured noise levels in the classrooms were high enough that it might interfere with the effectiveness of teaching and learning among students and teachers. The source of noise was mainly from the students’ activities in the classes. The current study discusses a few possible suggestions to improve the classroom acoustics.
KerkoCite.ItemAlsoKnownAs: 4874017:2C3JZ59Y 4874017:2C3JZ59Y 2129771:IUEKTI4S 4682641:RZI6LHWC 5072953:WDXTQ8NW 5072953:XFHY2BXM
Keywords: BE:LMIC; BE:RELEVANT; C:Malaysia; _z:class:countries; _z:class:themes; evidence_review_2; ⛔ No DOI found

Retraction: Perception and Knowledge on Climate Change: A Study of Private University Students in Bangladesh - Amjad, Karisma (Environmental and Earth Sciences Research Journal, 2020)
openalex: W3080099837 mag: 3080099837
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:yes

Retraction: Perception and Knowledge on Climate Change: A Study of Private University Students in Bangladesh - Amjad, Karisma (Environmental and Earth Sciences Research Journal, 2020)
openalex: W3080099837 mag: 3080099837
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:yes

Changing climate change: The carbon budget and the modifying-work of the IPCC. - Lahn, Bard (Sage Journals, 2020)
KerkoCite.ItemAlsoKnownAs: 10.1177/0306312720941933 4874017:DFI9G5HK 4874017:ZGXHX4VS 5072953:3VQI9PPM openalex: W3042446572
Keywords: _z:class:countries; _z:class:themes; oa:keyword:carbon budget; oa:keyword:climate change; oa:keyword:ipcc; oa:sdg:13 Climate action; oa:topic:T10119 Sustainability Transitions and Resilience in Social-Ecological Systems; oa:topic:T10471 Economic Implications of Climate Change Policies; oa:topic:T12615 Geoengineering and Climate Ethics; openalex:n:1; openalex:yes

What Stymies Action on Climate Change? Religious Institutions, Marginalization, and Efficacy in Kenya? - Keough School - University of Notre Dame - Honig, Lauren; Smith, Amy Erica; Bleck, Jaimie (2020)
openalex:W3168509389 mag:3168509389 KerkoCite.ItemAlsoKnownAs: 5072953:XBSK9FEN
Keywords: C:Kenya; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:kenya; oa:keyword:religious institutions; oa:topic:T13456 Role of Faith-Based Organizations in Development and Social Services; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

What Stymies Action on Climate Change? Religious Institutions, Marginalization, and Efficacy in Kenya? - Keough School - University of Notre Dame - Honig, Lauren; Smith, Amy Erica; Bleck, Jaimie (2020)
openalex:W3168509389 mag:3168509389 KerkoCite.ItemAlsoKnownAs: 5072953:XBSK9FEN
Keywords: _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:kenya; oa:keyword:religious institutions; oa:topic:T13456 Role of Faith-Based Organizations in Development and Social Services; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Perceptions about climate change among university students in Bangladesh - Haq, Shah Md Atiqul; Ahmed, Khandaker Jafor (Natural Hazards, 2020)
openalex: W3041938809 mag: 3041938809
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:yes

Understanding Women perception of promoting education and policy initiatives in regards to climate change in Rural areas of Sindh, Pakistan - Memon, Falak Shad; Amjad, Shahid (Journal of education and educational development, 2020)
Climate change is inevitable issue of modern world. Women often share the greater burden of all the impacts due to their lower knowledge base that leads to their limited adaptive capacity. Studies suggests that knowledge and education can result in better resilience and sustainable development. It helps in encouraging changes in attitude and behaviors that help them adapt to climate changes. This paper aims to explore the understanding of local rural women regarding current climate change education perception and try to gauge their knowledge of the policy initiatives that have been taken in this areas. A qualitative study was chosen to explore the current understanding for this study. The interviews of 20 women participants from rural areas of Sindh were taken. The study finding reveled that there is a lack of awareness regarding any policy initiatives and education programs, the main reasons for this may be lower literacy level and cultural hindrance they face in developing knowledge. The Lack of gender inclusiveness at all the levels was also highlighted as key issue.
openalex: W3082932365 mag: 3082932365
Keywords: C:Pakistan; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; oa:topic:T13839 Volunteer Tourism and Global Development Impacts; openalex:import; openalex:yes

Climate Change at the International School of Kenya - Singh, Hazel (FORUM, 2020)
This article is about the efforts of Students for the Environment, which operates at the International School of Kenya. It discusses their past successes, their current plans and what they hope for the future. It includes their operations, as well as the impact they have been able to have on their school community. It also introduces some of the ways they plan to positively affect their environment, mitigate negative impacts on their environment and how it contributes to climate change.
openalex:W3042588908 mag:3042588908 KerkoCite.ItemAlsoKnownAs: 10.15730/forum.2020.62.2.275 5072953:NPX453BP
Keywords: C:Kenya; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:kenya; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Analyzing capacity of a consumer-grade infrared camera in South Africa for cost-effective aerial inspection of building envelopes - Vorajee, Naadir; Mishra, Asit; Mishra, Amit (Frontiers of Architectural Research, 2020)
Prohibitive equipment cost and certain export regulations are the major obstacles to the widespread adoption of infrared (IR) thermography when evaluating building envelopes. In this work, we propose the use of an affordable and easily available camera as a first step of making the technology accessible. Combined with image post-processing, we hypothesize that a low-cost, low-resolution, and consumer-grade device can provide an economic alternative for the periodic evaluation of building envelopes. Following a market survey, the Seek Thermal Compact (STC) was chosen for evaluation. The STC was able to accurately measure the temperature of surfaces and distinguish small thermal anomalies (3 mm in diameter), and the IR images can be post-processed to reasonably estimate the anomaly areas. The STC was particularly effective when images were taken within 1.75 m from the surface. The 1.75 m distance did not pose a challenge in this study, as the goal was to mount the selected IR camera on an unmanned aerial vehicle for the surveys. The small size and weight of the STC were also useful. The results from the analysis of the capability of the STC and the image post-processing techniques may help form the basis of future investigations aiming at lowering the cost of building thermographic surveys.

[WITHDRAWN] Perception and Knowledge on Climate Change: A Study of Private University Students in Bangladesh - Amjad, Karisma (Environmental and Earth Sciences Research Journal, 2020)
openalex: W3038665853 mag: 3038665853
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:yes

[WITHDRAWN] Perception and Knowledge on Climate Change: A Study of Private University Students in Bangladesh - Amjad, Karisma (Environmental and Earth Sciences Research Journal, 2020)
openalex: W3038665853 mag: 3038665853
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:yes

Apraisal of Geography Teachers’ Knowledge on the Relevance of Secondary School Geography Curriculum Relating to Climate Change in Nigeria - Oladapo, Samuel Olanrewaju (2020)
Evidence shows that climate change is experienced all over the globe. Climate change is defined as a change in the state of the climate that can be identified and measured by changes in the mean and/or variability of its properties Climate change can persist over a long time, usually over decades and much longer and leads to extremes of weather conditions such as temperature, wind, rainfall, and humidity. Geography curriculum is basically on climate and environment generally The main purpose of the study is to explore geography teacher’s knowledge, attitude and the practices relating to climate change in Nigeria. Questionnaire on the knowledge of climatic change among geography was used as the main instrument for data collection. It was designed to elicit information on the basis of research questions set for this study. A total number of 60 geography teachers were used as the sample size. Descriptive statistics such as simple percentages and frequency counts were used in the analysis of the research data collected. The findings from the research work show among others that the teachers communicate effective on the topics relate to climate change. It also reveals that most teachers have knowledge of the contents of geography curriculum. Geography teachers according to the findings indicates the readiness of the teachers to continue teaching the topics relating to climate change. It is therefore, recommends that topics on climate change be made compulsory for students at all level of education.
openalex:W3081137457 mag:3081137457 KerkoCite.ItemAlsoKnownAs: 5072953:HV97A9HP
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; oa:keyword:geography teachers; oa:keyword:secondary school geography curriculum; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T14482 Innovations in Education Technology and Pedagogy; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Climate Change, Vulnerability, and Disability: Do We “Leave No One Behind”? - Mörchen, Manfred; Ocasiones, Erly; Relator, Rebie; Lewis, David (Disaster Medicine and Public Health Preparedness, 2020)
An abstract is not available for this content. As you have access to this content, full HTML content is provided on this page. A PDF of this content is also available in through the ‘Save PDF’ action button.
openalex: W3030526041 mag: 3030526041
Keywords: _z:class:countries; openalex:import; openalex:yes

Understanding Women’s Perceptions of Promoting Education and Policy Initiatives about Climate Change in Rural Areas of Sindh, Pakistan - Memon, Falak Shad (Social Science Research Network, 2020)
Climate change is an inevitable issue of modern world. Women often face greater risk and share greater burden due to their limited adaptive capacity. Studies suggest that knowledge and education can result in better resilience and sustainable development. Climate change education encourages changes in attitude and behavior that leads to better adaptability to climate changes. This paper aims to explore the local women’s understanding of climate change education and policy initiatives taken in rural areas. A qualitative exploratory study was chosen for this study. The data collection methodology was through qualitative process. 20 women participants from rural areas of Sindh were interviewed. The finding reveled that women in rural area of Sindh have very low understanding and knowledge of any climate change educational program conducted in their regions. The lack of awareness regarding any climate change policy initiatives was also observed. This lack of awareness was attributed to their low literacy rate, lack of gender inclusiveness and cultural barriers and hindrances. The understanding of these factors at all level of policy making is key for successful climate change education policy.
openalex: W3179999768 mag: 3179999768
Keywords: C:Pakistan; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; openalex:import; openalex:yes; ⛔ No DOI found

Constraints and contributing factors to implementing Climate Change Education as an emerging curriculum area at the basic education level in Cape Coast Metropolis, Ghana - Odoom, Michael (2020)
openalex:W3034186487 mag:3034186487 KerkoCite.ItemAlsoKnownAs: 5072953:8GI7XZK7
Keywords: C:Ghana; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change education; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Raising awareness of climate change issues in Nigeria through education for policy and practice - Abdullahi, Nimota Jibola Kadir (Journal Of Research, Policy & Practice of Teachers & Teacher Education, 2020)
The objective of this study is to raise awareness through education in mitigating of climate issues. Also, to finding out relationship between resilience teaching and learning and mitigating of climate change issues in North-central zone, Nigeria. The study investigated managing education toward mitigating climate change in North-central zone, Nigeria. Stratified random sampling technique was used to select 375 head teachers and 384 teachers in public primary schools in North-central zone, Nigeria. Questionnaire title “Managing Education Toward Mitigating Climate Change Issues Questionnaire (METACCIQ) was used to collect data for the study and analysed using descriptive statistics and t-test analysis. The results shown that there is no significant difference between raising awareness, resilience teaching and learning and mitigating of climate change issues in Nigeria. It was recommended that Government, school administrators, teachers and stakeholders should embark on raising awareness on climate change issues to encourage changes in young people attitudes and behavior. Also, resilience teaching and learning should be made interesting in order to increases climate literacy among learners through education.
openalex:W3049394061 mag:3049394061 KerkoCite.ItemAlsoKnownAs: 10.37134/jrpptte.vol10.1.2.2020 5072953:PA4N5TKE
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change issues; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T14482 Innovations in Education Technology and Pedagogy; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Raising awareness of climate change issues in Nigeria through education for policy and practice - Abdullahi, Nimota Jibola Kadir (Journal Of Research, Policy & Practice of Teachers & Teacher Education, 2020)
The objective of this study is to raise awareness through education in mitigating of climate issues. Also, to finding out relationship between resilience teaching and learning and mitigating of climate change issues in North-central zone, Nigeria. The study investigated managing education toward mitigating climate change in North-central zone, Nigeria. Stratified random sampling technique was used to select 375 head teachers and 384 teachers in public primary schools in North-central zone, Nigeria. Questionnaire title “Managing Education Toward Mitigating Climate Change Issues Questionnaire (METACCIQ) was used to collect data for the study and analysed using descriptive statistics and t-test analysis. The results shown that there is no significant difference between raising awareness, resilience teaching and learning and mitigating of climate change issues in Nigeria. It was recommended that Government, school administrators, teachers and stakeholders should embark on raising awareness on climate change issues to encourage changes in young people attitudes and behavior. Also, resilience teaching and learning should be made interesting in order to increases climate literacy among learners through education.
openalex:W3049394061 mag:3049394061 KerkoCite.ItemAlsoKnownAs: 10.37134/jrpptte.vol10.1.2.2020 5072953:PA4N5TKE
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change issues; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T14482 Innovations in Education Technology and Pedagogy; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Pandemics, climate change, and disability related to SCI - Alexander, Marcalee (Spinal Cord Series and Cases, 2020)
openalex: W3020860734 mag: 3020860734
Keywords: _z:class:countries; openalex:import; openalex:yes

Experimental evaluation of the effect of body mass on thermal comfort perception - Lipczyńska, Aleksandra; Mishra, Asit (2020)
Globally 39% of adults are overweight, 13% are obese, and 9% are underweight. Current thermal comfort standards, catering to the normal weight occupant, may hence be ignoring nearly 60% of the population. This could have significant comfort, productivity and energy implications. We performed a climate chamber study of the thermal response of 76 subjects in all the body mass index (BMI) categories, from 17 and 37 kg/m2. Every participant underwent the same four sessions at average operative temperatures of 19.9, 22.4, 25.3, and 28.2 °C. We obtained subjective feedback from participants on their thermal sensation and preference, humidity sensation and preference, thermal comfort rating, and air quality perception. We also measured skin temperature, blood pressure, pulse rate, blood glucose level, weight, height, waist and hip circumferences and body composition. Overall, we did not find significant impact of BMI on the thermal sensation. However, the overweight and obese participants preferred lower temperature compared to normal weight and underweight participants which may indicate practical implication for control strategies.
KerkoCite.ItemAlsoKnownAs: 5072953:M3FR3JSK 5072953:WMHR88D5

Carbon dioxide and its effect on occupant cognitive performance: A literature review - Mishra, Asit; Wargocki, Pawel; Tham, K. (2020)
Building ventilation standards use indoor carbon dioxide (CO2) levels as a proxy for air quality, acknowledging that at typical indoor levels, CO2 itself is not a pollutant. By 2100, outdoor CO2 levels may reach 900 ppm. With current ventilation standards, that would nearly double the levels of chronic, indoor CO2 exposure, raising concerns for its potential effect on occupants. In the last 15 years, an effort to gain this understanding, particularly regarding cognitive performance, has been made by 11 studies. They focused on the effect of elevated CO2 while minimizing exposure to other indoor pollutants. Five of the studies found an effect of CO2 exposure on performance and six studies did not. Four studies found an effect on cognitive performance under 2000 ppm exposure. But three of these four studies used the same proprietary, closed-source tool to measure cognitive performance. Physiological effects – like blood pressure, heart rate changes – were found only at exposures over 2500 ppm and were not always associated with cognitive decrements. These discrepancies could have been due to differences in measures used and individual differences in response to CO2. Future works should adopt a more in-depth and holistic approach.

Long-term monitoring for indoor climate assessment – The association between objective and subjective data - Loomans, M.G.L.C.; Mishra, Asit; Kooi, L. (Building and Environment, 2020)
To enhance indoor climate monitoring and indoor climate assessment, a better understanding of the collection and analysis of monitored data, over longer time periods, is necessary. The goal of this work is to improve long-term monitoring in order to arrive at better performance of building indoor climate, with the perception of occupants in mind. Indoor climate was monitored in an open plan office lay-out in two Case study office buildings, during two periods each. Indoor climate data was obtained at different resolution levels (locations) in the work environment. Additionally, information from the occupants was gathered using two methods: short, right-now surveys and wrist skin temperature measurements (biosensed data). In total, 160 subjective responses were obtained. Outcomes showed that measurement at a specific resolution level is required for representativeness. For the Case studies, this level depended on the office lay-out and could not be generalized. Correlations between perceived thermal comfort and objective data, either of the indoor climate or the biosensed data were moderate at best. Better applicability of the data was found when using it in combination with classification algorithms, obtaining predictions of higher accuracy (close to 65% for the group under investigation).

Investigating Pre-service Science, Technology, and Mathematics Teachers’ Attitudes toward Climate Change in Nigeria - Oladipo, A.J.; Awofala, Adeneye O. A.; Osokoya, Modupe M. (Journal of Educational Sciences, 2020)
The study investigated attitudes toward climate change among 480 pre-service science, technology, and mathematics (STM) teachers from four higher institutions of learning in Southwest, Nigeria using the quantitative research method within the blueprint of the descriptive survey design. Data collected using climate change attitude survey were analysed using the descriptive statistics of percentages, mean, and standard deviation and inferential statistics of factor analysis and independent samples t-test. Findings revealed that attitudes toward climate change assessed by the climate change attitude survey was a multi-dimensional construct (perceived beliefs component and intentions component). Gender differences in attitudes toward climate change among pre-service STM teachers were not significant even at the subscale level of perceived beliefs and intentions. In addition, the pre-service STM teachers showed a moderate level of attitudes toward climate change. In conclusion, there is need for a concerted effort to protect the earth from increased weather variability and the Nigerian government at all levels has both international and domestic commitments to reduce greenhouse gas emissions to ensuring sustainable human development. Future studies in Nigeria and elsewhere should conduct a confirmatory factor analysis on the climate change attitude survey to further generalise the findings of this study.
openalex:W3020303059 mag:3020303059 KerkoCite.ItemAlsoKnownAs: 10.31258/jes.4.2.p.220-238 5072953:FEQSNVWV
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

The relationships between classroom air quality and children’s performance in school - Wargocki, Pawel; Porras-Salazar, Jose Ali; Contreras-Espinoza, Sergio; Bahnfleth, William (Building and Environment, 2020)
The data from published studies were used to derive systematic relationships between learning outcomes and air quality in classrooms. Psychological tests measuring cognitive abilities and skills, school tasks including mathematical and language-based tasks, rating schemes, and tests used to assess progress in learning including end-of-year grades and exam scores were used to quantify learning outcomes. Short-term sick leave was also included because it may influence progress in learning. Classroom indoor air quality was characterized by the concentration of carbon dioxide (CO2). For psychological tests and school tasks, fractional changes in performance were regressed against the average concentrations of CO2 at which they occurred; all data reported in studies meeting the inclusion criteria were used to derive the relationship, regardless of whether the change in performance was statistically significant at the examined levels of classroom air quality. The analysis predicts that reducing CO2 concentration from 2,100 ppm to 900 ppm would improve the performance of psychological tests and school tasks by 12% with respect to the speed at which the tasks are performed and by 2% with respect to errors made. For other learning outcomes and short-term sick leave, only the relationships published in the original studies were available. They were therefore used to make predictions. These relationships show that reducing the CO2 concentration from 2,300 ppm to 900 ppm would improve performance on the tests used to assess progress in learning by 5% and that reducing CO2 from 4,100 ppm to 1,000 ppm would increase daily attendance by 2.5%. These results suggest that increasing the ventilation rate in classrooms in the range from 2 L/s-person to 10 L/s-person can bring significant benefits in terms of learning performance and pupil attendance; no data are available for higher rates. The results provide a strong incentive for improving classroom air quality and can be used in cost-benefit analyses.
KerkoCite.ItemAlsoKnownAs: 4874017:TU8FFWFE 10.1016/j.buildenv.2020.106749 2129771:L6UTHECG 4682641:LG7FP736 4682641:Q9NJM76P 4682641:S8B3SYD7 5072953:DK9RV95R openalex: W3006309879
Keywords: BE:RELEVANT; Carbon dioxide; Children; Cognitive performance; Elementary schools; Learning; _z:class:countries; _z:class:themes; evidence_review_2; oa:keyword:classroom air quality; oa:sdg:4 Quality education; oa:topic:T10190 Health Effects of Air Pollution; oa:topic:T11002 Indoor Air Quality and Health Effects; oa:topic:T11692 Effects of Noise Pollution on Health and Well-being; openalex:n:1; openalex:yes; type:meta-analysis

The relationships between classroom air quality and children’s performance in school - Wargocki, Pawel; Porras-Salazar, Jose Ali; Contreras-Espinoza, Sergio; Bahnfleth, William (Building and Environment, 2020)
The data from published studies were used to derive systematic relationships between learning outcomes and air quality in classrooms. Psychological tests measuring cognitive abilities and skills, school tasks including mathematical and language-based tasks, rating schemes, and tests used to assess progress in learning including end-of-year grades and exam scores were used to quantify learning outcomes. Short-term sick leave was also included because it may influence progress in learning. Classroom indoor air quality was characterized by the concentration of carbon dioxide (CO2). For psychological tests and school tasks, fractional changes in performance were regressed against the average concentrations of CO2 at which they occurred; all data reported in studies meeting the inclusion criteria were used to derive the relationship, regardless of whether the change in performance was statistically significant at the examined levels of classroom air quality. The analysis predicts that reducing CO2 concentration from 2,100 ppm to 900 ppm would improve the performance of psychological tests and school tasks by 12% with respect to the speed at which the tasks are performed and by 2% with respect to errors made. For other learning outcomes and short-term sick leave, only the relationships published in the original studies were available. They were therefore used to make predictions. These relationships show that reducing the CO2 concentration from 2,300 ppm to 900 ppm would improve performance on the tests used to assess progress in learning by 5% and that reducing CO2 from 4,100 ppm to 1,000 ppm would increase daily attendance by 2.5%. These results suggest that increasing the ventilation rate in classrooms in the range from 2 L/s-person to 10 L/s-person can bring significant benefits in terms of learning performance and pupil attendance; no data are available for higher rates. The results provide a strong incentive for improving classroom air quality and can be used in cost-benefit analyses.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.buildenv.2020.106749 2129771:LYTHHG7J 4874017:TITGKV97
Keywords: Carbon dioxide; Children; Cognitive performance; Elementary schools; Learning; evidence_review

Climate change and the fossil fuel divestment movement in Canadian higher education: The mobilities of actions, actors, and tactics - Maina, Naomi Mumbi; Murray, Jaylene; McKenzie, Marcia (Journal of Cleaner Production, 2020)
Situated within the broader climate justice movement, the fossil fuel divestment movement calls for both public and private divestment of financial holdings from fossil fuel companies. This paper examines the extent of fossil fuel divestment campaigns at higher education institutions across Canada, examining key actions and tactics through which campaigns are initiated and mobilized, as led by students, faculty, alumni, and climate justice organizations. Findings indicate that out of 220 accredited Canadian universities and colleges, there are 38 active divestment campaigns and 6 institutions that have committed to varying degrees of divestment. Tactics used in these campaigns include signing of petitions, sit-ins, rallies, and protests, facilitated through face-to-face and online platforms. Findings revealed significant borrowing of actions and tactics among campaign actors, including the use of branding and messaging from international environmental organizations, such as 350.org. This research contributes to scholarly knowledge on how higher education divestment movements and related campaigns for institutional change can influence how sustainability and climate change are addressed. Actors can build on this knowledge to develop sustained collaborative systems to address current and future challenges across institutions and in society at large.
openalex: W2996828751 mag: 2996828751
Keywords: C:Canada; _z:class:countries; _z:class:themes; oa:keyword:canadian higher education; oa:keyword:fossil fuel divestment movement; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; oa:topic:T11835 Sustainability Education in Higher Education Institutions; openalex:import; openalex:yes

Effects of Classroom Environment on Learning - Blaker, Andrew; Andrew, Blaker (甲南大学マネジメント創造学部HSMR編集委員会, 2020)
This paper introduces research around carbon dioxide, temperature and their effects on student learning in the classroom. It is shown that carbon dioxide has a negative effect on students’ cognitive performance, but that increasing the rate of ventilation ameliorates these effects. The negative effect on student motivation of high temperatures in the classroom is also introduced. The paper concludes that an investigation into student learning environments of each campus should be undergone to establish the possible effects that these issues may be having on students.
KerkoCite.ItemAlsoKnownAs: 4874017:FN7GWH6D 4874017:FN7GWH6D 10.14990/00003653 2129771:BUCLTNKF 4682641:5NU6IRQS 5072953:V3L52HKC
Keywords: BE:RELEVANT; _z:class:countries; _z:class:themes

Effects of Classroom Environment on Learning - Blaker, Andrew; Andrew, Blaker (甲南大学マネジメント創造学部HSMR編集委員会, 2020)
This paper introduces research around carbon dioxide, temperature and their effects on student learning in the classroom. It is shown that carbon dioxide has a negative effect on students’ cognitive performance, but that increasing the rate of ventilation ameliorates these effects. The negative effect on student motivation of high temperatures in the classroom is also introduced. The paper concludes that an investigation into student learning environments of each campus should be undergone to establish the possible effects that these issues may be having on students.
KerkoCite.ItemAlsoKnownAs: 10.14990/00003653 2129771:BUCLTNKF 2129771:IMP5FXHD 4682641:5NU6IRQS 4874017:FN7GWH6D 5072953:V3L52HKC
Keywords: BE:RELEVANT; _z:class:countries; _z:class:themes; evidence_review

A field study of the individual and combined effect of ventilation rate and lighting conditions on pupils’ performance - Hviid, Christian A.; Pedersen, Christian; Dabelsteen, Kent Helmann (Building and Environment, 2020)
A field lab study was conducted to determine how much the indoor climate parameters, ventilation and lighting, influence children's academic abilities. The study involved 92 children, aged 10–12 years, who over four weeks answered a questionnaire and three different performance tests, which measured their processing speed, concentration, logical reasoning and math solving abilities. An experimental design was constructed to test the effect of changing the lighting from constant warm light with a maintained correlated colour temperature average of 2900 K and lighting level of 450 lux to a dynamic cool light of 4900 K and 750 lux. The change was tested at both low (3.9 l/s per person) and high ventilation rate (10.6 l/s per person). The results showed that processing speed (6.6%, P < 0.001), concentration (8.3%, P < 0.001) and math skills (11.8%, P < 0.006), improved the most in the combined scenario with high ventilation rate and dynamic cool lighting. The logical reasoning test did not show any significant changes. The questionnaire results of the pupils' perception of the indoor environment suggested that they were satisfied in general, but the indoor environmental changes had only very limited effect on how they perceived the classroom. The combination of dynamic lighting and increased ventilation rate indicated a boosted positive impact on the speed and concentration of the children which means that future renovations would benefit from a holistic design including both of these factors.
KerkoCite.ItemAlsoKnownAs: 2129771:AG7BXKR9 2129771:AG7BXKR9 10.1016/j.buildenv.2019.106608 4874017:IGZWA26J 5072953:KJS26UPL openalex: W2996506711
Keywords: Indoor climate; Lighting; Productivity; Schools; Ventilation; _z:class:countries; _z:class:themes; evidence_review_2; oa:keyword:lighting conditions; oa:keyword:ventilation rate; oa:sdg:13 Climate action; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10692 Impact of Urban Green Space on Public Health; oa:topic:T12950 Learning Environments in Education; openalex:n:1; openalex:yes

The use of artificial intelligence (AI) methods in the prediction of thermal comfort in buildings: energy implications of AI-based thermal comfort controls - Ngarambe, Jack; Yun, Geun Young; Santamouris, Mat (Energy and Buildings, 2020)
Buildings consume about 40 % of globally-produced energy. A notable amount of this energy is used to provide sufficient comfort levels to the building occupants. Moreover, given recent increases in global temperatures as a result of climate change and the associated decrease in comfort levels, providing adequate comfort levels in indoor spaces has become increasingly important. However, striking a balance between reducing building energy use and providing adequate comfort levels is a significant challenge. Conventional control methods for indoor spaces, such as on/off, proportional-integral (PI), and proportional-integral-derivative (PID) controllers, display significant instabilities and frequently overshoot thermostats, resulting in unnecessary energy use. Additionally, conventional building control methods rarely include comfort regulatory schemes. Consequently, recent research efforts have focused on the use of advanced artificial intelligence (AI) methods to optimize building energy usage while maintaining occupant thermal comfort. We present a review of the current AI-based methodologies being used to enhance thermal comfort in indoor spaces. we focus on thermal comfort predictive models using diverse machine learning (ML) algorithms and their deployment in building control systems for energy saving purposes. We then discuss gaps in the existing literature and highlight potential future research directions.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2020.109807 5072953:9EVLBS9W openalex: W3001840828
Keywords: Artificial intelligence (AI); Comfort control; Machine learning (ML); Predictive control; Predictive modeling; _important; _z:class:countries; _z:class:themes; oa:keyword:thermal comfort; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; oa:topic:T11529 Refrigeration Systems and Technologies; openalex:n:1; openalex:yes; selected_for:Predictive models for classroom conditions 2024

Towards capacity building of media and awareness of public and students to develop strong science-policy communication on climate change in Pakistan (2020)
openalex: W4285703577
Keywords: C:Pakistan; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:yes

Integrating social learning into climate change adaptation public policy cycle: Building upon from experiences in Brazil and the United Kingdom - Nicolletti, Mariana; Maschietto, Fernanda; Moreno, Thais (Environmental Development, 2020)
This paper outlines good practices and serves as a guide to promote Social Learning in the elaboration and implementation processes of public policies for climate change adaptation at a local level. It is based on a multiple-case study covering 18 experiences from the United Kingdom and Brazil, an analysis of existing research about the contributions of Social Learning to socioenvironmental governance and public policies regarding wicked problems, as well as, empirical information collected during workshops held as part of the development of the AdaptaClima Platform. From the literature review, key aspects of Social Learning were identified, such as active participation; co-production of knowledge and development of capacities; iterative reflection and action. These were compared with four phases of the adaptation to climate change public policy implementation cycle [i) preparation and engagement; ii) analysis of impacts and vulnerabilities; iii) planning; iv) implementation and monitoring] and used to analyse the empirical information gathered. The results bring practical examples of how to include key Social Learning aspects in each phase. The findings may apply to different contexts, but are especially useful to developing countries.
openalex: W2993994191 mag: 2993994191
Keywords: C:Brazil; C:United Kingdom; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change adaptation; oa:sdg:13 Climate action; oa:topic:T10119 Sustainability Transitions and Resilience in Social-Ecological Systems; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T14147 Living Labs in Open Innovation Networks; openalex:import; openalex:yes

A social learning and transition perspective on a climate change project in South Africa - Scholz, Geeske; Methner, Nadine (Environmental Innovation and Societal Transitions, 2020)
The agricultural sector of the Western Cape is highly affected by climate change and thus requires fundamental change to move to a more resilient path. We analyze the development of a climate change plan to obtain a better understanding of what is needed to make such a strategic intervention meaningful in terms facilitating a sustainability transition. We use the concept of transition arena to understand how group composition and processes facilitated or hindered structural change, and apply social learning theory to uncover learning processes and outcomes for whether capacity and momentum for moving towards a more climate resilient sector were created. Commitment on the part of project members created trust in the project and vice versa, while the ongoing involvement of governmental actors was key for creating capacities and commitment for change. The limited participation of niche actors may have hampered the ability to identify more innovative development pathways.
openalex:W2993287539 mag:2993287539 KerkoCite.ItemAlsoKnownAs: 10.1016/j.eist.2019.10.011 5072953:HEKRX3EB
Keywords: C:South Africa; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change project; oa:keyword:social learning; oa:topic:T10119 Sustainability Transitions and Resilience in Social-Ecological Systems; oa:topic:T10439 Adaptation to Climate Change in Agriculture; oa:topic:T11810 System Dynamics Modeling and Applications; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Students’ Perception on Causes and Consequences of Climate Change in Public Universities of Ethiopia - Bazezew, Arega; Neka, Mulugeta; Belay, Meherte (2020)
Climate change is impacting socioeconomic and biophysical environments at both Global and local scales. This paper presents the results of the assessment study of student perception on the information sources, occurrences, causes, impacts and solutions of climate change in the public universities of Ethiopia. A questionnaire survey was conducted on a total of 357 university students attending undergraduate and postgraduate courses to generate the required data. The data gathered in this way was analyzed using descriptive and inferential statistics. The results indicated that over 57% of the students get climate change information from different sources. The main climate change information sources identified by the students include television, radio, friends, internet, government reports and school teachers. Among these, teachers are the major (82%) of the studied students. Over 60% of the students reported that they do not have sufficient knowledge about climate change. Giving special concern to climate change information, obeying the laws of nature, limited interference in nature, developing awareness among the public and adopting safe industrial environments are suggested solutions to minimize the hazards of climate change. It is suggested that state agencies should design ways to deliver climate information to the wider public so as to develop awareness on the causes and consequences of climate change among the public. Local agencies and land users need also to adhere with the natural laws and adapt proper interferences in the local natural environment.
openalex:W3009550954 mag:3009550954 KerkoCite.ItemAlsoKnownAs: 5072953:73I68TP8
Keywords: C:Ethiopia; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Students’ Perception on Causes and Consequences of Climate Change in Public Universities of Ethiopia - Bazezew, Arega; Neka, Mulugeta; Belay, Meherte (2020)
Climate change is impacting socioeconomic and biophysical environments at both Global and local scales. This paper presents the results of the assessment study of student perception on the information sources, occurrences, causes, impacts and solutions of climate change in the public universities of Ethiopia. A questionnaire survey was conducted on a total of 357 university students attending undergraduate and postgraduate courses to generate the required data. The data gathered in this way was analyzed using descriptive and inferential statistics. The results indicated that over 57% of the students get climate change information from different sources. The main climate change information sources identified by the students include television, radio, friends, internet, government reports and school teachers. Among these, teachers are the major (82%) of the studied students. Over 60% of the students reported that they do not have sufficient knowledge about climate change. Giving special concern to climate change information, obeying the laws of nature, limited interference in nature, developing awareness among the public and adopting safe industrial environments are suggested solutions to minimize the hazards of climate change. It is suggested that state agencies should design ways to deliver climate information to the wider public so as to develop awareness on the causes and consequences of climate change among the public. Local agencies and land users need also to adhere with the natural laws and adapt proper interferences in the local natural environment.
openalex:W3009550954 mag:3009550954 KerkoCite.ItemAlsoKnownAs: 5072953:73I68TP8
Keywords: _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Fatalism, Climate Resiliency Training and Farmers’ Adaptation Responses: Implications for Sustainable Rainfed-Wheat Production in Pakistan - Mahmood, Nasir; Arshad, Muhammad Umair; Kaechele, Harald; Shahzad, Muhammad Faisal; Ullah, Ayat; Mueller, Klaus (Sustainability, 2020)
Climate change is a severe threat to the agricultural sector in general and to rainfed farming in particular. The aim of this study was to investigate the factors that can potentially affect the adaptation process against climate change. This study focused on wheat farmers and farming systems in the rainfed agroecological zone of Pakistan. Farmers’ data related to climate change fatalism, the availability of climate-specific extension services, socioeconomic and institutional variables, and farm characteristics were collected. A logit model to assess farmers’ decisions to adopt an adaptation measure and a multinomial logit model to assess their choice of various adaptation measures were used. The results showed that fatalistic farmers were unlikely to implement climate change adaptation measures. The variables related to the climate-specific extension services, including farmers’ participation in training on climate-resilient crop farming and the availability of mobile communication-based advisory services, had highly significant and positive impacts on farmers’ decisions and their choice of adaptation measures. Input market access and tractor ownership also had positive and significant impacts on farmers’ decisions to adapt and their choice of adaptation measures. This study highlights the need to improve rainfed-wheat farmers’ education levels to change their fatalistic attitudes towards climate change. Furthermore, government action is needed to provide climate-specific extension services to ensure sustainable production levels that will ultimately lead to food and livelihood security under a changing climate.
openalex: W3007027287 mag: 3007027287
Keywords: C:Pakistan; _z:class:countries; _z:class:themes; oa:keyword:climate resiliency training; oa:topic:T10367 Agricultural Innovation and Livelihood Diversification; oa:topic:T10439 Adaptation to Climate Change in Agriculture; oa:topic:T11886 Risk Management and Vulnerability in Agriculture; openalex:import; openalex:yes

Temporary migration and climate variation in eastern Africa - Mueller, Valerie; Sheriff, Glenn; Dou, Xiaoya; Gray, Clark (World Development, 2020)
Africa is likely to experience warming and increased climate variability by the late 21st century. Climate extremes have been linked to adverse economic outcomes. Hence, adaptation is a key component of the United Nations Framework Convention on Climate Change agreements and development assistance. Effective climate adaptation policy requires an understanding of how temperature and rainfall variability affect migration patterns. Yet, how individuals in developing countries manage climate variation is poorly understood, especially in Africa. Combining high-resolution climate data with panel micro-data on migration, labor participation, and demographics, we employ regression analysis to assess temporary migration responses to local temperature and precipitation anomalies in four East African countries. We find that climate impacts are most pronounced in urban areas, with a standard deviation temperature increase and rainfall decrease leading to respective 10 and 12 percent declines in out-migration relative to mean values. Evidence from other labor market outcomes suggests that urban out-migration is not associated with reduced local employment opportunities. Instead, declines in urban out-migration appear to coincide with negative local climate employment impacts. These results challenge the narrative that temporary out-migration serves as a safety valve during climate extremes and that climate change will most strongly affect out-migration rates from rural areas in developing countries.
openalex: W2981422507 mag: 2981422507
Keywords: openalex:cites; openalex:import

A topography of climate change research - Callaghan, Max; Minx, Jan C.; Forster, Piers M. (Nature Climate Change, 2020)
The massive expansion of scientific literature on climate change1 poses challenges for global environmental assessments and our understanding of how these assessments work. Big data and machine learning can help us deal with large collections of scientific text, making the production of assessments more tractable, and giving us better insights about how past assessments have engaged with the literature. We use topic modelling to draw a topic map, or topography, of over 400,000 publications from the Web of Science on climate change. We update current knowledge on the IPCC, showing that compared with the baseline of the literature identified, the social sciences are in fact over-represented in recent assessment reports. Technical, solutions-relevant knowledge—especially in agriculture and engineering—is under-represented. We suggest a variety of other applications of such maps, and our findings have direct implications for addressing growing demands for more solution-oriented climate change assessments that are also more firmly rooted in the social sciences2,3. The perceived lack of social science knowledge in assessment reports does not necessarily imply an IPCC bias, but rather suggests a need for more social science research with a focus on technical topics on climate solutions. The rapid growth of climate change research presents challenges for IPCC assessments and their stated aim of being comprehensive, objective and transparent. Here the authors use topic modelling to map the climate change literature, and assess how well it is represented in IPCC reports.
openalex: W3003135817 mag: 3003135817
Keywords: evidence_review; openalex:cites; openalex:import; selected_for:effects of climate ch...on learning...LMICs 2024; tagged

Revisiting the climate driver and inhibitor mechanisms of international migration - Wesselbaum, Dennis (Climate and Development, 2020)
In this paper, we add to the literature on the driving forces of international migration out of Africa. We particularly focus on the direct effect of climate variables: temperature, rainfall, and weather-related disaster. We revisit the question whether climate is a driver or inhibitor of migration using migration flows out of all African countries from 1980 to 2015 into 16 OECD countries. Our findings show that climate can be a driver and an inhibitor of migration depending on the size of the temperature shock. We show that temperature has non-linear effects on migration. We observe a U-shaped relationship for temperature at destination and an inverted U-shaped relationship at origin. We also find that the agricultural pathway does quantitatively matter: countries relying more heavily on agriculture experience larger migration flows. Finally, weather-related disaster also have a significant effect on international migration.
openalex: W2999804001 mag: 2999804001
Keywords: openalex:cites; openalex:import

Research and Education in India on Climate Change - Ray, Alak (Science and culture, 2020)
openalex: W3002317688 mag: 3002317688
Keywords: C:India; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10471 Economic Implications of Climate Change Policies; openalex:import; openalex:yes

Towards optimal control of air handling units using deep reinforcement learning and recurrent neural network - Zou, Zhengbo; Yu, Xinran; Ergan, Semiha (Building and Environment, 2020)
Optimal control of heating, ventilation and air conditioning systems (HVACs) aims to minimize the energy consumption of equipment while maintaining the thermal comfort of occupants. Traditional rule-based control methods are not optimized for HVAC systems with continuous sensor readings and actuator controls. Recent developments in deep reinforcement learning (DRL) enabled control of HVACs with continuous sensor inputs and actions, while eliminating the need of building complex thermodynamic models. DRL control includes an environment, which approximates real-world HVAC operations; and an agent, that aims to achieve optimal control over the HVAC. Existing DRL control frameworks use simulation tools (e.g., EnergyPlus) to build DRL training environments with HVAC systems information, but oversimplify building geometrics. This study proposes a framework aiming to achieve optimal control over Air Handling Units (AHUs) by implementing long-short-term-memory (LSTM) networks to approximate real-world HVAC operations to build DRL training environments. The framework also implements state-of-the-art DRL algorithms (e.g., deep deterministic policy gradient) for optimal control over the AHUs. Three AHUs, each with two-years of building automation system (BAS) data, were used as testbeds for evaluation. Our LSTM-based DRL training environments, built using the first year's BAS data, achieved an average mean square error of 0.0015 across 16 normalized AHU parameters. When deployed in the testing environments, which were built using the second year's BAS data of the same AHUs, the DRL agents achieved 27%–30% energy saving comparing to the actual energy consumption, while maintaining the predicted percentage of discomfort (PPD) at 10%.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.buildenv.2019.106535 5072953:RJW6NN6D openalex: W2989354373
Keywords: C:Mali; Deep reinforcement learning; Energy consumption; HVAC control; Long-short-term-memory network; Thermal comfort; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:air handling units; oa:keyword:deep reinforcement learning; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10603 Demand Response in Smart Grids; oa:topic:T11529 Refrigeration Systems and Technologies; openalex:n:1; openalex:yes

Towards optimal control of air handling units using deep reinforcement learning and recurrent neural network - Zou, Zhengbo; Yu, Xinran; Ergan, Semiha (Building and Environment, 2020)
Optimal control of heating, ventilation and air conditioning systems (HVACs) aims to minimize the energy consumption of equipment while maintaining the thermal comfort of occupants. Traditional rule-based control methods are not optimized for HVAC systems with continuous sensor readings and actuator controls. Recent developments in deep reinforcement learning (DRL) enabled control of HVACs with continuous sensor inputs and actions, while eliminating the need of building complex thermodynamic models. DRL control includes an environment, which approximates real-world HVAC operations; and an agent, that aims to achieve optimal control over the HVAC. Existing DRL control frameworks use simulation tools (e.g., EnergyPlus) to build DRL training environments with HVAC systems information, but oversimplify building geometrics. This study proposes a framework aiming to achieve optimal control over Air Handling Units (AHUs) by implementing long-short-term-memory (LSTM) networks to approximate real-world HVAC operations to build DRL training environments. The framework also implements state-of-the-art DRL algorithms (e.g., deep deterministic policy gradient) for optimal control over the AHUs. Three AHUs, each with two-years of building automation system (BAS) data, were used as testbeds for evaluation. Our LSTM-based DRL training environments, built using the first year's BAS data, achieved an average mean square error of 0.0015 across 16 normalized AHU parameters. When deployed in the testing environments, which were built using the second year's BAS data of the same AHUs, the DRL agents achieved 27%–30% energy saving comparing to the actual energy consumption, while maintaining the predicted percentage of discomfort (PPD) at 10%.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.buildenv.2019.106535 5072953:RJW6NN6D openalex: W2989354373
Keywords: Deep reinforcement learning; Energy consumption; HVAC control; Long-short-term-memory network; Thermal comfort; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:air handling units; oa:keyword:deep reinforcement learning; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10603 Demand Response in Smart Grids; oa:topic:T11529 Refrigeration Systems and Technologies; openalex:n:1; openalex:yes

Perception and Knowledge on Climate Change: A Case Study of University Students in Bangladesh - Kumar, Bezon; Asad, Arif Ibne; Chandraaroy, Borun; Banik, Purnima (Journal of atmospheric science research, 2020)
This paper mainly investigates the perception and knowledge on climate change of the university students in Bangladesh. To carry out this study, primary data are collected from 370 students and uses several statistical methods. Perception and knowledge on the causes, effects and mitigation ways of climate change problems, and perceived duties to combat against climate change are analyzed with descriptive statistics. This paper finds that deforestation is the main cause of global warming and climate change and, the effects of climate change is very serious on people’s health. Majority portion of the students think that it is difficult to combat against climate change problem because it has already been too late to take action. Besides this study also finds that government is crucially responsible for combating against climate change problem. The study calls for government mainly besides industry and youths to aware people about the causes, effects, mitigation ways of climate change so that they can contribute to the sustainable development by mitigating climate change problem.
openalex: W2997599447 mag: 2997599447
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; openalex:import; openalex:yes

Perception and Knowledge on Climate Change: A Case Study of University Students in Bangladesh - Kumar, Bezon; Asad, Arif Ibne; Chandraaroy, Borun; Banik, Purnima (Journal of atmospheric science research, 2020)
This paper mainly investigates the perception and knowledge on climate change of the university students in Bangladesh. To carry out this study, primary data are collected from 370 students and uses several statistical methods. Perception and knowledge on the causes, effects and mitigation ways of climate change problems, and perceived duties to combat against climate change are analyzed with descriptive statistics. This paper finds that deforestation is the main cause of global warming and climate change and, the effects of climate change is very serious on people’s health. Majority portion of the students think that it is difficult to combat against climate change problem because it has already been too late to take action. Besides this study also finds that government is crucially responsible for combating against climate change problem. The study calls for government mainly besides industry and youths to aware people about the causes, effects, mitigation ways of climate change so that they can contribute to the sustainable development by mitigating climate change problem.
openalex: W2997599447 mag: 2997599447
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; openalex:import; openalex:yes

Canadian Law Schools Must Do Their Part to Help Combat Climate Change - Chen, Ling (Social Science Research Network, 2020)
The intensifying physical and socio-economic effects of climate change, mainstreamed by political debates and scientific evidence on anthropogenic disruptions to the global climate system, have motivated changing legislation, regulation, litigation, and institutions. But legal education is not keeping up; climate change has not yet been taught well and broadly in Canadian law schools. While a few schools have offered climate law courses, the majority have not done so in any systematic way. The unprecedentedly expanding demands from youth and students for aggressive climate action should call the attention of law schools to the roles they should play in combatting climate change.
openalex: W3128457757 mag: 3128457757
Keywords: _z:class:countries; _z:class:themes; oa:keyword:canadian law schools; oa:sdg:13 Climate action; oa:topic:T12895 Legal Recognition of Nature's Rights and Environmental Governance; openalex:import; openalex:yes; ⛔ No DOI found

Heat, comfort and well-being in a changing climate : learning from cooling practices in Malaysian households - Amin, M. Monalkumar; Tarmizi, Mohd Ariff Ahmad (2020)
openalex: W3111970042 mag: 3111970042
Keywords: C:Malaysia; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T13599 Cultural and Architectural Influences on Society; openalex:import; openalex:yes

Promoting Climate Change and Health Education for Sustainable Development in Nigeria - Anabaraonye, Benjamin; Ewa, Beatrice O; Okoro, Kenneth. I.; Anthony, Precious. C. (2020)
The impacts of climate change are felt profoundly on Nigeria’s health sector. The impacts of climate change on the health sector in Nigeria implies that due considerations to health issues as part of climate change mitigation and adaptation efforts has become a pressing issue. Training is a critical component of the global climate change response.. Climate change and health education is therefore vital in every community in order to prepare them for climate change impacts and to learn how to adapt and mitigate effectively for sustainable development in Nigeria. Consequently, mitigation and adaptation approaches are important for the successful management of Nigeria's health sector.. The objective of this paper is to highlight the impacts of climate change on the health sector in Nigeria. It also outlines the adaptation and mitigation strategies to climate change for building resilience and reducing vulnerability for a sustainable future. This study highlights the need to educate communities and various institutions about climate change and its impact on the health sector in Nigeria. This paper is therefore very significant as it explores new opportunities, practices and policies for climate changemitigation and adaptation on the health sector in Nigeria.
openalex:W3081839036 mag:3081839036 KerkoCite.ItemAlsoKnownAs: 5072953:8BBZM4DT
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; oa:keyword:sustainable development; oa:sdg:13 Climate action; oa:topic:T11244 Impact of Climate Change on Human Health; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Learning for development : factors that lead to successful development projects for marginalised communities affected by climate change in Bangladesh - Anmol, Khonker Taskin (2020)
openalex: W3154749984 mag: 3154749984
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:keyword:successful development projects; oa:sdg:13 Climate action; oa:topic:T10596 Maternal and Child Nutrition in Developing Countries; oa:topic:T12013 Measurement and Evaluation of Sustainable Development; oa:topic:T12656 Impact of Climate Change on Human Migration; openalex:import; openalex:yes

COVID-19’s Impact on Climate Change Research and Institutional Resilience in Higher Education in Vermont and Tanzania - Clément, Stéphanie (2020)
openalex:W3124117436 mag:3124117436 KerkoCite.ItemAlsoKnownAs: 5072953:3XTB94A3
Keywords: C:Tanzania; _z:class:countries; _z:class:themes; oa:keyword:institutional resilience; oa:sdg:13 Climate action; oa:topic:T10168 Impact of COVID-19 on Mental Health; oa:topic:T10747 Community Resilience to Natural Disasters; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

A practical artificial intelligence-based approach for predictive control in commercial and institutional buildings - Cotrufo, N.; Saloux, E.; Hardy, J. M.; Candanedo, J. A.; Platon, R. (Energy and Buildings, 2020)
This paper presents a methodology for the development and implementation of Model Predictive Control (MPC) in institutional buildings. This methodology relies on Artificial Intelligence (AI) for model development. An appropriate control-oriented model is a critical component in MPC; model development is no easy task, and it often requires significant technical expertise, effort and time, along with a substantial amount of information. AI techniques enable rapid development and calibration of models using a limited amount of information (i.e. measurements of few variables) while achieving relatively high accuracy. In this study, the MPC algorithm targets the reduction of natural gas consumption by optimizing the transition between night set-back and daytime indoor air set-point values as a function of the expected weather. This MPC strategy was implemented in an institutional building in Varennes (QC), Canada, during the heating season 2018–19. A significantly better performance was achieved when compared with “business as usual” control strategies: the natural gas consumption and greenhouse gas (GHG) emissions were reduced by approximately 22%, and the building heating demand by 4.3%. The proposed strategy is scalable and can be replicated in other buildings.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2019.109563 5072953:BJMQNEHE openalex: W2986659651
Keywords: C:Canada; _z:class:countries; _z:class:themes; oa:keyword:predictive control; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10791 Model Predictive Control in Industrial Processes; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:n:1; openalex:yes

Training Canadian doctors for the health challenges of climate change - Hackett, Finola; Got, Tiffany; Kitching, G; MacQueen, Kelsey T; Cohen, Arianne (The Lancet Planetary Health, 2020)
Our planet is changing, and as with any drastic upheaval to patients' surroundings, global environmental changes affect individual health. Climate change is a major threat to ecosystems and the wellbeing of current and future generations of people. From wildfire-related evacuation of hospitals to the spread of Lyme disease and heat-related deaths and injuries, the health effects of climate change are becoming increasingly clear in Canada.1Howard C Buse C Rose C MacNeill A Parkes M The Lancet Countdown on health and climate change: policy brief for Canada. 2019https://storage.googleapis.com/lancet-countdown/2019/11/Lancet-Countdown_Policy-brief-for-Canada_FINAL.pdfDate accessed: December 16, 2019Google Scholar The environment is an important yet sorely neglected determinant of health. Despite increasing pressure to include environment-related topics in their curricula, medical schools have not adequately addressed the urgent need for training. Climate change is clearly relevant for medical education, which prepares students for future practice and promotes public health and eco-health literacy.2Maxwell J Blashki G Teaching about climate change in medical education: an opportunity.J Public Health Res. 2016; 5: 673Crossref PubMed Scopus (78) Google Scholar The International Federation of Medical Students' Associations has called upon medical schools to integrate teaching related to climate change into their curricula by 20203International Federation of Medical Students' AssociationsSixty-fifth session of the WHO Regional Committee for the Eastern Mediterranean. 2018https://ifmsa.org/statements/Date accessed: December 16, 2019Google Scholar and UK medical students also highlighted this point in the BMJ, in which they called for “urgent action to safeguard the health of our future patients”.4Legard C Green M Tucker Y van Daalen K Climate change is impacting population health and our future patients: remaining silent is not an option.The BMJ Opinion. 2019; (Sept 26)https://blogs.bmj.com/bmj/2019/09/26/climate-change-is-impacting-population-health-and-our-future-patients-remaining-silent-is-not-an-option/Date accessed: December 16, 2019Google Scholar First, we suggest that the core competencies that health professionals should have relating to climate change must be agreed upon by the medical community. Fortunately, resources already exist in the international health and environment community. For instance, the Centre for Sustainable Healthcare has a peer network supporting teaching on planetary health and sustainable health systems,5Centre for Sustainable Healthcare NetworksEducation for sustainable healthcare.https://networks.sustainablehealthcare.org.uk/network/education-sustainable-healthcareDate accessed: November 17, 2019Google Scholar and the Canadian Association of Physicians for the Environment published a climate change toolkit for health professionals, with concise modules for adapting to and mitigating the effects of climate change on patients and within communities.6Canadian Association of Physicians for the EnvironmentClimate change toolkit for health professionals.https://cape.ca/campaigns/climate-health-policy/climate-change-toolkit-for-health-professionals/Date accessed: November 17, 2019Google Scholar Second, a mechanism must be created to integrate these competencies into curricula that are already packed full. Topics can be presented through didactic lectures and incorporated into existing lectures, such as integrating teaching on the effects of air pollution with respiratory health teaching, discussing climate-related displacement within teaching on refugee and migrant health, and exploring the increasing burden of heat stress on health-care systems. Furthermore, case-based sessions can highlight the effects on specific individuals. Examples could include considering isolated older people at risk of heat stroke or of being in extreme weather events, or discussing the effects of flooding or poor water quality on Indigenous communities. Lastly, there must be a national movement to change, as well as a system to evaluate and compare planetary health education across the nation. Members of the Health and Environment Adaptive Response Taskforce (HEART), part of the Canadian Federation of Medical Students, have responded to this call by creating a set of core competencies on planetary health, including the effects of climate change and other environmental changes on health. These competencies promote advocacy and provide a framework for curricular development in medical education. In 2019, HEART conducted a national evaluation of planetary health teaching in undergraduate medical education with the participation of Canadian medical students and faculty. The survey was developed with international leaders in planetary health and distributed to students and faculty in environmental health and sustainability at each of the Canadian medical schools. Survey scores were based on the inclusion and quality of didactic and case-based teaching on climate change and environmental topics, and on opportunities for student engagement. By September, 2019, all 17 Canadian medical schools had participated in the evaluation. The results of the HEART evaluation7Canadian Federation of Medical StudentsHealth and environment adaptive response task force.https://www.cfms.org/what-we-do/global-health/heart.htmlDate accessed: November 17, 2019Google Scholar outline a clear opportunity to improve planetary health education in Canadian medical schools. Institutions can recognise and address this opportunity by tapping into the strong movement to change, with student interest groups and faculty already taking steps to integrate these competencies. Ultimately, physicians must be equipped with the knowledge and skills to serve as medical experts and health advocates in their communities. A rapid increase in curricular content related to planetary health, including climate change, is required to equip future physicians to manage the effects of ecological change on health and health systems. As can be seen from the dynamic energy surrounding the Fridays for Future movement,8Hope M Contagious youth.Lancet Planetary Health. 2019; 3: e376-e377Summary Full Text Full Text PDF PubMed Scopus (4) Google Scholar young people have the passion to drive a healthy response to ecological change. Physicians across Canada are beginning to advocate, standing in solidarity with youth at the Global Day of Action on Sept 27, 2019, and leading a recent call to action on climate change and health.9Canadian Association of Physicians for the EnvironmentCall to action on climate change and health. 2019https://cape.ca/wp-content/uploads/2019/07/Call-to-Action-Full-logos-updated-EN-June-25-2019.pdfDate accessed: November 17, 2019Google Scholar However, to address the growing challenges associated with climate change, young physicians must first understand those challenges and their responsibilities as health-care providers. Medical professionals are gaining the tools to become leaders in this area as we progress to a safer, more sustainable future. We declare no competing interests.
openalex: W2999674132 mag: 2999674132
Keywords: C:Canada; _z:class:countries; _z:class:themes; oa:keyword:canadian doctors; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T11244 Impact of Climate Change on Human Health; oa:topic:T13123 Expanding Access to Radiotherapy Globally; oa:topic:T13555 Strategies to Reduce Low-Value Health Care Services; openalex:import; openalex:yes

Analysis on the Content Elements of Energy and Climate Change Education Presented in the Achievement Standards of the 2015 Revised National Curriculum and Special Education Basic Curriculum - Keun, Park Jae (Jounral of Energy and Climate Change Education, 2020)
openalex: W3124957501 mag: 3124957501
Keywords: _z:class:countries; openalex:import; openalex:yes

Assessing disability inclusive disaster risk reduction and climate change adaptation capabilities in Singapore - Lee, Chelsea Wen Si (2020)
openalex: W3046479211 mag: 3046479211
Keywords: _z:class:countries; openalex:import; openalex:yes

Effect of carbon dioxide concentration on respiratory parameters of occupants - Mishra, Asit; Wargocki, Pawel; Tham, KW (2020)
Climate models imply that by 2100 atmospheric CO2 levels could exceed 900 ppm. At these levels, subscribing to current ventilation rates would lead to indoor CO2 levels ≥1,400 ppm, possibly impacting our physiology and other responses. We ran a randomized, within-subject study with 15 participants to examine the physiological effects of 2,5 hour exposure to three CO2 levels: 900 ppm, 1450 ppm (reduced ventilation), and 1450 ppm (pure CO2 added, ventilation same as 900 ppm). End-tidal CO2 and respiration rate across the different exposures were not significantly different. Spirometry parameters reduced significantly from the beginning to the end at reduced ventilation exposure compared to the 900 ppm condition (p<0.013), but not during exposure to pure CO2. The results suggest no effect of increased pure CO2 on some physiological parameters in contrary to reduced ventilation.

Modelling hydrological responses under climate change using machine learning algorithms – semi-arid river basin of peninsular India - Naidu, G. Sireesha; Pratik, M.; Rehana, S. (H2Open journal, 2020)
Abstract Catchment scale conceptual hydrological models apply calibration parameters entirely based on observed historical data in the climate change impact assessment. The study used the most advanced machine learning algorithms based on Ensemble Regression and Random Forest models to develop dynamically calibrated factors which can form as a basis for the analysis of hydrological responses under climate change. The Random Forest algorithm was identified as a robust method to model the calibration factors with limited data for training and testing with precipitation, evapotranspiration and uncalibrated runoff based on various performance measures. The developed model was further used to study the runoff response under climate change variability of precipitation and temperatures. A statistical downscaling model based on K-means clustering, Classification and Regression Trees and Support Vector Regression was used to develop the precipitation and temperature projections based on MIROC GCM outputs with the RCP 4.5 scenario. The proposed modelling framework has been demonstrated on a semi-arid river basin of peninsular India, Krishna River Basin (KRB). The basin outlet runoff was predicted to decrease (13.26%) for future scenarios under climate change due to an increase in temperature (0.6 °C), compared to a precipitation increase (13.12%), resulting in an overall reduction in water availability over KRB.
openalex: W3103227824 mag: 3103227824
Keywords: C:India; _z:class:countries; _z:class:themes; oa:topic:T10330 Hydrological Modeling and Water Resource Management; oa:topic:T11186 Global Drought Monitoring and Assessment; oa:topic:T11490 Hydrological Modeling using Machine Learning Methods; openalex:import; openalex:yes

Effect of Change Effort in Raising Organizational Climate at the Kenya School of Government, Matuga Campus - Napoo, John Lokuruka; Nyambati, Richard (International Journal of Humanities and Social Science, 2020)
openalex:W3111930166 mag:3111930166 KerkoCite.ItemAlsoKnownAs: 10.30845/ijhss.v10n8p10 5072953:U7893VAQ
Keywords: C:Kenya; _z:class:countries; _z:class:themes; oa:keyword:raising organizational climate; oa:sdg:13 Climate action; oa:topic:T11810 System Dynamics Modeling and Applications; oa:topic:T13163 Demonstrating the Value of Learning Culture in Organizations; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Effect of Change Effort in Raising Organizational Climate at the Kenya School of Government, Matuga Campus - Napoo, John Lokuruka; Nyambati, Richard (International Journal of Humanities and Social Science, 2020)
openalex:W3111930166 mag:3111930166 KerkoCite.ItemAlsoKnownAs: 10.30845/ijhss.v10n8p10 5072953:U7893VAQ
Keywords: _z:class:countries; _z:class:themes; oa:keyword:raising organizational climate; oa:sdg:13 Climate action; oa:topic:T11810 System Dynamics Modeling and Applications; oa:topic:T13163 Demonstrating the Value of Learning Culture in Organizations; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Effectiveness of Disaster Risk Reduction (DRR) and Climate Change Adaptation (CCA) Training Programs: Views and Voices from Barisal Division, a Coastal Region in Bangladesh - Nipa, Sharmin Nahar; Oyshi, Jarin Tasneem; Rouf, Istiak Ibne (2020)
Barisal division, a coastal region of Bangladesh, is one of the most vulnerable zones in terms of climate-induced disasters, where the children, women, and young people are at high risk. Disaster Risk Reduction (DRR) and Climate Change Adaptation (CCA) training programs for children and youth usually aim to change the way of thinking and action, which can make the future generations or the communities more resilient. Trainings can help to improve skills, knowledge, and capacities to manage any disaster event. Considering this fact, the Centre for Climate Change and Environmental Research (C3ER) of BRAC University facilitated several capacity building training programs on DRR and CCA, which have been conducted in different districts of Barisal division. Nearly 105 children and youth of 3 districts (Barguna, Bhola, and Barisal) of Barisal division have transformed into Disaster Ambassador and helped to enhance the capacities of their communities to deal with climate-induced disasters. This chapter aims to find out the effectiveness of these training programs to build disaster resilient communities through the active participation of children and young people. It finds that the trained children and youths became able to contribute positively through making decisions and developing work plans which were supported by various organizations.
openalex: W3081555485 mag: 3081555485
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:keyword:climate change adaptation; oa:keyword:disaster risk reduction; oa:sdg:13 Climate action; oa:topic:T10747 Community Resilience to Natural Disasters; oa:topic:T10930 Global Flood Risk Assessment and Management; oa:topic:T12656 Impact of Climate Change on Human Migration; openalex:import; openalex:yes

Effectiveness of Disaster Risk Reduction (DRR) and Climate Change Adaptation (CCA) Training Programs: Views and Voices from Barisal Division, a Coastal Region in Bangladesh - Nipa, Sharmin Nahar; Oyshi, Jarin Tasneem; Rouf, Istiak Ibne (2020)
Barisal division, a coastal region of Bangladesh, is one of the most vulnerable zones in terms of climate-induced disasters, where the children, women, and young people are at high risk. Disaster Risk Reduction (DRR) and Climate Change Adaptation (CCA) training programs for children and youth usually aim to change the way of thinking and action, which can make the future generations or the communities more resilient. Trainings can help to improve skills, knowledge, and capacities to manage any disaster event. Considering this fact, the Centre for Climate Change and Environmental Research (C3ER) of BRAC University facilitated several capacity building training programs on DRR and CCA, which have been conducted in different districts of Barisal division. Nearly 105 children and youth of 3 districts (Barguna, Bhola, and Barisal) of Barisal division have transformed into Disaster Ambassador and helped to enhance the capacities of their communities to deal with climate-induced disasters. This chapter aims to find out the effectiveness of these training programs to build disaster resilient communities through the active participation of children and young people. It finds that the trained children and youths became able to contribute positively through making decisions and developing work plans which were supported by various organizations.
openalex: W3081555485 mag: 3081555485
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:keyword:climate change adaptation; oa:keyword:disaster risk reduction; oa:sdg:13 Climate action; oa:topic:T10747 Community Resilience to Natural Disasters; oa:topic:T10930 Global Flood Risk Assessment and Management; oa:topic:T12656 Impact of Climate Change on Human Migration; openalex:import; openalex:yes

Modelling and Simulating the Thermal Comfort Aspects of Natural Ventilated Classrooms in Hot-Humid Climates - Sasidhar, P. V.; Shrivastava, Kratika; Mopuri, Ramgopal (2020)
Providing a thermally comfortable environment is considered to be an essential requirement for effective learning in classrooms. Providing thermal comfort by using active but energy intensive environment control systems is not sustainable in a vast country like India. Though national building codes provide some specifications for classrooms, it is not known whether adherence to these standards ensures thermal comfort in a sustainable manner. This paper presents results obtained from a systematic study on a naturally ventilated classroom located in a hot and humid environment. A reference classroom is defined based on the National Building Code (NBC) of India and building simulations are carried out on this classroom using EnergyPlus. The comfort aspects of the classroom are evaluated by applying well-known adaptive thermal comfort standards. Various measures such as occupant density, class scheduling, external shading, night ventilation, and reflective roof paintings are introduced in the simulation systematically to evaluate their effect on comfort aspects of the classroom, individually and cumulatively. The relative importance of each of these measures and then the combined effect on thermal comfort are analyzed. Results show that the comfort hours of the reference classroom can be increased significantly by employing the suggested methods which are practically feasible and sustainable.
openalex:W3005075793 mag:3005075793 KerkoCite.ItemAlsoKnownAs: 10.1007/978-981-15-1063-2_11 5072953:UPDZXW4P
Keywords: C:India; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:natural ventilated classrooms; oa:keyword:thermal comfort aspects; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T12950 Learning Environments in Education

Influence of Different Roof Design Parameters on Classrooms’ Thermal Performance in Tropical Savannah Climate of Nigeria - Abba, Habu Yusuf; Bint Abdul-Majid, Roshida; Ahmed, Muhammad Hamdan; Said, El-Nafaty Abbas (Journal of Xi'an University of Architecture & Technology, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:C26A8GBA 4682641:29MGH7TW 5072953:8FCV9GGJ
Keywords: BE:LMIC; BE:RELEVANT; C:Nigeria; _z:class:countries; _z:class:themes; openalex:n:0; ⛔ No DOI found

Implementation Science 3.0 - Albers, Bianca; Shlonsky, Aron; Mildon, Robyn (Springer, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:W3XMUAEV
Keywords: evidence_review

On the Ventilation performance of low momentum confluent jets supply device in a classroom - Andersson, Harald; Kabanshi, Alan; Cehlin, Mathias; Moshfegh, Bahram (Energies, 2020)
KerkoCite.ItemAlsoKnownAs: 10.3390/en13205415 2129771:2ZISVLLE 4682641:XZMS6XBQ 5072953:XCZS62BK openalex: W3092860867
Keywords: BE:RELEVANT; _z:class:countries; _z:class:themes; oa:keyword:ventilation performance; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10990 Airborne Transmission of Respiratory Viruses; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:n:1; openalex:yes

Human Capital Accumulation and Disasters: Evidence from the Pakistan Earthquake of 2005 - Andrabi, T.; Daniels, B.; Das, J. (RISE Working Paper Series. 20/039: Human Capital Accumulation and Disasters: Evidence from the Pakistan Earthquake of 2005 | RISE Programme, 2020)

Does women’s participation in agricultural technology adoption decisions affect the adoption of climate-smart agriculture? Insights from Indo-Gangetic Plains of India - Aryal, J.; P. (Review of Development Economics, 2020)
KerkoCite.ItemAlsoKnownAs: 5072953:BHU9HQDK 5072953:IPDERMSH

Thermal environmental conditions for human occupancy - ASHRAE (2020)
KerkoCite.ItemAlsoKnownAs: 4874017:HF3Y2LCR 5072953:HADVIHD2
Keywords: _z:class:countries; _z:class:themes

Interventions in LICs and LMICs to improve air quality and/or mitigate its impacts - Avis, William; Bartington, Suzanne (Knowledge, evidence and learning for development, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:HYW73TIQ 4874017:IZPF5RDH 5072953:28FCRSN7 5072953:MM6S99NG
Keywords: _z:class:countries; _z:class:themes; ⛔ No DOI found

Technological (Mis)conceptions: Examining birth control as conservation in coastal Madagascar - Baker-Médard, M.; Sasser, J. (Geoforum, 2020)
KerkoCite.ItemAlsoKnownAs: 5072953:4YYVS48L 5072953:ZAWEPJAU

Evaluation of Physical Aspects of Classroom Environment in Terms of the Humanistic Approach: A Comprehensive Theoretical Framework - Barri, Moatasim A. (Journal of Education and Training Studies, 2020)
KerkoCite.ItemAlsoKnownAs: 10.11114/jets.v8i11.4974 2129771:8Z3C68NM 4682641:T2Y3JY37 5072953:TNWISK5H openalex: W3092954411
Keywords: BE:RELEVANT; _z:class:countries; _z:class:themes; oa:keyword:classroom environment; oa:keyword:humanistic approach; oa:topic:T12950 Learning Environments in Education; openalex:n:1; openalex:yes

Assessing the Strength of Evidence in the Education Sector - BE2 (2020)

A study protocol to determine heat-related health impacts among primary schoolchildren in South Africa - Bidassey-Manilal, Shalin; Wright, Caradee Yael; Kapwata, Thandi; Shirinde, Joyce (International journal of environmental research and public health, 2020)
Climate models predict that the global average temperature of Earth will rise in the future. Studies show that high classroom temperatures can affect the ability of the student to learn and function. It is important to understand the impact that heat will have on the health, wellbeing, and academic performance of learners, as they spend a significant amount of time in classrooms compared to any other environment. A follow-up panel study among 20 public primary schools in the Gauteng province (South Africa) will be carried out, in which Grade 4 learners will be selected to complete an hourly heat-health symptom questionnaire. A Cambridge Neuropsychological Test Automated Battery (CANTAB) test will be used to determine their memory and attention span. A nursing practitioner will measure body weight, height, and temperature. Lascar data loggers will be used to measure indoor classroom temperature. School principals will complete a questionnaire on existing school coping mechanisms and policies in place that help deal with hot weather conditions. This is the first study to quantitatively assess the effects of heat on learners’ health, well-being and school performance in South Africa. The outcomes of this study will enable policymakers and public officials to develop appropriate school heat adaptation and mitigation measures and will assist in channeling their resources where it is most needed.
openalex: W3045926951 KerkoCite.ItemAlsoKnownAs: 10.3390/ijerph17155531 2129771:DDZERB3C 4682641:JDAC6C9S 5072953:AVM5ZUTB 5072953:W7ZU7Q2P 5072953:Y2ZXEWX2
Keywords: BE:LMIC; BE:RELEVANT; C:South Africa; _z:class:countries; _z:class:themes; evidence_review; oa:sdg:13 Climate action; oa:topic:T10190 Health Effects of Air Pollution; oa:topic:T11109 Physiological Responses to Heat Stress in Humans; oa:topic:T11244 Impact of Climate Change on Human Health; openalex:n:1; openalex:yes

Calculating the sample size required for developing a clinical prediction model - D, Riley R.; J, Ensor; E, Snell K.I.; E, Harrell F.; P, Martin G.; B, Reitsma J.; M, Moons K.G.; G, Collins; M, Smeden (BMJ, 2020)

Factors affecting vulnerability level of farming households to climate change in developing countries: evidence from Eritrea - Debesai, M.G. (IOP Conference Series: Materials Science and Engineering, 2020)
KerkoCite.ItemAlsoKnownAs: 5072953:4QIU7IZ8 5072953:JG4HHSGS

Development and optimization of artificial neural network algorithms for the prediction of building specific local temperature for HVAC control - Demirezen, Gulsun; Fung, Alan S.; Deprez, Mathieu (International Journal of Energy Research, 2020)
KerkoCite.ItemAlsoKnownAs: 10.1002/er.5537 5072953:DDFVNU8Z openalex: W3034174159
Keywords: _z:class:countries; _z:class:themes; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10603 Demand Response in Smart Grids; oa:topic:T11052 Electricity Price and Load Forecasting Methods; openalex:n:1; openalex:yes

Three roles for education in climate change adaptation - Feinstein, N.; W.; Mach, K.; J. (Climate Policy, 2020)
KerkoCite.ItemAlsoKnownAs: 5072953:7EXV8EWC 5072953:YEQTXFBP
Keywords: _z:class:countries

An exploration of green roofs for indoor and exterior temperature regulation in the South African interior - Fitchett, A.; Govender, P.; Vallabh, P. (Environ Dev Sustain, 2020)

GlobalABC Regional Roadmap for Buildings and Construction in Africa: Towards a zero-emission, efficient and resilient buildings and construction sector - Global Alliance for Buildings and Construction; International Energy Agency; United Nations Environment Programme (2020)
KerkoCite.ItemAlsoKnownAs: 4874017:TZ2LWH6X 5072953:M59X5VAQ
Keywords: _z:class:countries; _z:class:themes

On the use of computer‐assistance to facilitate systematic mapping - Haddaway, Neal R.; Callaghan, Max W.; Collins, Alexandra M.; Lamb, William F.; Minx, Jan C.; Thomas, James; John, Denny (Campbell Systematic Reviews, 2020)
Abstract The volume of published academic research is growing rapidly and this new era of “big literature” poses new challenges to evidence synthesis, pushing traditional, manual methods of evidence synthesis to their limits. New technology developments, including machine learning, are likely to provide solutions to the problem of information overload and allow scaling of systematic maps to large and even vast literatures. In this paper, we outline how systematic maps lend themselves well to automation and computer‐assistance. We believe that it is a major priority to consolidate efforts to develop and validate efficient, rigorous and robust applications of these novel technologies, ensuring the challenges of big literature do not prevent the future production of systematic maps.
Keywords: evidence_review; selected_for:effects of climate ch...on learning...LMICs 2024; tagged

Factors affecting the women's empowerment in disaster risk governance structure in Sri Lanka - Hemachandra, Kinkini; Amaratunga, Dilanthi; Haigh, Richard (International Journal of Disaster Risk Reduction, 2020)
Women have been disproportionately affected by natural hazards due to many reasons. Minimum representation of women in disaster decision-making has been identified as such reasons for their high vulnerabilities in disasters. Hence, women's empowerment in disaster decision-making has been proposed by researchers and many international frameworks as a strategy to address vulnerabilities. Because women's empowerment in disaster risk governance is expected to reduce their vulnerabilities and strengthen overall societal resilience to future hazards. However, limited evidence is available on how to achieve women's empowerment in disaster risk governance. Hence, this chapter aims to explore the challenges that prevent their empowerment in disaster risk governance structure as input for policy makers of Sri Lanka. Sri Lanka was selected due to its increasing risks for disasters and the status of women's empowerment within the risk governance structure. Using a semi-structured interview guideline, which was developed based on the literature review, nine semi-structured interviews were conducted with the experts in the field of the study. Interview data were analysed qualitatively to identify the challenges that limit women's empowerment in disaster risk governance structure in Sri Lanka. The identified challenges are presented in this paper with the suggestions made by experts as inputs for the policymaking process. Accordingly, twenty challenges were identified within five broad themes as legal, institutional, individual, social & cultural and nature of the job. Accordingly, three suggestions were presented to overcome the identified challenges to enhance women's empowerment in disaster risk governance structure in Sri Lanka.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijdrr.2020.101779 5072953:45SMR5WE 5072953:LGTBIVQK 5072953:ZGYQ5PZP
Keywords: Disaster risk governance; Disasters; Governance; Sri Lanka; Women's empowerment; _z:class:countries

The sustainable development index: Measuring the ecological efficiency of human development in the anthropocene - Hickel, J. (Ecological Economics, 2020)

Global report on internal displacement - I.D.M.C. (Internal Displacement Monitoring Centre (IDMC, 2020)
KerkoCite.ItemAlsoKnownAs: 5072953:JRAAN53H 5072953:KDNRD47L
Keywords: _z:class:countries

The impacts of internal displacement on education in sub-Saharan Africa. Paper commissioned for the 2020 Global Education Monitoring Report, Inclusion and Education - I.D.M.C. (UNESCO. Internal Displacement Monitoring Centre (IDMC, 2020)
KerkoCite.ItemAlsoKnownAs: 5072953:FRPB5WVS 5072953:KLRUTLKR
Keywords: _z:class:countries

The impacts of internal displacement on education in sub-Saharan Africa. Paper commissioned for the 2020 Global Education Monitoring Report, Inclusion and Education - I.D.M.C. (UNESCO. Internal Displacement Monitoring Centre (IDMC, 2020)
KerkoCite.ItemAlsoKnownAs: 5072953:FRPB5WVS 5072953:KLRUTLKR

Utilizing artificial neural network for prediction of occupants thermal comfort: A case study of a test room fitted with a thermoelectric air-conditioning system - Irshad, Kashif; Khan, Asif Irshad; Irfan, Sayed Ameenuddin; Alam, Md Mottahir; Almalawi, Abdulmohsen; Zahir, Md Hasan (IEEE Access, 2020)
KerkoCite.ItemAlsoKnownAs: 10.1109/ACCESS.2020.2985036 5072953:VK65YU5B openalex: W3014862332
Keywords: _z:class:countries; _z:class:themes; oa:keyword:occupants thermal comfort; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11529 Refrigeration Systems and Technologies; openalex:n:1; openalex:yes; selected_for:Predictive models for classroom conditions 2024

Passive cooling for thermal comfort in informal housing - Kimemia, D.; Niekerk, A.; Annegarn, H.; Seedat, M. (Journal of Energy in Southern Africa, 2020)

Warmer environments increase implicit mental workload even if learning efficiency is enhanced - Kimura, Tsukasa; Takemura, Noriko; Nakashima, Yuta; Kobori, Hirokazu; Nagahara, Hajime; Numao, Masayuki; Shinohara, Kazumitsu (Frontiers in Psychology, 2020)
Climate change is one of the most important issues for humanity. To defuse this problem, it is considered necessary to improve energy efficiency, make energy sources cleaner, and reduce energy consumption in urban areas. The Japanese government has recommended an air conditioner setting of 28◦C in summer and 20◦C in winter since 2005. The aim of this setting is to save energy by keeping room temperatures constant. However, it is unclear whether this is an appropriate temperature for workers and students. This study examined whether thermal environments influence task performance over time. To examine whether the relationship between task performance and thermal environments influences the psychological states of participants, we recorded their subjective rating of mental workload along with their working memory score, electroencephalogram (EEG), heart rate variability, skin conductance level (SCL), and tympanum temperature during the task and compared the results among different conditions. In this experiment, participants were asked to read some texts and answer questions related to those texts. Room temperature (18, 22, 25, or 29◦C) and humidity (50%) were manipulated during the task and participants performed the task at these temperatures. The results of this study showed that the temporal cost of task and theta power of EEG, which is an index for concentration, decreased over time. However, subjective mental workload increased with time. Moreover, the low frequency to high frequency ratio and SCL increased with time and heat (25 and 29◦C). These results suggest that mental workload, especially implicit mental workload, increases in warmer environments, even if learning efficiency is facilitated. This study indicates integrated evidence for relationships among task performance, psychological state, and thermal environment by analyzing behavioral, subjective, and physiological indexes multidirectionally.
KerkoCite.ItemAlsoKnownAs: 10.3389/fpsyg.2020.00568 2129771:YWHYN59R 4682641:XYPND8K4 5072953:Z9FZP733 openalex: W3014420476
Keywords: BE:RELEVANT; _z:class:countries; _z:class:themes; oa:keyword:implicit mental workload; oa:sdg:7 Affordable and clean energy; oa:topic:T10042 Neural Mechanisms of Cognitive Control and Decision Making; oa:topic:T10525 Human Interaction with Automation Systems; oa:topic:T13219 Neuroscience of Mind Wandering and Attention Lapses; openalex:n:1; openalex:yes

Roadblocks to quality education in a time of climate change - Kwauk, C. (Center for Universal Education at The Brookings Institution, 2020)
KerkoCite.ItemAlsoKnownAs: 5072953:25IIF58A 5072953:69BB6PI4
Keywords: _z:class:countries

Perceived air quality and cognitive performance decrease at moderately raised indoor temperatures even when clothed for comfort - Lan, Li; Xia, Lulu; Hejjo, Rihab; Wyon, David P.; Wargocki, Pawel (Indoor Air, 2020)
This study investigated whether adjusting clothing to remain in neutral thermal comfort at moderately elevated temperature is capable of avoiding negative effects on perceived acute subclinical health symptoms, comfort, and cognitive performance. Two temperatures were examined: 23°C and 27°C. Twelve subjects were able to remain thermally comfortable at both temperatures by adjusting their clothing. They rated the physical environment, their comfort, the intensity of acute subclinical health symptoms, and their mental load, and they performed a number of cognitive tasks. Their physiological reactions were monitored. Their performance of several tasks was significantly worse at 27°C, and they reported increased mental load at this temperature. Skin temperature and humidity and respiration rate were higher, while blood oxygen saturation (SpO2) and pNN50 were lower at this temperature, the latter indicating increased stress. It is inferred that the observed physiological responses were mainly responsible for the negative effects on performance, as the subjects did not indicate any increased intensity of acute subclinical health symptoms although perceived air quality was worse at the higher temperature. The present results suggest that moderately elevated temperatures should be avoided even if thermal comfort can be achieved, as it may lead to reduced performance.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/ina.12685 KerkoCite.ItemAlsoKnownAs: 10.1111/ina.12685 2129771:KWRT2VHY 4874017:FT7326G2
Keywords: acute subclinical health symptoms; air temperature; elevated temperature; evidence_review; physiological responses; thermal comfort; work performance

Perceived air quality and cognitive performance decrease at moderately raised indoor temperatures even when clothed for comfort - Lan, Li; Xia, Lulu; Hejjo, Rihab; Wyon, David P.; Wargocki, Pawel (Indoor Air, 2020)
KerkoCite.ItemAlsoKnownAs: 10.1111/ina.12685 2129771:22S8LX8P 4682641:6U56RJSF 4682641:NY7JHG8I 5072953:HYIY8GHR openalex: W3020879128
Keywords: BE:RELEVANT; C:Denmark; _z:class:countries; _z:class:themes; oa:keyword:indoor temperatures; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11109 Physiological Responses to Heat Stress in Humans; oa:topic:T11244 Impact of Climate Change on Human Health; openalex:n:1; openalex:yes

Female parliamentarians and environmental performance: the role of the income threshold - Lv, Z. (Environmental Science and Pollution Research, 2020)
KerkoCite.ItemAlsoKnownAs: 5072953:3LKZWRI3 5072953:R43DP6SQ
Keywords: _z:class:countries

A determination of how African academics understand and maximise the existing and potential role of Indigenous knowledge and practices within their community-based research: Profiling the ecologically minded university and its contribution to sustainable development - Mbah, Marcellus; Johnson, Ane Turner (Soceity for Research into Higher Education, 2020)
KerkoCite.ItemAlsoKnownAs: 5072953:DQWZAGED
Keywords: _z:class:countries; _z:class:themes; ⛔ No DOI found

Gender inequality, reproductive justice, and decoupling economic growth and emissions: a panel analysis of the moderating association of gender equality on the relationship between economic growth and CO2 emissions - McGee, J. (Environmental Sociology, 2020)
KerkoCite.ItemAlsoKnownAs: 5072953:GSIHJNJK 5072953:JJ2BMPTS
Keywords: _z:class:countries

Pre-primary and primary teacher deployment strategy 2019-2021 - MOEST (2020)
KerkoCite.ItemAlsoKnownAs: 2129771:T5HDIZR2 4874017:EUWHPL62
Keywords: evidence_review

Impacts of Climate Change on Ecosystem Services and Livelihoods within the Great Limpopo Transfrontier Region - Mpofu, Ephraim (University of Johannesburg, 2020)

National climate change report - National Bureau of Statistics (2020)
KerkoCite.ItemAlsoKnownAs: 2129771:NV79LWTZ 4874017:GLATNQ63
Keywords: evidence_review

Thermal and visual comfort of schoolchildren in air-conditioned classrooms in hot and humid climates - Noda, Lumy; Lima, Amanda VP; Souza, Jullyanne F.; Leder, Solange; Quirino, Luana M. (Building and Environment, 2020)
KerkoCite.ItemAlsoKnownAs: 10.1016/j.buildenv.2020.107156 2129771:QJ7T644R 4682641:KNT9RTF7 5072953:9JF5UCIY openalex: W3046015340
Keywords: BE:RELEVANT; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11002 Indoor Air Quality and Health Effects; openalex:n:1; openalex:yes

Impact of a Severe Drought on Education: More Schooling but Less Learning - Nordstrom, A.; Cotton, C. (Queen’s Economics Department Working Paper No. 1430, 2020)
KerkoCite.ItemAlsoKnownAs: 5072953:77FJJVL2 5072953:TNJRUAL6
Keywords: _z:class:countries

Assessment of black globe thermometers employing various sensors and alternative materials - Obando Vega, Felipe Andrés; Montoya Ríos, Ana Paola; Osorio Saraz, Jairo Alexander; Vargas Quiroz, Luis Gonzalo; Alves Damasceno, Flávio (Agricultural and Forest Meteorology, 2020)
The black globe temperature (Tg) is employed in thermal comfort studies. It is mainly used to compute the Mean Radiant Temperature (MRT) required in bioclimatic analysis. A set of low cost Black Globe Thermometers (BGT) was developed to establish a suitable combination of temperature transducers, materials and globe diameters. The dynamic and static responses of the BGT were studied. A total of 18 BGT was deployed along with a data acquisition system based in the Arduino open-source platform. It was analyzed the inﬂuence of the globe material (metallic and polyethylene), globe diameter (100 mm and 67 mm for the metallic and 78 mm for polyethylene) and six types of temperature transducers (K type thermocouple, infrared temperature sensor, thermistor, RTD and two semiconductor-based transducers). It was observed that Tg estimation and response time were transducer and stimuli dependent. The BGT presents good responses for indoor measurements and it was established that the most accurate combination was achieved by the DS18B20 digital temperature sensor with a metallic globe of 67 mm of diameter.

Gender transformative impacts from watershed interventions: Insights from a mixed-methods study in the Bundelkhand region of India - Padmaja, R. (Transactions of the ASABE, 2020)
KerkoCite.ItemAlsoKnownAs: 5072953:FVP3RNLI 5072953:W69R6ZCE
Keywords: _z:class:countries

Gendered Impacts of Environmental Degradation in Informal Settlements: A Comparative Analysis and Policy Implications for India, Bangladesh, and Pakistan - Patel, Amit; Lotia, Hina; Malik, Ammar A.; Mundt, Marcia D.; Lee, Hyunjung; Rafiq, Muhammad Arshed (Journal of Comparative Policy Analysis: Research and Practice, 2020)
Degraded urban environments disproportionately affect marginalized populations, and especially impoverished women in South Asia’s informal settlements, where climate change vulnerabilities and gender inequalities are extreme. A comparative analysis was conducted of three neighboring countries, India, Bangladesh, and Pakistan, where urban environments, climate risks, and gender relations exhibit significant variances. With original survey data from 12 informal settlements across New Delhi, Dhaka, Islamabad, and Lahore, it was found that women are less empowered than men in all three countries, but their determinants related to environmental degradation and climate change vary. Qualitative data from key informants reveals several explanatory mechanisms of observed differences.
KerkoCite.ItemAlsoKnownAs: 5072953:CLQKCPFS 5072953:DFT6J8QC 5072953:LLYAF6N5
Keywords: _z:class:countries; comparative analysis; environmental degradation; informal settlements; mixed methods; women’s empowerment

Conditional nationally determined contributions in the Paris Agreement: foothold for equity or Achilles heel? - Pauw, W.P. (Climate policy, 2020)

The linkages between population change and climate change in Africa - Price, R. (Institute of Development Studies, 2020)
KerkoCite.ItemAlsoKnownAs: 5072953:TVSUFM64 5072953:W7RYTHKV
Keywords: _z:class:countries

Lessons from African champion countries for demographic transition - Quak, E. (2020)
Edition: K4D KerkoCite.ItemAlsoKnownAs: 5072953:R3CJS9AL 5072953:ZE3I9AGG
Keywords: _z:class:countries

CO2 and Greenhouse Gas Emissions - Ritchie, H.; Roser, M. (2020)

It’s time for the Green Human Development Index’ - Robeyns, I. (2020)

The right climate to learn: Education in a changing climate - School, Send My Friend (2020)
KerkoCite.ItemAlsoKnownAs: 5072953:2B6NDMP9 5072953:FYKLCRQH
Keywords: _z:class:countries

CBE Thermal Comfort Tool : online tool for thermal comfort calculations and visualizations - Tartarini, F.; Schiavon, S.; Cheung, T.; Hoyt, T. (SoftwareX, 2020)

What about children? Implications from their subjective perception and the risk of overheating in schools - te Kulve, Marije; Hellwig, Runa T.; van Dijken, Froukje; Boerstra, Atze (Windsor Conference 2020: Resilient Comfort, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:NETF85MA 4682641:9A63D3AE 5072953:CVYIXCJI
Keywords: BE:RELEVANT; _z:class:countries; _z:class:themes; evidence_review_2; ⛔ No DOI found

Indoor temperature and health: a global systematic review - Tham, S.; Thompson, R.; Landeg, O.; Murray, K. A.; Waite, Thomas (Public Health, 2020)
Objectives: The objective of this study was to identify and appraise evidence on the direct and indirect impacts of high indoor temperatures on health; the indoor temperature threshold at which the identified health impacts are observed; and to summarise the evidence for establishing a maximum indoor temperature threshold for health. Study design: This is a systematic literature review and narrative synthesis. Methods: A review of the published literature using MEDLINE, EMBASE, Global Health, PsycINFO, Maternity and Infant Care, Cochrane Library, CINAHL and GreenFILE databases was conducted. The search criteria were kept broad to capture evidence from all countries and contexts; no date or study design limits were applied, except English language limits. We included studies that specifically measured indoor temperature and examined its effect on physical or mental health outcomes. Evidence was graded using the National Institutes of Health framework. Results: Twenty-two articles were included in the review, including 11 observational, seven cross-sectional and three longitudinal cohort studies and one prospective caseecontrol study. Eight main health effects were described: respiratory, blood pressure, core temperature, blood glucose, mental health and cognition, heat-health symptoms, physical functioning and influenza transmission. Five studies found respiratory symptoms worsened in warm indoor environments, with one reporting indoor temperatures higher than 26 C, which was associated with increased respiratory distress calls being made to paramedics (odds ratio ¼ 1.63, P ¼ 0.056). Core symptoms of schizophrenia and dementia were found to be significantly exacerbated by indoor heat (the latter above a 26 C cumulative exposure threshold). The absorption of insulin doses in people with type one diabetes was also significantly accelerated in hot indoor environments. Only five studies reported the temperatures at which health outcomes worsened, with thresholds ranging between 26 C and 32 C. However, owing to insufficient data and the heterogeneity of the included studies (design, population, setting, exposure measures, outcomes and location), metaanalysis and an upper threshold determination was not feasible. Conclusions: High indoor temperatures affect aspects of human health, with the strongest evidence for respiratory health, diabetes management and core schizophrenia and dementia symptoms. Exacerbation of symptoms in warm indoor environments has clinical relevance to at-risk groups and those caring for them. Care staff and facility managers need to be vigilant of high temperatures in care environments and should incorporate indoor overheating into their risk management and sustainability and/or climate change adaptation plans. The indoor temperature threshold at which adverse effects begin to occur remains unclear as studies seldom report the exposureeresponse relationship over a temperature continuum. Until there is extensive scientific data to support a maximum indoor temperature threshold, 26 C may be the most suitable indoor temperature for atrisk groups in keeping with the existing guidance documents. Crown Copyright © 2019 Published by Elsevier Ltd on behalf of The Royal Society for Public Health. All rights reserved.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.puhe.2019.09.005 2129771:F8XATYS6 4682641:HRENV5V9 5072953:L9JCXDWQ openalex: W2987569619
Keywords: BE:RELEVANT; _z:class:countries; _z:class:themes; evidence_review; oa:keyword:indoor temperature; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10190 Health Effects of Air Pollution; oa:topic:T11244 Impact of Climate Change on Human Health; openalex:n:1; openalex:yes

Human Development Report 2020 The Next Frontier Human Development and the Anthropocene - U.N.D.P. (2020)
KerkoCite.ItemAlsoKnownAs: 5072953:F9ITD7V5 5072953:UMQ56DCM
Keywords: _z:class:countries

COVID-19 is a serious threat to aid to education recovery - U.N.E.S.C.O. (Policy Paper 41, 2020)

The impact of climate displacement on the right to education - U.N.E.S.C.O. (UNESCO Paris, 2020)
KerkoCite.ItemAlsoKnownAs: 5072953:7I9WMC2A 5072953:8XLY7LPV

Towards an equal future: Reimagining girls’ education through STEM - U.N.I.C.E.F. (2020)
Pages: – – – –2020 KerkoCite.ItemAlsoKnownAs: 5072953:TNHCZWG9 5072953:YJ6U8ZDG

Stronger together in crises: 2019 annual results report - Wait, Education Cannot (2020)
Pages: 2019– – KerkoCite.ItemAlsoKnownAs: 5072953:AUDUW2W3 5072953:KLL34F3J

Sample size estimation in clinical research: from randomized controlled trials to observational studies - Wang, X.; Ji, X. (Chest, 2020)

Short summary report for Realdania - Wargocki, Pawel (International Centre for Indoor Environment and Energy, 2020)
Summary of the research on how thermal, air quality, noise reduction, lighting, and daylighting improvements in classrooms benefit children’s educational attainments
KerkoCite.ItemAlsoKnownAs: 2129771:3UVQNI4M 4682641:3X27VCYX 5072953:MAEBHYZ7
Keywords: _z:class:countries; _z:class:themes

The full report of Realdania - Wargocki, Pawel; Wyon, David P (International Centre for Indoor Environment and Energy., 2020)
This report summarises published research on how children’s performance of schoolwork in primary and secondary schools and their subsequent educational attainments are affected by classroom temperature, air quality, noise, and lighting. The main conclusions (Items 1-20) are set out below as unequivocal statements that are validated by the findings of the detailed reviews of research published that form the bulk of the report, or by the findings of research published since those reviews were written and in some cases published. Bibliographic references to the original research reports are to be found in each detailed review or in the list that appears below. To each statement has been added brief comments based on other relevant findings noted in the reviews. A short list of what is NOT yet known about the effects of each indoor climate factor is then appended (Items 5, 10, 15, and 20), the implications for energy conservation (Items 21-25) and priorities for future research in this area (Items 26-30) are suggested. This report’ssummaryisprovidedseparatelywiththecurrentrecommendations and requirements of indoor environmental quality conditions in schools. Four appendixes contain detailed reviews based on which the present report was prepared.
KerkoCite.ItemAlsoKnownAs: 2129771:SGXEGTTH 4682641:TNZG44UN 5072953:THKUU6GD
Keywords: _z:class:countries; _z:class:themes; evidence_review_2

What difference does disaster risk reduction make? Insights from Vanuatu and tropical cyclone Pam - Webb, J. (Regional Environmental Change, 2020)
KerkoCite.ItemAlsoKnownAs: 5072953:EGNRYKGY 5072953:XFJ7UY79

Relationship Between Classroom Physical Environment and Students’ Academic Achievement at Secondary Level - Zaman, Fakhar; Begum, Shabnam; Ullah, Mati (2020)
For fruitful teaching and learning process, physical classroom environment is very essential. The key purpose of the study was examining relationship between classroom physical environment and students’ academic achievement at Secondary Level in Southern KP. The study was descriptive in nature. The population of the study comprised of the five districts in Southern KP in which (n = 400) respondents were taken as sample of the study by applying stratified random sampling technique in which 200 were urban (100 male students and 100 female students). Similarly, 200 were rural students (100 male and 100 female). From each selected district, 05 urban and 05 rural male schools and similarly 05 urban and 05 rural female schools were randomly selected among these 05 districts. Data were collected from 20 schools. A self-developed questionnaire was used to find views of the students about their physical class room environment. Cronbach Alpha was applied. The collected data was entered into SPSS. Results and conclusions were drawn according to the nature of study. Thus, some recommendations were suggested at the end for the further improvement and future researcher.
KerkoCite.ItemAlsoKnownAs: 2129771:S3KWJTKI 4682641:JWD5G4D2 5072953:YKSNTHSR
Keywords: BE:LMIC; BE:RELEVANT; _z:class:countries; _z:class:themes; evidence_review_2